CogDrisk, ANU-ADRI, CAIDE, and LIBRA Risk Scores for Estimating Dementia Risk. - Huque, Md Hamidul; Kootar, Scherazad; Eramudugolla, Ranmalee; Han, S Duke; Carlson, Michelle C; Lopez, Oscar L; Bennett, David A; Peters, Ruth; Anstey, Kaarin J (JAMA Netw Open, 2023)
IMPORTANCE: While the Australian National University-Alzheimer Disease Risk Index (ANU-ADRI), Cardiovascular Risk Factors, Aging, and Dementia (CAIDE), and Lifestyle for Brain Health (LIBRA) dementia risk tools have been widely used, a large body of new evidence has emerged since their publication. Recently, Cognitive Health and Dementia Risk Index (CogDrisk) and CogDrisk for Alzheimer disease (CogDrisk-AD) risk tools have been developed for the assessment of dementia and AD risk, respectively, using contemporary evidence; comparison of the relative performance of these risk tools is limited. OBJECTIVE: To evaluate the performance of CogDrisk, ANU-ADRI, CAIDE, LIBRA, and modified LIBRA (LIBRA with age and sex estimates from ANU-ADRI) in estimating dementia and AD risks (with CogDrisk-AD and ANU-ADRI). DESIGN, SETTING, AND PARTICIPANTS: This population-based cohort study obtained data from the Rush Memory and Aging Project (MAP), the Cardiovascular Health Study Cognition Study (CHS-CS), and the Health and Retirement Study-Aging, Demographics and Memory Study (HRS-ADAMS). Participants who were free of dementia at baseline were included. The factors were component variables in the risk tools that included self-reported baseline demographics, medical risk factors, and lifestyle habits. The study was conducted between November 2021 and March 2023, and statistical analysis was performed from January to June 2023. MAIN OUTCOMES AND MEASURES: Risk scores were calculated based on available factors in each of these cohorts. Area under the receiver operating characteristic curve (AUC) was calculated to measure the performance of each risk score. Multiple imputation was used to assess whether missing data may have affected estimates for dementia risk. RESULTS: Among the 6107 participants in 3 validation cohorts included for this study, 2184 participants without dementia at baseline were available from MAP (mean [SD] age, 80.0 [7.6] years; 1606 [73.5%] female), 548 participants without dementia at baseline were available from HRS-ADAMS (mean [SD] age, 79.5 [6.3] years; 288 [52.5%] female), and 3375 participants without dementia at baseline were available from CHS-CS (mean [SD] age, 74.8 [4.9] years; 1994 [59.1%] female). In all 3 cohorts, a similar AUC for dementia was obtained using CogDrisk, ANU-ADRI, and modified LIBRA (MAP cohort: CogDrisk AUC, 0.65 [95% CI, 0.61-0.69]; ANU-ADRI AUC, 0.65 [95% CI, 0.61-0.69]; modified LIBRA AUC, 0.65 [95% CI, 0.61-0.69]; HRS-ADAMS cohort: CogDrisk AUC, 0.75 [95% CI, 0.71-0.79]; ANU-ADRI AUC, 0.74 [95% CI, 0.70-0.78]; modified LIBRA AUC, 0.75 [95% CI, 0.71-0.79]; CHS-CS cohort: CogDrisk AUC, 0.70 [95% CI, 0.67-0.72]; ANU-ADRI AUC, 0.69 [95% CI, 0.66-0.72]; modified LIBRA AUC, 0.70 [95% CI, 0.68-0.73]). The CAIDE and LIBRA also provided similar but lower AUCs than the 3 aforementioned tools (eg, MAP cohort: CAIDE AUC, 0.50 [95% CI, 0.46-0.54]; LIBRA AUC, 0.53 [95% CI, 0.48-0.57]). The performance of CogDrisk-AD and ANU-ADRI in estimating AD risks was also similar. CONCLUSIONS AND RELEVANCE: CogDrisk and CogDrisk-AD performed similarly to ANU-ADRI in estimating dementia and AD risks. These results suggest that CogDrisk and CogDrisk-AD, with a greater range of modifiable risk factors compared with other risk tools in this study, may be more informative for risk reduction.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Australia; Cohort Studies; Female; Heart Disease Risk Factors; Humans; Male; Risk Factors

Cross-Lagged Associations Between Physical Activity, Self-Rated Health, and Psychological Resilience Among Older American Adults: A 3-Wave Study. - Lee, Sunwoo (J Phys Act Health, 2023)
The current study examined the reciprocal association between psychological resilience, physical activity, and self-rated health in older America adults. A 3-wave cross-lagged panel design was employed using data sampled from the Health and Retirement Study 2010, 2014, and 2018. In total, 8380 older adults, age ranged between 56 and 95 years at the baseline (mean age = 68.06, SD = 7.77), were analyzed. Using structural equation modeling, standardized path coefficients were estimated to determine the relationship between physical activity, self-rated health, and psychological resilience across 2 follow-up points. Cross-lagged analysis revealed that higher levels of physical activity at T1 and T2 were significantly associated with higher levels of self-rated health at T2 and T3, respectively. Self-rated health at T1 and T2 were significantly associated with physical activity at T2 and T3, respectively. Self-rated health and psychological resilience were positively related to one another at each time point. However, relationship between physical activity and psychological resilience was complex across time. Study findings support reciprocal prospective relationship between physical activity and self-rated health and the relationship between self-rated health and psychological resilience.
Keywords: Aged; Aged, 80 and over; Exercise; Humans; Middle Aged; Prospective Studies; Resilience, Psychological

Does personality always matter for health? Examining the moderating effect of age on the personality-health link from life span developmental and aging perspectives. - Luo, Jing; Zhang, Bo; Graham, Eileen K; Mroczek, Daniel K (Journal of personality and social psychology, 2023)
Extensive evidence has been found for the associations between personality traits and health. However, it remains unknown whether the relationships between personality and health show differential patterns across different life stages. The current research examined how the associations between the levels of and changes in the Big Five personality traits and different types of health outcomes (self-rated, physical, and physiological health outcomes) differ across ages over the life span (Sample 1, age range: 15-100) and during the aging process (Sample 2, age range: 50-109) in particular. Using data from the two large longitudinal studies-the Household, Income, and Labor Dynamics in Australia Survey and the Health and Retirement Study, we observed three important patterns. First, levels of and changes in personality traits were significantly associated with health across different life phases, and these effects were observed even in very old ages. Second, overall, the prospective relations between personality traits/changes in personality traits and health outcomes increased in strength in middle adulthood and/or early stages of late adulthood; however, the strength of their connections diminished in very old ages. Finally, there were some trait-specific and health outcome-specific patterns in the age-differential associations between personality and health. Findings from the present study contribute to enhancing our understanding of the personality-health link from a developmental perspective and provide critical information for the design and implementation of screening and interventions targeting health promotion. (PsycInfo Database Record (c) 2023 APA, all rights reserved).
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Aging; Humans; Longevity; Longitudinal Studies; Middle Aged; Personality; Personality Disorders; Young Adult

Gender differences in the association of polygenic risk and divergent depression trajectories from mid to late life: a national longitudinal study. - Chen, Ping; Li, Yi; Wu, Fang (Biodemography Soc Biol, 2023)
Our research fills a critical gap in the depression literature by utilizing a life course perspective to examine gender-gene interactions in association with depression trajectories over time. Using data from the Health and Retirement Study, we estimated multi-level negative binomial and logistic mixed models to analyze gender-specific trajectories of depressive symptoms (CESD-8) and potential clinical depression risk from middle to late adulthood in relation to gender-by-polygenic-risk (PRS) interactions. We found increasingly greater female-male gaps in the CESD-8 scale and a higher probability of clinical depression risk with increasing polygenic risk scores. Furthermore, females' higher genetic vulnerabilities to depressive conditions than males vary from ages 51 to 90 years, (e.g. 0.28 higher CESD-8 scale for females at ages 76-85 years than for similar-aged males; higher 3.44% probability of depression risk for females at ages 81-85 compared to similar-aged males) (e.g. about 2.40% higher probability of depression risk for females at ages 61-70 years than for similar-aged males) . This study contributes to new knowledge of how gender-by-polygenic-risk interactions are associated with depression trajectories across the life course.
Keywords: Adult; Aged; Aged, 80 and over; depression; Depressive Disorder, Major; Female; Humans; Longitudinal Studies; Male; Middle Aged; Risk Factors; Sex Factors

Personality and Risk of Incident Stroke in 6 Prospective Studies. - Stephan, Yannick; Sutin, Angelina R; Luchetti, Martina; Aschwanden, Damaris; Terracciano, Antonio (Stroke, 2023)
BACKGROUND: A large literature has examined a broad range of factors associated with increased risk of stroke. Few studies, however, have examined the association between personality and stroke. The present study adopted a systematic approach using a multi-cohort design to examine the associations between 5-Factor Model personality traits (neuroticism, extraversion, openness, agreeableness, and conscientiousness) and incident stroke using data from 6 large longitudinal samples of adults. METHODS: Participants (age range: 16-104 years old, N=58 105) were from the MIDUS (Midlife in the United States) Study, the HRS (Health and Retirement Study), The US (Understanding Society) study, the WLS (Wisconsin Longitudinal Study), the NHATS (National Health and Aging Trends Study), and the LISS (Longitudinal Internet Studies for the Social Sciences). Personality traits, demographic factors, clinical and behavioral risk factors were assessed at baseline; stroke incidence was tracked over 7 to 20 years follow-up. RESULTS: Meta-analyses indicated that higher neuroticism was related to a higher risk of incident stroke (hazard ratio, 1.15 [95% CI, 1.10-1.20]; <0.001), whereas higher conscientiousness was protective (HR, 0.89 [95% CI, 0.85-0.93]; <0.001). Additional meta-analyses indicated that BMI, diabetes, blood pressure, physical inactivity, and smoking as additional covariates partially accounted for these associations. Extraversion, openness, and agreeableness were unrelated to stroke incidence. CONCLUSIONS: Similar to other cardiovascular and neurological conditions, higher neuroticism is a risk factor for stroke incidence, whereas higher conscientiousness is a protective factor.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Humans; Longitudinal Studies; Middle Aged; Neuroticism; Personality; Prospective Studies; Stroke; United States; Young Adult

Preoperative Factors Predict Memory Decline After Coronary Artery Bypass Grafting or Percutaneous Coronary Intervention in an Epidemiological Cohort of Older Adults. - Tang, Angelina B; Diaz-Ramirez, L Grisell; Smith, Alexander K; Lee, Sei J; Whitlock, Elizabeth L (J Am Heart Assoc, 2023)
Background Durable memory decline may occur in older adults after surgical (coronary artery bypass grafting [CABG]) or nonsurgical (percutaneous coronary intervention) coronary revascularization. However, it is unknown whether individual memory risk can be predicted. We reanalyzed an epidemiological cohort of older adults to predict memory decline at ≈1 year after revascularization. Methods and Results We studied Health and Retirement Study participants who underwent CABG or percutaneous coronary intervention at age ≥65 years between 1998 and 2015 and participated in ≥1 biennial postprocedure assessment. Using a memory score based on direct and proxy cognitive tests, we identified participants whose actual postprocedure memory score was 1-2 ("mild") or >2 ("major") SDs below expected postprocedure performance. We modeled probability of memory decline using logistic regression on preoperatively known factors and evaluated model discrimination and calibration. A total of 1390 participants (551 CABG, 839 percutaneous coronary intervention) underwent CABG/percutaneous coronary intervention at 75±6 years old; 40% were women. The cohort was 83% non-Hispanic White, 8.4% non-Hispanic Black, 6.4% Hispanic ethnicity, and 1.7% from other groups masked by the HRS (Health and Retirement Study) to preserve participant confidentiality. At a median of 1.1 (interquartile range, 0.6-1.6) years after procedure, 267 (19%) had mild memory decline and 88 (6.3%) had major memory decline. Factors predicting memory decline included older age, frailty, and off-pump CABG; obesity was protective. The optimism-corrected area under the receiver operator characteristic curve was 0.73 (95% CI, 0.71-0.77). A cutoff of 50% probability of memory decline identified 14% of the cohort as high risk, and was 94% specific and 30% sensitive for late memory decline. Conclusions Preoperative factors can be used to predict late memory decline after coronary revascularization in an epidemiological cohort with high specificity.
Keywords: Aged; Aged, 80 and over; Coronary Artery Bypass; Coronary Artery Bypass, Off-Pump; Coronary Artery Disease; Female; Humans; Male; Memory Disorders; Percutaneous Coronary Intervention; Treatment Outcome

Sex differences in cognitive aging and the role of socioeconomic status: Evidence from multi-cohort studies. - Jin, Yinzi; Hong, Chenlu; Luo, Yanan (Psychiatry Res, 2023)
BACKGROUND: Sex differences exist in cognitive function, and socioeconomic status (SES) may play a role in changing these discrepancies. This study investigated the role of SES in contributing to sex differences in cognitive function. METHODS: We conducted a pooled multi-cohort study on the basis of four comparative cohort studies from the UK, the US, Europe and China to assess sex differences and the role of SES in cognitive decline by birth cohort (1930-1938, 1939-1945, 1946-1968). Cognitive function was measured in three domains based on the mean and SD of the corresponding tests: episodic memory, working memory, and time orientation. SES was the summed scores of education and household wealth. FINDINGS: 61,019 individuals were involved. Cognitive function of women declined faster than those of men as growing old (particularly after 80 years old). As SES increased, cognitive function increased more for women than for men in most cases among later-born cohorts (1930-1938, 1939-1945, 1946-1968) (e.g., episodic memory scores at 60 years old: women exhibited an increase from -0.09 [95%CI -0.12, -0.07] in low SES to 0.89 [0.86, 0.92] in high SES; men from -0.16 [-0.19, -0.14] to 0.59 [0.56, 0.62]). However, sex-specific cognitive benefits were absent in the oldest birth cohort (1895-1929). INTERPRETATION: These findings highlight the importance of considering the role of SES in the discrepancy of sex difference in cognitive aging.
Keywords: Aged, 80 and over; Aging; cognitive aging; Cohort Studies; Female; Humans; Male; Middle Aged; Sex Characteristics; Social Class; Socioeconomic factors

Structural Inequity and Socioeconomic Status Link to Osteoporosis Diagnosis in a Population-Based Cohort of Middle-Older-Age Americans. - Gough Courtney, Margaret; Roberts, Josephine; Godde, Kanya (Inquiry, 2023)
Socioeconomic status (SES) is an important social determinant of health inequities that has been linked to chronic conditions, including osteoporosis, but research tends to focus on socioeconomic disadvantage rather than how socioeconomic advantage may facilitate these inequities. This study accounts for structural inequities and assesses the relationship between early-life and later-life SES, and risk of osteoporosis diagnosis. Data come from the nationally representative, population-based cohort Health and Retirement Study and include individuals ages 50 to 90. The outcome variable is osteoporosis diagnosis. Logistic regression models of the relationship between SES and osteoporosis diagnosis are estimated, accounting for demographic, health, and childhood variables. Higher levels of childhood and adult SES link to lower odds of osteoporosis diagnosis. Structural inequities in income and underdiagnosis of osteoporosis among persons identifying as Black/African American were detected. Accounting for bone density scan access, inequities in osteoporosis diagnosis appear to stem from barriers to accessing health care due to financial constraints. The important role of SES and evidence of structural inequities leading to underdiagnosis suggest the critical importance of clinicians receiving Diversity, Equity, and Inclusion training to reduce health inequities.
Keywords: Adult; Aged; Aged, 80 and over; Black or African American; Humans; Income; Logistic Models; Middle Aged; Osteoporosis; Social Class; Socioeconomic factors

Peripheral edema: A common and persistent health problem for older Americans. - Besharat, Soroush; Grol-Prokopczyk, Hanna; Gao, Shan; Feng, Changyong; Akwaa, Frank; Gewandter, Jennifer S (PLoS One, 2021)
Peripheral edema (i.e., lower limb swelling) can cause pain, weakness, and limited range of motion. However, few studies have examined its prevalence in the U.S. or its association with demographics, comorbidities, activity, or mobility. This study used data from the Health and Retirement Study, a nationally representative longitudinal survey of U.S. adults (age 51+/ N = 19,988 for 2016), to evaluate time trends and correlates of peripheral edema using weighted descriptive statistics and logistic regressions, respectively. Peripheral edema was assessed with the question "Have you had… // Persistent swelling in your feet or ankles?" The weighted prevalence of edema among older U.S. adults was 19% to 20% between 2000 and 2016. Peripheral edema was associated with older age, female sex, non-white race, low wealth, obesity, diabetes, hypertension, pain, low activity levels, and mobility limitations (odds ratios ranging from 1.2-5.6; p-values ≤0.001). This study provides the first estimates of national prevalence and correlates of peripheral edema among older Americans. Peripheral edema is common and strongly associated with comorbidities, pain, low activity levels, and mobility limitations, and disproportionately affects poorer and minority groups. Peripheral edema should be a focus of future research in order to develop novel and cost-effective interventions.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Edema; ethnicity; Female; Follow-Up Studies; Humans; Longitudinal Studies; Lower Extremity; Male; Middle Aged; Mobility Limitation; Prognosis; Surveys and Questionnaires; United States

Disparities in patient-centered communication for Black and Latino men in the U.S.: Cross-sectional results from the 2010 health and retirement study. - Mitchell, Jamie A; Perry, Ramona (PLoS One, 2020)
BACKGROUND: A lack of patient-centered communication (PCC) with health providers plays an important role in perpetuating disparities in health care outcomes and experiences for minority men. This study aimed to identify factors associated with any racial differences in the experience of PCC among Black and Latino men in a nationally representative sample. METHODS: We employed a cross-sectional analysis of four indicators of PCC representative of interactions with doctors and nurses from (N = 3082) non-Latino White, Latino, and Black males from the 2010 Health and Retirement Study (HRS) Core and the linked HRS Health Care Mail in Survey (HCMS). Men's mean age was 66.76 years. The primary independent variable was Race/Ethnicity (i.e. Black and Hispanic/Latino compared to white males) and covariates included age, education, marital status, insurance status, place of care, and self-rated health. RESULTS: Bivariate manova analyses revealed racial differences across each of the four facets of PCC experience such that non-Hispanic white men reported PC experiences most frequently followed by black then Hispanic/Latino men. Multivariate linear regressions predictive of PCC by race/ethnicity revealed that for Black men, fewer PCC experiences were predicted by discriminatory experiences, reporting fewer chronic conditions and a lack of insurance coverage. For Hispanic/Latino men, access to a provider proved key where not having a place of usual care solely predicted lower PCC frequency. IMPLICATIONS: Researchers and health practitioners should continue to explore the impact of inadequate health care coverage, time-limited medical visits and implicit racial bias on medical encounters for underrepresented patients, and to advocate for accessible, inclusive and responsive communication between minority male patients and their health providers.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Chronic disease; Communication; Cross-Sectional Studies; Follow-Up Studies; Healthcare Disparities; Hispanic Americans; Humans; Insurance Coverage; Male; Middle Aged; Patient Education as Topic; Patient-Centered Care; Physician-Patient Relations; Prognosis; Racism

Relationship between smoking status and muscle strength in the United States older adults. - Wiener, R Constance; Findley, Patricia A; Shen, Chan; Dwibedi, Nilanjana; Sambamoorthi, Usha (Epidemiology and Health, 2020)
OBJECTIVES: Muscle strength in older adults is associated with greater physical ability. Identifying interventions to maintain muscle strength can therefore improve quality of life. The purpose of this study was to evaluate whether current or former smoking status is associated with a decrease in muscle strength in older adults. METHODS: Data from the Health and Retirement Study from 2012-2014 were analyzed with regard to maximum dominant hand grip strength, maximum overall hand grip strength, and smoking status (current, former, or never). Unadjusted linear regression was conducted. Other factors known to be related to strength were included in the adjusted linear regression analyses. RESULTS: For maximum grip strength, the regression coefficient was 4.91 for current smoking (standard error [SE], 0.58; p<0.001), 3.58 for former smoking (SE, 0.43; p<0.001), and 28.12 for never smoking (SE, 0.34). Fully adjusted linear regression on the relationship between dominant hand grip strength and smoking did not yield a significant result. The factors significantly associated with dominant hand grip strength were male sex, younger age, a race/ethnicity of non-Hispanic White or non-Hispanic Black, higher income, morbidity of ≤1 condition, no pain, and moderate or vigorous exercise more than once a week. CONCLUSIONS: Muscle strength in older adults was not associated with smoking status in the adjusted analysis.
Keywords: Aged; Aged, 80 and over; Female; Hand Strength; Humans; Male; Middle Aged; Muscle Strength; Smoking; United States

Genetic heterogeneity of Alzheimer's disease in subjects with and without hypertension. - Nazarian, Alireza; Konstantin G Arbeev; Arseniy P Yashkin; Alexander M Kulminski (Geroscience, 2019)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder caused by the interplay of multiple genetic and non-genetic factors. Hypertension is one of the AD risk factors that has been linked to underlying pathological changes like senile plaques and neurofibrillary tangles formation as well as hippocampal atrophy. In this study, we investigated the differences in the genetic architecture of AD between hypertensive and non-hypertensive subjects in four independent cohorts. Our genome-wide association analyses revealed significant associations of 15 novel potentially AD-associated polymorphisms (P < 5E-06) that were located outside the chromosome 19q13 region and were significant either in hypertensive or non-hypertensive groups. The closest genes to 14 polymorphisms were not associated with AD at P < 5E-06 in previous genome-wide association studies (GWAS). Also, four of them were located within two chromosomal regions (i.e., 3q13.11 and 17q21.2) that were not associated with AD at P < 5E-06 before. In addition, 30 genes demonstrated evidence of group-specific associations with AD at the false discovery rates (FDR) < 0.05 in our gene-based and transcriptome-wide association analyses. The chromosomal regions corresponding to four genes (i.e., 2p13.1, 9p13.3, 17q12, and 18q21.1) were not associated with AD at P < 5E-06 in previous GWAS. These genes may serve as a list of prioritized candidates for future functional studies. Our pathway-enrichment analyses revealed the associations of 11 non-group-specific and four group-specific pathways with AD at FDR < 0.05. These findings provided novel insights into the potential genetic heterogeneity of AD among subjects with and without hypertension.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer disease; Cohort Studies; disease progression; Female; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Polymorphism, Single Nucleotide; Prognosis; Prospective Studies; Risk Assessment

Having a Happy Spouse Is Associated With Lowered Risk of Mortality. - Stavrova, Olga (Psychological Science, 2019)
Studies have shown that individuals' choice of a life partner predicts their life outcomes, from their relationship satisfaction to their career success. The present study examined whether the reach of one's spouse extends even further, to the ultimate life outcome: mortality. A dyadic survival analysis using a representative sample of elderly couples ( N = 4,374) followed for up to 8 years showed that a 1-standard-deviation-higher level of spousal life satisfaction was associated with a 13% lower mortality risk. This effect was robust to controlling for couples' socioeconomic situation (e.g., household income), both partners' sociodemographic characteristics, and baseline health. Exploratory mediation analyses pointed toward partner and actor physical activity as sequential mediators. These findings suggest that life satisfaction has not only intrapersonal but also interpersonal associations with longevity and contribute to the fields of epidemiology, positive psychology, and relationship research.
Keywords: Aged; Aged, 80 and over; Exercise; Female; Happiness; Humans; Interpersonal Relations; Longevity; Male; Middle Aged; Mortality; Personal Satisfaction; Risk Reduction Behavior; Self Report; Sexual Partners; Socioeconomic factors; Spouses; Survival Analysis

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Yun Ju Sung; Schwander, Karen; Thomas W Winkler; Jakupović, Hermina; Daniel I Chasman; Alisa Manning; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nature Communications, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asians; Blacks; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic or Latino; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; Whites; Young Adult

One-Year Mortality After Dialysis Initiation Among Older Adults. - Melissa W Wachterman; O'Hare, Ann M; Rahman, Omari-Khalid; Karl A Lorenz; Edward R Marcantonio; Alicante, Gabrielle K; Amy Kelley (JAMA Intern Med, 2019)
This cohort study examines the incidence of mortality 1 year after the start of hemodialysis in patients 65 years and older.
Keywords: Aged; Aged, 80 and over; Female; Humans; Male; Renal Dialysis; United States

Activity Engagement and Activity-Related Experiences: The Role of Personality. - Nicky J Newton; Pladevall-Guyer, Jana; Gonzalez, Richard; Jacqui Smith (J Gerontol B Psychol Sci Soc Sci, 2018)
Objectives: The associations of personality with activity participation and well-being have been well studied. However, less is known concerning the relationship between personality and specific aspects of activity engagement in older adults. We conducted a fine-grained examination of the effects of extraversion and conscientiousness on reported activity engagement-which we define as participation, time allocated, and affective experience-during 8 everyday activities. Method: Data were obtained using a day reconstruction measure from a subgroup of participants in the 2012 Health and Retirement Study (HRS: N = 5,484; mean age = 67.98 years). Results: We found mixed support for hypotheses suggesting that specific personality traits would be associated with activity participation, time allocated, and activity-affective experience. For example, extraverts were more likely to socialize and experienced higher socializing-related positive affect, but did not spend more time socializing. Discussion: Results are discussed in light of the value of including personality in, and its contribution to, studies of activity engagement in later life. In addition, the need to acknowledge the complexity of the concept of activity engagement in future research is highlighted.
Keywords: Age Factors; Aged; Aged, 80 and over; Educational Status; Female; Humans; Interviews as Topic; Male; Marital Status; Middle Aged; Personality; Personality Inventory; Sex Factors; Social participation; Surveys and Questionnaires

Are coresidence and nursing homes substitutes? Evidence from Medicaid spend-down provisions. - Corina D Mommaerts (J Health Econ, 2018)
This paper measures the extent to which the price of nursing home care affects a potential substitute living arrangement: coresidence with adult children. Exploiting variation in state Medicaid income "spend-down" provisions over time, I find that living in a state with a spend-down provision decreases the prevalence of coresidence with adult children by 1-4 percentage points for single elderly individuals, with a corresponding increase in the use of nursing home care. These findings suggest that changes in Medicaid eligibility for long-term care benefits could have large impacts on living arrangements, care utilization patterns, and Medicaid expenditures.
Keywords: Adult children; Aged; Aged, 80 and over; Female; Health Expenditures; Homes for the Aged; Humans; Long-term Care; Male; Medicaid; Nursing homes; Residence Characteristics; United States

Arthritis, Depression, and Falls Among Community-Dwelling Older Adults: Evidence From the Health and Retirement Study. - Lien Quach; Jeffrey A Burr (J Appl Gerontol, 2018)
The aims of this study were to examine the association between different types of arthritis and falls and to investigate whether clinically significant depression symptoms (CSDS) moderate these relationships. The study used nationally representative data from the 2008 Health and Retirement Study ( n = 7,715, M age = 75, 62% female, and 90% White). Among the respondents, 42% experienced at least one fall during the previous 2 years. About one third had some form of arthritis: 22% osteoarthritis (OA), 4.8% rheumatoid arthritis (RA), 2.3% both OA and RA, and 7.9% with other arthritis types. About one fifth of respondents had CSDS. OA and CSDS are associated with the odds of falling (17% and 29%, respectively), adjusting for socio-demographic characteristics, lifestyle, health conditions, and psychiatric medications. There was no statistically significant interaction between types of arthritis and CSDS. Health care providers should pay attention to managing arthritis, especially OA, and CSDS to prevent falls among older adults.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Arthritis, Rheumatoid; Comorbidity; depression; Female; Health Surveys; Humans; Independent Living; Male; Osteoarthritis; United States

Drinking Patterns Among Older Couples: Longitudinal Associations With Negative Marital Quality. - Kira S. Birditt; James A. Cranford; Jasmine A Manalel; Toni C Antonucci (J Gerontol B Psychol Sci Soc Sci, 2018)
Objectives: Research with younger couples indicates that alcohol use has powerful effects on marital quality, but less work has examined the effects of drinking among older couples. This study examined whether dyadic patterns of drinking status among older couples are associated with negative marital quality over time. Method: Married participants (N = 4864) from the Health and Retirement Study reported on alcohol consumption (whether they drink alcohol and average amount consumed per week) and negative marital quality (e.g., criticism and demands) across two waves (Wave 1 2006/2008 and Wave 2 2010/2012). Results: Concordant drinking couples reported decreased negative marital quality over time, and these links were significantly greater among wives. Wives who reported drinking alcohol reported decreased negative marital quality over time when husbands also reported drinking and increased negative marital quality over time when husbands reported not drinking. Discussion: The present findings stress the importance of considering the drinking status rather than the amount of alcohol consumed of both members of the couple when attempting to understand drinking and marital quality among older couples. These findings are particularly salient given the increased drinking among baby boomers and the importance of marital quality for health among older couples.
Keywords: Aged; Aged, 80 and over; Alcohol Drinking; Family Conflict; Female; Humans; Longitudinal Studies; Male; Marriage; Middle Aged; Sex Factors; Spouses

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Richard Karlsson Linnér; Mark Alan Fontana; Kundu, Tushar; et al. (Nature Genetics, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.
Keywords: Adult; Aged; Aged, 80 and over; Cohort Studies; Educational Status; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide

Later Life Marital Dissolution and Repartnership Status: A National Portrait. - Susan L. Brown; Lin, I-Fen; Anna M Hammersmith; Matthew R Wright (J Gerontol B Psychol Sci Soc Sci, 2018)
OBJECTIVES: Our study compares two types of later life marital dissolution that occur after age 50-divorce and widowhood-and their associations with repartnership status (i.e., remarried, cohabiting, or unpartnered). METHOD: We used data from the Health and Retirement Study to provide a portrait of later life divorce and widowhood for women and men. Next, we tested whether marital dissolution type is related to women's and men's repartnered status, distinguishing among remarrieds, cohabitors, and unpartnereds, net of key sociodemographic indicators. RESULTS: Divorcees are more often repartnered through either remarriage or cohabitation than are widoweds. This gap persists among women net of an array of sociodemographic factors. For men, the differential is reduced to nonsignificance with the inclusion of these factors. DISCUSSION: Later life marital dissolution increasingly occurs through divorce rather than widowhood, and divorce is more often followed by repartnership. The results from this study suggest that gerontological research should not solely focus on widowhood but also should pay attention to divorce and repartnering during later life.
Keywords: Age Factors; Aged; Aged, 80 and over; Divorce; Female; Humans; Longitudinal Studies; Male; Marriage; Middle Aged; Socioeconomic factors; Spouses; United States; Widowhood

Linked Lives: Dyadic Associations of Mastery Beliefs With Health (Behavior) and Health (Behavior) Change Among Older Partners. - Drewelies, Johanna; William J. Chopik; Christiane A Hoppmann; Jacqui Smith; Denis Gerstorf (J Gerontol B Psychol Sci Soc Sci, 2018)
Objectives: Mastery beliefs are known to contribute to healthy aging. However, it is an open question whether individual mastery-health associations impact the health of close long-term partners. Method: We applied actor-partner interdependence models to 4-wave, 6-year longitudinal dyadic data from married and cohabitating partners in the Health and Retirement Study (N = 1,981 partners; age at baseline: M = 67 years, SD = 8.93, range 50-94 years). Results: Higher individual mastery beliefs were associated with better individual physical health and health behaviors. Higher mastery beliefs were associated with subsequent increases in light physical activity. Having a partner with higher levels of mastery was uniquely associated with fewer functional limitations, better self-rated health, and more physical activity. Actor × Partner interaction effects for functional limitations indicated multiplicative associations of actor and partner mastery with health. Of note, mastery-health associations for individuals and their partners were invariant across age, gender, education, employment status, perceived stress over one's own and partner's health, and cognition. Discussion: Findings suggest that partner mastery beliefs matter for the health (behaviors) of older adults. We discuss possible mechanisms underlying partner interrelations in mastery and health, their age invariance, and consider implications arising from our results.
Keywords: Aged; Aged, 80 and over; Dominance-Subordination; Female; Health Behavior; Health Status; Humans; Male; Marriage; Middle Aged; Models, Theoretical; Psychological Tests; Risk Reduction Behavior; Surveys and Questionnaires

Smoking Cessation and Changes in Body Mass Index Among Middle Aged and Older Adults. - Sharma, Andy (J Appl Gerontol, 2018)
OBJECTIVE: This study contributes to the body of literature examining smoking cessation and body mass index (BMI) for adults aged 50 and older. METHOD: Utilizing the 2004 and 2010 waves of the RAND Health and Retirement Study, this analysis utilized Fixed Effects (FE) regression on a sample of 1,316 adults aged 50 and older. RESULTS: Older adults undergo a small change in BMI after a transition from smoking to nonsmoking during a 6-year period, and this occurs after accounting for individual-level unobserved heterogeneity. More specifically, men experience a BMI gain of 1.24 ( p< .01) and women experience a BMI gain of 1.58 ( p< .01). DISCUSSION: Gerontologists/health professionals can use these results to inform older adults about the potential for a small increase in BMI and, in the process, assuage any apprehensions about excessive weight gain. This insight may encourage a greater number of older adults to cease smoking.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Female; Humans; Male; Middle Aged; Models, Statistical; Smoking cessation; Weight Gain

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Gail Davies; Lam, Max; Sarah E Harris; Joey W Trampush; Luciano, Michelle; W David Hill; Hagenaars, Saskia P; Ritchie, Stuart J; Riccardo E Marioni; Fawns-Ritchie, Chloe; David C Liewald; Okely, Judith A; et al. (Nature Communications, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cognition; Genetic Loci; Genetic Predisposition to Disease; Humans; Mental Disorders; Middle Aged; Multifactorial Inheritance; Neurodegenerative Diseases; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Reaction Time; Young Adult

Survival Advantage Mechanism: Inflammation as a Mediator of Positive Self-Perceptions of Aging on Longevity. - Becca R Levy; Bavishi, Avni (J Gerontol B Psychol Sci Soc Sci, 2018)
OBJECTIVE: Previous studies have found that positive self-perceptions of aging (SPA) are associated with longer survival; however, a biological mechanism was unknown. We examined whether C-reactive protein (CRP), a marker of cumulative stress-related inflammation, mediates the relationship between SPA and survival. METHOD: The SPA of participants aged 50 and older in the Health and Retirement Study (N = 4,149) were assessed at baseline. Inflammation was measured by the level of CRP 4 years later. Survival was followed for up to 6 years. RESULTS: As hypothesized, CRP mediated the impact of SPA on survival. Following the steps of a mediation analysis, positive SPA at baseline predicted lower CRP after 4 years (β = -.29, p = .03) and longer survival in the 2 years following the CRP measurement (β = .20, p =.003); additionally, lower CRP predicted longer survival, after adjusting for positive SPA (β = -.02, p = .0001). All models adjusted for baseline age, CRP, health, sex, race, and education. DISCUSSION: It was found that lower CRP partially mediates the relationship between positive SPA and longer survival. Hence, this study presents a novel pathway to explain the process by which positive SPA extend longevity.
10.1093/geronb/gbw035
Keywords: Aged; Aged, 80 and over; Aging; Biomarkers; C-reactive protein; Female; Humans; Inflammation; Longevity; Male; Middle Aged; Self Concept; Surveys and Questionnaires; Survival Analysis

Aging perceptions and self-efficacy mediate the association between personality traits and depressive symptoms in older adults. - O'Shea, Deirdre M; Vonetta M Dotson; Fieo, Robert A (Int J Geriatr Psychiatry, 2017)
OBJECTIVE: Personality traits have been shown to be predictors of depressive symptoms in late life. Thus, we examined whether other more modifiable sources of individual differences such as self-efficacy and self-perceptions of aging would mediate the association between personality traits and depressive symptoms in older adults. METHOD: Data were obtained from 3,507 older adult participants who took part in the 2012 Health and Retirement Study. The "Big Five" personality traits, self-efficacy, aging perceptions, and depressive symptoms were assessed. Mediation analyses tested the hypothesis that self-efficacy and aging perceptions would mediate the relationship between personality traits and depressive symptoms. RESULTS: All five personality traits were significant predictors of depressive symptoms. Neuroticism was positively associated with depressive symptoms and had the greatest effect compared with the other personality traits. There was a significant indirect effect of neuroticism, extraversion, and conscientiousness on depressive symptoms (including both mediators). The mediating effect of aging perceptions on the relationship between neuroticism and depressive symptoms was the strongest compared with self-efficacy, accounting for approximately 80% of the total indirect effect. CONCLUSION: Our results provide support for interventions aimed at improving self-perceptions related to efficacy and aging in order to reduce depressive symptoms in older adults. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: Aged; Aged, 80 and over; Aging; Depressive Disorder; Female; Humans; Male; Middle Aged; Personality; Risk Factors; Self Concept; Self Efficacy

Another Paradox? The Life Satisfaction of Older Hispanic Immigrants in the United States. - Rocío Calvo; Dawn C Carr; Matz-Costa, Christina (J Aging Health, 2017)
OBJECTIVE: To investigate disparities in life satisfaction among older Hispanic immigrants in the United States relative to their native-born Hispanic and non-Hispanic White counterparts, and to identify factors associated with such disparities. METHOD: Cross-sectional data from 9,798 individuals age 60 and above from the Health and Retirement Study (HRS) were used to estimate ordinary least squares (OLS) regression models. RESULTS: Hispanic immigrants reported the highest levels of life satisfaction of all groups. Wealthier older adults, who were socially engaged, had social support, and experienced fewer functional limitations and lower exposure to discrimination, were more satisfied with their lives in the overall sample. Interaction effects revealed that although education was associated with greater life satisfaction only among non-Hispanic Whites, co-residing with children was associated with greater life satisfaction only among Hispanics. DISCUSSION: Although older Hispanic immigrants had the least amount of socioeconomic resources of all groups in our study, they were the most satisfied with their lives. Possible explanations and directions for future research are discussed.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Emigrants and Immigrants; Female; Health Status; Humans; Male; Middle Aged; Models, Theoretical; Personal Satisfaction; Surveys and Questionnaires

The association between antidepressant use and hemoglobin A1C in older adults. - Kammer, Jamie; Akiko S Hosler; Leckman-Westin, Emily; A. Gregory DiRienzo (Geriatr Nurs, 2017)
Depression is known to increase diabetes risk and worsen glycemic control in older adults, who already experience high rates of diabetes. The independent impact of antidepressants on glucose control is less clear. Data was drawn from the Health and Retirement Study, a large nationally-representative longitudinal study of retired individuals. Crude and adjusted linear models stratified by diabetes status were used to examine the cross-sectional associations between antidepressant use categorized by subclass and continuous hemoglobin A1C. The sample included 1,153 individuals, most over the age of 70. Antidepressant use was not associated with hemoglobin A1C in any model whether stratified or in the total combined sample. Antidepressants as a class were also not associated with hemoglobin A1C. These findings add to the literature suggesting that antidepressants are not associated with diabetes risk or glycemic control. Prospective studies with larger sample sizes are needed to confirm this finding.
Keywords: Aged; Aged, 80 and over; Antidepressive Agents; Blood Glucose; Cross-Sectional Studies; depression; Diabetes Mellitus, Type 2; Female; Glycated Hemoglobin A; Humans; Longitudinal Studies; Male; Risk Factors; Surveys and Questionnaires

Associations Among Individuals' Perceptions of Future Time, Individual Resources, and Subjective Well-Being in Old Age. - Christiane A Hoppmann; Frank J Infurna; Ram, Nilam; Denis Gerstorf (J Gerontol B Psychol Sci Soc Sci, 2017)
OBJECTIVES: Perceptions of future time are of key interest to aging research because of their implications for subjective well-being. Interestingly, perceptions about future time are only moderately associated with age when looking at the second half of life, pointing to a vast heterogeneity in future time perceptions among older adults. We examine associations between future time perceptions, age, and subjective well-being across two studies, including moderations by individual resources. METHOD: Using data from the Berlin Aging Study (N = 516; Mage = 85 years), we link one operationalization (subjective nearness to death) and age to subjective well-being. Using Health and Retirement Study data (N = 2,596; Mage = 77 years), we examine associations of another future time perception indicator (subjective future life expectancy) and age with subjective well-being. RESULTS: Consistent across studies, perceptions of limited time left were associated with poorer subjective well-being (lower life satisfaction and positive affect; more negative affect and depressive symptoms). Importantly, individual resources moderated future time perception-subjective well-being associations with those of better health exhibiting reduced future time perception-subjective well-being associations. DISCUSSION: We discuss our findings in the context of the Model of Strength and Vulnerability Integration.
Keywords: Affect; Age Factors; Aged; Aged, 80 and over; Aging; Attitude; depression; Female; Forecasting; Health Status; Humans; Male; Personal Satisfaction

Associations between community-level disaster exposure and individual-level changes in disability and risk of death for older Americans. - Samuel L. Brilleman; Wolfe, Rory; Moreno-Betancur, Margarita; Anne E Sales; Kenneth M. Langa; Yun Li; Elizabeth L. Daugher Biddison; Rubinson, Lewis; Theodore J Iwashyna (Soc Sci Med, 2017)
Disasters occur frequently in the United States (US) and their impact on acute morbidity, mortality and short-term increased health needs has been well described. However, barring mental health, little is known about the medium or longer-term health impacts of disasters. This study sought to determine if there is an association between community-level disaster exposure and individual-level changes in disability and/or the risk of death for older Americans. Using the US Federal Emergency Management Agency's database of disaster declarations, 602 disasters occurred between August 1998 and December 2010 and were characterized by their presence, intensity, duration and type. Repeated measurements of a disability score (based on activities of daily living) and dates of death were observed between January 2000 and November 2010 for 18,102 American individuals aged 50-89 years, who were participating in the national longitudinal Health and Retirement Study. Longitudinal (disability) and time-to-event (death) data were modelled simultaneously using a 'joint modelling' approach. There was no evidence of an association between community-level disaster exposure and individual-level changes in disability or the risk of death. Our results suggest that future research should focus on individual-level disaster exposures, moderate to severe disaster events, or higher-risk groups of individuals.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Community Participation; Continental Population Groups; Disabled Persons; Disaster Planning; Disasters; Female; Humans; Income; Longitudinal Studies; Male; Middle Aged; Mortality; United States

Back to Work? Not Everyone. Examining the Longitudinal Relationships Between Informal Caregiving and Paid Work After Formal Retirement. - Gonzales, Ernest; Lee, Yeonjung; Brown, Celeste (Journal of Gerontology, Series B, 2017)
Objectives: Research on unretirement (retirees who re-enter the workforce) is burgeoning. However, no longitudinal study has examined how informal care relates to unretirement. Utilizing role theory, this study aims to explore the heterogeneity of informal care responsibilities in retirement and to examine how informal care informs re-entering the workforce in later life. Method: Data were drawn from the Health and Retirement Study of fully retired individuals aged 62 years and older in 1998 (n = 8,334) and followed to 2008. Informal care responsibilities included helping a spouse/partner with activities of daily living (ADLs) or instrumental activities of daily living (IADLs); helping parent(s) or parent-in-law(s) with ADLs or IADLs; and single or co-occurrence of care roles. Covariates included economic and social factors. Cox proportional hazard models were utilized. Results: When compared with noncaregivers, helping a spouse with ADLs or IADLs reduced the odds of returning-to-work in the subsequent wave by 78% and 55%, respectively (hazard ratio [HR]: 0.22, confidence interval [CI]: 0.06-0.87; HR: 0.45, CI: 0.21-0.97). There was no statistical difference to returning-to-work between noncaregivers and helping parents with ADLs/IADLs or multiple caregiving responsibilities. Discussion: Role theory provided a useful framework to understand the relationships of informal care and unretirement. Aspects of role strain emerged, where, spousal caregivers were less likely to come out of retirement. Spousal caregivers may face challenges to working longer, and subsequently, opportunities to bolster their retirement security are diminished. Research and policy implications are discussed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Employment; Family; Female; Humans; Longitudinal Studies; Male; Middle Aged; Retirement; return to work

Is Childhood Socioeconomic Status Independently Associated with Adult BMI after Accounting for Adult and Neighborhood Socioeconomic Status? - Gregory Pavela (PLoS One, 2017)
Childhood socioeconomic status (SES) is inversely associated with adult weight in high income countries. Whether the influence of childhood SES on adult weight is best described using a critical period model or an accumulation of risk model is not yet settled. This research tests whether childhood SES is associated with adult BMI and likelihood of obesity independent of adult socioeconomic status and neighborhood characteristics. Data on individual childhood and adult characteristics come from the Health and Retirement Study (N = 13,545). Data on neighborhood characteristics come from the 2000 Decennial Census and American Community Survey (2005-2009). In the fully adjusted models, perceived financial hardship before the age of sixteen and having a father who was unemployed are associated with higher BMI among males and, among females, paternal education remains associated with adult BMI. However, childhood SES is not associated with likelihood of obesity after fully adjusting for adult SES and neighborhood characteristics, suggesting that the direct effects of early childhood SES on BMI are small relative to the other factors associated with obesity in adulthood.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alabama; Body Mass Index; Child; Female; Health Behavior; Humans; Male; Middle Aged; Obesity; Residence Characteristics; Risk Factors; Social Class; Socioeconomic factors; Young Adult

The Costs of Fall-Related Injuries among Older Adults: Annual Per-Faller, Service Component, and Patient Out-of-Pocket Costs. - Geoffrey J Hoffman; Hays, Ron D; Martin F Shapiro; Steven P Wallace; Susan L Ettner (Health Serv Res, 2017)
OBJECTIVE: To estimate expenditures for fall-related injuries (FRIs) among older Medicare beneficiaries. DATA SOURCES: The 2007-2009 Medicare claims and 2008 Health and Retirement Study (HRS) data for 5,497 (228 FRI and 5,269 non-FRI) beneficiaries. STUDY DESIGN: FRIs were indicated by inpatient/outpatient ICD-9 diagnostic codes for fractures, trauma, dislocations, and by e-codes. A pre-post comparison group design was used to estimate the differential change in pre-post expenditures for the FRI relative to the non-FRI cohort (FRI expenditures). Out-of-pocket (OOP) costs, service category total annual FRI-related Medicare expenditures, expenditures related to the type of initial FRI treatment (inpatient, ED, outpatient), and the risk of persistently high expenditures (4th quartile for each post-FRI quarter) were estimated. PRINCIPAL FINDINGS: Estimated FRI expenditures were $9,389 (95 percent CI: $5,969-$12,808). Inpatient, physician/outpatient, skilled nursing facility, and home health comprised 31, 18, 39, and 12 percent of the total. OOP costs were $1,363.0 (95 percent CI: $889-$1,837). Expenditures for FRIs initially treated in inpatient/ED/outpatient settings were $21,424/$6,142/$8,622. The FRI cohort had a 64 percent increased risk of persistently high expenditures. Total Medicare expenditures were $13 billion (95 percent CI: $9-$18 billion). CONCLUSIONS: FRIs are associated with substantial, persistent Medicare expenditures. Cost-effectiveness of multifactorial falls prevention programs should be assessed using these expenditure estimates.
Keywords: Accidental Falls; Age Factors; Aged; Aged, 80 and over; Female; Financing, Personal; Health Expenditures; Health Services; Humans; Male; Medicare; Models, Econometric; Sex Factors; Socioeconomic factors; United States; Wounds and Injuries

Death across the lifespan: Age differences in death-related thoughts and anxiety. - William J. Chopik (Death Stud, 2017)
Many studies have found age-related declines in death-related anxiety. Why do death-related thoughts and anxiety decline across the lifespan when exposure to, and likelihood of, death increase over time? In Study 1, a cross-sectional survey of 2,363 adults, death-related thoughts declined across the lifespan. In Study 2, a longitudinal study of 9,815 adults followed over a 4-year period, death anxiety declined across the lifespan. Further, greater social support predicted lower levels of death anxiety over time, after controlling for self-rated health and chronic illnesses. Close relationships serve emotion regulation functions to decrease death anxiety and thoughts across the lifespan.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Aging; Anxiety; Attitude to Death; Cross-Sectional Studies; Female; Humans; Longitudinal Studies; Male; Middle Aged; Thinking; Young Adult

Development and Validation of a 10-Year Mortality Prediction Model: Meta-Analysis of Individual Participant Data From Five Cohorts of Older Adults in Developed and Developing Countries. - Suemoto, Claudia Kimie; Ueda, Hiroshi; Hiram Beltrán-Sánchez; Lebrão, Maria Lucia; Duarte, Yeda Aparecida; Rebeca Wong; Danaei, Goodarz (J Gerontol A Biol Sci Med Sci, 2017)
Background: Existing mortality prediction models for older adults have been each developed using a single study from the United States or Western Europe. We aimed to develop and validate a 10-year mortality prediction model for older adults using data from developed and developing countries. Methods: We used data from five cohorts, including data from 16 developed and developing countries: ELSA (English Longitudinal Study of Aging), HRS (Health and Retirement Study), MHAS (Mexican Health and Aging Study), SABE-Sao Paulo (The Health, Well-being and Aging), and SHARE (Survey on Health, Ageing and Retirement in Europe). 35,367 older adults were split into training (two thirds) and test (one third) data sets. Baseline predictors included age, sex, comorbidities, and functional and cognitive measures. We performed an individual participant data meta-analysis using a sex-stratified Cox proportional hazards model, with time to death as the time scale. We validated the model using Harrell's C statistic (discrimination) and the estimated slope between observed and predicted 10-year mortality risk across deciles of risk (calibration). Results: During a median of 8.6 years, 8,325 participants died. The final model included age, sex, diabetes, heart disease, lung disease, cancer, smoking, alcohol use, body mass index, physical activity, self-reported health, difficulty with bathing, walking several blocks, and reporting date correctly. The model showed good discrimination (Harrell's C = 0.76) and calibration (slope = 1.005). Models for developed versus developing country cohorts performed equally well when applied to data from developing countries. Conclusion: A parsimonious mortality prediction model using data from multiple cohorts in developed and developing countries can be used to predict mortality in older adults in both settings.
Keywords: Aged; Aged, 80 and over; Developed Countries; Developing Countries; Female; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Statistical; Mortality; Prognosis; Time Factors

Do Regular Cholesterol Screenings Lead to Lower Cholesterol Levels and Better Health Behaviors for All? Spotlight on Middle-Aged and Older Adults in the United States. - Choi, Yool; Lee, Hyo Jung (J Aging Health, 2017)
OBJECTIVE: This study investigates how the causal effects of cholesterol screening differ by likelihood of using this preventive care service in terms of accessibility gaps and effects on health-related outcomes across groups with advantaged and disadvantaged backgrounds. METHOD: We use propensity score matching to analyze a nationally representative sample using data from 2008, 2010, and 2012 waves of the Health and Retirement Study ( N = 3,907). RESULTS: We find that respondents who are least likely to get their cholesterol tested benefit most from the use of cholesterol screening when they do use it, while its effects are smallest for those who are most likely to use this service. DISCUSSION: Understanding the heterogeneous effects of preventive health service has important policy implications, particularly in terms of how to maximize the public health benefits of preventive care.
Keywords: Aged; Aged, 80 and over; Cholesterol; Female; Health Behavior; Humans; Longitudinal Studies; Male; Mass Screening; Middle Aged; Preventive Health Services; United States

Emergency Preparedness of Persons Over 50 Years Old: Further Results From the Health and Retirement Study. - Timothy S Killian; Zola K Moon; McNeill, Charleen; Garrison, Betsy; Moxley, Shari (Disaster Med Public Health Prep, 2017)
OBJECTIVE: This article conceptualized emergency preparedness as a complex, multidimensional construct and empirically examined an array of sociodemographic, motivation, and barrier variables as predictors of levels of emergency preparedness. METHODS: The authors used the 2010 wave of the Health and Retirement Study's emergency preparedness module to focus on persons 50 years old and older in the United States by use of logistic regression models and reconsidered a previous analysis. RESULTS: The models demonstrated 3 key findings: (1) a lack of preparedness is widespread across virtually all sociodemographic variables and regions of the country; (2) an authoritative voice, in the role of health care personnel, was a strong predictor of preparedness; and (3) previous experience in helping others in a disaster predisposes individuals to be better prepared. Analyses also suggest the need for caution in creating simple summative indexes and the need for further research into appropriate measures of preparedness. CONCLUSION: This population of older persons was generally not well prepared for emergencies, and this lack of preparedness was widespread across social, demographic, and economic groups in the United States. Findings with implications for policy and outreach include the importance of health care providers discussing preparedness and the use of experienced peers for outreach. (Disaster Med Public Health Preparedness. 2017;11:80-89).
Keywords: Aged; Aged, 80 and over; Attitude to Health; Civil Defense; Equipment and Supplies; Female; Help-Seeking Behavior; Humans; Male; Middle Aged; Retirement; United States; Vulnerable Populations

Extracting Response Style Bias From Measures of Positive and Negative Affect in Aging Research. - Stefan Schneider (J Gerontol B Psychol Sci Soc Sci, 2017)
Objectives: This study investigated the role of response style biases in the assessment of positive and negative affect in aging research; it addressed whether response styles (a) are associated with age-related changes in cognitive abilities, (b) lead to distorted conclusions about age differences in affect, and (c) reduce the convergent and predictive validity of affect measures in relation to health outcomes. Method: A multidimensional item response theory model was used to extract response styles from affect ratings provided by respondents to the psychosocial questionnaire (n = 6,295; aged 50-100 years) in the Health and Retirement Study (HRS). Results: The likelihood of extreme response styles (disproportionate use of "not at all" and "very much" response categories) increased significantly with age, and this effect was mediated by age-related decreases in HRS cognitive test scores. Removing response styles from affect measures did not alter age patterns in positive and negative affect; however, it consistently enhanced the convergent validity (relationships with concurrent depression and mental health problems) and predictive validity (prospective relationships with hospital visits, physical illness onset) of the affect measures. Discussion: The results support the importance of detecting and controlling response styles when studying self-reported affect in aging research.
Keywords: Affect; Age Factors; Aged; Aged, 80 and over; Bias; cognitive aging; Geriatrics; Humans; Male; Middle Aged; Models, Psychological; Psychology; Reproducibility of Results; Research; Surveys and Questionnaires

Feeling Older and the Development of Cognitive Impairment and Dementia. - Yannick Stephan; Angelina R Sutin; Martina Luchetti; Antonio Terracciano (J Gerontol B Psychol Sci Soc Sci, 2017)
Objective: Subjective age is a biopsychosocial marker of aging associated with a range of outcomes in old age. In the domain of cognition, feeling older than one's chronological age is related to lower cognitive performance and steeper cognitive decline among older adults. The present study examines whether an older subjective age is associated with the risk of incident cognitive impairment and dementia. Method: Participants were 5,748 individuals aged 65 years and older drawn from the Health and Retirement Study. Measures of subjective age, cognition, and covariates were obtained at baseline, and follow-up cognition was assessed over a 2- to 4-year period. Only participants without cognitive impairment were included at baseline. At follow-up, participants were classified into one of the three categories: normal functioning, cognitive impairment without dementia (CIND), and dementia. Results: An older subjective age at baseline was associated with higher likelihood of CIND (odds ratio [OR] = 1.18; 1.09-1.28) and dementia (OR = 1.29; 1.02-1.63) at follow-up, controlling for chronological age, other demographic factors, and baseline cognition. Physical inactivity and depressive symptoms partly accounted for these associations. Conclusion: An older subjective age is a marker of individuals' risk of subsequent cognitive impairment and dementia.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer disease; Cognitive Dysfunction; depression; disease progression; Female; Health Behavior; Humans; Life Style; Likelihood Functions; Logistic Models; Longitudinal Studies; Male; Risk Factors; Self Concept

Financial Care for Older Adults With Dementia. - Pan, Xi; Lee, Yeonjung; Dye, Cheryl; Laurie Theriot Roley (Int J Aging Hum Dev, 2017)
This article describes an examination of the sociodemographic characteristics of adult children, particularly Baby Boomer caregivers, who provide financial care to older parents with dementia. The sample including 1,011adult children dementia caregivers aged 50 to 64 years is selected from a nationally representative sample in the 2010 Health and Retirement Study. Exact logistic regression revealed that race, provision of financial assistance to caregiver children, and the number of their children are significantly associated with financial caregiving of parents. Non-White caregivers are more likely to provide financial care to their parents or parents-in-law with dementia; those who have more children and provide financial assistance to their children are less likely to provide financial care to parents with dementia. The current findings present valuable new information on the sociodemographic characteristics of adult children who provide financial assistance to parents with dementia and inform research, programs, and services on dementia caregiving.
Keywords: Adult children; Aged; Aged, 80 and over; Dementia; Female; Humans; Male; Middle Aged; United States

Foundations of Activity of Daily Living Trajectories of Older Americans. - Linda G Martin; Zachary Zimmer; Jinkook Lee (J Gerontol B Psychol Sci Soc Sci, 2017)
OBJECTIVES: The disablement process can be viewed conceptually as a progression from disease to impairment to functional limitation and finally disability (frequently operationalized as activity limitation). This article assesses the extent to which early phases of the process are associated with individual-level disability trajectories by age. METHOD: We use data from seven waves of the Health and Retirement Study, 1998 to 2010, to investigate for individuals aged 65-84 years how baseline sociodemographic characteristics and self-reported disease, pain, and functional limitation (physical, cognitive, or sensory) are related to the dynamics of limitations in activities of daily living (ADLs). Our modeling approach jointly estimates multiperiod trajectories of ADL limitation and mortality and yields estimates of the number of, shapes of, and factors associated with the most common trajectories. RESULTS: Individual probability of ADL limitation can best be described by three common trajectories. In comparison with disease, pain, and functional limitation, sociodemographic characteristics have weak associations with trajectory group membership. Notably, neither sex nor education is strongly associated with group membership in multivariate models. DISCUSSION: The analysis confirms the importance of the early phases of the disablement process and their relationships with subsequent trajectories of activity limitation.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Chronic pain; cognitive aging; Disability Evaluation; disease progression; Female; Humans; Individuality; Male; Middle Aged; Socioeconomic factors; Statistics as Topic; United States

Genome-wide Association Study of Parental Life Span. - Toshiko Tanaka; Ambarish Dutta; Luke C Pilling; Xue, Luting; Kathryn L Lunetta; Joanne M Murabito; Bandinelli, Stefania; Robert B Wallace; David Melzer; Luigi Ferrucci (J Gerontol A Biol Sci Med Sci, 2017)
Background: Having longer lived parents has been shown to be an important predictor of health trajectories and life span. As such, parental life span is an important phenotype that may uncover genes that affect longevity. Methods: A genome-wide association study of parental life span in participants of European and African ancestry from the Health and Retirement Study was conducted. Results: A genome-wide significant association was observed for rs35715456 (log10BF = 6.3) on chromosome 18 for the dichotomous trait of having at least one long-lived parent versus not having any long-lived parent. This association was not replicated in an independent sample from the InCHIANTI and Framingham Heart Study. The most significant association among single nucleotide polymorphisms in longevity candidate genes (APOE, MINIPP1, FOXO3, EBF1, CAMKIV, and OTOL1) was observed in the EBF1 gene region (rs17056207, p = .0002). Conclusions: A promising genetic signal for parental life span was identified but was not replicated in independent samples.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human, Pair 18; Female; Genome-Wide Association Study; Humans; Longevity; Male; Middle Aged; Parents; Phenotype; Polymorphism, Single Nucleotide; Trans-Activators

Healthy Aging in the Context of Educational Disadvantage: The Role of "Ordinary Magic". - Sara J McLaughlin (J Aging Health, 2017)
OBJECTIVE: The objective of this study is to examine the correlates of healthy aging in the context of educational disadvantage and the extent to which identified correlates are shared with the wider, more educationally advantaged population. METHOD: Data are from the 2012 Health and Retirement Study. The analytic sample included 17,484 self-respondents ≥50 years of age. Educational disadvantage was defined as having less than a high school diploma. Using logistic regression, healthy aging was regressed on demographic, early-life, and health-related factors by educational status. RESULTS: Among educationally disadvantaged adults, demographic characteristics (e.g., age), health practices (e.g., physical activity), and the presence of health conditions were independently correlated with healthy aging. With few exceptions, correlates of healthy aging were similar among educationally advantaged and disadvantaged adults. DISCUSSION: Ordinary factors are associated with healthy aging among adults without a high school diploma, suggesting that healthy aging is possible for larger numbers of adults aging in the context of educational disadvantage.
Keywords: Aged; Aged, 80 and over; Educational Status; Female; Health Behavior; healthy aging; Humans; Logistic Models; Male; Middle Aged; Social Class; United States

Home and community-based service and other senior service use: Prevalence and characteristics in a national sample. - Amanda Sonnega; Kristen N Robinson; Helen G Levy (Home Health Care Serv Q, 2017)
We report on the use of home and community-based services (HCBS) and other senior services and factors affecting utilization of both among Americans over age 60 in the Health and Retirement Study (HRS). Those using HCBS were more likely to be older, single, Black, lower income, receiving Medicaid, and in worse health. Past use of less traditional senior services, such as exercise classes and help with tax preparation, were found to be associated with current use of HCBS. These findings suggest use of less traditional senior services may serve as a "gateway" to HCBS that can help keep older adults living in the community.
Keywords: Aged; Aged, 80 and over; Community Health Services; Female; Home Care Services; Humans; Logistic Models; Longitudinal Studies; Male; Middle Aged; Prevalence; Senior Centers; United States

Identifying adults aging with disability using existing data: The case of the Health and Retirement Study. - Caitlin E. Coyle; Putnam, Michelle (Disabil Health J, 2017)
BACKGROUND: The population of persons aging with disabilities is growing. Being able to segment aging with disability sub-populations within national data sets is becoming increasingly important in order to understand the relationship of aging with disability to a range of outcomes in later life including health and wellness, economic security, and health and long-term service and support need and use. OBJECTIVE: The purpose of this study was to identify viable sub-samples of adults aging with disabilities within the Health and Retirement Study, one of the most used secondary data sets to study aging and older adults. METHOD: Samples used in this research are drawn from wave 11 (2012) of the HRS. Five operationalizations of disability were used: childhood disability (n = 719), childhood chronic condition (n = 3070), adult chronic condition (n = 13,723), functional limitation in adulthood (n = 4448) and work disability (n = 5632). RESULTS: These subsamples are not mutually exclusive. Among respondents that reported having a childhood disability, 87% also report having at least one chronic disease in adulthood, 50% report having functional limitations in adulthood and 38% report interruption in their ability to work due to a disability. Compared to the childhood disability samples, rates of reporting fair/poor health are nearly double among adults with functional limitations or those with work disruptions because of disability. CONCLUSION: Work disability and functional limitation appeared to be the most viable sub-sample options to consider when using the HRS to study experiences of adults aging with disability. Overall, age at onset is unclear.
Keywords: Activities of Daily Living; Adolescent; Age of Onset; Aged; Aged, 80 and over; Aging; Child; Child Health; Chronic disease; Disabled Persons; Female; health; Health Status; Health Surveys; Humans; Male; Middle Aged; Retirement; Self Report; Work

Identifying Older Adults with Serious Illness: A Critical Step toward Improving the Value of Health Care. - Amy Kelley; Kenneth E Covinsky; Rebecca Jean Gorges; McKendrick, Karen; Bollens-Lund, Evan; R Sean Morrison; Christine S Ritchie (Health Serv Res, 2017)
OBJECTIVE: To create and test three prospective, increasingly restrictive definitions of serious illness. DATA SOURCES: Health and Retirement Study, 2000-2012. STUDY DESIGN: We evaluated subjects' 1-year outcomes from the interview date when they first met each definition: (A) one or more severe medical conditions (Condition) and/or receiving assistance with activities of daily living (Functional Limitation); (B) Condition and/or Functional Limitation and hospital admission in the last 12 months and/or residing in a nursing home (Utilization); and (C) Condition and Functional Limitation and Utilization. Definitions are increasingly restrictive, but not mutually exclusive. DATA COLLECTION: Of 11,577 eligible subjects, 5,297 met definition A; 3,151 definition B; and 1,447 definition C. PRINCIPAL FINDINGS: One-year outcomes were as follows: hospitalization 33 percent (A), 44 percent (B), 47 percent (C); total average Medicare costs $20,566 (A), $26,349 (B), and $30,828 (C); and mortality 13 percent (A), 19 percent (B), 28 percent (C). In comparison, among those meeting no definition, 12 percent had hospitalizations, total Medicare costs averaged $7,789, and 2 percent died. CONCLUSIONS: Prospective identification of older adults with serious illness is feasible using clinically accessible criteria and may be a critical step toward improving health care value. These definitions may aid clinicians and health systems in targeting patients who could benefit from additional services.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Critical Illness; Early Diagnosis; Female; Health Care Costs; Hospitalization; Humans; Male; Medicare; Nursing homes; Prospective Studies; Quality Improvement; United States

Identifying Specific Combinations of Multimorbidity that Contribute to Health Care Resource Utilization: An Analytic Approach. - Nicholas K Schiltz; David F Warner; Jiayang Sun; Paul M Bakaki; Avi Dor; Charles W Given; Kurt C Stange; Siran M Koroukian (Med Care, 2017)
BACKGROUND: Multimorbidity affects the majority of elderly adults and is associated with higher health costs and utilization, but how specific patterns of morbidity influence resource use is less understood. OBJECTIVE: The objective was to identify specific combinations of chronic conditions, functional limitations, and geriatric syndromes associated with direct medical costs and inpatient utilization. DESIGN: Retrospective cohort study using the Health and Retirement Study (2008-2010) linked to Medicare claims. Analysis used machine-learning techniques: classification and regression trees and random forest. SUBJECTS: A population-based sample of 5771 Medicare-enrolled adults aged 65 and older in the United States. MEASURES: Main covariates: self-reported chronic conditions (measured as none, mild, or severe), geriatric syndromes, and functional limitations. Secondary covariates: demographic, social, economic, behavioral, and health status measures. OUTCOMES: Medicare expenditures in the top quartile and inpatient utilization. RESULTS: Median annual expenditures were $4354, and 41% were hospitalized within 2 years. The tree model shows some notable combinations: 64% of those with self-rated poor health plus activities of daily living and instrumental activities of daily living disabilities had expenditures in the top quartile. Inpatient utilization was highest (70%) in those aged 77-83 with mild to severe heart disease plus mild to severe diabetes. Functional limitations were more important than many chronic diseases in explaining resource use. CONCLUSIONS: The multimorbid population is heterogeneous and there is considerable variation in how specific combinations of morbidity influence resource use. Modeling the conjoint effects of chronic conditions, functional limitations, and geriatric syndromes can advance understanding of groups at greatest risk and inform targeted tailored interventions aimed at cost containment.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Comorbidity; Female; Health Behavior; Health Expenditures; Health Status; Humans; Machine learning; Male; Medicare; Retrospective Studies; Self Report; Socioeconomic factors; United States

Loneliness, depression and cognitive function in older U.S. adults. - Nancy J. Donovan; Bei Wu; Dorene M. Rentz; Reisa A. Sperling; Gad A. Marshall; M. Maria Glymour (Int J Geriatr Psychiatry, 2017)
OBJECTIVE: To examine reciprocal relations of loneliness and cognitive function in older adults. METHODS: Data were analyzed from 8382 men and women, age 65 and older, participating in the US Health and Retirement Study from 1998 to 2010. Participants underwent biennial assessments of loneliness and depression (classified as no, low or high depression) determined by the Center for Epidemiologic Studies Depression scale (8-item version), cognition (a derived memory score based on a word list memory task and proxy-rated memory and global cognitive function), health status and social and demographic characteristics from 1998 to 2010. We used repeated measures analysis to examine the reciprocal relations of loneliness and cognitive function in separate models controlling sequentially and cumulatively for socio-demographic factors, social network, health conditions and depression. RESULTS: Loneliness at baseline predicted accelerated cognitive decline over 12 years independent of baseline socio-demographic factors, social network, health conditions and depression (β = -0.2, p = 0.002). After adjustment for depression interacting with time, both low and high depression categories were related to faster cognitive decline and the estimated effect of loneliness became marginally significant. Reciprocally, poorer cognition at baseline was associated with greater odds of loneliness over time in adjusted analyses (OR 1.3, 95% CI (1.1-1.5) p = 0.005), but not when controlling for baseline depression. Furthermore, cognition did not predict change in loneliness over time. CONCLUSION: Examining longitudinal data across a broad range of cognitive abilities, loneliness and depressive symptoms appear to be related risk factors for worsening cognition but low cognitive function does not lead to worsening loneliness over time. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Demography; Depressive Disorder; Female; Humans; Loneliness; Longitudinal Studies; Male; Middle Aged; Risk Factors

A Longitudinal Analysis of Site of Death: The Effects of Continuous Enrollment in Medicare Advantage Versus Conventional Medicare. - Elizabeth Edmiston Chen; Edward Alan Miller (Res Aging, 2017)
This study assessed the odds of dying in hospital associated with enrollment in Medicare Advantage (M-A) versus conventional Medicare Fee-for-Service (M-FFS). Data were derived from the 2008 and 2010 waves of the Health and Retirement Study ( n = 1,030). The sample consisted of elderly Medicare beneficiaries who died in 2008-2010 (34% died in hospital, and 66% died at home, in long-term senior care, a hospice facility, or other setting). Logistic regression estimated the odds of dying in hospital for those continuously enrolled in M-A from 2008 until death compared to those continuously enrolled in M-FFS and those switching between the two plans. Results indicate that decedents continuously enrolled in M-A had 43% lower odds of dying in hospital compared to those continuously enrolled in M-FFS. Financial incentives in M-A contracts may reduce the odds of dying in hospital.
Keywords: Aged; Aged, 80 and over; Decision making; Fee-for-Service Plans; Female; health policy; Hospices; Hospital Mortality; Humans; Longitudinal Studies; Male; Medicare Part C; Terminal Care; United States

Neighborhood age structure and cognitive function in a nationally-representative sample of older adults in the U.S. - Esther M Friedman; Regina A Shih; Mary E Slaughter; Margaret M Weden; Kathleen A. Cagney (Soc Sci Med, 2017)
Recent evidence suggests that living in a neighborhood with a greater percentage of older adults is associated with better individual health, including lower depression, better self-rated health, and a decreased risk of overall mortality. However, much of the work to date suffers from four limitations. First, none of the U.S.-based studies examine the association at the national level. Second, no studies have examined three important hypothesized mechanisms - neighborhood socioeconomic status and neighborhood social and physical characteristics - which are significantly correlated with both neighborhood age structure and health. Third, no U.S. study has longitudinally examined cognitive health trajectories. We build on this literature by examining nine years of nationally-representative data from the Health and Retirement Study (2002-2010) on men and women aged 51 and over linked with Census data to examine the relationship between the percentage of adults 65 and older in a neighborhood and individual cognitive health trajectories. Our results indicate that living in a neighborhood with a greater percentage of older adults is related to better individual cognition at baseline but we did not find any significant association with cognitive decline. We also explored potential mediators including neighborhood socioeconomic status, perceived neighborhood cohesion and perceived neighborhood physical disorder. We did not find evidence that neighborhood socioeconomic status explains this relationship; however, there is suggestive evidence that perceived cohesion and disorder may explain some of the association between age structure and cognition. Although more work is needed to identify the precise mechanisms, this work may suggest a potential contextual target for public health interventions to prevent cognitive impairment.
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Female; Health Status; Humans; Interpersonal Relations; Male; Residence Characteristics; Social Support; Socioeconomic factors; United States

Personality and Lung Function in Older Adults. - Antonio Terracciano; Yannick Stephan; Martina Luchetti; Gonzalez-Rothi, Ricardo; Angelina R Sutin (J Gerontol B Psychol Sci Soc Sci, 2017)
OBJECTIVES: Lung disease is a leading cause of disability and death among older adults. We examine whether personality traits are associated with lung function and shortness of breath (dyspnea) in a national cohort with and without chronic obstructive pulmonary disease (COPD). METHOD: Participants (N = 12,670) from the Health and Retirement Study were tested for peak expiratory flow (PEF) and completed measures of personality, health behaviors, and a medical history. RESULTS: High neuroticism and low extraversion, openness, agreeableness, and conscientiousness were associated with lower PEF, and higher likelihood of COPD and dyspnea. Conscientiousness had the strongest and most consistent associations, including lower risk of PEF less than 80% of the predicted value (OR = 0.67; 0.62-0.73) and dyspnea (OR = 0.52; 0.47-0.57). Although attenuated, the associations remained significant when accounting for smoking, physical activity, and chronic diseases including cardiovascular and psychiatric disorders. The associations between personality and PEF or dyspnea were similar among those with or without COPD, suggesting that psychological links to lung function are not disease dependent. In longitudinal analyses, high neuroticism (β = -0.019) and low conscientiousness (β = 0.027) predicted steeper declines in PEF. DISCUSSION: A vulnerable personality profile is common among individuals with limited lung function and COPD, predicts shortness of breath and worsening lung function.
Keywords: Aged; Aged, 80 and over; Anxiety Disorders; Character; Disease Susceptibility; Dyspnea; Female; Follow-Up Studies; Health Behavior; Humans; Male; Medical History Taking; Middle Aged; Neuroticism; Peak Expiratory Flow Rate; Pulmonary Disease, Chronic Obstructive; Risk Factors

Psychosocial correlates of cervical cancer screening among older Hispanic women. - Tamara J. Cadet; Stewart, Kathleen; Howard, Tenial (Soc Work Health Care, 2017)
Early detection through screening can reduce mortality rates of cervical cancer, and yet Hispanic women who have incidence rates higher than their non-Hispanic White counterparts are least likely to participate in cancer screening initiatives. This study utilized data from the 2008 wave of the Health and Retirement Study to investigate the psychosocial correlates associated with older Hispanic women's participation in cervical cancer screening services. Logistic regression models were used. Findings indicated that greater life satisfaction and religiosity were associated with a greater likelihood of participating in cervical cancer screening. Despite ongoing national conversations, evidence indicates there is agreement that underserved women need to be screened, particularly the older Hispanic population.
Keywords: Adult; Aged; Aged, 80 and over; Attitude to Health; Early Detection of Cancer; Female; Hispanic Americans; Humans; Logistic Models; Mass Screening; Middle Aged; Uterine Cervical Neoplasms

Race Differences in Advance Directive Completion. - Catheryn S Koss; Tamara A. Baker (J Aging Health, 2017)
OBJECTIVE: Rates of advance directive completion have increased over the past decade, but significant race differences remain. This study examined how overall increases in advance directive completion have affected disparities between White and African American older adults. METHOD: Data were taken from the Health and Retirement Study (HRS). Using logistic regression models, the odds of having an advance directive among a sample of older African Americans and Whites who died between 2001 and 2012 were compared ( N = 5,832). RESULTS: Odds for African Americans were 16% of the odds for Whites, p < .001, 95% confidence interval (CI) = [0.11, 0.23]. There were no significant interactions between race and year of death before 2010. During 2010-2012, the increase in the odds for African Americans was greater than for Whites, odds ratio (OR) = 1.95, p = .02, 95% CI = [1.14, 3.35]. DISCUSSION: Although race disparities remain, the gap between Whites and African Americans has begun to narrow.
Keywords: Advance directives; Aged; Aged, 80 and over; Black or African American; Female; Humans; Interviews as Topic; Logistic Models; Male; Qualitative Research; White People

Rates of Recovery to Pre-Fracture Function in Older Persons with Hip Fracture: an Observational Study. - Victoria L. Tang; Rebecca L. Sudore; Irena Cenzer; W John Boscardin; Alexander K Smith; Christine S Ritchie; Margaret Wallhagen; Finlayson, Emily; Petrillo, Laura; Kenneth E Covinsky (J Gen Intern Med, 2017)
BACKGROUND: Knowledge about expected recovery after hip fracture is essential to help patients and families set realistic expectations and plan for the future. OBJECTIVES: To determine rates of functional recovery in older adults who sustained a hip fracture based on one's previous function. DESIGN: Observational study. PARTICIPANTS: We identified subjects who sustained a hip fracture while enrolled in the nationally representative Health and Retirement Study (HRS) using linked Medicare claims. HRS interviews subjects every 2 years. Using information from interviews collected during the interview preceding the fracture and the first interview 6 or more months after the fracture, we determined the proportion of subjects who returned to pre-fracture function. MAIN MEASURES: Functional outcomes of interest were: (1) ADL dependency, (2) mobility, and (3) stair-climbing ability. We examined baseline characteristics associated with a return to: (1) ADL independence, (2) walking one block, and (3) climbing a flight of stairs. KEY RESULTS: A total of 733 HRS subjects ≥65 years of age sustained a hip fracture (mean age 84 ± 7 years, 77 % female). Thirty-one percent returned to pre-fracture ADL function, 34 % to pre-fracture mobility function, and 41 % to pre-fracture climbing function. Among those who were ADL independent prior to fracture, 36 % returned to independence, 27 % survived but needed ADL assistance, and 37 % died. Return to ADL independence was less likely for those ≥85 years old (26 % vs. 44 %), with dementia (8 % vs. 39 %), and with a Charlson comorbidity score >2 (23 % vs. 44 %). Results were similar for those able to walk a block and for those able to climb a flight of stairs prior to fracture. CONCLUSIONS: Recovery rates are low, even among those with higher levels of pre-fracture functional status, and are worse for patients who are older, cognitively impaired, and who have multiple comorbidities.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Comorbidity; Dementia; Female; Geriatric Assessment; Hip Fractures; Humans; Longitudinal Studies; Male; Mobility Limitation; Recovery of Function; Walking

Receipt of Caregiving and Fall Risk in US Community-dwelling Older Adults. - Geoffrey J Hoffman; Hays, Ron D; Steven P Wallace; Martin F Shapiro; Yakusheva, Olga; Susan L Ettner (Med Care, 2017)
BACKGROUND: Falls and fall-related injuries (FRI) are common and costly occurrences among older adults living in the community, with increased risk for those with physical and cognitive limitations. Caregivers provide support for older adults with physical functioning limitations, which are associated with fall risk. DESIGN: Using the 2004-2012 waves of the Health and Retirement Study, we examined whether receipt of low (0-13 weekly hours) and high levels (≥14 weekly hours) of informal care or any formal care is associated with lower risk of falls and FRIs among community-dwelling older adults. We additionally tested whether serious physical functioning (≥3 activities of daily living) or cognitive limitations moderated this relationship. RESULTS: Caregiving receipt categories were jointly significant in predicting noninjurious falls (P=0.03) but not FRIs (P=0.30). High levels of informal care category (P=0.001) and formal care (P<0.001) had stronger associations with reduced fall risk relative to low levels of informal care. Among individuals with ≥3 activities of daily living, fall risks were reduced by 21% for those receiving high levels of informal care; additionally, FRIs were reduced by 42% and 58% for those receiving high levels of informal care and any formal care. High levels of informal care receipt were also associated with a 54% FRI risk reduction among the cognitively impaired. CONCLUSIONS: Fall risk reductions among older adults occurred predominantly among those with significant physical and cognitive limitations. Accordingly, policy efforts involving fall prevention should target populations with increased physical functioning and cognitive limitations. They should also reduce financial barriers to informal and formal caregiving.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Female; Geriatric Assessment; Humans; Independent Living; Longitudinal Studies; Male; Middle Aged; Risk Assessment; Risk Factors; United States

The relationship between family support; pain and depression in elderly with arthritis. - Hung, Man; Bounsanga, Jerry; Maren W Voss; Anthony B. Crum; Wei Chen; Wendy Church Birmingham (Psychol Health Med, 2017)
The prevalence and chronic nature of arthritis make it the most common cause of disability among U.S.A adults. Family support reduces the negative impact of chronic conditions generally but its role in pain and depression for arthritic conditions is not well understood. A total of 844 males (35.0%) and 1567 females (65.0%) with arthritic conditions (n = 2411) were drawn from the 2012 Health and Retirement Study to examine the effect of family support on pain and depressive symptoms. Using regression analysis and controlling for age, ethnicity, gender, marital/educational status and employment/income, physical function/disability status, pain and antidepressant medications, and other clinical indicators of chronic health conditions, we examined the effects of family support (spouse, children, other) on pain and depression levels. Results indicated that depressive symptoms decreased significantly with strong family and spousal support (p < .05). Pain decreased as support levels increased, but was non-statistically significant. This study provides new insights into the relationship between family support, pain, and depression for individuals with arthritis. Future longitudinal studies are needed to evaluate family support and relationships over a wider spectrum of demographics.
Keywords: Aged; Aged, 80 and over; Aging; Arthralgia; Arthritis; depression; Family; Female; Humans; Male; Middle Aged; Social Support; United States

Social Activities, Incident Cardiovascular Disease, and Mortality. - Sae Hwang Han; Jane Tavares; Evans, Molly; Jane S Saczynski; Jeffrey A Burr (J Aging Health, 2017)
OBJECTIVE: This study examined the relationships between social activities, incident cardiovascular disease (CVD), and non-CVD mortality among older adults in the United States. METHOD: Data from the Health and Retirement Study (2006-2010) were employed. Two measures of social engagement, volunteering and informal helping, along with two measures of social participation, attendance at religious services and social group meetings, were included. Mediation models for health behaviors were estimated. RESULTS: Multinomial logistic regression models demonstrated that volunteering provided the most consistent results in terms of a lower risk of incident CVD and mortality. Furthermore, volunteering at higher time commitments is related to lower CVD incidence and death; informally helping others at a modest time commitment is related to lower risk of death only. Health behaviors mediated the relationships. Social participation was not related to either CVD or mortality. DISCUSSION: Social activity is a modifiable behavior that may be considered a potential health intervention.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Humans; Incidence; Leisure activities; Logistic Models; Male; Middle Aged; Retirement; United States

Social Capital and Unretirement: Exploring the Bonding, Bridging, and Linking Aspects of Social Relationships. - Guillermo Ernest Gonzales; Nowell, William Benjamin (Res Aging, 2017)
Working longer is an important area of research given extended life expectancy, shortfalls of retirement income, desires to remain socially engaged, and solvency concerns of social insurance programs. The purpose of this longitudinal population-based study of older adults is to examine how different types of social resources (social bonding, bridging, and linking) relate to returning to work after retirement. Data were drawn from the Health and Retirement Study of fully retired older adults aged 62+ in 1998 ( N = 8,334) and followed to 2008. After controlling for a comprehensive set of fixed and time-varying covariates, findings suggest that social bridging (informal volunteering) and social linking (formal volunteering, partnered with an employed spouse) were strongly and positively related to returning to work (Hazard Ratio [HR]: 1.49, p < .001; HR: 1.58, p < .0001; and HR: 1.75, p < .0001, respectively). Social bonding resources were not significantly associated with returning to work. Implications for social policy are discussed.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cross-Sectional Studies; Employment; Female; Humans; Longitudinal Studies; Male; Middle Aged; Retirement; Social capital; United States

Social determinants, multimorbidity, and patterns of end-of-life care in older adults dying from cancer. - Siran M Koroukian; Nicholas K Schiltz; David F Warner; Charles W Given; Mark Schluchter; Owusu, Cynthia; Nathan A. Berger (J Geriatr Oncol, 2017)
OBJECTIVE: Most prior studies on aggressive end-of-life care in older patients with cancer have accounted for social determinants of health (e.g., race, income, and education), but rarely for multimoribidity (MM). In this study, we examine the association between end-of-life care and each of the social determinants of health and MM, hypothesizing that higher MM is associated with less aggressive care. METHODS: From the linked 1991-2008 Health and Retirement Study, Medicare data, and the National Death Index, we identified fee-for-service patients age ≥66years who died from cancer (n=835). MM was defined as the occurrence or co-occurrence of chronic conditions, functional limitations, and/or geriatric syndromes. Aggressive care was based on claims-derived measures of receipt of cancer-directed treatment in the last two weeks of life; admission to the hospital and/or emergency department (ED) within the last month; and in-hospital death. We also identified patients enrolled in hospice. In multivariable logistic regression models, we analyzed the associations of interest, adjusting for potential confounders. RESULTS: While 61.2% of the patients enrolled in hospice, 24.6% underwent cancer-directed treatment; 55.1% were admitted to the hospital and/or ED; and 21.7% died in the hospital. We observed a U-shaped distribution between income and in-hospital death. Chronic conditions and geriatric syndromes were associated with some outcomes, but not with others. CONCLUSIONS: To improve quality end-of-life care and curtail costs incurred by dying patients, relevant interventions need to account for social determinants of health and MM in a nuanced fashion.
Keywords: Age Factors; Aged; Aged, 80 and over; Emergency Service, Hospital; Female; Health Surveys; Hospices; Hospital Mortality; Humans; Logistic Models; Male; multimorbidity; Neoplasms; Population Surveillance; Quality of Health Care; Risk Factors; Socioeconomic factors; Terminal Care

Social Inequalities in Inflammation: Age Variations in Older Persons. - Uchechi A Mitchell; Carol S Aneshensel (J Aging Health, 2017)
OBJECTIVE: Systemic inflammation is an important risk factor for cardiovascular diseases and inequalities by race/ethnicity, gender, and education have been documented. However, there is incomplete knowledge as to how these disparities present across age, especially in late life. This study assesses whether differences in C-reactive protein (CRP), a marker of inflammation, are contingent on age among older persons. METHOD: Data are from the 2006/2008 Health and Retirement Study ( n = 10,974) biomarker assessment. CRP was regressed on interactions between age and other status characteristics. RESULTS: Racial/ethnic differences in inflammation do not vary significantly by age. However, gender and education differences are greatest at younger ages and then narrow steadily with increasing age. DISCUSSION: There is considerable heterogeneity in how disparities in inflammation present across age and characteristics such as race/ethnicity, gender, and education. Understanding status differences in the influence of age on factors affecting late-life health is useful for health disparities research.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; C-reactive protein; Female; Health Status Disparities; Humans; Inflammation; Male; Middle Aged; Racial Groups; Self Report; Socioeconomic factors

Sociodemographic disparities in chronic pain, based on 12-year longitudinal data. - Grol-Prokopczyk, Hanna (Pain, 2017)
Existing estimates of sociodemographic disparities in chronic pain in the United States are based on cross-sectional data, often treat pain as a binary construct, and rarely test for nonresponse or other types of bias. This study uses 7 biennial waves of national data from the Health and Retirement Study (1998-2010; n = 19,776) to describe long-term pain disparities among older (age 51+) American adults. It also investigates whether pain severity, reporting heterogeneity, survey nonresponse, and/or mortality selection might bias estimates of social disparities in pain. In the process, the article clarifies whether 2 unexpected patterns observed cross-sectionally-plateauing of pain above age 60, and lower pain among racial/ethnic minorities-are genuine or artefactual. Findings show high prevalence of chronic pain: 27.3% at baseline, increasing to 36.6% thereafter. Multivariate latent growth curve models reveal extremely large disparities in pain by sex, education, and wealth, which manifest primarily as differences in intercept. Net of these variables, there is no racial/ethnic minority disadvantage in pain scores, and indeed a black advantage vis-à-vis whites. Pain levels are predictive of subsequent death, even a decade in the future. No evidence of pain-related survey attrition is found, but surveys not accounting for pain severity and reporting heterogeneity are likely to underestimate socioeconomic disparities in pain. The lack of minority disadvantage (net of socioeconomic status) appears genuine. However, the age-related plateauing of pain observed cross-sectionally is not replicated longitudinally, and seems partially attributable to mortality selection, as well as to rising pain levels by birth cohort.
Keywords: Age Distribution; Age Factors; Aged; Aged, 80 and over; Chronic disease; Ethnic Groups; Female; Healthcare Disparities; Humans; Longitudinal Studies; Male; Middle Aged; Sex Factors; Social Class

Successful Aging as the Intersection of Individual Resources, Age, Environment, and Experiences of Well-being in Daily Activities. - Shannon T. Mejia; Lindsay H Ryan; Gonzalez, Richard; Jacqui Smith (J Gerontol B Psychol Sci Soc Sci, 2017)
Objective: We conceptualize successful aging as a cumulative index of individual resources (the absence of disease and disability, high cognitive and physical functioning, social embeddedness) in the service of successful aging outcomes (global well-being, experienced well-being, and vital status), and conditioned by age, social structure, and environment. Method: The study used baseline and follow-up data from the 2008-2014 waves of the Health and Retirement Study (N = 17,230; age = 51-101). Linear, multilevel, and logistic models compared individual resources at baseline as independent, cumulative, and binary predictors of outcomes 4 years later. Results: Individual resources were unequally distributed across age group and social structures (education, wealth, race, gender) and had a cumulative effect on all successful aging outcomes. For experienced well-being, individual resources were most important at midlife and for groups with lower education. Person-environment congruence (social cohesion, city satisfaction) was associated with all successful aging outcomes and conditioned the effect of individual resources on experienced well-being. Discussion: A cumulative index allows for gradations in resources that can be compensated for by external factors such as person-environment congruence. This index could guide policy and interventions to enhance resources in vulnerable subgroups and diminish inequalities in successful aging outcomes.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Aging; environment; Female; Follow-Up Studies; Health Status; Humans; Male; Middle Aged; Personal Satisfaction; Social Support; United States

Successful Aging in the Context of the Disablement Process: Working and Volunteering as Moderators on the Association Between Chronic Conditions and Subsequent Functional Limitations. - Ben Lennox Kail; Dawn C Carr (J Gerontol B Psychol Sci Soc Sci, 2017)
Objectives : This study evaluated the successful aging model by assessing the impact of two forms of productive engagement-working and volunteering-as potential interventions in the process of disablement. Method : The Health and Retirement Study was used to (a) estimate two-stage selection equations of (i) currently working part time and full time and (ii) currently volunteering less than 100 hours and volunteering 100 hours or more per year (net of chronic health problems) and (b) assess whether, net of selection, working, and volunteering moderate the association between chronic conditions and subsequent functional limitations. Results : Chronic conditions were associated with elevated levels of subsequent functional limitations, whereas both working and volunteering were associated with lower levels of subsequent functional limitations. Moreover, workers and volunteers of less than 100 hours per year experienced a reduction in the association of chronic conditions on subsequent functional limitations. Discussion : This research highlights the role of productive engagement as a key element in successful aging. Not only do work and volunteering have direct associations with health outcomes themselves, but they also act as potential interventions in the process of disablement by attenuating the way in which chronic conditions are translated into subsequent functional limitations. This suggests that (a) future research should apply successful aging models to health processes as well as health outcomes and (b) policy makers should support social institutions that foster late-life productive engagement.
Keywords: Aged; Aged, 80 and over; Aging; Disabled Persons; Employment; Female; Humans; Male; United States; Volunteers

Timing of Advance Directive Completion and Relationship to Care Preferences. - Enguidanos, Susan; Jennifer A Ailshire (J Pain Symptom Manage, 2017)
CONTEXT: Given recent Medicare rules reimbursing clinicians for engaging in advance care planning, there is heightened need to understand factors associated with the timing of advance directive (AD) completion before death and how the timing impacts care decisions. OBJECTIVE: The purpose of this study was to investigate patterns in timing of AD completion and the relationship between timing and documented care preferences. We hypothesize that ADs completed late in the course of illness or very early in the disease trajectory will reflect higher preferences for aggressive care. METHODS: We conducted a retrospective study using logistic regressions to analyze data from the Health and Retirement Study, a nationally representative longitudinal survey of older adults. RESULTS: The analytic sample included exit interviews conducted from 2000 to 2012 among 2904 proxy reporters of deceased participants who had an AD. Nearly three-quarters (71%) of ADs were completed a year or more before death. Being younger or a racial/ethnic minority, and having lower education, a diagnosis of cancer or lung disease, and an expected death were associated with completing an AD within the three months before death, while having the lowest quartile of assets and memory problems were inversely associated with AD completion. Minorities, those with lower education, expected death, and timing of AD completion were associated with electing aggressive care. CONCLUSION: Early documentation of care wishes may not be associated with an increased likelihood of electing aggressive care; however, ADs completed in the last months of life have higher rates of election of aggressive care.
Keywords: Advance care planning; Advance directives; Aged; Aged, 80 and over; Female; Humans; Male; Middle Aged; Patient Participation; Patient Preference; Retrospective Studies

The Use of Life-Sustaining Procedures in the Last Month of Life Is Associated With More Depressive Symptoms in Surviving Spouses. - Katherine A Ornstein; Melissa D. Aldridge; Melissa M Garrido; Rebecca Jean Gorges; Bollens-Lund, Evan; Albert L Siu; Kenneth M. Langa; Amy Kelley (J Pain Symptom Manage, 2017)
CONTEXT: Family caregivers of individuals with serious illness who undergo intensive life-sustaining medical procedures at the end of life may be at risk of negative consequences including depression. OBJECTIVES: The objective of this study was to determine the association between patients' use of life-sustaining procedures at the end of life and depressive symptoms in their surviving spouses. METHODS: We used data from the Health and Retirement Study, a longitudinal survey of U.S. residents, linked to Medicare claims data. We included married Medicare beneficiaries aged 65 years and older who died between 2000 and 2011 (n = 1258) and their surviving spouses. The use of life-sustaining procedures (i.e., intubation/mechanical ventilation, tracheostomy, gastrostomy tube insertion, enteral/parenteral nutrition, and cardiopulmonary resuscitation) in the last month of life was measured via claims data. Using propensity score matching, we compared change in depressive symptoms of surviving spouses. RESULTS: Eighteen percent of decedents underwent one or more life-sustaining procedures in the last month of life. Those whose spouses underwent life-sustaining procedures had a 0.32-point increase in depressive symptoms after death (scale range = 0-8) and a greater likelihood of clinically significant depression (odds ratio = 1.51) compared with a matched sample of spouses of those who did not have procedures (P < 0.05). CONCLUSION: Surviving spouses of those who undergo intensive life-sustaining procedures at the end of life experience a greater magnitude of increase in depressive symptoms than those whose spouses do not undergo such procedures. Further study of the circumstances and decision making surrounding these procedures is needed to understand their relationship with survivors' negative mental health consequences and how best to provide appropriate support.
Keywords: Aged; Aged, 80 and over; Caregivers; depression; Female; Humans; Intubation; Longitudinal Studies; Male; Mental Health; Respiration, Artificial; Spouses; Survivors; Terminal Care

Accelerated increase and decrease in subjective age as a function of changes in loneliness and objective social indicators over a four-year period: results from the health and retirement study. - Liat Ayalon; Yuval Palgi; Sharon Avidor; Ehud Bodner (Aging Ment Health, 2016)
OBJECTIVES: The study examined the role of changes in loneliness and objective social indicators in the formation of changes in subjective age over a four-year period. METHODS: The Health and Retirement Study is a US nationally representative study of older adults over 50 and their spouse of any age. We restricted the sample to individuals, 65 years of age and older (n = 2591). An accelerated increase in subjective age was defined as an increase in subjective age over the two waves greater than five years. An accelerated decrease in subjective age was defined as a difference that was lower than three years. These were examined against a change in subjective age in the range of three to five years (i.e., change consistent with the passage of time). RESULTS: For 23.4% of the sample, changes in subjective age were consistent with the passage of time. A total of 38.3% had an accelerated decrease in subjective age, whereas 38.3% had an accelerated increase. A decrease in loneliness over the two waves resulted in an accelerated decrease in subjective age, whereas an increase in depressive symptoms resulted in an accelerated increase in subjective age. Changes in objective social indicators, physical difficulties or medical comorbidity did not predict changes in subjective age. CONCLUSIONS: This is one of very few studies that examined changes in subjective age over time. Changes in subjective age represent an important construct that corresponding to other changes in subjective experiences.
Keywords: Aged; Aged, 80 and over; Aging; depression; Female; Humans; Loneliness; Male; Retirement; Social Change

Allostatic Load and Personality: A 4-Year Longitudinal Study. - Yannick Stephan; Angelina R Sutin; Martina Luchetti; Antonio Terracciano (Psychosom Med, 2016)
OBJECTIVE: Dysregulation across multiple physiological systems, referred to as allostatic load, has pervasive consequences for an individual's health. The present study examined whether allostatic load is associated with personality and personality changes during a 4-year follow-up. METHODS: A total of 5200 participants aged from 50 to 99 years (59.5% women, mean [standard deviation] age = 66.91 [8.88] years) from the Health and Retirement Study provided data on cardiovascular, metabolic, and immune markers at baseline and personality both at baseline and at 4 years later. RESULTS: Higher allostatic load was related to higher neuroticism (β = 0.03, p = .042), lower extraversion (β = -0.06, p < .001), and lower conscientiousness (β = -0.06, p < .001) at baseline, and to declines in extraversion (β = -0.03, p = .007), conscientiousness (β = -0.04, p < .001), and agreeableness (β = -0.02, p = .020) over the 4-year period, controlling for demographic covariates. A significant quadratic relation between allostatic load and changes in openness (β = -0.03, p = .002) suggested that openness declines when individuals exceed a high level of cumulative physiological dysregulation. No association was found with changes in neuroticism. CONCLUSIONS: Allostatic load is associated with personality change across adulthood and old age. The findings indicate that physiological dysregulation across multiple systems challenges personality stability and is associated with accelerated personality traits change.
Keywords: Aged; Aged, 80 and over; Aging; Allostasis; Anxiety Disorders; Biomarkers; Conscience; Extraversion, Psychological; Female; Humans; Longitudinal Studies; Male; Middle Aged; Neuroticism; Personality

Antidepressant use and functional limitations in U.S. older adults. - An, Ruopeng; Lu, Lingyun (J Psychosom Res, 2016)
OBJECTIVE: The upsurge in prevalence and long-term use of antidepressants among older adults might have profound health implications beyond depressive symptom management. This study examined the relationship between antidepressant use and functional limitation onset in U.S. older adults. METHODS: Study sample came from 2006 and 2008 waves of the Health and Retirement Study, in combination with data from 2005 and 2007 Prescription Drug Study. Self-reported antidepressant use was identified based on the therapeutic classification of Cerner Multum's Lexicon. Functional limitations were classified into those pertaining to physical mobility, large muscle function, activities of daily living, gross motor function, fine motor function, and instrumental activities of daily living. Cox proportional hazard models were performed to assess the effects of antidepressant use on future functional limitation onset by limitation category, antidepressant type, and length of use, adjusted by depression status and other individual characteristics. RESULTS: Antidepressant use for one year and longer was associated with an increase in the risk of functional limitation by 8% (95% confidence interval=4%-12%), whereas the relationship between antidepressant use less than a year and function limitation was statistically nonsignificant. Antidepressant use was associated with an increase in the risk of functional limitation by 8% (3%-13%) among currently nondepressed participants but not currently depressed participants. CONCLUSION: Long-term antidepressant use in older adults should be prudently evaluated and regularly monitored to reduce the risk of functional limitation. Future research is warranted to examine the health consequences of extended and/or off-label antidepressant use in absence of depressive symptoms.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Antidepressive Agents; depression; Drug Utilization; Female; Health Surveys; Humans; Longitudinal Studies; Male; Mobility Limitation; Muscle, Skeletal; Prevalence; Risk Factors; Socioeconomic factors; United States

Association of a Genetic Risk Score With Body Mass Index Across Different Birth Cohorts. - Stefan Walter; Mejía-Guevara, Iván; Estrada, Karol; Sze Y Liu; M. Maria Glymour (JAMA, 2016)
IMPORTANCE: Many genetic variants are associated with body mass index (BMI). Associations may have changed with the 20th century obesity epidemic and may differ for black vs white individuals. OBJECTIVE: Using birth cohort as an indicator for exposure to obesogenic environment, to evaluate whether genetic predisposition to higher BMI has a larger magnitude of association among adults from more recent birth cohorts, who were exposed to the obesity epidemic at younger ages. DESIGN, SETTING, AND PARTICIPANTS: Observational study of 8788 adults in the US national Health and Retirement Study who were aged 50 years and older, born between 1900 and 1958, with as many as 12 BMI assessments from 1992 to 2014. EXPOSURES: A multilocus genetic risk score for BMI (GRS-BMI), calculated as the weighted sum of alleles of 29 single nucleotide polymorphisms associated with BMI, with weights equal to the published per-allele effects. The GRS-BMI represents how much each person's BMI is expected to differ, based on genetic background (with respect to these 29 loci), from the BMI of a sample member with median genetic risk. The median-centered GRS-BMI ranged from -1.68 to 2.01. MAIN OUTCOMES AND MEASURES: BMI based on self-reported height and weight. RESULTS: GRS-BMI was significantly associated with BMI among white participants (n = 7482; mean age at first assessment, 59 years; 3373 [45%] were men; P <.001) and among black participants (n = 1306; mean age at first assessment, 57 years; 505 [39%] were men; P <.001) but accounted for 0.99% of variation in BMI among white participants and 1.37% among black participants. In multilevel models accounting for age, the magnitude of associations of GRS-BMI with BMI were larger for more recent birth cohorts. For example, among white participants, each unit higher GRS-BMI was associated with a difference in BMI of 1.37 (95% CI, 0.93 to 1.80) if born after 1943, and 0.17 (95% CI, -0.55 to 0.89) if born before 1924 (P = .006). For black participants, each unit higher GRS-BMI was associated with a difference in BMI of 3.70 (95% CI, 2.42 to 4.97) if born after 1943, and 1.44 (95% CI, -1.40 to 4.29) if born before 1924. CONCLUSIONS AND RELEVANCE: For participants born between 1900 and 1958, the magnitude of association between BMI and a genetic risk score for BMI was larger among persons born in later cohorts. This suggests that associations of known genetic variants with BMI may be modified by obesogenic environments.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Alleles; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Multilocus Sequence Typing; Obesity; Polymorphism, Single Nucleotide; Risk Factors; United States

Association of Alcohol Use and Loneliness Frequency Among Middle-Aged and Older Adult Drinkers. - Sarah L. Canham; Pia M Mauro; Christopher N Kaufmann; Sixsmith, Andrew (J Aging Health, 2016)
OBJECTIVES: We examined the association between alcohol use, at-risk drinking, and binge drinking, and loneliness in a sample of middle-aged and older adults. METHOD: We studied participants aged 50+ years from the 2008 wave of the Health and Retirement Study who reported alcohol use. We ran separate multinomial logistic regressions to assess the association of three alcohol use outcomes (i.e., weekly alcohol consumption, at-risk drinking, and binge drinking) and loneliness. RESULTS: After adjusting for covariates, being lonely was associated with reduced odds of weekly alcohol consumption 4 to 7 days per week, but not 1 to 3 days per week, compared with average alcohol consumption 0 days per week in the last 3 months. No association was found between at-risk drinking or binge drinking and loneliness. DISCUSSION: Results suggest that among a sample of community-based adults aged 50+, loneliness was associated with reduced alcohol use frequency, but not with at-risk or binge drinking.
Keywords: Aged; Aged, 80 and over; Alcohol Drinking; Binge drinking; Cross-Sectional Studies; Female; Humans; Loneliness; Male; Middle Aged; Risk-Taking

Associations between health literacy and preventive health behaviors among older adults: findings from the health and retirement study. - Dena M. Fernandez; Janet L. Larson; Brian J Zikmund-Fisher (BMC Public Health, 2016)
BACKGROUND: While the association between inadequate health literacy and adverse health outcomes has been well documented, less is known about the impact of health literacy on health perceptions, such as perceptions of control over health, and preventive health behaviors. METHODS: We identified a subsample of participants (N = 707) from the Health and Retirement Study (HRS), a nationally representative sample of older adults, who participated in health literacy testing. Self-reported health literacy was measured with a literacy screening question, and objective health literacy with a summed score of items from the Test of Functional Health Literacy. We compared answers on these items to those related to participation in health behaviors such as cancer screening, exercise, and tobacco use, as well as self-referencing health beliefs. RESULTS: In logistic regression models adjusted for gender, education, race, and age, participants with adequate self-reported health literacy (compared to poorer levels of health literacy) had greater odds of participation in mammography within the last 2 years (Odds ratio [OR] = 2.215, p = 0.01) and participation in moderate exercise two or more times per week (OR = 1.512, p = 0.03). Participants with adequate objective health literacy had reduced odds of participation in monthly breast self-exams (OR = 0.369, p = 0.004) and reduced odds of current tobacco use (OR = 0.456, p = 0.03). In adjusted linear regression analyses, self-reported health literacy made a small but significant contribution to explaining perceived control of health (β 0.151, p = <0.001) and perceived social standing (β 0.112, p = 0.002). CONCLUSION: In a subsample of older adult participants of the HRS, measures of health literacy were positively related to several health promoting behaviors and health-related beliefs and non-use of breast self-exams, a screening behavior of questionable benefit. These relationships varied however, between self-reported and objectively-measured health literacy. Further investigation into the specific mechanisms that lead higher literacy people to pursue health promoting actions appears clearly warranted.
Keywords: Aged; Aged, 80 and over; Female; Health Behavior; Health Knowledge, Attitudes, Practice; Health Literacy; Health Promotion; Humans; Logistic Models; Male; Middle Aged; Odds Ratio; Preventive Health Services; Regression Analysis; Retirement; United States

The Benefits of Social Technology Use Among Older Adults Are Mediated by Reduced Loneliness. - William J. Chopik (Cyberpsychol Behav Soc Netw, 2016)
Technology has the ability to enhance and enrich the lives of older adults by facilitating better interpersonal relationships. However, few studies have directly examined associations between technology use for social reasons and physical and psychological health among older adults. The current study examines the benefits of technology use in 591 older adults from the 2012 wave of the Health and Retirement Study (Mage = 68.18, SD = 10.75; 55.5% female). Social technology use was assessed through five technology-based behaviors (i.e., using e-mail, social networking sites, online video/phone calls, online chatting/instant messaging, using a smartphone). Attitudes toward the usability and benefits of technology use were also assessed. Older adults had generally positive attitudes toward technology. Higher social technology use was associated with better self-rated health, fewer chronic illnesses, higher subjective well-being, and fewer depressive symptoms. Furthermore, each of the links between social technology use and physical and psychological health was mediated by reduced loneliness. Close relationships are a large determinant of physical health and well-being, and technology has the potential to cultivate successful relationships among older adults.
Keywords: Aged; Aged, 80 and over; Attitude to Computers; depression; Female; Health Status; Humans; Interpersonal Relations; Loneliness; Male; Middle Aged; Personal Satisfaction; Social Networking; Telecommunications

Can social policy influence socioeconomic disparities? Korean War GI Bill eligibility and markers of depression. - Anusha M Vable; Canning, David; M. Maria Glymour; Ichiro Kawachi; Marcia P Jimenez; S. V. Subramanian (Ann Epidemiol, 2016)
PURPOSE: The Korean War GI Bill provided socioeconomic benefits to veterans; however, its association with health is unclear; we hypothesize GI Bill eligibility is associated with fewer depressive symptoms and smaller disparities. METHODS: Data from 246 Korean War GI Bill eligible veterans and 240 nonveterans from the Health and Retirement Study were matched on birth year, southern birth, race, height, and childhood health using coarsened exact matching. Number of depressive symptoms in 2010 (average age = 78 years) was assessed using a modified, validated Center for Epidemiologic Studies-Depression Scale, dichotomized to reflect elevated depressive symptoms. Regression analyses were stratified into low (at least one parent < 8 years schooling/missing data, n = 167) or high (both parents ≥ 8 years schooling, n = 319) childhood socioeconomic status (cSES) groups. RESULTS: Korean War GI Bill eligibility predicted fewer depressive symptoms among individuals from low cSES backgrounds [β = -0.64, 95% confidence interval (CI) = (-1.18, -0.09), P = .022]. Socioeconomic disparities were smaller among veterans than nonveterans for number of depressive symptoms [β = -0.76, 95% CI = (-1.33, -0.18), P = .010] and elevated depressive symptoms [β = -11.7, 95% CI = (-8.2, -22.6), P = .035]. CONCLUSIONS: Korean War GI Bill eligibility predicted smaller socioeconomic disparities in depression markers.
Keywords: Aged; Aged, 80 and over; depression; Health Status Disparities; Humans; Korean War; Male; Public Policy; Residence Characteristics; Risk Factors; Socioeconomic factors; Veterans

Changes in Depressive Symptoms among Older Adults with Multiple Chronic Conditions: Role of Positive and Negative Social Support. - Ahn, SangNam; Kim, Seonghoon; Zhang, Hongmei (Int J Environ Res Public Health, 2016)
Depression severely affects older adults in the United States. As part of the social environment, significant social support was suggested to ameliorate depression among older adults. We investigate how varying forms of social support moderate depressive symptomatology among older adults with multiple chronic conditions (MCC). Data were analyzed using a sample of 11,400 adults, aged 65 years or older, from the 2006-2012 Health and Retirement Study. The current study investigated the moderating effects of positive or negative social support from spouse, children, other family, and friends on the association between MCC and depression. A linear mixed model with repeated measures was used to estimate the effect of MCC on depression and its interactions with positive and negative social support in explaining depression among older adults. Varying forms of social support played different moderating roles in depressive symptomatology among older adults with MCC. Positive spousal support significantly weakened the deleterious effect of MCC on depression. Conversely, all negative social support from spouse, children, other family, and friends significantly strengthened the deleterious effect of MCC on depression. Minimizing negative social support and maximizing positive spousal support can reduce depression caused by MCC and lead to successful aging among older adults.
Keywords: Aged; Aged, 80 and over; Aging; depression; Family; Female; Friends; Humans; Male; Multiple Chronic Conditions; Social Support; United States

Changes in Visual Function in the Elderly Population in the United States: 1995-2010. - Chen, Yiqun; Hahn, Paul; Frank A Sloan (Ophthalmic Epidemiol, 2016)
PURPOSE: To document recent trends in visual function among the United States population aged 70+ years and investigate how the trends can be explained by inter-temporal changes in: (1) population sociodemographic characteristics, and chronic disease prevalence, including eye diseases (compositional changes); and (2) effects of the above factors on visual function (structural changes). METHODS: Data from the 1995 Asset and Health Dynamics among the Oldest Old (AHEAD) and the 2010 Health and Retirement Study (HRS) were merged with Medicare Part B claims in the interview years and the 2 previous years. Decomposition analysis was performed. Respondents from both studies were aged 70+ years. The outcome measure was respondent self-reported visual function on a 6-point scale (from 6 = blind to 1 = excellent). RESULTS: Overall, visual function improved from slightly worse than good (3.14) in 1995 to slightly better than good (2.98) in 2010. A decline in adverse effects of aging on vision was found. Among the compositional changes were higher educational attainment leading to improved vision, and higher prevalence of such diseases as diabetes mellitus, which tended to lower visual function. However, compared to compositional changes, structural changes were far more important, including decreased adverse effects of aging, diabetes mellitus (when not controlling for eye diseases), and diagnosed glaucoma. CONCLUSION: Although the US population has aged and is expected to age further, visual function improved among elderly persons, especially among persons 80+ years, likely reflecting a favorable role of structural changes identified in this study in mitigating the adverse effect of ongoing aging on vision.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Chronic disease; Cross-Sectional Studies; Female; Humans; Male; Medicare Part B; Prevalence; Self Report; Socioeconomic factors; United States; Visual Acuity; Visually Impaired Persons

A chapter a day: Association of book reading with longevity. - Bavishi, Avni; Martin D Slade; Becca R Levy (Soc Sci Med, 2016)
Although books can expose people to new people and places, whether books also have health benefits beyond other types of reading materials is not known. This study examined whether those who read books have a survival advantage over those who do not read books and over those who read other types of materials, and if so, whether cognition mediates this book reading effect. The cohort consisted of 3635 participants in the nationally representative Health and Retirement Study who provided information about their reading patterns at baseline. Cox proportional hazards models were based on survival information up to 12 years after baseline. A dose-response survival advantage was found for book reading by tertile (HRT2 = 0.83, p < 0.001, HRT3 = 0.77, p < 0.001), after adjusting for relevant covariates including age, sex, race, education, comorbidities, self-rated health, wealth, marital status, and depression. Book reading contributed to a survival advantage that was significantly greater than that observed for reading newspapers or magazines (tT2 = 90.6, p < 0.001; tT3 = 67.9, p < 0.001). Compared to non-book readers, book readers had a 23-month survival advantage at the point of 80% survival in the unadjusted model. A survival advantage persisted after adjustment for all covariates (HR = .80, p < .01), indicating book readers experienced a 20% reduction in risk of mortality over the 12 years of follow up compared to non-book readers. Cognition mediated the book reading-survival advantage (p = 0.04). These findings suggest that the benefits of reading books include a longer life in which to read them.
Keywords: Aged; Aged, 80 and over; Books; Chi-Square Distribution; Cohort Studies; Female; Humans; Longevity; Male; Michigan; Middle Aged; Reading; Survival Analysis

Claims-based Identification Methods and the Cost of Fall-related Injuries Among US Older Adults. - Geoffrey J Hoffman; Hays, Ron D; Martin F Shapiro; Steven P Wallace; Susan L Ettner (Med Care, 2016)
OBJECTIVES: Compare expenditures of fall-related injuries (FRIs) using several methods to identify FRIs in administrative claims data. RESEARCH DESIGN: Using 2007-2009 Medicare claims and 2008 Health and Retirement Survey data, FRIs were identified using external-cause-of-injury (e-codes 880/881/882/884/885/888) only, e-codes plus a broad set of primary diagnosis codes, and a newer approach using e-codes and diagnostic and procedural codes. Linear regression models adjusted for sociodemographic, health, and geographic characteristics were used to estimate per-FRI, service component, patient cost share, expenditures by type of initial FRI treatment (inpatient, emergency department only, outpatient), and total annual FRI-related Medicare expenditures. SUBJECTS: The analysis included 5497 community-dwelling adults ≥65 (228 FRI, 5269 non-FRI individuals) with continuous Medicare coverage and alive during the 24-month study. RESULTS: The 3 FRI identification methods produced differing distributions of index FRI type and varying estimated expenditures: $12,171 [95% confidence interval (CI), $4662-$19,680], $5648 (95% CI, $3819-$7476), and $9388 (95% CI, $5969-$12,808). In all models, most spending occurred in hospital, outpatient, and skilled nursing facility (SNF) settings, but greater proportions of SNF and outpatient spending were observed with commonly used FRI identification methods. Patient cost-sharing was estimated at $691-$1900 across the 3 methods. Inpatient-treated index FRIs were more expensive than emergency department and outpatient-treated FRIs across all methods, but were substantially higher when identifying FRI using only e-codes. Estimated total FRI-related Medicare expenditures were highly variable across methods. CONCLUSIONS: FRIs are costly, with implications for Medicare and its beneficiaries. However, expenditure estimates vary considerably based on the method used to identify FRIs.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Cross-Over Studies; Female; Humans; Insurance Claim Review; Male; Medicare; United States; Wounds and Injuries

Combinations of Chronic Conditions, Functional Limitations, and Geriatric Syndromes that Predict Health Outcomes. - Siran M Koroukian; Nicholas K Schiltz; David F Warner; Jiayang Sun; Paul M Bakaki; Kathleen A Smyth; Kurt C Stange; Charles W Given (J Gen Intern Med, 2016)
BACKGROUND: The strategic framework on multiple chronic conditions released by the US Department of Health and Human Services calls for identifying homogeneous subgroups of older adults to effectively target interventions aimed at improving their health. OBJECTIVE: We aimed to identify combinations of chronic conditions, functional limitations, and geriatric syndromes that predict poor health outcomes. DESIGN, SETTING AND PARTICIPANTS Data from the 2010-2012 Health and Retirement Study provided a representative sample of U.S. adults 50 years of age or older (n = 16,640). MAIN MEASURES: Outcomes were: Self-reported fair/poor health, self-rated worse health at 2 years, and 2-year mortality. The main independent variables included self-reported chronic conditions, functional limitations, and geriatric syndromes. We conducted tree-based classification and regression analysis to identify the most salient combinations of variables to predict outcomes. KEY RESULTS: Twenty-nine percent and 23 % of respondents reported fair/poor health and self-rated worse health at 2 years, respectively, and 5 % died in 2 years. The top combinations of conditions identified through our tree analysis for the three different outcome measures (and percent respondents with the outcome) were: a) for fair/poor health status: difficulty walking several blocks, depressive symptoms, and severe pain (> 80 %); b) for self-rated worse health at 2 years: 68.5 years of age or older, difficulty walking several blocks and being in fair/poor health (60 %); and c) for 2-year mortality: 80.5 years of age or older, and presenting with limitations in both ADLs and IADLs (> 40 %). CONCLUSIONS: Rather than chronic conditions, functional limitations and/or geriatric syndromes were the most prominent conditions in predicting health outcomes. These findings imply that accounting for chronic conditions alone may be less informative than also accounting for the co-occurrence of functional limitations and geriatric syndromes, as the latter conditions appear to drive health outcomes in older individuals.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Chronic disease; Comorbidity; Female; Geriatric Assessment; Health Status; Health Status Indicators; Humans; Longitudinal Studies; Male; Middle Aged; Mobility Limitation; Prognosis; Risk Factors; Self Report; Sex Distribution; Socioeconomic factors; Syndrome; United States

Comparing Alternative Effect Decomposition Methods: The Role of Literacy in Mediating Educational Effects on Mortality. - Thu T Nguyen; Eric J. Tchetgen Tchetgen; Ichiro Kawachi; Stephen E. Gilman; Stefan Walter; M. Maria Glymour (Epidemiology, 2016)
BACKGROUND: Inverse odds ratio weighting, a newly proposed tool to evaluate mediation in exposure-disease associations, may be valuable for a host of research questions, but little is known about its performance in real data. We compare this approach to a more conventional Baron and Kenny type of decomposition on an additive hazards scale to estimate total, direct, and indirect effects using the example of the role of literacy in mediating the effects of education on mortality. METHODS: Health and Retirement Study participants born in the United States between 1900 and 1947 were interviewed biennially for up to 12 years (N = 17,054). Literacy was measured with a brief vocabulary assessment. Decomposition estimates were derived based on Aalen additive hazards models. RESULTS: A 1 standard deviation difference in educational attainment (3 years) was associated with 6.7 fewer deaths per 1000 person-years (β = -6.7, 95% confidence interval [CI]: -7.9, -5.4). Of this decrease, 1.3 fewer deaths (β = -1.3, 95% CI: -4.0, 1.2) were attributed to the literacy pathway (natural indirect), representing 19% of the total effect. Baron and Kenny estimates were consistent with inverse odds ratio weighting estimates but were less variable (natural indirect effect: -1.2 [95% CI: -1.7, -0.69], representing 18% of total effect). CONCLUSION: In a cohort of older Americans, literacy partially mediated the effect of education on mortality. See Video Abstract at http://links.lww.com/EDE/B78.
Keywords: Aged; Aged, 80 and over; Educational Status; Female; Humans; Literacy; Longitudinal Studies; Male; Middle Aged; Mortality; Odds Ratio; Proportional Hazards Models; United States

Correlates and predictors of loneliness in older-adults: a review of quantitative results informed by qualitative insights. - Cohen-Mansfield, Jiska; Hazan, Haim; Lerman, Yaffa; Shalom, Vera (Int Psychogeriatr, 2016)
BACKGROUND: Older persons are particularly vulnerable to loneliness because of common age-related changes and losses. This paper reviews predictors of loneliness in the older population as described in the current literature and a small qualitative study. METHODS: Peer-reviewed journal articles were identified from psycINFO, MEDLINE, and Google Scholar from 2000-2012. Overall, 38 articles were reviewed. Two focus groups were conducted asking older participants about the causes of loneliness. RESULTS: Variables significantly associated with loneliness in older adults were: female gender, non-married status, older age, poor income, lower educational level, living alone, low quality of social relationships, poor self-reported health, and poor functional status. Psychological attributes associated with loneliness included poor mental health, low self-efficacy beliefs, negative life events, and cognitive deficits. These associations were mainly studied in cross-sectional studies. In the focus groups, participants mentioned environmental barriers, unsafe neighborhoods, migration patterns, inaccessible housing, and inadequate resources for socializing. Other issues raised in the focus groups were the relationship between loneliness and boredom and inactivity, the role of recent losses of family and friends, as well as mental health issues, such as shame and fear. CONCLUSIONS: Future quantitative studies are needed to examine the impact of physical and social environments on loneliness in this population. It is important to better map the multiple factors and ways by which they impact loneliness to develop better solutions for public policy, city, and environmental planning, and individually based interventions. This effort should be viewed as a public health priority.
Keywords: Aged; Aged, 80 and over; Aging; Cross-Sectional Studies; Female; Focus Groups; Humans; Loneliness; Male; Marital Status; Motor Activity; Qualitative Research; Quality of Life; Residence Characteristics; Sex Factors; Social Environment; social isolation; Socioeconomic factors

C-reactive protein level partially mediates the relationship between moderate alcohol use and frailty: the Health and Retirement Study. - Mona Shah; Daniel Paulson (Age Ageing, 2016)
BACKGROUND: frailty is an indicator of late-life decline marked by higher rates of disability and healthcare utilisation. Research has linked health benefits with moderate alcohol use, including frailty risk reduction. Past work suggests inflammation, measured by C-reactive protein (CRP), as one candidate mechanism for this effect. OBJECTIVE: this study aims to elucidate a possible mechanism - CRP modulation - by which moderate alcohol consumption may protect against frailty. METHODS: a cross-sectional study using data from the 2008 wave of the Health and Retirement Study (HRS) conducted by the University of Michigan. The HRS is a cohort study on health, retirement and aging on adults aged 50 and older living in the USA. A final sample of 3,229 stroke-free participants, over the age of 65 years and with complete data, was identified from the 2008 wave. Alcohol use was measured via self-report. Frailty was measured using the Paulson-Lichtenberg Frailty Index. CRP was collected through the HRS protocol. RESULTS: results from structural equation modelling support the hypothesised model that moderate alcohol use is associated with less frailty and lower CRP levels. Furthermore, the indirect relationship from moderate alcohol use to frailty through CRP was statistically significant. CONCLUSIONS: overall findings suggest that inflammation measured by CRP is one mechanism by which moderate alcohol use may confer protective effects for frailty. These findings inform future research relating alcohol use and frailty, and suggest inflammation as a possible mechanism in the relationship between moderate alcohol use and other beneficial health outcomes.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Alcohol Drinking; Biomarkers; C-reactive protein; Cross-Sectional Studies; Female; Frail Elderly; Frailty; Geriatric Assessment; Humans; Inflammation Mediators; Male; Protective factors; Risk Factors; United States

Depression and Frailty in Late Life: Evidence for a Common Vulnerability. - Matthew C. Lohman; Dumenci, Levent; Briana Mezuk (J Gerontol B Psychol Sci Soc Sci, 2016)
OBJECTIVES: The study purpose is to estimate the correlation between depression and competing models of frailty, and to determine to what degree the comorbidity of these syndromes is determined by shared symptomology. METHODS: Data come from the 2010 Health and Retirement Study. Analysis was limited to community-dwelling participants 65 and older (N = 3,453). Depressive symptoms were indexed by the 8-item Centers for Epidemiologic Studies Depression (CESD) scale. Frailty was indexed by 3 alternative conceptual models: (a) biological syndrome, (b) frailty index, and (c) functional domains. Confirmatory factor analysis (CFA) was used to estimate the correlation between depression and each model of frailty. RESULTS: Each of the 3 frailty latent factors was significantly correlated with depression: biological syndrome (ρ = .68, p < .01), functional domains (ρ = .70, p < .01), and frailty index (ρ = .61, p < .01). Substantial correlation remained when accounting for shared symptoms between depression and the biological syndrome (ρ = .45) and frailty index (ρ = .56) models. DISCUSSION: Results indicate that the correlation of frailty and depression in late life is substantial. The association between the two constructs cannot be fully explained by symptom overlap, suggesting that psychological vulnerability may be an important component of frailty.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; depression; Female; Frail Elderly; Geriatric Assessment; Humans; Independent Living; Interview, Psychological; Male

Desire for predictive testing for Alzheimer's disease and impact on advance care planning: a cross-sectional study. - Sheffrin, Meera; Stijacic-Cenzer, Irena; Michael A Steinman (Alzheimers Res Ther, 2016)
BACKGROUND: It is unknown whether older adults in the United States would be willing to take a test predictive of future Alzheimer's disease, or whether testing would change behavior. Using a nationally representative sample, we explored who would take a free and definitive test predictive of Alzheimer's disease, and examined how using such a test may impact advance care planning. METHODS: A cross-sectional study within the 2012 Health and Retirement Study of adults aged 65 years or older asked questions about a test predictive of Alzheimer's disease (N = 874). Subjects were asked whether they would want to take a hypothetical free and definitive test predictive of future Alzheimer's disease. Then, imagining they knew they would develop Alzheimer's disease, subjects rated the chance of completing advance care planning activities from 0 to 100. We classified a score > 50 as being likely to complete that activity. We evaluated characteristics associated with willingness to take a test for Alzheimer's disease, and how such a test would impact completing an advance directive and discussing health plans with loved ones. RESULTS: Overall, 75% (N = 648) of the sample would take a free and definitive test predictive of Alzheimer's disease. Older adults willing to take the test had similar race and educational levels to those who would not, but were more likely to be ≤75 years old (odds ratio 0.71 (95% CI 0.53-0.94)). Imagining they knew they would develop Alzheimer's, 81% would be likely to complete an advance directive, although only 15% had done so already. CONCLUSIONS: In this nationally representative sample, 75% of older adults would take a free and definitive test predictive of Alzheimer's disease. Many participants expressed intent to increase activities of advance care planning with this knowledge. This confirms high public interest in predictive testing for Alzheimer's disease and suggests this may be an opportunity to engage patients in advance care planning discussions.
Keywords: Advance care planning; Aged; Aged, 80 and over; Alzheimer disease; Cross-Sectional Studies; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Patient Acceptance of Health Care

Disparity in dental attendance among older adult populations: a comparative analysis across selected European countries and the USA. - Richard J. Manski; John F Moeller; Haiyan Chen; Widstrom, Eeva; Listl, Stefan (Int Dent J, 2016)
BACKGROUND: The current study addresses the extent to which diversity in dental attendance across population subgroups exists within and between the USA and selected European countries. METHOD: The analyses relied on 2006/2007 data from the Survey of Health, Ageing and Retirement in Europe (SHARE) and 2004-2006 data from the Health and Retirement Study (HRS) in the USA for respondents≥51 years of age. Logistic regression models were estimated to identify impacts of dental-care coverage, and of oral and general health status, on dental-care use. RESULTS: We were unable to discern significant differences in dental attendance across population subgroups in countries with and without social health insurance, between the USA and European countries, and between European countries classified according to social welfare regime. Patterns of diverse dental use were found, but they did not appear predominately in countries classified according to welfare state regime or according to the presence or absence of social health insurance. CONCLUSIONS: The findings of this study suggest that income and education have a stronger, and more persistent, correlation with dental use than the correlation between dental insurance and dental use across European countries. We conclude that: (i) higher overall rates of coverage in most European countries, compared with relatively lower rates in the USA, contribute to this finding; and that (ii) policies targeted to improving the income of older persons and their awareness of the importance of oral health care in both Europe and the USA can contribute to improving the use of dental services.
Keywords: Aged; Aged, 80 and over; Demography; Dental Care; Europe; Female; Humans; Insurance Coverage; Interviews as Topic; Male; Middle Aged; Oral Health; Patient Acceptance of Health Care; United States

Dispositional Optimism and Incidence of Cognitive Impairment in Older Adults. - Katerina A B Gawronski; Eric S Kim; Kenneth M. Langa; Laura D Kubzansky (Psychosom Med, 2016)
OBJECTIVE: Higher levels of optimism have been linked with positive health behaviors, biological processes, and health conditions that are potentially protective against cognitive impairment in older adults. However, the association between optimism and cognitive impairment has not been directly investigated. We examined whether optimism is associated with incident cognitive impairment in older adults. METHODS: Data are from the Health and Retirement Study. Optimism was measured by using the Life Orientation Test-R and cognitive impairment with a modified version of the Telephone Interview for Cognitive Status derived from the Mini-Mental State Examination. Using multiple logistic regression models, we prospectively assessed whether optimism was associated with incident cognitive impairment in 4624 adults 65 years and older during a 4-year period. RESULTS: Among participants, 312 women and 190 men developed cognitive impairment during the 4-year follow-up. Higher optimism was associated with decreased risk of incident cognitive impairment. When adjusted for sociodemographic factors, each standard deviation increase in optimism was associated with reduced odds (odds ratio [OR] = 0.70, 95% confidence interval [CI] = 0.61-0.81) of becoming cognitively impaired. A dose-response relationship was observed. Compared with those with the lowest levels of optimism, people with moderate levels had somewhat reduced odds of cognitive impairment (OR = 0.78, 95% CI = 0.59-1.03), whereas people with the highest levels had the lowest odds of cognitive impairment (OR = 0.52, 95% CI = 0.36-0.74). These associations remained after adjusting for health behaviors, biological factors, and psychological covariates that could either confound the association of interest or serve on the pathway. CONCLUSIONS: Optimism was prospectively associated with a reduced likelihood of becoming cognitively impaired. If these results are replicated, the data suggest that potentially modifiable aspects of positive psychological functioning such as optimism play an important role in maintaining cognitive functioning.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Female; Humans; Incidence; Male; Optimism; Protective factors; United States

Do Higher Levels of Resilience Buffer the Deleterious Impact of Chronic Illness on Disability in Later Life? - Lydia K Manning; Dawn C Carr; Ben Lennox Kail (Gerontologist, 2016)
PURPOSE OF THE STUDY: In examining the ability of resilience, or the ability to navigate adversity in a manner that protects well-being, to buffer the impact of chronic disease onset on disability in later life, the authors tested 2 hypotheses: (a) People with greater levels of resilience will have lower levels of disability and (b) resilience will moderate the association between the onset of a new chronic condition and subsequent disability. DESIGN AND METHODS: This study used a sample of 10,753 Americans between the ages of 51 and 98, derived from 3 waves of the Health and Retirement Study (2006-2010). Ordinary least squares regression was used to estimate the impact of resilience on changes in disability (measured as difficulty with activities of daily living [ADLs] and instrumental activities of daily living [IADLs]) over a 2-year period using a simplified resilience score. RESULTS: Resilience protects against increases in ADL and IADL limitations that are often associated with aging. Resilience mitigates a considerable amount of the deleterious consequences related to the onset of chronic illness and subsequent disability. IMPLICATIONS: Our results support our hypotheses and are consistent with claims that high levels of resilience can protect against the negative impact of disability in later life.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Chronic disease; Disability Evaluation; Disabled Persons; Female; Humans; Longitudinal Studies; Male; Middle Aged; Resilience, Psychological; Retirement; Surveys and Questionnaires

The five-factor model of personality and self-reported versus biomarker diabetic control. - Phillips, Amanda S; Charles A Guarnaccia (J Health Psychol, 2016)
Five-factor personality was examined as an element of self-report diabetic control accuracy versus biomarker control (HbA1c) for 1474 diabetics in the 2006 and 2008 Health and Retirement Study. Correlations of extraversion and self-reported control (r = -.06, p < .01), and extraversion and HbA1c (r = .03, non-significant), were significantly different (t = 2.87, p < .01). Correlations of openness and self-reported control (r = -.05, p < .05), and openness and HbA1c (r = .01, non-significant), were significantly different (t = 1.91, p < .05). Associations were found between self-reported control and conscientiousness (r = -.05, p < .05), neuroticism (r = .04, p < .05), and openness (r = -.05, p < .05). Neuroticism was associated with self-reports that diabetes was worse (r = .07, p < .01). Other correlations and comparisons were non-significant.
Keywords: Aged; Aged, 80 and over; Biomarkers; Diabetes Mellitus; Female; Glycated Hemoglobin; Humans; Male; Middle Aged; Personality; Self Report

Functional status in older women diagnosed with pelvic organ prolapse. - Tatiana V D Sanses; Nicholas K Schiltz; Bruna M. Couri; Sangeeta T Mahajan; Holly E Richter; David F Warner; Jack M. Guralnik; Siran M Koroukian (Am J Obstet Gynecol, 2016)
BACKGROUND: Functional status plays an important role in the comprehensive characterization of older adults. Functional limitations are associated with an increased risk of adverse treatment outcomes, but there are limited data on the prevalence of functional limitations in older women with pelvic floor disorders. OBJECTIVE: The aim of the study was to describe the prevalence of functional limitations based on health status in older women with pelvic organ prolapse (POP). STUDY DESIGN: This pooled, cross-sectional study utilized data from the linked Health and Retirement Study and Medicare files from 1992 through 2008. The analysis included 890 women age ≥65 years with POP. We assessed self-reported functional status, categorized in strength, upper and lower body mobility, activities of daily living (ADL), and instrumental ADL (IADL) domains. Functional limitations were evaluated and stratified by respondents self-reported general health status. Descriptive statistics were used to compare categorical and continuous variables, and logistic regression was used to measure differences in the odds of functional limitation by increasing age. RESULTS: The prevalence of functional limitations was 76.2% in strength, 44.9% in upper and 65.8% in lower body mobility, 4.5% in ADL, and 13.6% in IADL. Limitations were more prevalent in women with poor or fair health status than in women with good health status, including 91.5% vs 69.9% in strength, 72.9% vs 33.5% in upper and 88.0% vs 56.8% in lower body mobility, 11.6% vs 0.9% in ADL, and 30.6% vs 6.7% in IADL; all P < .01. The odds of all functional limitations also increased significantly with advancing age. CONCLUSION: Functional limitations, especially in strength and body mobility domains, are highly prevalent in older women with POP, particularly in those with poor or fair self-reported health status. Future research is necessary to evaluate if functional status affects clinical outcomes in pelvic reconstructive and gynecologic surgery and whether it should be routinely assessed in clinical decision-making when treating older women with POP.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cross-Sectional Studies; Female; Health Status; Health Surveys; Humans; Medicare; Middle Aged; Mobility Limitation; Muscle Strength; Pelvic Organ Prolapse; United States; Upper Extremity

Functioning, Forgetting, or Failing Health: Which Factors Are Associated With a Community-Based Move Among Older Adults? - Esther M Friedman; Margaret M Weden; Regina A Shih; Stephanie Kovalchik; Singh, Reema; José J Escarce (J Gerontol B Psychol Sci Soc Sci, 2016)
OBJECTIVE: To examine whether the health and functioning of middle-aged and older adults are associated with an increased likelihood of community-based moves. METHOD: Biennial data from adults aged 51 and older in the Health and Retirement Study (HRS) and discrete-time survival models were used to assess the likelihood of community-based moves from 2000 to 2010 as a function of 11 measures of health and functioning. RESULTS: Respondents diagnosed with heart disease, stroke, hypertension, lung disease, and psychiatric problems were more likely to move during the study period than those with no such diagnosis. Changes in activities of daily living and instrumental activities of daily living functioning, cognitive impairment, and falls were also related to a greater likelihood of moving during the study period. Cancer and diabetes were not related to overall moves, although diabetes was associated with an increased likelihood of local moves. For the most part, it was longstanding not recent diagnoses that were significantly related to the likelihood of moving. DISCUSSION: Although some health conditions precipitate moves among middle-aged and older adults, others do not. This work has important implications for understanding the role of different aspects of health and functioning in the likelihood of migration among older adults.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Female; Health Status; Health Surveys; Humans; Male; Middle Aged; Population Dynamics; Residence Characteristics; United States

A Genetic Network Associated With Stress Resistance, Longevity, and Cancer in Humans. - Morgan E. Levine; Eileen M. Crimmins (J Gerontol A Biol Sci Med Sci, 2016)
Human longevity and diseases are likely influenced by multiple interacting genes within a few biologically conserved pathways. Using long-lived smokers as a phenotype (n = 90)-a group whose survival may signify innate resilience-we conducted a genome-wide association study comparing them to smokers at ages 52-69 (n = 730). These results were used to conduct a functional interaction network and pathway analysis, to identify single nucleotide polymorphisms that collectively related to smokers' longevity. We identified a set of 215 single nucleotide polymorphisms (all of which had p <5×10(-3) in the genome-wide association study) that were located within genes making-up a functional interaction network. These single nucleotide polymorphisms were then used to create a weighted polygenic risk score that, using an independent validation sample of nonsmokers (N = 6,447), was found to be significantly associated with a 22% increase in the likelihood of being aged 90-99 (n = 253) and an over threefold increase in the likelihood of being a centenarian (n = 4), compared with being at ages 52-79 (n = 4,900). Additionally, the polygenic risk score was also associated with an 11% reduction in cancer prevalence over up to 18 years (odds ratio: 0.89, p = .011). Overall, using a unique phenotype and incorporating prior knowledge of biological networks, this study identified a set of single nucleotide polymorphisms that together appear to be important for human aging, stress resistance, cancer, and longevity.
Keywords: Aged; Aged, 80 and over; Aging; Alleles; Case-Control Studies; Gene Regulatory Networks; Genome-Wide Association Study; Genotype; Humans; Longevity; Longitudinal Studies; Middle Aged; Neoplasms; Phenotype; Polymorphism, Single Nucleotide; Smoking; Stress, Physiological; United States

High Levels of Geriatric Palliative Care Needs in Hip Fracture Patients Before the Hip Fracture. - Christine S Ritchie; Amy Kelley; Irena Cenzer; Margaret Wallhagen; Kenneth E Covinsky (J Pain Symptom Manage, 2016)
CONTEXT: Most hip fracture care models are grounded in curative models where the goal is to return the patient to independent function. In many instances, however, hip fractures contribute to continued functional decline and mortality. Although the negative impact of hip fractures is appreciated once they have occurred, what is less understood is what proportion of older adults have high illness burden before experiencing hip fracture and might benefit from geriatric palliative care. OBJECTIVES: Using data from the Health and Retirement Study linked to Medicare claims (January 1992 through December 2010), we sought to understand the extent of premorbid illness burden before hip fracture. METHODS: Characteristics were based on the interview before hip fracture. Features used to indicate need for geriatric palliative care included evidence of functional and medical vulnerability, pain, and depression. RESULTS: Eight hundred fifty-six older adults who experienced a hip fracture were compared to 851 age-, gender-, and race-matched controls. Older adults with hip fractures had significantly more premorbid functional vulnerability (activities of daily living dependent 25.7% vs. 16.1% [P < 0.001]; dementia 16.2% vs. 7.3% (P < 0.001); use of helpers 41.2% vs. 28.7% [P < 0.001]). They also experienced more medical vulnerability (multimorbidity 43% vs. 29.8% [P < 0.001]; high health care utilization 30.0% vs. 20.9% [P < 0.001]; and poor prognosis 36.1% vs. 25.4% [P < 0.001] in controls). There was no difference in premorbid pain and depression between subsequent hip fracture patients and controls. CONCLUSIONS: A significant proportion of older adults have evidence of functional and medical vulnerability before hip fracture. For these individuals, integration of geriatric palliative care may be particularly important for optimizing quality of life and addressing the high morbidity experienced by this population.
Keywords: Activities of Daily Living; Aged, 80 and over; Dementia; depression; Female; Hip Fractures; Humans; Interviews as Topic; Male; multimorbidity; pain; Palliative care; Patient Acceptance of Health Care; Prodromal Symptoms; Vulnerable Populations

The Influence of Sociodemographic and Psychosocial Factors on Advance Care Planning. - Inoue, Megumi (J Gerontol Soc Work, 2016)
This study investigated sociodemographic and psychosocial factors that enhance or impede the completion of advance care planning, analyzing data from the Health and Retirement Study. The analytic subsample included the panel participants who died between 2006 and 2010 and who had answered the psychosocial and lifestyle questionnaire when they were alive. Multinomial logistic regression was executed to answer the research question (N = 1,056). The study found that persons who were older, who were women, who identified themselves as White, and who had higher levels of income and education were more likely to be motivated to complete advance care planning. Having greater sense of control was found to weaken the adverse relationship between being African American and the completion of advance directives. Having cancer, suffering from the illnesses for longer periods of time, and having experience of nursing home institutionalization also predicted the completion of advance care planning. Implications include incorporating a culturally tailored approach for racial/ethnic minorities and using advance directives that are clear and easily understood. In addition, future research needs to include a larger minority population and examine the extent to which variations between racial/ethnic groups exist in relation to advance care planning.
Keywords: Advance care planning; Advance directives; African Americans; Aged; Aged, 80 and over; Continental Population Groups; European Continental Ancestry Group; Female; Health Status; Hispanic Americans; Humans; Logistic Models; Longitudinal Studies; Male; Middle Aged; Psychology; Social Class

Instrumental variable approaches to identifying the causal effect of educational attainment on dementia risk. - Thu T Nguyen; Eric J. Tchetgen Tchetgen; Ichiro Kawachi; Stephen E. Gilman; Stefan Walter; Sze Y Liu; Jennifer J Manly; M. Maria Glymour (Ann Epidemiol, 2016)
PURPOSE: Education is an established correlate of cognitive status in older adulthood, but whether expanding educational opportunities would improve cognitive functioning remains unclear given limitations of prior studies for causal inference. Therefore, we conducted instrumental variable (IV) analyses of the association between education and dementia risk, using for the first time in this area, genetic variants as instruments as well as state-level school policies. METHODS: IV analyses in the Health and Retirement Study cohort (1998-2010) used two sets of instruments: (1) a genetic risk score constructed from three single-nucleotide polymorphisms (SNPs; n = 7981); and (2) compulsory schooling laws (CSLs) and state school characteristics (term length, student teacher ratios, and expenditures; n = 10,955). RESULTS: Using the genetic risk score as an IV, there was a 1.1% reduction in dementia risk per year of schooling (95% confidence interval, -2.4 to 0.02). Leveraging compulsory schooling laws and state school characteristics as IVs, there was a substantially larger protective effect (-9.5%; 95% confidence interval, -14.8 to -4.2). Analyses evaluating the plausibility of the IV assumptions indicated estimates derived from analyses relying on CSLs provide the best estimates of the causal effect of education. CONCLUSIONS: IV analyses suggest education is protective against risk of dementia in older adulthood.
Keywords: Aged; Aged, 80 and over; Dementia; Education, Nonprofessional; Educational Status; Female; Genetic Predisposition to Disease; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Protective factors; Risk Factors; Schools; United States

Late mortality after sepsis: propensity matched cohort study. - Hallie C Prescott; Osterholzer, John J; Kenneth M. Langa; Angus, Derek C; Theodore J Iwashyna (BMJ, 2016)
OBJECTIVES:  To determine whether late mortality after sepsis is driven predominantly by pre-existing comorbid disease or is the result of sepsis itself. DEIGN:  Observational cohort study. SETTING:  US Health and Retirement Study. PARTICIPANTS:  960 patients aged ≥65 (1998-2010) with fee-for-service Medicare coverage who were admitted to hospital with sepsis. Patients were matched to 777 adults not currently in hospital, 788 patients admitted with non-sepsis infection, and 504 patients admitted with acute sterile inflammatory conditions. MAIN OUTCOME MEASURES:  Late (31 days to two years) mortality and odds of death at various intervals. RESULTS:  Sepsis was associated with a 22.1% (95% confidence interval 17.5% to 26.7%) absolute increase in late mortality relative to adults not in hospital, a 10.4% (5.4% to 15.4%) absolute increase relative to patients admitted with non-sepsis infection, and a 16.2% (10.2% to 22.2%) absolute increase relative to patients admitted with sterile inflammatory conditions (P<0.001 for each comparison). Mortality remained higher for at least two years relative to adults not in hospital. CONCLUSIONS:  More than one in five patients who survives sepsis has a late death not explained by health status before sepsis.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cause of Death; Female; Hospital Mortality; Hospitalization; Humans; Longitudinal Studies; Male; Medicare; Propensity Score; Prospective Studies; Sepsis; Time Factors; United States

Life Course Pathways to Racial Disparities in Cognitive Impairment among Older Americans. - Zhang, Zhenmei; Mark D Hayward; Yu, Yan-Liang (J Health Soc Behav, 2016)
Blacks are especially hard hit by cognitive impairment at older ages compared to whites. Here, we take advantage of the Health and Retirement Study (1998-2010) to assess how this racial divide in cognitive impairment is associated with the racial stratification of life course exposures and resources over a 12-year period among 8,946 non-Hispanic whites and blacks ages 65 and older in 1998. We find that blacks suffer from a higher risk of moderate/severe cognitive impairment at baseline and during the follow-up. Blacks are also more likely to report childhood adversity and to have grown up in the segregated South, and these early-life adversities put blacks at a significantly higher risk of cognitive impairment. Adulthood socioeconomic status is strongly associated with the risk of cognitive impairment, net of childhood conditions. However, racial disparities in cognitive impairment, though substantially reduced, are not eliminated when controlling for these life course factors.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; European Continental Ancestry Group; Female; Health Status Disparities; Humans; Male; Neuropsychological tests; Risk Factors; Severity of Illness Index; United States

Life Expectancy With and Without Pain in the U.S. Elderly Population. - Zachary Zimmer; Rubin, Sara (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: This study contributes to dialogue on quality versus quantity of life by examining years older persons can expect to live in various states of pain. METHODS: Data from seven waves of the Health and Retirement Study; N = 26,896; age 55+. Estimations using the Interpolative Markov Chain approach apply probability transitions to multistate life table functions. Two estimates are interpreted: (i) population-based, which provide population averages aggregated across baseline states and (ii) status-based, which provide independent estimates by baseline state. Age- and sex-specific years with no pain, milder nonlimiting, and severe or limiting pain are reported as is percent of life in states of pain. RESULTS: Females have higher life expectancy than males but similar expectations of pain-free life. Total life expectancy varies only slightly by baseline pain states but pain-free life expectancy varies greatly. For example, an 85-year-old female pain-free at baseline expects 7.04 more years, 5.28 being pain-free. An 85-year-old female with severe pain at baseline expects 6.42 years with only 2.66 pain-free. Percent of life with pain decreases by age for those pain-free at baseline and increases for those with pain at baseline. CONCLUSION: Pain is moderately associated with quantity of or total life but substantially and importantly associated with quality of or pain-free life.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Disabled Persons; Female; Health Status Indicators; Humans; Incidence; Life Expectancy; Life Tables; Male; Middle Aged; pain; Quality of Life; Risk Factors; Surveys and Questionnaires; United States

Life Satisfaction and Psychological Well-Being of Older Adults With Cancer Experience: The Role of Optimism and Volunteering. - Jinmoo Heo; Sanghee Chun; Lee, Sunwoo; Kim, Junhyoung (Int J Aging Hum Dev, 2016)
Promoting health and well-being among individuals of advancing age is a significant issue due to increased incidence of cancer among older adults. This study demonstrates the benefits of expecting positive outcomes and participating in volunteer activities among older adults with cancer. We used a nationally representative sample of 2,670 individuals who have experienced cancer from the 2008 wave of the Health and Retirement Study. We constructed a structural equation model to explore the associations of optimism, volunteerism, life satisfaction, and psychological well-being. The level of optimism was a significant predictor of volunteerism, which in turn affected life satisfaction and psychological well-being. The level of engagement in volunteer activities was found to have significant path coefficients toward both life satisfaction and psychological well-being. Our study provides evidence that older adults who have experienced cancer and maintained a positive outlook on their lives and engaged in personally meaningful activities tended to experience psychological well-being and life satisfaction.
Keywords: Aged; Aged, 80 and over; Aging; Female; Humans; Male; Middle Aged; Neoplasms; Optimism; Personal Satisfaction; Volunteers

Lifespan adversity and later adulthood telomere length in the nationally representative US Health and Retirement Study. - Puterman, Eli; Gemmill, Alison; Karasek, Deborah; David R Weir; Nancy E Adler; Aric A Prather; Elissa S Epel (Proc Natl Acad Sci U S A, 2016)
Stress over the lifespan is thought to promote accelerated aging and early disease. Telomere length is a marker of cell aging that appears to be one mediator of this relationship. Telomere length is associated with early adversity and with chronic stressors in adulthood in many studies. Although cumulative lifespan adversity should have bigger impacts than single events, it is also possible that adversity in childhood has larger effects on later life health than adult stressors, as suggested by models of biological embedding in early life. No studies have examined the individual vs. cumulative effects of childhood and adulthood adversities on adult telomere length. Here, we examined the relationship between cumulative childhood and adulthood adversity, adding up a range of severe financial, traumatic, and social exposures, as well as comparing them to each other, in relation to salivary telomere length. We examined 4,598 men and women from the US Health and Retirement Study. Single adversities tended to have nonsignificant relations with telomere length. In adjusted models, lifetime cumulative adversity predicted 6% greater odds of shorter telomere length. This result was mainly due to childhood adversity. In adjusted models for cumulative childhood adversity, the occurrence of each additional childhood event predicted 11% increased odds of having short telomeres. This result appeared mainly because of social/traumatic exposures rather than financial exposures. This study suggests that the shadow of childhood adversity may reach far into later adulthood in part through cellular aging.
Keywords: Aged; Aged, 80 and over; Cellular Senescence; Female; Humans; Longevity; Male; Middle Aged; Multivariate Analysis; Odds Ratio; Public Health Surveillance; Risk Factors; Stress, Psychological; Telomere; Telomere Shortening; United States

The Long-Term Benefits of Increased Aspirin Use by At-Risk Americans Aged 50 and Older. - David B. Agus; Gaudette, Étienne; Dana P Goldman; Messali, Andrew (PLoS One, 2016)
BACKGROUND: The usefulness of aspirin to defend against cardiovascular disease in both primary and secondary settings is well recognized by the medical profession. Multiple studies also have found that daily aspirin significantly reduces cancer incidence and mortality. Despite these proven health benefits, aspirin use remains low among populations targeted by cardiovascular prevention guidelines. This article seeks to determine the long-term economic and population-health impact of broader use of aspirin by older Americans at higher risk for cardiovascular disease. METHODS AND FINDINGS: We employ the Future Elderly Model, a dynamic microsimulation that follows Americans aged 50 and older, to project their lifetime health and spending under the status quo and in various scenarios of expanded aspirin use. The model is based primarily on data from the Health and Retirement Study, a large, representative, national survey that has been ongoing for more than two decades. Outcomes are chosen to provide a broad perspective of the individual and societal impacts of the interventions and include: heart disease, stroke, cancer, life expectancy, quality-adjusted life expectancy, disability-free life expectancy, and medical costs. Eligibility for increased aspirin use in simulations is based on the 2011-2012 questionnaire on preventive aspirin use of the National Health and Nutrition Examination Survey. These data reveal a large unmet need for daily aspirin, with over 40% of men and 10% of women aged 50 to 79 presenting high cardiovascular risk but not taking aspirin. We estimate that increased use by high-risk older Americans would improve national life expectancy at age 50 by 0.28 years (95% CI 0.08-0.50) and would add 900,000 people (95% CI 300,000-1,400,000) to the American population by 2036. After valuing the quality-adjusted life-years appropriately, Americans could expect $692 billion (95% CI 345-975) in net health benefits over that period. CONCLUSIONS: Expanded use of aspirin by older Americans with elevated risk of cardiovascular disease could generate substantial population health benefits over the next twenty years and do so very cost-effectively.
Keywords: Aged; Aged, 80 and over; Anti-Inflammatory Agents, Non-Steroidal; Aspirin; Cardiovascular Diseases; Female; Humans; Incidence; Life Expectancy; Male; Middle Aged; Nutrition Surveys; Primary Prevention; Quality-Adjusted Life Years; Risk Assessment; United States

Marital history and survival after a heart attack. - Matthew E Dupre; Nelson, Alicia (Soc Sci Med, 2016)
Heart disease is the leading cause of death in the United States and nearly one million Americans will have a heart attack this year. Although the risks associated with a heart attack are well established, we know surprisingly little about how marital factors contribute to survival in adults afflicted with heart disease. This study uses a life course perspective and longitudinal data from the Health and Retirement Study to examine how various dimensions of marital life influence survival in U.S. older adults who suffered a heart attack (n = 2197). We found that adults who were never married (odds ratio [OR] = 1.73), currently divorced (OR = 1.70), or widowed (OR = 1.34) were at significantly greater risk of dying after a heart attack than adults who were continuously married; and the risks were not uniform over time. We also found that the risk of dying increased by 12% for every additional marital loss and decreased by 7% for every one-tenth increase in the proportion of years married. After accounting for more than a dozen socioeconomic, psychosocial, behavioral, and physiological factors, we found that current marital status remained the most robust indicator of survival following a heart attack. The implications of the findings are discussed in the context of life course inequalities in chronic disease and directions for future research.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Divorce; Female; Humans; Male; Marital Status; Myocardial Infarction; Prospective Studies; Retrospective Studies; Single Person; Spouses; Survivors; United States; Widowhood

Marital quality, marital dissolution, and mortality risk during the later life course. - Jennifer R. Bulanda; J Scott Brown; Takashi Yamashita (Soc Sci Med, 2016)
This study examines the relationship between later-life marital quality, marital dissolution, and mortality using discrete-time event history models with data from nine waves (1992-2008) of the Health and Retirement Study (n = 7388). Results show marital status is more important for men's mortality risk than women's, whereas marital quality is more important for women's survival than men's. Being widowed or divorced more than two years raises mortality risk for men, but later-life marital dissolution is not significantly associated with women's mortality risk, regardless of the type of dissolution or length of time since it occurred. Low-quality marital interaction is negatively related to women's odds of death, but none of the marital quality measures are significantly associated with mortality for men. Marital satisfaction moderates the relationship between widowhood and mortality for women, but the relationship between marital dissolution and mortality is similar for men regardless of marital quality prior to divorce/widowhood. Results suggest the importance of accounting for both marital status and marital quality when examining older individuals' mortality risk.
Keywords: Aged; Aged, 80 and over; Female; Humans; Male; Marital Status; Marriage; Middle Aged; Mortality; Retirement; Sex Factors

Methodological Aspects of Subjective Life Expectancy: Effects of Culture-Specific Reporting Heterogeneity Among Older Adults in the United States. - Lee, Sunghee; Jacqui Smith (The Journals of Gerontology: Series B, 2016)
OBJECTIVES: Subjective life expectancy (SLE) has been suggested as a predictor of mortality and mortality-related behaviors. Although critical for culturally diverse societies, these findings do not consider cross-cultural methodological comparability. Culture-specific reporting heterogeneity is a well-known phenomenon introducing biases, and research on this issue with SLE is not established. METHOD: Using data from the Health and Retirement Study, we examined reporting heterogeneity in SLE focusing on item nonresponse, focal points, and reports over time for five ethnic-cultural groups: non-Hispanic Whites, non-Hispanic Blacks, non-Hispanic other races, English-interviewed Hispanics, and Spanish-interviewed Hispanics. RESULTS: On item nonresponse, Spanish-interviewed Hispanics said, "I don't know," to SLE significantly more than any other groups. Nearly half of the respondents chose 0, 50, or 100, making them focal points. However, the focal points differed: 50 for Whites, 100 for Blacks, and 0 for Spanish-interviewed Hispanics. The relationship of SLE measured at two time points was higher for Whites than minorities. Moreover, those who said "I don't know" to SLE showed higher subsequent mortality than those who gave an answer. SLE was not a significant mortality predictor for Hispanics. DISCUSSION: Overall, SLE is not free from culture-specific reporting heterogeneity. This warrants further research about its culture-relevant measurement mechanisms.
Keywords: Aged; Aged, 80 and over; Bias; Cross-Cultural Comparison; Cross-Sectional Studies; Diagnostic Self Evaluation; Ethnic Groups; Female; Frail Elderly; Humans; Language; Life Expectancy; Longitudinal Studies; Male; Middle Aged; Self Report; United States

Multimorbidity is associated with anxiety in older adults in the Health and Retirement Study. - Christine E Gould; Ruth O'Hara; Mary K. Goldstein; Sherry A. Beaudreau (Int J Geriatr Psychiatry, 2016)
OBJECTIVES: The present study determined whether the number of medical conditions was associated with increased occurrence of anxiety and whether triads of medical conditions were associated with anxiety in a nationally representative sample of older Americans. We determined whether multimorbidity findings were unique to anxiety as compared with depressive symptoms. METHODS: A sample of 4219 participants (65 years or older) completed anxiety and depression measures in the Health and Retirement Study 2006 wave. The logistic regression models' outcome was elevated anxiety (≥12 on five-item Beck Anxiety Inventory) or depressive symptoms (≥12 on eight-item Center for Epidemiological Studies Depression Scale). The predictor variable was a tally of seven self-report of doctor-diagnosed conditions: arthritis, cancer, diabetes, heart conditions, high blood pressure, lung disease, and stroke. Analyses were adjusted for age, gender, and depressive or anxiety symptoms. Associations among elevated anxiety or depressive symptoms and 35 triads of medical conditions were examined using Bonferroni corrected chi-square analyses. RESULTS: Three or more medical conditions conferred a 2.30-fold increase in elevated anxiety (95% confidence interval: 1.44-4.01). Twenty triads were associated with elevated anxiety as compared with 13 associated with depressive symptoms. Six of seven medical conditions, with the exception being stroke, were present in the majority of triads. CONCLUSION: Number of medical conditions and specific conditions are associated with increased occurrence of elevated anxiety. Compared with elevated depressive symptoms, anxiety is associated with greater multimorbidity. As anxiety and depression cause significant morbidity, it may be beneficial to consider these mental health symptoms when evaluating older adults with multimorbidity. Published 2016. This article is a U.S. Government work and is in the public domain in the USA.
Keywords: Aged; Aged, 80 and over; Anxiety Disorders; Chronic disease; Depressive Disorder; Female; Humans; Logistic Models; Male; multimorbidity; Retirement; United States

Neighborhood Support and Aging-in-Place Preference Among Low-Income Elderly Chinese City-Dwellers. - Terry Y S Lum; Vivian W Q Lou; Chen, Yanyan; Wong, Gloria; Luo, Hao; Tracy Tong (J Gerontol B Psychol Sci Soc Sci, 2016)
OBJECTIVES: Preferences for aging-in-place are unclear among low-income elderly Chinese city-dwellers, who are more likely to be geographically bound, to have little care support, but possess strong filial values and family cohesiveness. This study investigated the preferences for aging-in-place and its contributing neighborhood factors among low-income Chinese elderly in a metropolitan city. METHOD: We conducted interviews with 400 older people residing in public housing estates in Hong Kong. RESULTS: The majority of low-income elderly persons (80.4%) prefer to age in place even if their health and functioning has deteriorated beyond independent living. Logistic regression showed that (a) having very low income (<HK$2,000/month) and not receiving means-tested welfare predicted lower preference for this option [odd ratios (OR) = 0.27]; and (b) having medical facilities within reach (OR =9.02); and (c) an elderly center in the area (OR = 2.98) were associated with a preference for aging in place, after controlling for demographic, and functioning characteristics. DISCUSSION: Low-income elderly Chinese city-dwellers prefer to age in place, given appropriate neighborhood support. These findings can be interpreted in light of Lawton's ecological theory of aging and suggest a service model similar to the Naturally Occurring Retirement Community with Supportive Service Programs.
Keywords: Aged; Aged, 80 and over; Aging; Asian Continental Ancestry Group; Female; Hong Kong; Humans; Independent Living; Interview, Psychological; Male; Middle Aged; Poverty; Quality of Life; Residence Characteristics; Social Support; Urban Population

Neuroimaging overuse is more common in Medicare compared with the VA. - James F. Burke; Eve A Kerr; Ryan J McCammon; Holleman, Rob; Kenneth M. Langa; Brian C. Callaghan (Neurology, 2016)
OBJECTIVE: To inform initiatives to reduce overuse, we compared neuroimaging appropriateness in a large Medicare cohort with a Department of Veterans Affairs (VA) cohort. METHODS: Separate retrospective cohorts were established in Medicare and in VA for headache and neuropathy from 2004 to 2011. The Medicare cohorts included all patients enrolled in the Health and Retirement Study (HRS) with linked Medicare claims (HRS-Medicare; n = 1,244 for headache and 998 for neuropathy). The VA cohorts included all patients receiving services in the VA (n = 93,755 for headache and 183,642 for neuropathy). Inclusion criteria were age over 65 years and an outpatient visit for incident neuropathy or a primary headache. Neuroimaging use was measured with Current Procedural Terminology codes and potential overuse was defined using published criteria for use with administrative data. Increasingly specific appropriateness criteria excluded nontarget conditions for which neuroimaging may be appropriate. RESULTS: For both peripheral neuropathy and headache, potentially inappropriate imaging was more common in HRS-Medicare compared with the VA. Forty-nine percentage of all headache patients received neuroimaging in HRS-Medicare compared with 22.1% in the VA (p < 0.001) and differences persist when analyzing more specific definitions of overuse. A total of 23.7% of all HRS-Medicare incident neuropathy patients received neuroimaging compared with 9.0% in the VA (p < 0.001), and the difference persisted after excluding nontarget conditions. CONCLUSIONS: Overuse of neuroimaging is likely less common in the VA than in a Medicare population. Better understanding the reasons for the more selective use of neuroimaging in the VA could help inform future initiatives to reduce overuse of diagnostic testing.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Headache Disorders, Primary; Humans; Male; Medicare; Neuroimaging; Peripheral Nervous System Diseases; United States; United States Department of Veterans Affairs; Unnecessary Procedures

Older adults with poor self-rated memory have less depressive symptoms and better memory performance when perceived self-efficacy is high. - O'Shea, Deirdre M; Vonetta M Dotson; Fieo, Robert A; Tsapanou, Angeliki; Laura B Zahodne; Stern, Yaakov (Int J Geriatr Psychiatry, 2016)
OBJECTIVE: To investigate whether self-efficacy moderates the association between self-rated memory and depressive symptoms in a large sample of older adults. The influence of self-efficacy and depressive symptoms on memory performance was also examined in a subsample of individuals who reported poor memory. METHODS: Non-demented participants (n = 3766) were selected from the 2012 wave of the Health and Retirement Study. Depressive symptomatology was assessed with the 8-item Center for Epidemiologic Studies Depression Scale. A modified version of the Midlife Developmental Inventory Questionnaire was used as the measure of self-efficacy. Participants were asked to rate their memory presently on a five-point scale from Excellent (1) to Poor (5). Immediate memory and delayed memory (after a 5-min interval) were measured by the number of correct words recalled from a 10-item word list. RESULTS: Multiple regression analyses revealed that negative ratings of memory were significantly associated with greater levels of depressive symptoms, with this effect being greatest in those with low levels of self-efficacy. Additionally, greater self-efficacy was associated with optimal objective memory performances but only when depressive symptoms were low in individuals who reported poor memory function (n = 1196). CONCLUSION: Self-efficacy moderates the relationship between self-rated memory function and depressive symptoms. Higher self-efficacy may buffer against the impact of subjective memory difficulty on one's mood and thereby mitigating the effect of depressive symptoms on memory. Interventions should focus on increasing perceived self-efficacy in older adults reporting poor memory function to potentially minimize memory impairment.
Keywords: Aged; Aged, 80 and over; depression; Female; Humans; Male; Memory; Middle Aged; Regression Analysis; Self Efficacy; Surveys and Questionnaires

One-Year Mortality After Hip Fracture: Development and Validation of a Prognostic Index. - Irena Cenzer; Victoria L. Tang; W John Boscardin; Christine S Ritchie; Margaret Wallhagen; Espaldon, Roxanne; Kenneth E Covinsky (J Am Geriatr Soc, 2016)
OBJECTIVES: To develop a prediction index for 1-year mortality after hip fracture in older adults that includes predictors from a wide range of domains. DESIGN: Retrospective cohort study. SETTINGS: Health and Retirement Study (HRS). PARTICIPANTS: HRS participants who experienced hip fracture between 1992 and 2010 as identified according to Medicare claims data (N = 857). MEASUREMENTS: Outcome measure was death within 1 year of hip fracture. Predictor measures were participant demographic characteristics, socioeconomic status, social support, health, geriatric symptoms, and function. Variables independently associated with 1-year mortality were identified, and best-subsets regression was used to identify the final model. The selected variables were weighted to create a risk index. The index was internally validated using bootstrapping to estimate model optimism. RESULTS: Mean age at time of hip fracture was 84, and 76% of the participants were women. There were 235 deaths (27%) during the 1-year follow up. Five predictors of mortality were included in the final model: aged 90 and older (2 points), male sex (2 points), congestive heart failure (2 points), difficulty preparing meals (2 points), and not being able to drive (1 point). The point scores of the index were associated with 1-year mortality, with 0 points predicting 10% risk and 7 to 9 points predicting 66% risk. The c-statistic for the final model was 0.73, with an estimated optimism penalty of 0.01, indicating very little evidence of overfitting. CONCLUSION: The prognostic index combines demographic, comorbidity, and function variables and can be used to differentiate between individuals at low and high risk of 1-year mortality after hip fracture.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cause of Death; Cohort Studies; Comorbidity; Disability Evaluation; Female; Hip Fractures; Humans; Incidence; Longitudinal Studies; Male; Prognosis; Retrospective Studies; Risk Assessment; Survival Analysis; United States

Personality trait development at the end of life: Antecedents and correlates of mean-level trajectories. - Wagner, Jenny; Ram, Nilam; Jacqui Smith; Denis Gerstorf (J Pers Soc Psychol, 2016)
Empirical evidence over the past 20 years has documented that key aspects of personality traits change during adulthood. However, it is essentially an open question whether and how traits change at the very end of life and what role health, cognitive performance, perceived control, and social factors play in those changes. To examine these questions, we applied growth models to 13-year longitudinal data obtained from now-deceased participants in the Berlin Aging Study (N = 463; age at baseline M = 85.9 years, SD = 8.4; 51% men). Results revealed that neuroticism, on average, increases (about 0.3 SD in the last 10 years) and that this increase becomes even steeper at the end of life. In contrast, extraversion and openness decline rather steadily at the end of life (about -0.5 SD in the last 10 years). Additionally, poor health manifested as a risk factor for declines in extraversion and openness late in life but not neuroticism. Similar to earlier phases of life, better cognitive performance related to more openness. More loneliness was associated with higher neuroticism, whereas more social activity was associated with higher levels of extraversion and openness. Intriguing additional insights indicated that more personal control was associated with higher levels of extraversion and openness, whereas the feeling that one's life is controlled by others was associated with higher neuroticism but also with higher openness closer to death. We discuss potential pathways by which health, cognitive performance, control, and social inclusion resources and risk factors affect personality development late in life. (PsycINFO Database Record
Keywords: Aged; Aged, 80 and over; Aging; Anxiety Disorders; Berlin; Extraversion, Psychological; Female; Health Status; Human Development; Humans; Internal-External Control; Longitudinal Studies; Male; Neuroticism; Personality; Social Support

A pilot study among older adults of the concordance between their self-reports to a health survey and spousal proxy reports on their behalf. - Frederic D Wolinsky; Ayres, Lioness; Michael P Jones; Yiyue Lou; George L Wehby; Fred A Ullrich (BMC Health Serv Res, 2016)
BACKGROUND: Proxy respondents are frequently used in health surveys, and the proxy is most often the spouse. Longstanding concerns linger, however, about the validity of using spousal proxies, especially for older adults. The purpose of this pilot study was to evaluate the concordance between self-reports and spousal proxy reports to a standard health survey in a small convenience sample of older married couples. METHODS: We used the Seniors Together in Aging Research (STAR) volunteer registry at the University of Iowa to identify and consent a cross-sectional, convenience sample of 28 married husband and wife couples. Private, personal interviews with each member of the married couple using a detailed health survey based on the 2012 Health and Retirement Study (HRS) instrument were conducted using computer assisted personal interviewing software. Within couples, each wife completed the health survey first for herself and then for her husband, and each husband completed the health survey first for himself and then for his wife. The health survey topics included health ratings, health conditions, mobility, instrumental activities of daily living (IADLs), health services use, and preventative services. Percent of agreement and prevalence and bias adjusted kappa statistics (PABAKs) were used to evaluate concordance. RESULTS: PABAK coefficients indicated moderate to excellent concordance (PABAKs >0.60) for most of the IADL, health condition, hospitalization, surgery, preventative service, and mobility questions, but only slight to fair concordance (PABAKs = -0.21 to 0.60) for health ratings, and physician and dental visits. CONCLUSIONS: These results do not allay longstanding concerns about the validity of routinely using spousal proxies in health surveys to obtain health ratings or the number of physician and dental visits among older adults. Further research is needed in a nationally representative sample of older couples in which each wife completes the health survey first for herself and then for her husband, each husband completes the health survey first for himself and then for his wife, and both spouses' Medicare claims are linked to their health survey responses to determine not just the concordance between spousal reports, but the concordance of those survey responses to the medical record.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Epidemiologic Methods; Female; Health Status; Hospitalization; Humans; Iowa; Male; Medicare; Middle Aged; Patient Acceptance of Health Care; Physicians; Proxy; Spouses; United States

Prevalence and Outcomes of Breathlessness in Older Adults: A National Population Study. - David C. Currow; Amy P Abernethy; Miriam J Johnson; Yinghui Miao; W John Boscardin; Christine S Ritchie (J Am Geriatr Soc, 2016)
OBJECTIVES: To determine the prevalence and outcomes of breathlessness in older Americans. SETTING: Community-dwelling older adults. PARTICIPANTS: Individuals aged 70 and older in the nationally representative Health and Retirement Study (2008, follow-up through 2012) (N = 3,671; mean age 78). MEASUREMENTS: Breathlessness was assessed by asking the question, "How often do you become short of breath while awake?" Responses of often or sometimes were considered to represent a level of breathlessness sufficient to warrant clinical attention. The prevalence of breathlessness is described overall and in subpopulations, then rates of associated symptoms, well-being, and health services use of participants who were breathless are compared with rates of those who were not. The risk of decline in activities of daily living (ADLs) and death through 2012 was estimated by creating a multivariable Cox proportional hazards model, adjusting for age, sex, race and ethnicity, and education. RESULTS: Twenty-five percent of participants reported breathlessness. The prevalence of breathlessness was higher in certain subpopulations: chronic lung disease (63%), multimorbidity (≥2 chronic conditions) (45%), current smokers (38%), heart disease (36%), obesity (body mass index ≥30.0 kg/m ) (33%), and education less than high school (32%). Breathlessness was associated with higher rates of depression, anxiety, and severe fatigue; lower ratings of well-being; and higher rates of clinic and emergency department visits and hospitalizations (all P < .001). Breathlessness predicted ADL decline over 5 years (adjusted hazard ratio (aHR) = 1.43, 95% confidence interval (CI) = 1.22-1.68) and death (aHR 1.62, 95% CI = 1.32-2.02). CONCLUSION: One in four adults aged 70 and older in the United States experiences breathlessness, which is associated with lack of well-being, greater health services use, and a 40% greater risk of worsened function and 60% greater risk of death over the next 5 years.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Anxiety; Chronic disease; Comorbidity; depression; Dyspnea; Female; Geriatric Assessment; Hospitalization; Humans; Male; Prevalence; Proportional Hazards Models; Risk Assessment; Risk Factors; Symptom Assessment; United States

Promoting and Protecting Against Stigma in Assisted Living and Nursing Homes. - Zimmerman, Sheryl; Dobbs, Debra; Roth, Erin G; Goldman, Susan; Peeples, Amanda D; Wallace, Brandy (Gerontologist, 2016)
PURPOSE OF THE STUDY: To determine the extent to which structures and processes of care in multilevel settings (independent living, assisted living, and nursing homes) result in stigma in assisted living and nursing homes. DESIGN AND METHODS: Ethnographic in-depth interviews were conducted in 5 multilevel settings with 256 residents, families, and staff members. Qualitative analyses identified the themes that resulted when examining text describing either structures of care or processes of care in relation to 7 codes associated with stigma. RESULTS: Four themes related to structures of care and stigma were identified, including the physical environment, case mix, staff training, and multilevel settings; five themes related to processes of care and stigma, including dining, independence, respect, privacy, and care provision. For each theme, examples were identified illustrating how structures and processes of care can potentially promote or protect against stigma. IMPLICATIONS: In no instance were examples or themes identified that suggested the staff intentionally promoted stigma; on the other hand, there was indication that some structures and processes were intentionally in place to protect against stigma. Perhaps the most important theme is the stigma related to multilevel settings, as it has the potential to reduce individuals' likelihood to seek and accept necessary care. Results suggest specific recommendations to modify care and reduce stigma.
Keywords: Aged; Aged, 80 and over; Aging; Anthropology, Cultural; Assisted Living Facilities; Attitude of Health Personnel; Female; Humans; Male; Nursing homes; Prejudice; Social Stigma

Racial and ethnic differences in cognitive function among older adults in the USA. - Díaz-Venegas, Carlos; Brian Downer; Kenneth M. Langa; Rebeca Wong (International Journal of Geriatric Psychiatry, 2016)
OBJECTIVE: Examine differences in cognition between Hispanic, non-Hispanic black (NHB), and non-Hispanic white (NHW) older adults in the United States. DATA/METHODS: The final sample includes 18 982 participants aged 51 or older who received a modified version of the Telephone Interview for Cognitive Status during the 2010 Health and Retirement Study follow-up. Ordinary least squares will be used to examine differences in overall cognition according to race/ethnicity. RESULTS: Hispanics and NHB had lower cognition than NHW for all age groups (51-59, 60-69, 70-79, 80+). Hispanics had higher cognition than NHB for all age groups but these differences were all within one point. The lower cognition among NHB compared to NHW remained significant after controlling for age, gender, and education, whereas the differences in cognition between Hispanics and NHW were no longer significant after controlling for these covariates. Cognitive scores increased with greater educational attainment for all race/ethnic groups, but Hispanics exhibited the least benefit. DISCUSSION: Our results highlight the role of education in race/ethnic differences in cognitive function during old age. Education seems beneficial for cognition in old age for all race/ethnic groups, but Hispanics appear to receive a lower benefit compared to other race/ethnic groups. Further research is needed on the racial and ethnic differences in the pathways of the benefits of educational attainment for late-life cognitive function. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: African Americans; Aged; Aged, 80 and over; Cognition; Ethnic Groups; European Continental Ancestry Group; Female; Hispanic Americans; Humans; Male; Middle Aged; United States

Racial and Ethnic Differences in End-of-Life Medicare Expenditures. - Byhoff, Elena; Tamara B Harris; Kenneth M. Langa; Theodore J Iwashyna (Journal of the American Geriatrics Society, 2016)
OBJECTIVES: To determine to what extent demographic, social support, socioeconomic, geographic, medical, and End-of-Life (EOL) planning factors explain racial and ethnic variation in Medicare spending during the last 6 months of life. DESIGN: Retrospective cohort study. SETTING: Health and Retirement Study (HRS). PARTICIPANTS: Decedents who participated in HRS between 1998 and 2012 and previously consented to survey linkage with Medicare claims (N = 7,105). MEASUREMENTS: Total Medicare expenditures in the last 180 days of life according to race and ethnicity, controlling for demographic factors, social supports, geography, illness burden, and EOL planning factors, including presence of advance directives, discussion of EOL treatment preferences, and whether death had been expected. RESULTS: The analysis included 5,548 (78.1%) non-Hispanic white, 1,030 (14.5%) non-Hispanic black, and 331 (4.7%) Hispanic adults and 196 (2.8%) adults of other race or ethnicity. Unadjusted results suggest that average EOL Medicare expenditures were $13,522 (35%, P < .001) more for black decedents and $16,341 (42%, P < .001) more for Hispanics than for whites. Controlling for demographic, socioeconomic, geographic, medical, and EOL-specific factors, the Medicare expenditure difference between groups fell to $8,047 (22%, P < .001) more for black and $6,855 (19%, P < .001) more for Hispanic decedents than expenditures for non-Hispanic whites. The expenditure differences between groups remained statistically significant in all models. CONCLUSION: Individuals-level factors, including EOL planning factors do not fully explain racial and ethnic differences in Medicare spending in the last 6 months of life. Future research should focus on broader systemic, organizational, and provider-level factors to explain these differences.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; Comorbidity; Cross-Cultural Comparison; Ethnic Groups; European Continental Ancestry Group; Female; Health Care Surveys; Health Expenditures; Hispanic Americans; Humans; Life Support Care; Longitudinal Studies; Male; Medicare; Rate Setting and Review; Social Support; Socioeconomic factors; Terminal Care; United States

Racial and Socioeconomic Variation in Genetic Markers of Telomere Length: A Cross-Sectional Study of U.S. Older Adults. - Hamad, Rita; Tuljapurkar, Shripad; David Rehkopf (EBioMedicine, 2016)
BACKGROUND: Shorter telomere length (TL) has been associated with stress and adverse socioeconomic conditions, yet U.S. blacks have longer TL than whites. The role of genetic versus environmental factors in explaining TL by race and socioeconomic position (SEP) remains unclear. METHODS: We used data from the U.S. Health and Retirement Study (N=11,934) to test the hypothesis that there are differences in TL-associated SNPs by race and SEP. We constructed a TL polygenic risk score (PRS) and examined its association with race/ethnicity, educational attainment, assets, gender, and age. RESULTS: U.S. blacks were more likely to have a lower PRS for TL, as were older individuals and men. Racial differences in TL were statistically accounted for when controlling for population structure using genetic principal components. The GWAS-derived SNPs for TL, however, may not have consistent associations with TL across different racial/ethnic groups. CONCLUSIONS: This study showed that associations of race/ethnicity with TL differed when accounting for population stratification. The role of race/ethnicity for TL remains uncertain, however, as the genetic determinants of TL may differ by race/ethnicity. Future GWAS samples should include racially diverse participants to allow for better characterization of the determinants of TL in human populations.
Keywords: Age Factors; Aged; Aged, 80 and over; Alleles; Cross-Sectional Studies; Ethnic Groups; Female; Gene Frequency; Genetic Markers; Genome-Wide Association Study; Geriatric Assessment; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Population Surveillance; Socioeconomic factors; Telomere Homeostasis; United States

Racial/Ethnic Differences in Trajectories of Cognitive Function in Older Adults. - Elizabeth Vasquez; Anda Botoseneanu; Joan M. Bennett; Benjamin A Shaw (J Aging Health, 2016)
OBJECTIVE: The objective of this study is to (a) examine racial/ethnic differences in trajectories of cognitive function and (b) evaluate the role of education and health behaviors (physical activity [PA] and smoking) as mediators of racial/ethnic differences in the rate of decline in cognitive function in older adults. METHOD: Data for this study came from the Health and Retirement Study ( n = 3,424). Hierarchical linear models were used to define the trajectory of cognitive function between 2002 and 2008. Participants were classified based on PA as non-vigorously active, intermittent vigorously active, and consistently vigorously active. RESULTS: After adding education, the Hispanic's and Black's disparities in cognitive performance were slightly attenuated (Hispanics, β = -1.049, p < .001; Blacks, β = -3.397, p < .001) but were still different from Whites. Smoking was not associated with the cognition intercept or rate of decline. DISCUSSION: We found education had a partial mediating effect on racial differences in levels of cognition but not on the rate of change over time.
Keywords: Aged; Aged, 80 and over; Black People; Cognition; Cognition Disorders; Female; Health Behavior; Hispanic or Latino; Humans; Male; White People

Self-Reported Hearing in the Last 2 Years of Life in Older Adults. - Christine S Ritchie; Yinghui Miao; W John Boscardin; Margaret Wallhagen (J Am Geriatr Soc, 2016)
OBJECTIVES: To assess the prevalence and correlates of self-reported hearing loss during the last 2 years of life. DESIGN: Observational cohort study. SETTING: The Health and Retirement Study (HRS), a longitudinal nationally representative cohort of adults aged 50 and older (2000-13). PARTICIPANTS: Older adults (N = 5,895, mean age at death 78, 53% female, 20% nonwhite). MEASUREMENTS: The HRS interview closest to death was used (mean 12.2 months before death). Participants rated their hearing (excellent, very good, good, fair, poor) and indicated whether they used hearing aids. The prevalence and correlates of fair and poor ratings are described, adjusted for age and sex. RESULTS: Thirty-two percent (95% confidence interval (CI) = 31-34%) of all participants and 60% (95% CI = 57-64%) of the 7% of participants who used hearing aids rated their hearing as fair or poor. The prevalence of fair or poor hearing was highest in participants interviewed closest to death (29% 19-24 months before death, 36% 1-6 months before death, P for trend = .01). Correlates of fair or poor hearing during the last 2 years of life included age at death (50-59, 22%; 60-69, 21%; 70-79, 26%; 80-89, 38%; ≥90, 50%), sex (men 35%, women 30%), race and ethnicity (Hispanic 42%, white 33%), wealth (lowest quartile 38%, highest quartile 27%), history of heart disease (yes 38%, no 27%), activity of daily living dependence (yes 42%, no 26%), difficulty taking medications (yes 46%, no 29%), and probable dementia (yes 44%, no 24%). CONCLUSION: Self-reported hearing loss increases during the last 2 years of life and is associated with physical and social vulnerability.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; California; Demography; Female; Hearing aids; Hearing loss; Humans; Longitudinal Studies; Male; Middle Aged; Prevalence; Quality of Life; Risk Factors; Self Report; Vulnerable Populations

Self-reported herpes zoster, pain, and health care seeking in the Health and Retirement Study: implications for interpretation of health care-based studies. - Hales, Craig M; Harpaz, Rafael; Bialek, Stephanie R (Ann Epidemiol, 2016)
PURPOSE: To describe self-reported herpes zoster (HZ) and explore factors that could impact interpretation of results from health care-based HZ studies. METHODS: We performed logistic regression using data from the 2008 Health and Retirement Study (HRS) to evaluate risk factors for having a history of HZ and experiencing severe HZ pain, and predictors for seeking health care for HZ. RESULTS: Among 14,564 respondents aged ≥55 years, women were more likely than men to report a history of HZ (15.7% vs. 11.6%, P < .01). Blacks (6.4% vs. 14.7% in whites, P < .01) and respondents with less than a high school diploma (12.2% vs.14.2% in respondents with at least a high school diploma, P = .01) were less likely to report a history of HZ. Women, blacks, Hispanics, and those with less than a high school diploma were more likely to report severe HZ pain. Most (91.1%) respondents sought health care for HZ; Hispanics (64.2% vs. 92.1% in whites, P < .001) and those with recurrent HZ were less likely to seek health care for HZ, whereas those with severe pain were more likely (95.4% vs. 87.9% in those without severe pain, P < .01). CONCLUSIONS: HRS provides a new platform for studies of HZ, one which allowed us to uncover issues that warrant particular attention when interpreting results of health care-based studies.
Keywords: Age Factors; Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Health Surveys; Herpes Zoster; Humans; Independent Living; Logistic Models; Male; Middle Aged; Outcome Assessment, Health Care; pain; Pain Measurement; Patient Acceptance of Health Care; Reproducibility of Results; Retirement; Risk Assessment; Self Report; Severity of Illness Index; Sex Factors; Treatment Outcome; United States

Sex-Specific and Time-Varying Associations Between Cigarette Smoking and Telomere Length Among Older Adults. - Zhang, Chenan; Diane S. Lauderdale; Brandon L Pierce (Am J Epidemiol, 2016)
Inconsistent associations between smoking and telomere length (TL) have been reported in epidemiologic studies, perhaps because of the time-varying nature of smoking behaviors. We estimated the associations of TL, which was measured by quantitative polymerase chain reaction using saliva DNA, with concurrent and past smoking status reported biennially for up to 16 years before TL measurement in 5,624 participants in the Health and Retirement Study (1992-2008). Smoking was associated with reduced TL when we used prospective data on smoking statuses among men and women, but the association was strongly attenuated among men in cross-sectional analyses. This attenuation was largely due to a higher rate of smoking cessation during the study period among men with shorter TL than among men with longer TL. Short TL was also associated with poorer overall health in men, which suggests that male smokers with short TL were more likely to quit smoking because of poor health. Analyses of years since cessation, smoking duration, and pack-years of smoking all support the hypothesis that increased cigarette use shortens TL. Our results provide a potential explanation for the inconsistent associations between smoking and TL reported in previous cross-sectional studies. Time-varying associations should be considered in future studies of smoking behavior, TL, aging, and disease risk.
Keywords: Aged; Aged, 80 and over; Aging; Biomarkers; DNA; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Oxidative stress; Polymerase Chain Reaction; Prospective Studies; Saliva; Sex Distribution; Smoking; Smoking cessation; Telomere Shortening

Skin Cancer in U.S. Elderly Adults: Does Life Expectancy Play a Role in Treatment Decisions? - Linos, Eleni; Chren, Mary-Margaret; Irena Cenzer; Kenneth E Covinsky (J Am Geriatr Soc, 2016)
OBJECTIVES: To examine whether life expectancy influences treatment pattern of nonmelanoma skin cancer, or keratinocyte carcinoma (KC), the most common malignancy and the fifth most costly cancer to Medicare. DESIGN: Nationally representative cross-sectional study. SETTING: Nationally representative Health and Retirement Study linked to Medicare claims. PARTICIPANTS: Treatments (N = 9,653) from individuals aged 65 and older treated for basal or squamous cell carcinoma between 1992 and 2012 (N = 2,702) were included. MEASUREMENTS: Limited life expectancy defined according to aged 85 and older, medical comorbidities, Charlson Comorbidity Index score of 3 or greater, difficulty in at least one activity of daily living (ADL), and a Lee index of 13 or greater. Treatment type (Mohs micrographic surgery (MMS) (most intensive, highest cost), excision, or electrodesiccation and curettage (ED&C) (least intensive, lowest cost)), according to procedure code. RESULTS: Most KCs (61%) were treated surgically. Rates of MMS (19%), excision (42%), and ED&C (39%) were no different in participants with limited life expectancy and those with normal life expectancy. For example, 19% of participants with difficulty or dependence in ADLs, 20% of those with a Charlson comorbidity score greater than 3, and 15% of those in their last year of life underwent MMS; participants who died within 1 year of diagnosis were treated in the same way as those who lived longer. CONCLUSION: A one-size-fits-all approach in which advanced age, health status, functional status, and prognosis are not associated with intensiveness of treatment appears to guide treatment for KC, a generally nonfatal condition. Although intensive treatment of skin cancer when it causes symptoms may be indicated regardless of life expectancy, persons with limited life expectancy should be given choices to ensure that the treatment matches their goals and preferences.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Carcinoma, Basal Cell; Carcinoma, Squamous Cell; Comorbidity; Cost-Benefit Analysis; Cross-Sectional Studies; Curettage; Decision Support Techniques; Disability Evaluation; Electrosurgery; Female; Humans; Keratinocytes; Life Expectancy; Male; Mohs Surgery; Prognosis; Skin Neoplasms

Trajectories of body mass indices and development of frailty: Evidence from the health and retirement study. - Briana Mezuk; Matthew C. Lohman; Rock, Andrew K; Payne, Martha E (Obesity (Silver Spring), 2016)
OBJECTIVE: To estimate trajectories of body mass index (BMI) and determine their association with incident frailty in later life. METHODS: Data come from the 2004 to 2012 waves of the Health and Retirement Study, a longitudinal survey of older adults. Analysis was restricted to respondents who were not frail at baseline (n = 10,827). BMI (kg/m(2) ) was calculated from self-reported weight and height. Incident frailty was assessed using the Frailty Index. Longitudinal growth mixture modeling was used to estimate the relationship between BMI trajectories and incident frailty over a 10-year period. RESULTS: Four trajectory classes were identified: weight gain (n = 162 [1.4%], mean final BMI = 42 kg/m(2) ), weight loss (n = 171 [1.7%], mean final BMI = 25.0 kg/m(2) ), consistent obesity (n = 640 [6.8%], mean final BMI = 34.7 kg/m(2) ), and consistent overweight (n = 9,864 [90.1%] mean final BMI = 26.0 kg/m(2) ). Cumulative incidence of frailty was 19.9%. Relative to the consistent overweight class, the weight gain class had the highest likelihood of incident frailty (odds ratio, OR: 3.61, 95% confidence interval, CI: 2.39-5.46). The consistent obesity (OR: 2.72, 95% CI: 2.06-3.58) and weight loss (OR: 2.81, 95% CI: 1.84-4.30) classes had similarly elevated risk of frailty. CONCLUSIONS: Weight change and obesity are associated with risk of frailty.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Body Weight; Female; Frail Elderly; Geriatric Assessment; Health Status; Humans; Incidence; Longitudinal Studies; Male; Obesity; Retirement; Risk Factors; Weight Gain

Trajectories of depressive symptoms and oral health outcomes in a community sample of older adults. - Celia F. Hybel; Joan M. Bennett; Lawrence R Landerman; Jersey Liang; Brenda L Plassman; Bei Wu (Int J Geriatr Psychiatry, 2016)
OBJECTIVE: Adverse outcomes associated with chronic depressive symptoms are of clinical importance. The objective was to identify subgroups of older adults based on their trajectories of depressive symptoms over a 10-year period and determine if these subgroups predicted oral health outcomes. METHODS: The sample was 944 adults aged 65+ who participated in the oral health module of the the Health and Retirement Survey in 2008. Depressive symptoms were measured with a modified version of the Center for Epidemiologic Studies-Depression (CES-D) scale. Latent class trajectory analysis was used to identify distinct subgroups of elders based on their CES-D scores from 1998-2008. Group membership was used to predict self-rated oral health, overall mouth condition (problems with bleeding gums, gum sensitivity, and food avoidance), and edentulism in 2008. RESULTS: Three distinct subgroups were identified using zero-inflated Poisson regression models: (i) minimal depressive symptoms over the study period (43%), (ii) low but generally stable level of depressive symptoms (41%), and (iii) moderate symptoms and higher CES-D scores than the other groups over the 10 years (16%). Controlling for demographic and health variables and edentulism status, having a trajectory of moderate symptoms was associated with poorer mouth condition (p < 0.0001) and poorer self-rated oral health (p = 0.0003) compared with those with minimal symptoms. Having low levels of depressive symptoms was not significantly associated with these two outcomes. Group membership was not significantly associated with the probability of edentulism. CONCLUSIONS: Chronic moderate depressive symptoms are associated with poorer oral health in older adults.
Keywords: Aged; Aged, 80 and over; Chronic disease; Depressive Disorder; Female; Humans; Longitudinal Studies; Male; Oral Health; Regression Analysis

Validating a summary measure of weight history for modeling the health consequences of obesity. - Andrew C. Stokes; Ni, Yu (Ann Epidemiol, 2016)
PURPOSE: Data on weight history may enhance the predictive validity of epidemiologic models of the health risks of obesity, but collecting such data is often not feasible. In this study, we investigate the validity of a summary measure of weight history. METHODS: We evaluated the quality of reporting of maximum weight in a sample of adults aged 50-84 years using data from the Health and Retirement Study. Recalled max body mass index (BMI, measured in kilogram per square meter) based on recalled weight in 2004 was compared with calculated max BMI based on self-reported weight collected biennially between 1992 and 2004. Logistic regression was used to assess similarity between the measures in predicting prevalent conditions. RESULTS: The correlation coefficient between recalled and calculated max weight in the overall sample was 0.95. Recalled max BMI value was within three BMI units of the calculated value 91.4% of the time. The proportions of individuals with obese I (BMI: 30.0-34.9), obese II (BMI: 35.0-39.9), and obese III (BMI: 40.0 and above) were 28.8%, 12.7%, and 6.6% using recalled values compared with 27.1%, 10.5%, and 4.9% using calculated values. In multivariate analyses, the two BMI measures similarly predicted disease prevalence across a number of chronic conditions. CONCLUSIONS: Recalled max BMI was strongly correlated with max BMI calculated over the 12-year period before recall, suggesting that this measure can serve as a reliable summary measure of recent weight status.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Body Weight; Chronic disease; Female; Health Surveys; Humans; Logistic Models; Longitudinal Studies; Male; Middle Aged; Obesity; Self Report; United States

Volunteering Is Associated with Lower Risk of Cognitive Impairment. - Frank J Infurna; Morris A Okun; Kevin J. Grimm (J Am Geriatr Soc, 2016)
OBJECTIVES: To examine whether psychosocial factors that can be a target for interventions, such as volunteering, are associated with risk of cognitive impairment. DESIGN: Health and Retirement Study (HRS) data from 1998 to 2012, a nationally representative longitudinal panel survey of older adults assessed every 2 years, were used. SETTING: The HRS interviews participants aged 50 and older across the contiguous United States. PARTICIPANTS: Individuals aged 60 and older in 1998 (N = 13,262). MEASUREMENTS: Personal interviews were conducted with respondents to assess presence of cognitive impairment, measured using a composite across cognitive measures. RESULTS: Volunteering at the initial assessment and volunteering regularly over time independently decreased the risk of cognitive impairment over 14 years, and these findings were maintained independent of known risk factors for cognitive impairment. Greater risk of onset of cognitive impairment was associated with being older, being female, being nonwhite, having fewer years of education, and reporting more depressive symptoms. CONCLUSION: Consistent civic engagement in old age is associated with lower risk of cognitive impairment and provides impetus for interventions to protect against the onset of cognitive impairment. Given the increasing number of baby boomers entering old age, the findings support the public health benefits of volunteering and the potential role of geriatricians, who can promote volunteering by incorporating "prescriptions to volunteer" into their patient care.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Female; Geriatric Assessment; Health Surveys; Humans; Interviews as Topic; Male; Middle Aged; Risk Factors; United States; Volunteers

Work-Family Trajectories and the Higher Cardiovascular Risk of American Women Relative to Women in 13 European Countries. - van Hedel, Karen; Mejía-Guevara, Iván; Mauricio Avendano; Erika L. Sabbath; Lisa F Berkman; Johan P Mackenbach; van Lenthe, Frank J (Am J Public Health, 2016)
OBJECTIVES: To investigate whether less-healthy work-family life histories contribute to the higher cardiovascular disease prevalence in older American compared with European women. METHODS: We used sequence analysis to identify distinct work-family typologies for women born between 1935 and 1956 in the United States and 13 European countries. Data came from the US Health and Retirement Study (1992-2006) and the Survey of Health, Aging, and Retirement in Europe (2004-2009). RESULTS: Work-family typologies were similarly distributed in the United States and Europe. Being a lone working mother predicted a higher risk of heart disease, stroke, and smoking among American women, and smoking for European women. Lone working motherhood was more common and had a marginally stronger association with stroke in the United States than in Europe. Simulations indicated that the higher stroke risk among American women would only be marginally reduced if American women had experienced the same work-family trajectories as European women. CONCLUSIONS: Combining work and lone motherhood was more common in the United States, but differences in work-family trajectories explained only a small fraction of the higher cardiovascular risk of American relative to European women.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Computer Simulation; Europe; Female; Humans; Middle Aged; Obesity; Single Parent; Smoking; Socioeconomic factors; United States; Women, Working; Young Adult

Adherence to diabetes guidelines for screening, physical activity and medication and onset of complications and death. - Chen, Yiqun; Frank A Sloan; Arseniy P Yashkin (J Diabetes Complications, 2015)
AIMS: Analyze relationships between adherence to guidelines for diabetes care - regular screening; physical activity; and medication - and diabetes complications and mortality. METHODS: Outcomes were onset of congestive heart failure (CHF), stroke, renal failure, moderate complications of lower extremities, lower-limb amputation, proliferative diabetic retinopathy (PDR), and mortality during follow-up. Participants were persons aged 65+ in the Health and Retirement Study (HRS) 2003 Diabetes Study and had Medicare claims in follow-up period (2004-8). RESULTS: Adherence to screening recommendations decreased risks of developing CHF (odds ratio (OR)=0.83; 95% confidence interval (CI): 0.72-0.96), stroke (OR=0.80; 95% CI: 0.68-0.94); renal failure (OR=0. 82; 95% CI: 0.71-0.95); and death (OR=0.86; 95% CI: 0.74-0.99). Adherence to physical activity recommendation reduced risks of stroke (OR=0.64; 95% CI: 0.45-0.90), renal failure (OR=0.71; 95% CI: 0.52-0.97), moderate lower-extremity complications (OR=0.71; 95% CI: 0.51-0.99), having a lower limb amputation (OR=0.31, 95% CI: 0.11-0.85), and death (OR=0.56, 95% CI: 0.41-0.77). Medication adherence was associated with lower risks of PDR (OR=0.35, 95% CI: 0.13-0.93). CONCLUSIONS: Adherence to screening, physical activity and medication guidelines was associated with lower risks of diabetes complications and death. Relative importance of adherence differed among outcome measures.
Keywords: Aged; Aged, 80 and over; Combined Modality Therapy; Diabetes Complications; Diabetes Mellitus; Early Diagnosis; Female; Health Promotion; Health Surveys; Humans; Hypoglycemic Agents; Longitudinal Studies; Male; Mass Screening; Medicare Part A; Medicare Part B; Medication Adherence; Motor Activity; Patient Compliance; Practice Guidelines as Topic; Risk; United States

Antidepressant Use and Cognitive Decline: The Health and Retirement Study. - Jane S Saczynski; Allison B Rosen; Ryan J McCammon; Zivin, Kara; Susan E. Andrade; Kenneth M. Langa; Sandeep Vijan; Paul A Pirraglia; Becky A. Briesacher (Am J Med, 2015)
BACKGROUND: Depression is associated with cognitive impairment and dementia, but whether treatment for depression with antidepressants reduces the risk for cognitive decline is unclear. We assessed the association between antidepressant use and cognitive decline over 6 years. METHODS: Participants were 3714 adults aged 50 years or more who were enrolled in the nationally representative Health and Retirement Study and had self-reported antidepressant use. Depressive symptoms were assessed using the 8-item Center for Epidemiologic Studies Depression Scale. Cognitive function was assessed at 4 time points (2004, 2006, 2008, 2010) using a validated 27-point scale. Change in cognitive function over the 6-year follow-up period was examined using linear growth models, adjusted for demographics, depressive symptoms, comorbidities, functional limitations, and antidepressant anticholinergic activity load. RESULTS: At baseline, cognitive function did not differ significantly between the 445 (12.1%) participants taking antidepressants and those not taking antidepressants (mean, 14.9%; 95% confidence interval, 14.3-15.4 vs mean, 15.1%; 95% confidence interval, 14.9-15.3). During the 6-year follow up period, cognition declined in both users and nonusers of antidepressants, ranging from -1.4 change in mean score in those with high depressive symptoms and taking antidepressants to -0.5 change in mean score in those with high depressive symptoms and not taking antidepressants. In adjusted models, cognition declined in people taking antidepressants at the same rate as those not taking antidepressants. Results remained consistent across different levels of baseline cognitive function, age, and duration of antidepressant use (prolonged vs short-term). CONCLUSIONS: Antidepressant use did not modify the course of 6-year cognitive change in this nationally representative sample.
Keywords: Age Distribution; Aged; Aged, 80 and over; Antidepressive Agents; Cognition; Cross-Sectional Studies; Depressive Disorder; Female; Follow-Up Studies; Geriatric Assessment; Humans; Incidence; Male; Middle Aged; Reference Values; Risk Assessment; Sex Distribution; Surveys and Questionnaires; United States

Are older adults living in more equal counties healthier than older adults living in more unequal counties? A propensity score matching approach. - Choi, Hwajung; Sarah A. Burgard; Irma Elo; Michele M Heisler (Soc Sci Med, 2015)
We assessed the potential contextual effect of income inequality on health by: 1) comparing individuals with similar socioeconomic status (SES) but who reside in counties with different levels of income inequality; and 2) examining whether the potential effect of county-level income inequality on health varies across SES groups. We used the Health and Retirement Study, a nationally representative study of Americans over the age of 50. Using propensity score matching, we selected SES-comparable individuals living in high-income inequality counties and in low-income inequality counties. We examined differences in self-rated overall health outcomes and in other specific physical/mental health outcomes between the two groups using logistic regression (n = 34,994) and imposing different sample restrictions based on residential duration in the area. We then used logistic regression with interactions to assess whether, and if so how, health outcomes differed among participants of different SES groups defined by wealth, income, and education. In bivariate analyses of the unmatched full sample, adults living in high-income inequality counties have worse health outcomes for most health measures. After propensity score matching, adults in high-income inequality counties had worse self-rated health status (AOR = 1.12; 95% CI 1.04-1.19) and were more likely to report diagnosed psychiatric problems (AOR = 1.08; 95% CI 0.99-1.19) than their matched counterparts in low-income inequality counties. These associations were stronger with longer-term residents in the area. Adverse health outcomes associated with living in high-income inequality counties were significant particularly for individuals in the 30(th) or greater percentiles of income/wealth distribution and those without a college education. In summary, after using more precise matching methods to compare individuals with similar characteristics and addressing measurement error by excluding more recently arrived county residents, adults living in high-income inequality counties had worse reported overall physical and mental health than adults living in low-income inequality counties.
Keywords: Aged; Aged, 80 and over; Female; Health Status Indicators; Health Surveys; Healthcare Disparities; Humans; Logistic Models; Male; Middle Aged; Propensity Score; Self Report; Socioeconomic factors

Association Between Hospice Use and Depressive Symptoms in Surviving Spouses. - Katherine A Ornstein; Melissa D. Aldridge; Melissa M Garrido; Rebecca Jean Gorges; Diane E Meier; Amy Kelley (JAMA Intern Med, 2015)
IMPORTANCE: Family caregivers of individuals with serious illness are at risk for depressive symptoms and depression. Hospice includes the provision of support services for family caregivers, yet evidence is limited regarding the effect of hospice use on depressive symptoms among surviving caregivers. OBJECTIVE: To determine the association between hospice use and depressive symptoms in surviving spouses. DESIGN, SETTING, AND PARTICIPANTS: We linked data from the Health and Retirement Study, a nationally representative longitudinal survey of community-dwelling US adults 50 years or older, to Medicare claims. Participants included a propensity score-matched sample of 1016 Health and Retirement Study decedents with at least 1 serious illness and their surviving spouses interviewed between August 2002 and May 2011. We compared the spouses of individuals enrolled in hospice with the spouses of individuals who did not use hospice, performing our analysis between January 30, 2014, and January 16, 2015. EXPOSURES: Hospice enrollment for at least 3 days in the year before death. MAIN OUTCOMES AND MEASURES: Spousal depressive symptom scores measured 0 to 2 years after death with the Center for Epidemiologic Studies Depression Scale, which is scored from 0 (no symptoms) to 8 (severe symptoms). RESULTS: Of the 1016 decedents in the matched sample, 305 patients (30.0%) used hospice services for 3 or more days in the year before death. Of the 1016 spouses, 51.9% had more depressive symptoms over time (mean [SD] change, 2.56 [1.65]), with no significant difference related to hospice use. A minority (28.2%) of spouses of hospice users had improved Center for Epidemiologic Studies Depression Scale scores compared with 21.7% of spouses of decedents who did not use hospice, although the difference was not statistically significant (P = .06). Among the 662 spouses who were the primary caregivers, 27.3% of spouses of hospice users had improved Center for Epidemiologic Studies Depression Scale scores compared with 20.7% of spouses of decedents who did not use hospice; the difference was not statistically significant (P = .10). In multivariate analysis, the odds ratio for the association of hospice enrollment with improved depressive symptoms after the spouse's death was 1.63 (95% CI, 1.00-2.65). CONCLUSIONS AND RELEVANCE: After bereavement, depression symptoms increased overall for surviving spouses regardless of hospice use. A modest reduction in depressive symptoms was more likely among spouses of hospice users than among spouses of nonhospice users.
10.1001/jamainternmed.2015.1722
Keywords: Aged; Aged, 80 and over; Caregivers; depression; Female; Hospice Care; Hospices; Humans; Male; Prospective Studies; Spouses; Survivors

The association of depression, cognitive impairment without dementia, and dementia with risk of ischemic stroke: a cohort study. - Dimitry S Davydow; Deborah A Levine; Zivin, Kara; Wayne J Katon; Kenneth M. Langa (Psychosom Med, 2015)
OBJECTIVE: To determine if depression, cognitive impairment without dementia (CIND), and/or dementia are each independently associated with risk of ischemic stroke and to identify characteristics that could modify these associations. METHODS: This retrospective-cohort study examined a population-based sample of 7031 Americans older than 50 years participating in the Health and Retirement Study (1998-2008) who consented to have their interviews linked to their Medicare claims. The eight-item Center for Epidemiologic Studies Depression Scale and/or International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) depression diagnoses were used to identify baseline depression. The Modified Telephone Interview for Cognitive Status and/or ICD-9-CM dementia diagnoses were used to identify baseline CIND or dementia. Hospitalizations for ischemic stroke were identified via ICD-9-CM diagnoses. RESULTS: After adjusting for demographics, medical comorbidities, and health-risk behaviors, CIND alone (odds ratio [OR] = 1.37, 95% confidence interval [CI] = 1.11-1.69) and co-occurring depression and CIND (OR = 1.65, 95% CI = 1.24-2.18) were independently associated with increased odds of ischemic stroke. Depression alone was not associated with odds of ischemic stroke (OR = 1.11, 95% CI = 0.88-1.40) in unadjusted analyses. Neither dementia alone (OR = 1.09, 95% CI = 0.82-1.45) nor co-occurring depression and dementia (OR = 1.25, 95% CI = 0.89-1.76) were associated with odds of ischemic stroke after adjusting for demographics. CONCLUSIONS: CIND and co-occurring depression and CIND are independently associated with increased risk of ischemic stroke. Individuals with co-occurring depression and CIND represent a high-risk group that may benefit from targeted interventions to prevent stroke.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Dementia; depression; Female; Humans; Male; Middle Aged; Psychiatric Status Rating Scales; Retrospective Studies; Risk Factors; Stroke; United States

Becoming centenarians: disease and functioning trajectories of older US Adults as they survive to 100. - Jennifer A Ailshire; Hiram Beltrán-Sánchez; Eileen M. Crimmins (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: Little is known about the health and functioning of individuals who become centenarians in the years prior to reaching age 100. We examined long-term trajectories of disease, disability, and cognitive function in a sample of U.S. centenarians to determine how their aging experience differs from their nonsurviving cohort counterparts, and if there is heterogeneity in the aging experience of centenarians. METHODS: Data are from the 1993-2010 waves of the nationally representative Health and Retirement Study. Among those who had the potential to become centenarians, we identified 1,045 respondents who died before reaching age 100 and 96 who survived to their 100th birthday. Respondents, or their proxies, reported on diagnosis of six major diseases (hypertension, heart disease, lung disease, stroke, cancer, and diabetes), limitations in activities of daily living, and cognitive function. RESULTS: As they age to 100, centenarians are generally healthier than nonsurviving members of their cohort, and a number of individuals who become centenarians reach 100 with no self-reported diseases or functional impairments. About 23% of centenarians reached age 100 with no major chronic disease and approximately the same number had no disability (18%). Over half (55%) reached 100 without cognitive impairment. Disease and functioning trajectories of centenarians differ by sex, education, and marital status. CONCLUSIONS: While some centenarians have poor health and functioning upon reaching age 100, others are able to achieve exceptional longevity in relatively good health and without loss of functioning. This study underscores the importance of examining variation in the growing centenarian population.
Keywords: Activities of Daily Living; Aged, 80 and over; Aging; Chronic disease; Cognition; Disability Evaluation; Educational Status; Female; Geriatric Assessment; Health Status; Health Surveys; Humans; Longevity; Longitudinal Studies; Male; Marital Status; Prospective Studies; Sex Factors; United States

The burden of health care costs for patients with dementia in the last 5 years of life. - Amy Kelley; Kathleen McGarry; Rebecca Jean Gorges; Jonathan S Skinner (Ann Intern Med, 2015)
BACKGROUND: Common diseases, particularly dementia, have large social costs for the U.S. population. However, less is known about the end-of-life costs of specific diseases and the associated financial risk for individual households. OBJECTIVE: To examine social costs and financial risks faced by Medicare beneficiaries 5 years before death. DESIGN: Retrospective cohort. SETTING: The HRS (Health and Retirement Study). PARTICIPANTS: Medicare fee-for-service beneficiaries, aged 70 years or older, who died between 2005 and 2010 (n = 1702), stratified into 4 groups: persons with a high probability of dementia or those who died because of heart disease, cancer, or other causes. MEASUREMENTS: Total social costs and their components, including Medicare, Medicaid, private insurance, out-of-pocket spending, and informal care, measured over the last 5 years of life; and out-of-pocket spending as a proportion of household wealth. RESULTS: Average total cost per decedent with dementia ($287 038) was significantly greater than that of those who died of heart disease ($175 136), cancer ($173 383), or other causes ($197 286) (P < 0.001). Although Medicare expenditures were similar across groups, average out-of-pocket spending for patients with dementia ($61 522) was 81% higher than that for patients without dementia ($34 068); a similar pattern held for informal care. Out-of-pocket spending for the dementia group (median, $36 919) represented 32% of wealth measured 5 years before death compared with 11% for the nondementia group (P < 0.001). This proportion was greater for black persons (84%), persons with less than a high school education (48%), and unmarried or widowed women (58%). LIMITATION: Imputed Medicaid, private insurance, and informal care costs. CONCLUSION: Health care expenditures among persons with dementia were substantially larger than those for other diseases, and many of the expenses were uncovered (uninsured). This places a large financial burden on families, and these burdens are particularly pronounced among the demographic groups that are least prepared for financial risk. PRIMARY FUNDING SOURCE: National Institute on Aging.
Keywords: Aged; Aged, 80 and over; Cost of Illness; Dementia; Female; Health Expenditures; Humans; Insurance, Health; Male; Medicaid; Medicare; Retrospective Studies; Socioeconomic factors; Terminal Care; United States

Changes in Depressive Symptoms and Incidence of First Stroke Among Middle-Aged and Older US Adults. - Stefan Walter; Eric J. Tchetgen Tchetgen; Kristen K Patton; J Robin Moon; Benjamin D Capistrant; Jessica R Marden; Laura D Kubzansky; Paola Gilsanz; Ichiro Kawachi; M. Maria Glymour (J Am Heart Assoc, 2015)
BACKGROUND: Although research has demonstrated that depressive symptoms predict stroke incidence, depressive symptoms are dynamic. It is unclear whether stroke risk persists if depressive symptoms remit. METHODS AND RESULTS: Health and Retirement Study participants (n=16 178, stroke free and noninstitutionalized at baseline) were interviewed biennially from 1998 to 2010. Stroke and depressive symptoms were assessed through self-report of doctors' diagnoses and a modified Center for Epidemiologic Studies - Depression scale (high was ≥3 symptoms), respectively. We examined whether depressive symptom patterns, characterized across 2 successive interviews (stable low/no, onset, remitted, or stable high depressive symptoms) predicted incident stroke (1192 events) during the subsequent 2 years. We used marginal structural Cox proportional hazards models adjusted for demographics, health behaviors, chronic conditions, and attrition. We also estimated effects stratified by age (≥65 years), race or ethnicity (non-Hispanic white, non-Hispanic black, Hispanic), and sex. Stroke hazard was elevated among participants with stable high (adjusted hazard ratio 2.14, 95% CI 1.69 to 2.71) or remitted (adjusted hazard ratio 1.66, 95% CI 1.22 to 2.26) depressive symptoms compared with participants with stable low/no depressive symptoms. Stable high depressive symptom predicted stroke among all subgroups. Remitted depressive symptoms predicted increased stroke hazard among women (adjusted hazard ratio 1.86, 95% CI 1.30 to 2.66) and non-Hispanic white participants (adjusted hazard ratio 1.66, 95% CI 1.18 to 2.33) and was marginally associated among Hispanics (adjusted hazard ratio 2.36, 95% CI 0.98 to 5.67). CONCLUSIONS: In this cohort, persistently high depressive symptoms were associated with increased stroke risk. Risk remained elevated even if depressive symptoms remitted over a 2-year period, suggesting cumulative etiologic mechanisms linking depression and stroke.
Keywords: Adult; Aged; Aged, 80 and over; Aging; depression; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Sex Factors; Stroke; Time Factors

Childhood and later life stressors and increased inflammatory gene expression at older ages. - Morgan E. Levine; Steven W. Cole; David R Weir; Eileen M. Crimmins (Soc Sci Med, 2015)
Adverse experiences in early life have the ability to "get under the skin" and affect future health. This study examined the relative influence of adversities during childhood and adulthood in accounting for individual differences in pro-inflammatory gene expression in late life. Using a pilot-sample from the Health and Retirement Study (N = 114) aged from 51 to 95, OLS regression models were run to determine the association between a composite score from three proinflammatory gene expression levels (PTGS2, ILIB, and IL8) and 1) childhood trauma, 2) childhood SES, 3) childhood health, 4) adult traumas, and 5) low SES in adulthood. Our results showed that only childhood trauma was found to be associated with increased inflammatory transcription in late life. Furthermore, examination of interaction effects showed that childhood trauma exacerbated the influence of low SES in adulthood on elevated levels of inflammatory gene expression-signifying that having low SES in adulthood was most damaging for persons who had experienced traumatic events during their childhood. Overall our study suggests that traumas experienced during childhood may alter the stress response, leading to more sensitive reactivity throughout the lifespan. As a result, individuals who experienced greater adversity in early life may be at higher risk of late life health outcomes, particularly if adulthood adversity related to SES persists.
Keywords: Adolescent; Age Factors; Aged; Aged, 80 and over; Body Mass Index; Continental Population Groups; Cyclooxygenase 2; Female; Health Status; Health Surveys; Humans; Interleukin-1beta; Interleukin-8; Life Change Events; Male; Middle Aged; Obesity; RNA; Sex Factors; Smoking; Socioeconomic factors; Stress, Psychological

Comorbidity and functional trajectories from midlife to old age: the Health and Retirement Study. - Stenholm, Sari; Westerlund, Hugo; Head, Jenny; Hyde, Martin; Ichiro Kawachi; Pentti, Jaana; Mika Kivimäki; Vahtera, Jussi (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The number of diseases and physical functioning difficulties tend to increase with age. The aim of this study was to examine the trajectories of physical functioning across age groups and whether the trajectories differ according to disease status in different population subgroups. METHODS: Repeat data from a nationally representative population sample, the Health and Retirement Study, was used. Participants were 10,709 men and 13,477 women aged 60-107 years at baseline with biennial surveys from 1992 to 2010. Average length of follow-up was 10.3 years ranging from 0 to 18 years. Disease status and physical functioning was asked about at all study phases and 10 items were summed to obtain a physical functioning score (0-10). RESULTS: Age modified the relationship between number of chronic diseases and physical functioning with older participants having more physical functioning difficulties with increasing number of diseases. An average 70-year-old participant with no diseases had 0.89 (95% CI: 0.85-0.93) physical functioning difficulties, with one disease 1.72 (95% CI: 1.69-1.76) difficulties, with two diseases 2.57 (95% CI: 2.52-2.62) difficulties, and with three or more diseases 3.82 (95% CI: 3.76-3.88) difficulties. Of the individual diseases memory-related diseases, stroke, pulmonary diseases, and arthritis were associated with significantly higher physical functioning difficulties compared with other diseases. CONCLUSIONS: Comorbidity is associated with greater burden of physical functioning difficulties. Of the studied diseases, memory-related diseases, stroke, pulmonary diseases, and arthritis alone or in combination limit most physical functioning.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Chronic disease; Comorbidity; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Retirement; Socioeconomic factors; United States

Cost of informal caregiving for patients with heart failure. - Heesoo Joo; Fang, Jing; Jan L Losby; Wang, Guijing (Am Heart J, 2015)
BACKGROUND: Heart failure is a serious health condition that requires a significant amount of informal care. However, informal caregiving costs associated with heart failure are largely unknown. METHODS: We used a study sample of noninstitutionalized US respondents aged ≥50 years from the 2010 HRS (n = 19,762). Heart failure cases were defined by using self-reported information. The weekly informal caregiving hours were derived by a sequence of survey questions assessing (1) whether respondents had any difficulties in activities of daily living or instrumental activities of daily living, (2) whether they had caregivers because of reported difficulties, (3) the relationship between the patient and the caregiver, (4) whether caregivers were paid, and (5) how many hours per week each informal caregiver provided help. We used a 2-part econometric model to estimate the informal caregiving hours associated with heart failure. The first part was a logit model to estimate the likelihood of using informal caregiving, and the second was a generalized linear model to estimate the amount of informal caregiving hours used among those who used informal caregiving. Replacement approach was used to estimate informal caregiving cost. RESULTS: The 943 (3.9%) respondents who self-reported as ever being diagnosed with heart failure used about 1.6 more hours of informal caregiving per week than those who did not have heart failure (P < .001). Informal caregiving hours associated with heart failure were higher among non-Hispanic blacks (3.9 hours/week) than non-Hispanic whites (1.4 hours/week). The estimated annual informal caregiving cost attributable to heart failure was $3 billion in 2010. CONCLUSION: The cost of informal caregiving was substantial and should be included in estimating the economic burden of heart failure. The results should help public health decision makers in understanding the economic burden of heart failure and in setting public health priorities.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Heart Failure; Humans; Linear Models; Male; Middle Aged; Models, Econometric

Cross-National Differences in Disability Among Elders: Transitions in Disability in Mexico and the United States. - Kerstin Gerst; Rebeca Wong; Alejandra Michaels-Obregon; Alberto Palloni (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: Little is known about how exposure to a combination of infectious and chronic conditions throughout the lifecourse could impact disability in old age. This paper compares 2 cohorts of adults who have aged under very different country contexts by contrasting disability transitions among elders in Mexico with elders in the United States. METHODS: Data comes from the Mexican Health and Aging Study (MHAS) and the U.S. Health and Retirement Study (HRS). Estimated probabilities of 2-year transitions among disability states and mortality are presented for adults aged 50 and older. RESULTS: The levels of disability prevalence and 2 year transitions are consistent with a higher rate of disability for the United States compared to Mexico. In 2-year transitions, the U.S. sample was more likely to transition to a disabled state or increase the number of disabilities than the Mexican counterparts, while Mexicans are more likely to move out of disability or reduce the number of disabilities reported. DISCUSSION: The findings suggest that the current rate of disability in old age is lower for a less developed country compared with a developed society. We discuss implications, possible explanations, and likely future scenarios.
Keywords: Aged; Aged, 80 and over; Aging; Cross-Cultural Comparison; Disabled Persons; Female; Humans; Male; Mexico; Middle Aged; Mortality; Prevalence; United States

Disability Trajectories at the End of Life: A "Countdown" Model. - Douglas A. Wolf; Vicki A Freedman; Jan I Ondrich; Christopher L Seplaki; Brenda C Spillman (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: Studies of late-life disablement typically address the role of advancing age as a factor in developing disability, and in some cases have pointed out the importance of time to death (TTD) in understanding changes in functioning. However, few studies have addressed both factors simultaneously, and none have dealt satisfactorily with the problem of missing data on TTD in panel studies. METHODS: We fit latent-class trajectory models of disablement using data from the Health and Retirement Study. Among survivors (~20% of the sample), TTD is unknown, producing a missing-data problem. We use an auxiliary regression equation to impute TTD and employ multiple imputation techniques to obtain final parameter estimates and standard errors. RESULTS: Our best-fitting model has 3 latent classes. In all 3 classes, the probability of having a disability increases with nearness to death; however, in only 2 of the 3 classes is age associated with disability. We find gender, race, and educational differences in class-membership probabilities. DISCUSSION: The model reveals a complex pattern of age- and time-dependent heterogeneity in late-life disablement. The techniques developed here could be applied to other phenomena known to depend on TTD, such as cognitive change, weight loss, and health care spending.
Keywords: Aged; Aged, 80 and over; Aging; Death; Disabled Persons; Female; Humans; Male; Time Factors; United States

Disaggregating activities of daily living limitations for predicting nursing home admission. - Joelle H Fong; Olivia S. Mitchell; Benedict S K Koh (Health Serv Res, 2015)
OBJECTIVE: To examine whether disaggregated activities of daily living (ADL) limitations better predict the risk of nursing home admission compared to conventionally used ADL disability counts. DATA SOURCES: We used panel data from the Health and Retirement Study (HRS) for years 1998-2010. The HRS is a nationally representative survey of adults older than 50 years (n = 18,801). STUDY DESIGN: We fitted Cox regressions in a continuous time survival model with age at first nursing home admission as the outcome. Time-varying ADL disability types were the key explanatory variables. PRINCIPAL FINDINGS: Of the six ADL limitations, bathing difficulty emerged as the strongest predictor of subsequent nursing home placement across cohorts. Eating and dressing limitations were also influential in driving admissions among more recent cohorts. Using simple ADL counts for analysis yielded similar adjusted R(2) s; however, the amount of explained variance doubled when we allowed the ADL disability measures to time-vary rather than remain static. CONCLUSIONS: Looking beyond simple ADL counts can provide health professionals insights into which specific disability types trigger long-term nursing home use. Functional disabilities measured closer in time carry more prognostic power than static measures.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Female; Geriatric Assessment; Homes for the Aged; Humans; Male; Middle Aged; Nursing homes; Patient Admission; Residence Characteristics; Risk Factors; Sex Factors; Socioeconomic factors

Does Stroke Contribute to Racial Differences in Cognitive Decline? - Deborah A Levine; Mohammed U Kabeto; Kenneth M. Langa; Lynda D Lisabeth; Mary A M Rogers; Andrzej T Galecki (Stroke, 2015)
BACKGROUND AND PURPOSE: It is unknown whether blacks' elevated risk of dementia is because of racial differences in acute stroke, the impact of stroke on cognitive health, or other factors. We investigated whether racial differences in cognitive decline are explained by differences in the frequency or impact of incident stroke between blacks and whites, controlling for baseline cognition. METHODS: Among 4908 black and white participants aged ≥65 years free of stroke and cognitive impairment in the nationally representative Health and Retirement Study with linked Medicare data (1998-2010), we examined longitudinal changes in global cognition (modified version of the Telephone Interview for Cognitive Status) by race, before and after adjusting for time-dependent incident stroke followed by a race-by-incident stroke interaction term, using linear mixed-effects models that included fixed effects of participant demographics, clinical factors, and cognition, and random effects for intercept and slope for time. RESULTS: We identified 34 of 453 (7.5%) blacks and 300 of 4455 (6.7%) whites with incident stroke over a mean (SD) of 4.1 (1.9) years of follow-up (P=0.53). Blacks had greater cognitive decline than whites (adjusted difference in modified version of the Telephone Interview for Cognitive Status score, 1.47 points; 95% confidence interval, 1.21 to 1.73 points). With further adjustment for cumulative incidence of stroke, the black-white difference in cognitive decline persisted. Incident stroke was associated with a decrease in global cognition (1.21 points; P<0.001) corresponding to ≈7.9 years of cognitive aging. The effect of incident stroke on cognition did not statistically differ by race (P=0.52). CONCLUSIONS: In this population-based cohort of older adults, incident stroke did not explain black-white differences in cognitive decline or impact cognition differently by race.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Cognition Disorders; European Continental Ancestry Group; Female; Humans; Longitudinal Studies; Male; Risk Factors; Stroke

The effects of income on mental health: evidence from the social security notch. - Ezra Golberstein (J Ment Health Policy Econ, 2015)
BACKGROUND: Mental health is a key component of overall wellbeing and mental disorders are relatively common, including among older adults. Yet the causal effect of income on mental health status among older adults is poorly understood. AIMS: This paper considers the effects of a major source of transfer income, Social Security retirement benefits, on the mental health of older adults. METHODS: The Social Security benefit "Notch" is as a large, permanent, and exogenous shock to Social Security income in retirement. The "Notch" is used to identify the causal effect of Social Security income on mental health among older ages using data from the AHEAD cohort of the Health and Retirement Study. RESULTS: We find that increases in Social Security income significantly improve mental health status and the likelihood of a psychiatric diagnosis for women, but not for men. DISCUSSION: The effects of income on mental health for older women are statistically significant and meaningful in magnitude. While this is one of the only studies to use plausibly exogenous variation in household income to identify the effect of income on mental health, a limitation of this work is that the results only directly pertain to lower-education households. IMPLICATIONS: Public policy proposals that alter retirement benefits for the elderly may have important effects on the mental health of older adults.
Keywords: Age Factors; Aged; Aged, 80 and over; Female; Humans; Income; Male; Mental Health; Models, Econometric; Retirement; Sex Factors; Social Security; Socioeconomic factors; United States

Estimating the Effects of Obesity and Weight Change on Mortality Using a Dynamic Causal Model. - Cao, Bochen (PLoS One, 2015)
BACKGROUND: A well-known challenge in estimating the mortality risks of obesity is reverse causality attributable to illness-associated and smoking-associated weight loss. Given that the likelihood of chronic and acute illnesses rises with age, reverse causality is most threatening to estimates derived from elderly populations. METHODS: I analyzed data from 12,523 respondents over 50 years old from a nationally representative longitudinal dataset, the Health and Retirement Study (HRS). The effects of both baseline body weight and time-varying weight change on mortality are estimated, adjusting for demographic and socio-economic variables, as well as time-varying confounders including illness and smoking. Body weight is measured by body mass index (BMI). In survival models for mortality, illness and smoking were lagged to minimize bias from reverse causality in estimates of the effect of weight change. Furthermore, because illness both causes and is caused by changes in BMI, I used a marginal structural model (MSM) rather than standard adjustment to control confounding by this and other time-dependent factors. RESULTS: Overall, relative to normal weight, underweight and Class II/III at baseline are associated with hazard ratios that are 2.07 (95% confidence interval (CI): 1.28-3.37) and 1.82 (1.54-2.16) respectively, whereas overweight and Class I obesity do not significantly lower or raise the mortality risks. Furthermore, relative to stable weight change, all types of weight change lead to significantly increased risk of mortality. Specifically, large weight loss results in a mortality risk that is nearly 3.86 (3.26-4.58) times of staying in the stable weight range and small weight loss is about 1.81 (1.55-2.11 ) times riskier. In contrast, large weight gain and small weight gain are associated with hazard ratios that are 1.98 (1.67-2.35) and 1.20 (1.02-1.41) respectively. CONCLUSIONS: Being underweight or severe obese at baseline is associated with excess mortality risk, and weight change tend to raise mortality risk. Both the confounding by illness and by smoking lead to overestimates of the effects of being underweight at baseline and of weight loss, but underestimates the effect of being obese at baseline.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Body Weight; Female; Humans; Male; Middle Aged; Models, Theoretical; Obesity; Overweight; Risk Factors; Thinness; Weight Gain; Weight Loss

Explaining Disability Trends in the U.S. Elderly and Near-Elderly Population. - Chen, Yiqun; Frank A Sloan (Health Serv Res, 2015)
OBJECTIVE: To examine disability trends among U.S. near-elderly and elderly persons and explain observed trends. DATA SOURCE: 1996-2010 waves of the Health and Retirement Study. STUDY DESIGN: We first examined trends in Activities of Daily Living and Instrumental Activities of Daily Living limitations, and large muscle, mobility, gross motor, and fine motor indexes. Then we used decomposition analysis to estimate contributions of changes in sociodemographic composition, self-reported chronic disease prevalence and health behaviors, and changes in disabling effects of these factors to disability changes between 1996 and 2010. PRINCIPAL FINDINGS: Disability generally increased or was unchanged. Increased trends were more apparent for near-elderly than elderly persons. Sociodemographic shifts tended to reduce disability, but their favorable effects were largely offset by increased self-reported chronic disease prevalence. Changes in smoking and heavy drinking prevalence had relatively minor effects on disability trends. Increased obesity rates generated sizable effects on lower-body functioning changes. Disabling effects of self-reported chronic diseases often declined, and educational attainment became a stronger influence in preventing disability. CONCLUSIONS: Such unfavorable trends as increased chronic disease prevalence and higher obesity rates offset or outweighed the favorable effects with the result that disability remained unchanged or increased.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Alcohol Drinking; Chronic disease; Disabled Persons; Female; Health Behavior; Health Surveys; Humans; Male; Middle Aged; Mobility Limitation; Obesity; Prevalence; Sex Distribution; Smoking; Socioeconomic factors; United States

Factors associated with cognitive evaluations in the United States. - Vikas Kotagal; Kenneth M. Langa; Brenda L Plassman; Gwenith G Fisher; Bruno J Giordani; Robert B Wallace; James F. Burke; David C Steffens; Mohammed U Kabeto; Roger L. Albin; Norman L Foster (Neurology, 2015)
OBJECTIVE: We aimed to explore factors associated with clinical evaluations for cognitive impairment among older residents of the United States. METHODS: Two hundred ninety-seven of 845 subjects in the Aging, Demographics, and Memory Study (ADAMS), a nationally representative community-based cohort study, met criteria for dementia after a detailed in-person study examination. Informants for these subjects reported whether or not they had ever received a clinical cognitive evaluation outside of the context of ADAMS. Among subjects with dementia, we evaluated demographic, socioeconomic, and clinical factors associated with an informant-reported clinical cognitive evaluation using bivariate analyses and multivariable logistic regression. RESULTS: Of the 297 participants with dementia in ADAMS, 55.2% (representing about 1.8 million elderly Americans in 2002) reported no history of a clinical cognitive evaluation by a physician. In a multivariable logistic regression model (n = 297) controlling for demographics, physical function measures, and dementia severity, marital status (odds ratio for currently married: 2.63 [95% confidence interval: 1.10-6.35]) was the only significant independent predictor of receiving a clinical cognitive evaluation among subjects with study-confirmed dementia. CONCLUSIONS: Many elderly individuals with dementia do not receive clinical cognitive evaluations. The likelihood of receiving a clinical cognitive evaluation in elderly individuals with dementia associates with certain patient-specific factors, particularly severity of cognitive impairment and current marital status.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Cohort Studies; Dementia; Female; Humans; Logistic Models; Male; Marital Status; Multivariate Analysis; Neuropsychological tests; Severity of Illness Index; United States

FASTKD2 is associated with memory and hippocampal structure in older adults. - Vijay K Ramanan; Nho, Kwangsik; Shen, Li; Shannon L Risacher; Brenna C McDonald; Martin R Farlow; Tatiana Foroud; Gao, Sujuan; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; et al. (Mol Psychiatry, 2015)
Memory impairment is the cardinal early feature of Alzheimer's disease, a highly prevalent disorder whose causes remain only partially understood. To identify novel genetic predictors, we used an integrative genomics approach to perform the largest study to date of human memory (n=14 781). Using a genome-wide screen, we discovered a novel association of a polymorphism in the pro-apoptotic gene FASTKD2 (fas-activated serine/threonine kinase domains 2; rs7594645-G) with better memory performance and replicated this finding in independent samples. Consistent with a neuroprotective effect, rs7594645-G carriers exhibited increased hippocampal volume and gray matter density and decreased cerebrospinal fluid levels of apoptotic mediators. The MTOR (mechanistic target of rapamycin) gene and pathways related to endocytosis, cholinergic neurotransmission, epidermal growth factor receptor signaling and immune regulation, among others, also displayed association with memory. These findings nominate FASTKD2 as a target for modulating neurodegeneration and suggest potential mechanisms for therapies to combat memory loss in normal cognitive aging and dementia.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer disease; Female; Genetic Association Studies; Genome-Wide Association Study; Hippocampus; Humans; Longitudinal Studies; Male; Memory; Memory Disorders; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Structure-Activity Relationship

Functional impairment and hospital readmission in Medicare seniors. - S. Ryan Greysen; Irena Cenzer; Andrew D. Auerbach; Kenneth E Covinsky (JAMA Intern Med, 2015)
IMPORTANCE: Medicare currently penalizes hospitals for high readmission rates for seniors but does not account for common age-related syndromes, such as functional impairment. OBJECTIVE: To assess the effects of functional impairment on Medicare hospital readmissions given the high prevalence of functional impairments in community-dwelling seniors. DESIGN, SETTING, AND PARTICIPANTS: We created a nationally representative cohort of 7854 community-dwelling seniors in the Health and Retirement Study, with 22,289 Medicare hospitalizations from January 1, 2000, through December 31, 2010. MAIN OUTCOMES AND MEASURES: Outcome was 30-day readmission assessed by Medicare claims. The main predictor was functional impairment determined from the Health and Retirement Study interview preceding hospitalization, stratified into the following 5 levels: no functional impairments, difficulty with 1 or more instrumental activities of daily living, difficulty with 1 or more activities of daily living (ADL), dependency (need for help) in 1 to 2 ADLs, and dependency in 3 or more ADLs. Adjustment variables included age, race/ethnicity, sex, annual income, net worth, comorbid conditions (Elixhauser score from Medicare claims), and prior admission. We performed multivariable logistic regression to adjust for clustering at the patient level to characterize the association of functional impairments and readmission. RESULTS: Patients had a mean (SD) age of 78.5 (7.7) years (range, 65-105 years); 58.4% were female, 84.9% were white, 89.6% reported 3 or more comorbidities, and 86.0% had 1 or more hospitalizations in the previous year. Overall, 48.3% had some level of functional impairment before admission, and 15.5% of hospitalizations were followed by readmission within 30 days. We found a progressive increase in the adjusted risk of readmission as the degree of functional impairment increased: 13.5% with no functional impairment, 14.3% with difficulty with 1 or more instrumental activities of daily living (odds ratio [OR], 1.06; 95% CI, 0.94-1.20), 14.4% with difficulty with 1 or more ADL (OR, 1.08; 95% CI, 0.96-1.21), 16.5% with dependency in 1 to 2 ADLs (OR, 1.26; 95% CI, 1.11-1.44), and 18.2% with dependency in 3 or more ADLs (OR, 1.42; 95% CI, 1.20-1.69). Subanalysis restricted to patients admitted with conditions targeted by Medicare (ie, heart failure, myocardial infarction, and pneumonia) revealed a parallel trend with larger effects for the most impaired (16.9% readmission rate for no impairment vs 25.7% for dependency in 3 or more ADLs [OR, 1.70; 95% CI, 1.04-2.78]). CONCLUSIONS AND RELEVANCE: Functional impairment is associated with increased risk of 30-day all-cause hospital readmission in Medicare seniors, especially those admitted for heart failure, myocardial infarction, or pneumonia. Functional impairment may be an important but underaddressed factor in preventing readmissions for Medicare seniors.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Comorbidity; Female; Heart Failure; Humans; Income; Logistic Models; Male; Medicare; Myocardial Infarction; Patient Readmission; Pneumonia; Risk Assessment; Risk Factors; Sex Factors; United States

Gender Differences in Institutional Long-Term Care Transitions. - Mudrazija, Stipica; Thomeer, Mieke Beth; Jacqueline L. Angel (Womens Health Issues, 2015)
INTRODUCTION: This study investigates the relationship between gender, the likelihood of discharge from institutional long-term care (LTC) facilities, and post-discharge living arrangements, highlighting sociodemographic, health, socioeconomic, and family characteristics. METHODS: We use the Health and Retirement Study to examine individuals age 65 and older admitted to LTC facilities between 2000 and 2010 (n = 3,351). We examine discharge patterns using survival analyses that account for the competing risk of death and estimate the probabilities of post-discharge living arrangements using multinomial logistic regression models. RESULTS: Women are more likely than men to be discharged from LTC facilities during the first year of stay. Women are more likely to live alone or with kin after discharge, whereas men are more likely to live with a spouse or transfer to another institution. Gender differences in the availability and use of family support may partly account for the gender disparity of LTC discharge and post-discharge living arrangements. CONCLUSION: Our findings suggest that women and men follow distinct pathways after LTC discharge. As local and federal efforts begin to place more emphasis on the transition from LTC facilities to prior communities (e.g., transitional care initiatives under the Patient Protection and Affordable Care Act), policymakers should take these gender differences into account in the design of community transition programs.
Keywords: Aged; Aged, 80 and over; Continuity of Patient Care; Family Characteristics; Female; Geriatric Assessment; Home Care Services; Humans; Length of Stay; Logistic Models; Long-term Care; Male; Marital Status; Middle Aged; Nursing homes; Patient Discharge; Residence Characteristics; Sex Characteristics; United States

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Gail Davies; Armstrong, N.; Joshua C. Bis; Bressler, J.; Chouraki, V.; Giddaluru, S.; Edith Hofer; Carla A Ibrahim-Verbaas; Kirin, M.; J. Lahti; Sven J van der Lee; Stephanie Le Hellard; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetically predicted body mass index and Alzheimer's disease-related phenotypes in three large samples: Mendelian randomization analyses. - Mukherjee, Shubhabrata; Stefan Walter; Kauwe, John S K; Andrew J Saykin; David A Bennett; Eric B Larson; Paul K Crane; M. Maria Glymour (Alzheimers Dement, 2015)
Observational research shows that higher body mass index (BMI) increases Alzheimer's disease (AD) risk, but it is unclear whether this association is causal. We applied genetic variants that predict BMI in Mendelian randomization analyses, an approach that is not biased by reverse causation or confounding, to evaluate whether higher BMI increases AD risk. We evaluated individual-level data from the AD Genetics Consortium (ADGC: 10,079 AD cases and 9613 controls), the Health and Retirement Study (HRS: 8403 participants with algorithm-predicted dementia status), and published associations from the Genetic and Environmental Risk for AD consortium (GERAD1: 3177 AD cases and 7277 controls). No evidence from individual single-nucleotide polymorphisms or polygenic scores indicated BMI increased AD risk. Mendelian randomization effect estimates per BMI point (95% confidence intervals) were as follows: ADGC, odds ratio (OR) = 0.95 (0.90-1.01); HRS, OR = 1.00 (0.75-1.32); GERAD1, OR = 0.96 (0.87-1.07). One subscore (cellular processes not otherwise specified) unexpectedly predicted lower AD risk.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Body Mass Index; Female; Genotype; Humans; Linear Models; Male; Mendelian Randomization Analysis; Obesity; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Greater Perceived Age Discrimination in England than the United States: Results from HRS and ELSA. - Rippon, Isla; Zaninotto, Paola; Andrew Steptoe (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: We examined cross-national differences in perceptions of age discrimination in England and the United States. Under the premise that the United States has had age discrimination legislation in place for considerably longer than England, we hypothesized that perceptions of age discrimination would be lower in the United States. METHODS: We analyzed data from two nationally representative studies of aging, the U.S. Health and Retirement Study (n = 4,818) and the English Longitudinal Study of Ageing (n = 7,478). Respondents aged 52 years and older who attributed any experiences of discrimination to their age were treated as cases of perceived age discrimination. We used multivariable logistic regression to estimate the odds ratios of experiencing perceived age discrimination in relation to selected sociodemographic factors. RESULTS: Perceptions of age discrimination were significantly higher in England than the United States, with 34.8% of men and women in England reporting age discrimination compared with 29.1% in the United States. Associations between perceived age discrimination and older age and lower levels of household wealth were observed in both countries, but we found differences between England and the United States in the relationship between perceived age discrimination and education. DISCUSSION: Our study revealed that levels of perceived age discrimination are lower in the United States than England and are less socially patterned. This suggests that differing social and political circumstances in the two countries may have an important role to play.
Keywords: Aged; Aged, 80 and over; Ageism; England; Female; Humans; Longitudinal Studies; Male; Middle Aged; Perception; Surveys and Questionnaires; United States

GWAS of longevity in CHARGE consortium confirms APOE and FOXO3 candidacy. - Broer, Linda; Aron S Buchman; Deelen, Joris; Daniel S Evans; Jessica Faul; Kathryn L Lunetta; Sebastiani, Paola; Jennifer A Smith; Albert Vernon Smith; Toshiko Tanaka; Lei Yu; Alice M. Arnold; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The genetic contribution to longevity in humans has been estimated to range from 15% to 25%. Only two genes, APOE and FOXO3, have shown association with longevity in multiple independent studies. METHODS: We conducted a meta-analysis of genome-wide association studies including 6,036 longevity cases, age ≥90 years, and 3,757 controls that died between ages 55 and 80 years. We additionally attempted to replicate earlier identified single nucleotide polymorphism (SNP) associations with longevity. RESULTS: In our meta-analysis, we found suggestive evidence for the association of SNPs near CADM2 (odds ratio [OR] = 0.81; p value = 9.66 × 10(-7)) and GRIK2 (odds ratio = 1.24; p value = 5.09 × 10(-8)) with longevity. When attempting to replicate findings earlier identified in genome-wide association studies, only the APOE locus consistently replicated. In an additional look-up of the candidate gene FOXO3, we found that an earlier identified variant shows a highly significant association with longevity when including published data with our meta-analysis (odds ratio = 1.17; p value = 1.85×10(-10)). CONCLUSIONS: We did not identify new genome-wide significant associations with longevity and did not replicate earlier findings except for APOE and FOXO3. Our inability to find new associations with survival to ages ≥90 years because longevity represents multiple complex traits with heterogeneous genetic underpinnings, or alternatively, that longevity may be regulated by rare variants that are not captured by standard genome-wide genotyping and imputation of common variants.
Keywords: Aged; Aged, 80 and over; Apolipoproteins E; Cell Adhesion Molecules; Cohort Studies; Female; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome-Wide Association Study; Humans; Longevity; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Kainic Acid

Harmonizing Measures of Cognitive Performance Across International Surveys of Aging Using Item Response Theory. - Kitty S. Chan; Alden L Gross; Liliana E Pezzin; Jason Brandt; Judith D Kasper (J Aging Health, 2015)
OBJECTIVE: To harmonize measures of cognitive performance using item response theory (IRT) across two international aging studies. METHOD: Data for persons ≥65 years from the Health and Retirement Study (HRS, N = 9,471) and the English Longitudinal Study of Aging (ELSA, N = 5,444). Cognitive performance measures varied (HRS fielded 25, ELSA 13); 9 were in common. Measurement precision was examined for IRT scores based on (a) common items, (b) common items adjusted for differential item functioning (DIF), and (c) DIF-adjusted all items. RESULTS: Three common items (day of date, immediate word recall, and delayed word recall) demonstrated DIF by survey. Adding survey-specific items improved precision but mainly for HRS respondents at lower cognitive levels. DISCUSSION: IRT offers a feasible strategy for harmonizing cognitive performance measures across other surveys and for other multi-item constructs of interest in studies of aging. Practical implications depend on sample distribution and the difficulty mix of in-common and survey-specific items.
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Female; Humans; Internationality; Longitudinal Studies; Male; Psychological Theory; Reproducibility of Results; Surveys and Questionnaires; United Kingdom; United States

Health literacy and the digital divide among older Americans. - Helen G Levy; Alexander T Janke; Kenneth M. Langa (J Gen Intern Med, 2015)
BACKGROUND: Among the requirements for meaningful use of electronic medical records (EMRs) is that patients must be able to interact online with information from their records. However, many older Americans may be unprepared to do this, particularly those with low levels of health literacy. OBJECTIVE: The purpose of the study was to quantify the relationship between health literacy and use of the Internet for obtaining health information among Americans aged 65 and older. DESIGN: We performed retrospective analysis of 2009 and 2010 data from the Health and Retirement Study, a longitudinal survey of a nationally representative sample of older Americans. PARTICIPANTS: Subjects were community-dwelling adults aged 65 years and older (824 individuals in the general population and 1,584 Internet users). MAIN MEASURES: Our analysis included measures of regular use of the Internet for any purpose and use of the Internet to obtain health or medical information; health literacy was measured using the Rapid Estimate of Adult Literacy in Medicine-Revised (REALM-R) and self-reported confidence filling out medical forms. KEY RESULTS: Only 9.7% of elderly individuals with low health literacy used the Internet to obtain health information, compared with 31.9% of those with adequate health literacy. This gradient persisted after controlling for sociodemographic characteristics, health status, and general cognitive ability. The gradient arose both because individuals with low health literacy were less likely to use the Internet at all (OR = 0.36 [95% CI 0.24 to 0.54]) and because, among those who did use the Internet, individuals with low health literacy were less likely to use it to get health or medical information (OR = 0.60 [95% CI 0.47 to 0.77]). CONCLUSION: Low health literacy is associated with significantly less use of the Internet for health information among Americans aged 65 and older. Web-based health interventions targeting older adults must address barriers to substantive use by individuals with low health literacy, or risk exacerbating the digital divide.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Digital Divide; Female; Health Literacy; Humans; Internet; Male; Prospective Studies; Retrospective Studies; Surveys and Questionnaires; United States

Hospitalization Type and Subsequent Severe Sepsis. - Hallie C Prescott; Dickson, R. P.; Mary A M Rogers; Kenneth M. Langa; Lwashyna, T. J. (Am J Respir Crit Care Med, 2015)
RATIONALE: Hospitalization is associated with microbiome perturbation (dysbiosis), and this perturbation is more severe in patients treated with antimicrobials. OBJECTIVES: To evaluate whether hospitalizations known to be associated with periods of microbiome perturbation are associated with increased risk of severe sepsis after hospital discharge. METHODS: We studied participants in the U.S. Health and Retirement Study with linked Medicare claims (1998-2010). We measured whether three hospitalization types associated with increasing severity of probable dysbiosis (non-infection-related hospitalization, infection-related hospitalization, and hospitalization with Clostridium difficile infection [CDI]) were associated with increasing risk for severe sepsis in the 90 days after hospital discharge. We used two study designs: the first was a longitudinal design with between-person comparisons and the second was a self-controlled case series design using within-person comparison. MEASUREMENTS AND MAIN RESULTS: We identified 43,095 hospitalizations among 10,996 Health and Retirement Study-Medicare participants. In the 90 days following non-infection-related hospitalization, infection-related hospitalization, and hospitalization with CDI, adjusted probabilities of subsequent admission for severe sepsis were 4.1% (95% confidence interval [CI], 3.8-4.4%), 7.1% (95% CI, 6.6-7.6%), and 10.7% (95% CI, 7.7-13.8%), respectively. The incidence rate ratio (IRR) of severe sepsis was 3.3-fold greater during the 90 days after hospitalizations than during other observation periods. The IRR was 30% greater after an infection-related hospitalization versus a non-infection-related hospitalization. The IRR was 70% greater after a hospitalization with CDI than an infection-related hospitalization without CDI. CONCLUSIONS: There is a strong dose-response relationship between events known to result in dysbiosis and subsequent severe sepsis hospitalization that is not present for rehospitalization for nonsepsis diagnoses.
Keywords: Aged; Aged, 80 and over; Anti-Bacterial Agents; Clostridioides difficile; Dysbiosis; Enterocolitis, Pseudomembranous; Female; Hospitalization; Humans; Incidence; Information Storage and Retrieval; Longitudinal Studies; Male; Medicare; Patient Readmission; Retrospective Studies; Risk Factors; Sepsis; United States

How old do you feel? The role of age discrimination and biological aging in subjective age. - Yannick Stephan; Angelina R Sutin; Antonio Terracciano (PLoS One, 2015)
Subjective age, or how young or old individuals experience themselves to be relative to their chronological age, is a crucial construct in gerontology. Subjective age is a significant predictor of important health outcomes, but little is known about the criteria by which individuals' subjectively evaluate their age. To identify psychosocial and biomedical factors linked to the subjective evaluation of age, this study examined whether perceived age discrimination and markers of biological aging are associated with subjective age. Participants were 4776 adults (Mage = 68) from the 2008 and 2010 waves of the Health and Retirement Study (HRS) who completed measures of subjective age, age discrimination, demographic variables, self-rated health and depression, and had physical health measures, including peak expiratory flow, grip strength, waist circumference, systolic and diastolic blood pressure. Telomere length was available for a subset of participants in the 2008 wave (n = 2214). Regression analysis indicated that perceived age discrimination, lower peak expiratory flow, lower grip strength, and higher waist circumference were associated with an older subjective age, controlling for sociodemographic factors, self-rated health, and depression. In contrast, blood pressure and telomere length were not related to subjective age. These findings are consistent with the hypothesis that how old a person feels depends in part on psychosocial and biomedical factors, including the experiences of ageism and perceptible indices of fitness and biological age.
Keywords: Aerobiosis; Aged; Aged, 80 and over; Aging; Cardiovascular Physiological Phenomena; Cellular Senescence; Discrimination, Psychological; Emotions; Female; Humans; Male; Middle Aged; Muscle Strength; Perception

Improving the validity of activity of daily living dependency risk assessment. - Daniel O. Clark; Timothy E. Stump; Tu, Wanzhu; Douglas K Miller (J Appl Gerontol, 2015)
OBJECTIVES: Efforts to prevent activity of daily living (ADL) dependency may be improved through models that assess older adults' dependency risk. We evaluated whether cognition and gait speed measures improve the predictive validity of interview-based models. METHOD: Participants were 8,095 self-respondents in the 2006 Health and Retirement Survey who were aged 65 years or over and independent in five ADLs. Incident ADL dependency was determined from the 2008 interview. Models were developed using random 2/3rd cohorts and validated in the remaining 1/3rd. RESULTS: Compared to a c-statistic of 0.79 in the best interview model, the model including cognitive measures had c-statistics of 0.82 and 0.80 while the best fitting gait speed model had c-statistics of 0.83 and 0.79 in the development and validation cohorts, respectively. CONCLUSION: Two relatively brief models, one that requires an in-person assessment and one that does not, had excellent validity for predicting incident ADL dependency but did not significantly improve the predictive validity of the best fitting interview-based models.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cognition; Cognition Disorders; Female; Gait; Geriatric Assessment; Humans; Independent Living; Interviews as Topic; Male; Quality Improvement; Reproducibility of Results; Risk Assessment

Increase in Disability Prevalence Before Hip Fracture. - Irena Cenzer; W John Boscardin; Christine S Ritchie; Margaret Wallhagen; Kenneth E Covinsky (J Am Geriatr Soc, 2015)
OBJECTIVES: To establish the prevalence and correlates of disability during the 2 years before hip fracture. DESIGN: Data from participants who experienced hip fracture in the Health and Retirement Study (HRS) with hip fracture identified using linked Medicare claims. Each participant was interviewed at varying time points in the 2 years before hip fracture. Disability was defined as self-report of the need for assistance in any activity of daily living (walking across the room, eating, bathing, dressing, using the toilet, transferring). Based on the timing between interview and hip fracture, prevalence of disability was calculated in the cohort as a whole over the 2 years before hip fracture and in subgroups defined according to demographic and clinical characteristics. SETTING: The HRS is a nationally representative longitudinal study (1992-2010). PARTICIPANTS: HRS participants aged ≥65 with hip fracture (mean age at fracture 84, 77% female). RESULTS: The adjusted prevalence of disability was 20% (95% confidence interval (CI) = 14-25%) 2 years before hip fracture, with little change until approximately 10 months before fracture, when it started to rise, reaching 44% (95% CI = 33-55%) in the month before hip fracture. The prevalence of disability was highest in the last month before fracture for persons aged 85 and older (53%) and for those with dementia (60%). CONCLUSION: Care models for hip fracture need to consider not only the acute medical and surgical needs, but also the high level of need for supportive care and caregiver assistance that chronically disabled individuals require.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Dementia; Disability Evaluation; Disabled Persons; Educational Status; Female; Health Surveys; Hip Fractures; Humans; Income; Male; Mobility Limitation; Prevalence; United States

Life satisfaction and use of preventive health care services. - Eric S Kim; Laura D Kubzansky; Jacqui Smith (Health Psychol, 2015)
OBJECTIVE: Although a growing body of research shows that life satisfaction is linked with enhanced health behaviors and physical health, no study has examined life satisfaction's association with use of preventive health care services. From prior research the authors hypothesized that people with higher life satisfaction would be more proactive in taking care of their health, hence more likely to use preventive health care services. METHOD: Multiple logistic regression models were used to examine the association between life satisfaction and preventive services. Participants were drawn from the Health and Retirement Study, a prospective and nationally representative panel study of adults (age >50). Participants' use of preventive services was collected over 2 years of follow-up. RESULTS: In models adjusting for sociodemographic factors, each standard deviation increase in life satisfaction was associated with a higher likelihood that people would obtain a cholesterol test. Further, women with higher life satisfaction were more likely to obtain a mammogram-x-ray or pap smear and also regularly check their breasts for lumps, whereas men were more likely to obtain a prostate exam. CONCLUSION: Higher life satisfaction was associated with higher use of several preventive services. A growing body of randomized controlled trials targeting life satisfaction has shown that levels of life satisfaction are modifiable. Thus, if these findings are replicated, life satisfaction may provide an important target for interventions aimed at enhancing preventive behaviors and health.
Keywords: Aged; Aged, 80 and over; Female; Health Behavior; Humans; Male; Mammography; Middle Aged; Personal Satisfaction; Preventive Health Services; Prospective Studies

Lifespan and Healthspan: Past, Present, and Promise. - Eileen M. Crimmins (Gerontologist, 2015)
The past century was a period of increasing life expectancy throughout the age range. This resulted in more people living to old age and to spending more years at the older ages. It is likely that increases in life expectancy at older ages will continue, but life expectancy at birth is unlikely to reach levels above 95 unless there is a fundamental change in our ability to delay the aging process. We have yet to experience much compression of morbidity as the age of onset of most health problems has not increased markedly. In recent decades, there have been some reductions in the prevalence of physical disability and dementia. At the same time, the prevalence of disease has increased markedly, in large part due to treatment which extends life for those with disease. Compressing morbidity or increasing the relative healthspan will require "delaying aging" or delaying the physiological change that results in disease and disability. While moving to life expectancies above age 95 and compressing morbidity substantially may require significant scientific breakthroughs; significant improvement in health and increases in life expectancy in the United States could be achieved with behavioral, life style, and policy changes that reduce socioeconomic disparities and allow us to reach the levels of health and life expectancy achieved in peer societies.
Keywords: Aged; Aged, 80 and over; Aging; Disabled Persons; Humans; Life Expectancy; Socioeconomic factors; United States

Loneliness, eudaimonia, and the human conserved transcriptional response to adversity. - Steven W. Cole; Morgan E. Levine; Jesusa M. G. Arevalo; Ma, Jeffrey; David R Weir; Eileen M. Crimmins (Psychoneuroendocrinology, 2015)
BACKGROUND: Chronic social adversity activates a conserved transcriptional response to adversity (CTRA) marked by increased expression of pro-inflammatory genes and decreased expression of antiviral- and antibody-related genes. Recent findings suggest that some psychological resilience factors may help buffer CTRA activation, but the relative impact of resilience and adversity factors remains poorly understood. Here we examined the relative strength of CTRA association for the two best-established psychological correlates of CTRA gene expression-the risk factor of perceived social isolation (loneliness) and the resilience factor of eudaimonic well-being (purpose and meaning in life). METHODS: Peripheral blood samples and validated measures of loneliness and eudaimonic well-being were analyzed in 108 community-dwelling older adults participating in the longitudinal US Health and Retirement Study (56% female, mean age 73). Mixed effect linear model analyses quantified the strength of association between CTRA gene expression and measures of loneliness and eudaimonic well-being in separate and joint analyses. RESULTS: As in previous studies, separate analyses found CTRA gene expression to be up-regulated in association with loneliness and down-regulated in association with eudaimonic well-being. In joint analyses, effects of loneliness were completely abrogated whereas eudaimonic well-being continued to associate with CTRA down-regulation. Similar eudaimonia-dominant effects were observed for positive and negative affect, optimism and pessimism, and anxiety symptoms. All results were independent of demographic and behavioral health risk factors. CONCLUSIONS: Eudaimonic well-being may have the potential to compensate for the adverse impact of loneliness on CTRA gene expression. Findings suggest a novel approach to targeting the health risks associated with social isolation by promoting purpose and meaning in life.
Keywords: Aged; Aged, 80 and over; Down-Regulation; Female; Humans; Inflammation; Loneliness; Longitudinal Studies; Male; Mental Health; Middle Aged; social isolation; Social Support; Stress, Psychological; Transcriptome

Longitudinal patient-oriented outcomes in neuropathy: Importance of early detection and falls. - Brian C. Callaghan; Kevin Kerber; Kenneth M. Langa; Banerjee, Mousumi; Rodgers, Ann; Ryan J McCammon; James F. Burke; Eva L Feldman (Neurology, 2015)
OBJECTIVE: To evaluate longitudinal patient-oriented outcomes in peripheral neuropathy over a 14-year time period including time before and after diagnosis. METHODS: The 1996-2007 Health and Retirement Study (HRS)-Medicare Claims linked database identified incident peripheral neuropathy cases (ICD-9 codes) in patients ≥65 years. Using detailed demographic information from the HRS and Medicare claims, a propensity score method identified a matched control group without neuropathy. Patient-oriented outcomes, with an emphasis on self-reported falls, pain, and self-rated health (HRS interview), were determined before and after neuropathy diagnosis. Generalized estimating equations were used to assess differences in longitudinal outcomes between cases and controls. RESULTS: We identified 953 peripheral neuropathy cases and 953 propensity-matched controls. The mean (SD) age was 77.4 (6.7) years for cases, 76.9 (6.6) years for controls, and 42.1% had diabetes. Differences were detected in falls 3.0 years before neuropathy diagnosis (case vs control; 32% vs 25%, p = 0.008), 5.0 years for pain (36% vs 27%, p = 0.002), and 5.0 years for good to excellent self-rated health (61% vs 74%, p < 0.0001). Over time, the proportion of fallers increased more rapidly in neuropathy cases compared to controls (p = 0.002), but no differences in pain (p = 0.08) or self-rated health (p = 0.9) were observed. CONCLUSIONS: In older persons, differences in falls, pain, and self-rated health can be detected 3-5 years prior to peripheral neuropathy diagnosis, but only falls deteriorates more rapidly over time in neuropathy cases compared to controls. Interventions to improve early peripheral neuropathy detection are needed, and future clinical trials should incorporate falls as a key patient-oriented outcome.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Early Diagnosis; Female; Humans; International Classification of Diseases; Longitudinal Studies; Male; Medicare; Patient-Centered Care; Peripheral Nervous System Diseases; Treatment Outcome; United States

Measurement Invariance of Cognitive Abilities Across Ethnicity, Gender, and Time Among Older Americans. - A Nayena Blankson; John J McArdle (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: The aim of this research was to test the invariance of the cognitive variables in the Health and Retirement Study/Asset Health Dynamics Among the Oldest Old studies (HRS/AHEAD) across ethnicity, gender, and time. METHOD: Analyses were conducted using a selected subsample of the HRS/AHEAD data set. The cognitive performance tests measuring episodic memory and mental status were used, and invariance of a two-factor structure was tested using confirmatory factor analyses and multilevel modeling for longitudinal data. RESULTS: Results provided some support for "strict" factorial invariance of the episodic memory and mental status measures across ethnicity and gender. Further support of weak ("metric") measurement invariance was found across time. DISCUSSION: Results of the research further our understanding of invariance of the HRS/AHEAD cognitive ability measures. Further implications are discussed.
Keywords: Aged; Aged, 80 and over; Black People; Female; Hispanic or Latino; Humans; Male; Memory, Episodic; Mental Processes; Middle Aged; Neuropsychological tests; Psychometrics; Psychomotor Performance; Reproducibility of Results; Sex Factors; Time Factors; United States; White People

Multimorbidity redefined: prospective health outcomes and the cumulative effect of co-occurring conditions. - Siran M Koroukian; David F Warner; Owusu, Cynthia; Charles W Given (Prev Chronic Dis, 2015)
INTRODUCTION: Multimorbidity is common among middle-aged and older adults; however the prospective effects of multimorbidity on health outcomes (health status, major health decline, and mortality) have not been fully explored. This study addresses this gap in the literature. METHODS: We used self-reported data from the 2008 and 2010 Health and Retirement Study. Our study population included 13,232 adults aged 50 or older. Our measure of baseline multimorbidity in 2008 was based on the occurrence or co-occurrence of chronic conditions, functional limitations, and/or geriatric syndromes, as follows: MM0, no chronic conditions, functional limitations, or geriatric syndromes; MM1, occurrence (but no co-occurrence) of chronic conditions, functional limitations, or geriatric syndromes; MM2, co-occurrence of any 2 of chronic conditions, functional limitations, or geriatric syndromes; and MM3, co-occurrence of all 3 of chronic conditions, functional limitations, and geriatric syndromes. Outcomes in 2010 included fair or poor health status, major health decline, and mortality. RESULTS: All 3 outcomes were significantly associated with multimorbidity. Compared with MM0 (respectively for fair or poor health and major health decline), the adjusted odds ratios (AORs) and 95% confidence intervals were as follows: 2.61 (1.79-3.78) and 2.20 (1.42-3.41) for MM1; 7.49 (5.20-10.77) and 3.70 (2.40-5.71) for MM2; and 22.66 (15.64-32.83) and 4.72 (3.03-7.37) for MM3. Multimorbidity was also associated with mortality: an adult classified as MM3 was nearly 12 times (AOR, 11.87 [5.72-24.62]) as likely as an adult classified as MM0 to die within 2 years. CONCLUSION: Given the strong and significant association between multimorbidity and prospective health status, major health decline, and mortality, multimorbidity may be used - both in clinical practice and in research - to identify older adults with heightened vulnerability for adverse outcomes.
Keywords: Aged; Aged, 80 and over; Alcohol Drinking; Body Mass Index; Chronic disease; Cognition Disorders; Comorbidity; Cross-Sectional Studies; Data Interpretation, Statistical; ethnicity; Female; Health Status Indicators; Humans; Interviews as Topic; Male; Middle Aged; Mobility Limitation; Outcome Assessment, Health Care; Prospective Studies; Recurrence; Retirement; Self Report; Smoking; Social Class; Syndrome; United States; Vulnerable Populations

The Paulson-Lichtenberg Frailty Index: evidence for a self-report measure of frailty. - Daniel Paulson; Peter A Lichtenberg (Aging Ment Health, 2015)
OBJECTIVES: This study evaluates the Paulson-Lichtenberg Frailty Index (PLFI), a self-report measure that is based on Fried's well-established frailty phenotype. The PLFI is examined using longitudinal data from the Health and Retirement Study (HRS) database, for which it was developed. METHODS: The sample was drawn from the HRS and included 8844 community-dwelling older adults. Frailty was measured using the PLFI's five-item frailty index (wasting, weakness, slowness, falls, and fatigue). RESULTS: In comparison to intermediate-frail or non-frail respondents, frail respondents were found to be older, more medically compromised, and less independent for activities of daily living (ADLs) and instrumental activities of daily living (IADLs). On average, frail respondents reported worse self-rated health and had fewer years of education. Women, ethnic minorities, and those who were not partnered were also more likely to be frail. Over subsequent years, frail respondents were more likely to be hospitalized, report more loss of independence, and experience higher mortality rates. CONCLUSIONS: The PLFI is a valid tool for assessing frailty in the HRS data set.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Fatigue; Female; Frail Elderly; Geriatric Assessment; Health Status; Health Surveys; Humans; Longitudinal Studies; Male; Self Report; Socioeconomic factors; Walking

The prevalence of older couples with ADL limitations and factors associated with ADL help receipt. - Shen, Huei-Wern; Sheila Feld; Ruth E Dunkle; Tracy Schroepfer; Amanda J Lehning (J Gerontol Soc Work, 2015)
Using the Andersen-Newman model, we investigated the prevalence of activities of daily living (ADLs) limitations in married couples, and couple characteristics associated with ADL help-receipt. In this sample of 3,235 couples age 65+ in the 2004 Health and Retirement Study, 74.3%, 22.1%, and 3.6% were couples in which neither partner, one partner, or both partners had limitations, respectively. Logistic regression results indicate that help-receipt was associated with certain health needs in the couple, but not with their predisposing characteristics or enabling resources. Social workers could target couples most in need of assistance by assessing both partners' health problems.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Health Services Accessibility; Humans; Male; Social Support; Socioeconomic factors

A Research Note on Transitions in Out-of-Pocket Spending on Dental Services. - Richard J. Manski; John F Moeller; Haiyan Chen; Jody Schimmel Hyde; John V Pepper; Patricia A St Clair (Res Aging, 2015)
OBJECTIVE: We analyze correlates of the direction and magnitude of changes in out-of-pocket (OOP) payments for dental care by older Americans over a recent 4-year period. METHODS: We analyzed data from the 2006 and 2008 waves of the Health and Retirement Study. We estimated multinomial logistic models of the direction and linear regression models of the amounts of OOP changes over survey periods. RESULTS: Financial-based factors were more strongly associated with the direction and magnitude of changing self-payments for dental care than were health factors. DISCUSSION: Findings suggested that dental coverage, income, and wealth and changes in these financial factors were more strongly correlated with the persistence of and changes in OOP payments for dental care over time than were health status and changes in health status. The sensitivity to dental coverage changes should be considered as insurance and retirement policy reforms are deliberated.
Keywords: Aged; Aged, 80 and over; Dental Care; Female; Health Expenditures; Humans; Insurance, Dental; Longitudinal Studies; Male; Middle Aged; United States

Social Relationships, Gender, and Recovery From Mobility Limitation Among Older Americans. - Kenzie Latham; Philippa J Clarke; Gregory Pavela (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: Evidence suggests social relationships may be important facilitators for recovery from functional impairment, but the extant literature is limited in its measurement of social relationships including an over emphasis on filial social support and a paucity of nationally representative data. METHODS: Using data from Waves 4-9 (1998-2008) of the Health and Retirement Study (HRS), this research examines the association between social relationships and recovery from severe mobility limitation (i.e., difficulty walking one block or across the room) among older Americans. Using a more nuanced measure of recovery that includes complete and partial recovery, a series of discrete-time event history models with multiple competing recovery outcomes were estimated using multinomial logistic regression. RESULTS: Providing instrumental support to peers increased the odds of complete and partial recovery from severe mobility limitation, net of numerous social, and health factors. Having relatives living nearby decreased the odds of complete recovery, while being engaged in one's neighborhood increased the odds of partial recovery. The influence of partner status on partial and complete recovery varied by gender, whereby partnered men were more likely to experience recovery relative to partnered women. The effect of neighborhood engagement on partial recovery also varied by gender. Disengaged women were the least likely to experience partial recovery compared with any other group. DISCUSSION: The rehabilitative potential of social relationships has important policy implications. Interventions aimed at encouraging older adults with mobility limitation to be engaged in their neighborhoods and/or provide instrumental support to peers may improve functional health outcomes.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Family; Female; Humans; Interpersonal Relations; Male; Middle Aged; Mobility Limitation; Peer Group; Recovery of Function; Residence Characteristics; Sex Factors; Social Support; United States

Socioeconomic stratification and multidimensional health trajectories: evidence of convergence in later old age. - Xiao Xu; Jersey Liang; Joan M. Bennett; Anda Botoseneanu; Heather G. Allore (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: This research sought to examine socioeconomic stratification in the joint trajectories of physical, emotional, and cognitive functioning among older Americans and how it differs by age groups. METHODS: We used data from a nationally representative sample of 9,237 Americans age 65 or older from the Health and Retirement Study, who were observed biennially from 1998 to 2010. Joint trajectories of physical, emotional, and cognitive functioning were characterized using a group-based mixture model. We then applied multinomial logistic regression analysis to evaluate their linkages with socioeconomic status and how the linkages differ by age groups. RESULTS: We identified four distinct patterns of joint changes in physical, emotional, and cognitive functioning over time. Accounting for 29.3%, 23.5%, 24.5%, and 22.6% of the older Americans, respectively, these trajectory patterns characterized groups of individuals experiencing minimal to severe levels of impairment and deterioration. Lower education, income, and net worth were associated with trajectories featuring greater impairment or more rapid deterioration in these functional dimensions. Disparities based on education, however, attenuated in later old age, whereas health benefits associated with higher income and higher net worth persisted into advanced age. DISCUSSION: Distinct patterns of joint trajectories of physical, emotional, and cognitive functioning exist in old age. There were significant socioeconomic differences in the joint trajectories, with education-based inequality in health converging in later old age. Further research identifying strategies to alleviate the disproportionate burden of poor multidimensional health trajectories in lower socioeconomic groups is important.
Keywords: Aged; Aged, 80 and over; Aging; Cognition Disorders; Disabled Persons; Educational Status; Female; Health Status; Humans; Male; Social Class; United States

Spouse and Child Availability for Newly Disabled Older Adults: Socioeconomic Differences and Potential Role of Residential Proximity. - Choi, Hwajung; Robert F. Schoeni; Kenneth M. Langa; Michele M Heisler (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: To examine the potential role of child and spousal availability in facilitating community-based care for disabled older adults. METHOD: We used the Health and Retirement Study, a nationally representative longitudinal study of older adults. The analysis sample included older adults who were nondisabled at baseline, but who then developed at least one activity of daily living (ADL) limitation over the subsequent 2-year period (N = 2,094). Using multivariate, multinomial logistic regression, we examined the association of child and spouse availability prior to disablement of the older adults with ADL care receipt status after the onset of disablement, after adjusting for other sociodemographic and clinical characteristics. RESULTS: Lower socioeconomic status (SES) was associated with less availability of a spouse but greater availability of children at baseline. Compared with older adults who had no children nearby (i.e., all children lived further than 30 miles), older adults who had at least one child living with or near them prior to the onset of the ADL limitation were less likely to go to a nursing home (adjusted odds ratio [AOR]: 0.26 for coresident; AOR: 0.44 for 1- 30 miles) and less likely to depend on formal care (AOR: 0.39 for coresident; AOR: 0.51 for 1-30 miles) after the onset of new ADL limitation/s. DISCUSSION: Understanding SES variations in the informal care resources, and potential role of child geographic availability, may inform the development of cost-effective community-based care programs and policies.
Keywords: Activities of Daily Living; Adult children; Aged; Aged, 80 and over; Aging; Disabled Persons; Female; Home Nursing; Humans; Male; Middle Aged; Nursing homes; Residence Characteristics; Social Class; Spouses

Substance-use coping and self-rated health among US middle-aged and older adults. - Pia M Mauro; Sarah L. Canham; Silvia S Martins; Adam P Spira (Addict Behav, 2015)
The prevalence of alcohol, drug, and tobacco use among US middle-aged and older adults is increasing. A subset of this population uses substances to cope with stress, but the characteristics of these individuals, and the association between substance-use coping and health outcomes remain unclear. We identified correlates of substance-use coping and measured its association with self-rated health in a community-based sample of adults aged 54-99 in the Health and Retirement Study (HRS). In the 2008 HRS, 1351 participants reported their frequency of prescription/other drug-, alcohol-, and cigarette-use coping with stress and reported self-rated health (excellent/very good, good, or fair/poor); 1201 of these participants also reported self-rated health in 2010. One in six participants frequently used substances to cope. The oldest participants were least likely to engage in frequent alcohol-use coping. Those with elevated depressive symptoms were more likely to frequently engage in cigarette- and prescription/other drug-use coping. In multivariable-adjusted analyses, participants who frequently used cigarettes (compared to participants who infrequently used cigarettes) to cope had 2.7 times (95% CI=1.1-6.7) the odds of poor (vs. excellent) self-rated health. Relative to participants who infrequently used prescription/other drugs to cope, participants who frequently used prescription/other drugs to cope had 2.4 times (95% CI=1.1-5.1) the odds of reporting poor self-rated health. The association between prescription/other drug-use coping in 2008 and self-rated health in 2010 was statistically significant (relative OR=3.5, 95% CI=1.7-7.2). Participants engaging in substance-use coping likely have particular demographic and clinical characteristics. Interventions to reduce substance-use coping may prevent adverse health outcomes.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Alcohol Drinking; depression; Female; Health Status; Humans; Male; Middle Aged; Smoking; Substance-Related Disorders; United States

Variation in the effects of family background and birth region on adult obesity: results of a prospective cohort study of a Great Depression-era American cohort. - Hui Zheng; Dmitry Tumin (BMC Public Health, 2015)
BACKGROUND: Studies have identified prenatal and early childhood conditions as important contributors to weight status in later life. To date, however, few studies have considered how weight status in adulthood is shaped by regional variation in early-life conditions, rather than the characteristics of the individual or their family. Furthermore, gender and life course differences in the salience of early life conditions to weight status remain unclear. This study investigates whether the effect of family background and birth region on adult obesity status varies by gender and over the life course. METHODS: We used data from a population-based cohort of 6,453 adults from the Health and Retirement Study, 1992-2008. Early life conditions were measured retrospectively at and after the baseline. Obesity was calculated from self-reported height and weight. Logistic models were used to estimate the net effects of family background and birth region on adulthood obesity risk after adjusting for socioeconomic factors and health behaviors measured in adulthood. Four economic and demographic data sets were used to further test the birthplace effect. RESULTS: At ages 50-61, mother's education and birth region were associated with women's obesity risk, but not men's. Each year's increase in mother's education significantly reduces the odds of being obese by 6% (OR = 0.94; 95% CI: 0.92, 0.97) among women, and this pattern persisted at ages 66-77. Women born in the Mountain region were least likely to be obese in late-middle age and late-life. Measures of per capita income and infant mortality rate in the birth region were also associated with the odds of obesity among women. CONCLUSIONS: Women's obesity status in adulthood is influenced by early childhood conditions, including regional conditions, while adulthood health risk factors may be more important for men's obesity risk. Biological and social mechanisms may account for the gender difference.
Keywords: Aged; Aged, 80 and over; Body Weight; Cohort Studies; ethnicity; Family Characteristics; Female; Health Behavior; Humans; Interviews as Topic; Logistic Models; Male; Middle Aged; Obesity; Prospective Studies; Qualitative Research; Retirement; Risk Factors; Socioeconomic factors; United States

What can genes tell us about the relationship between education and health? - Jason D Boardman; Benjamin W Domingue; Daw, Jonathan (Soc Sci Med, 2015)
We use genome wide data from respondents of the Health and Retirement Study (HRS) to evaluate the possibility that common genetic influences are associated with education and three health outcomes: depression, self-rated health, and body mass index. We use a total of 1.7 million single nucleotide polymorphisms obtained from the Illumina HumanOmni2.5-4v1 chip from 4233 non-Hispanic white respondents to characterize genetic similarities among unrelated persons in the HRS. We then used the Genome Wide Complex Trait Analysis (GCTA) toolkit, to estimate univariate and bivariate heritability. We provide evidence that education (h(2) = 0.33), BMI (h(2) = 0.43), depression (h(2) = 0.19), and self-rated health (h(2) = 0.18) are all moderately heritable phenotypes. We also provide evidence that some of the correlation between depression and education as well as self-rated health and education is due to common genetic factors associated with one or both traits. We find no evidence that the correlation between education and BMI is influenced by common genetic factors.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Computer Simulation; depression; Educational Status; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Health Status; Health Status Disparities; Humans; Male; Phenotype; Polymorphism, Single Nucleotide; Social determinants of health; Socioeconomic factors; White People

Are people healthier if their partners are more optimistic? The dyadic effect of optimism on health among older adults. - Eric S Kim; William J. Chopik; Jacqui Smith (J Psychosom Res, 2014)
OBJECTIVE: Optimism has been linked with an array of positive health outcomes at the individual level. However, researchers have not examined how a spouse's optimism might impact an individual's health. We hypothesized that being optimistic (and having an optimistic spouse) would both be associated with better health. METHODS: Participants were 3940 adults (1970 couples) from the Health and Retirement Study, a nationally representative panel study of American adults over the age of 50. Participants were tracked for four years and outcomes included: physical functioning, self-rated health, and number of chronic illnesses. We analyzed the dyadic data using the actor-partner interdependence model. RESULTS: After controlling for several psychological and demographic factors, a person's own optimism and their spouse's optimism predicted better self-rated health and physical functioning (bs = .08-.25, ps<.01). More optimistic people also reported better physical functioning (b = -.11, p<.01) and fewer chronic illnesses (b=-.01, p<.05) over time. Further, having an optimistic spouse uniquely predicted better physical functioning (b = -.09, p<.01) and fewer chronic illnesses (b = -.01, p<.05) over time. The strength of the relationship between optimism and health did not diminish over time. CONCLUSIONS: Being optimistic and having an optimistic spouse were both associated with better health. Examining partner effects is important because such analyses reveal the unique role that spouses play in promoting health. These findings may have important implications for future health interventions.
Keywords: Adult; Affect; Aged; Aged, 80 and over; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Personal Satisfaction; Self Report; Spouses

Chiropractic use in the Medicare population: prevalence, patterns, and associations with 1-year changes in health and satisfaction with care. - Paula A Weigel; Jason Hockenberry; Frederic D Wolinsky (J Manipulative Physiol Ther, 2014)
OBJECTIVE: The purpose of this study was to examine how chiropractic care compares to medical treatments on 1-year changes in self-reported function, health, and satisfaction with care measures in a representative sample of Medicare beneficiaries. METHODS: Logistic regression using generalized estimating equations is used to model the effect of chiropractic relative to medical care on decline in 5 functional measures and 2 measures of self-rated health among 12170 person-year observations. The same method is used to estimate the comparative effect of chiropractic on 6 satisfaction with care measures. Two analytic approaches are used, the first assuming no selection bias and the second using propensity score analyses to adjust for selection effects in the outcome models. RESULTS: The unadjusted models show that chiropractic is significantly protective against 1-year decline in activities of daily living, lifting, stooping, walking, self-rated health, and worsening health after 1 year. Persons using chiropractic are more satisfied with their follow-up care and with the information provided to them. In addition to the protective effects of chiropractic in the unadjusted model, the propensity score results indicate a significant protective effect of chiropractic against decline in reaching. CONCLUSION: This study provides evidence of a protective effect of chiropractic care against 1-year declines in functional and self-rated health among Medicare beneficiaries with spine conditions, and indications that chiropractic users have higher satisfaction with follow-up care and information provided about what is wrong with them.
Keywords: Aged; Aged, 80 and over; Female; Humans; Male; Manipulation, Chiropractic; Medicare; Patient Satisfaction; Time Factors; Treatment Outcome; United States

The comparative effect of episodes of chiropractic and medical treatment on the health of older adults. - Paula A Weigel; Jason Hockenberry; Suzanne E Bentler; Frederic D Wolinsky (J Manipulative Physiol Ther, 2014)
OBJECTIVES: The comparative effect of chiropractic vs medical care on health, as used in everyday practice settings by older adults, is not well understood. The purpose of this study is to examine how chiropractic compares to medical treatment in episodes of care for uncomplicated back conditions. Episodes of care patterns between treatment groups are described, and effects on health outcomes among an older group of Medicare beneficiaries over a 2-year period are estimated. METHODS: Survey data from the nationally representative Survey on Assets and Health Dynamics among the Oldest Old were linked to participants' Medicare Part B claims under a restricted Data Use Agreement with the Centers for Medicare and Medicaid Services. Logistic regression was used to model the effect of chiropractic use in an episode of care relative to medical treatment on declines in function and well-being among a clinically homogenous older adult population. Two analytic approaches were used, the first assumed no selection bias and the second using propensity score analyses to adjust for selection effects in the outcome models. RESULTS: Episodes of care between treatment groups varied in duration and provider visit pattern. Among the unadjusted models, there was no significant difference between chiropractic and medical episodes of care. The propensity score results indicate a significant protective effect of chiropractic against declines in activities of daily living (ADLs), instrumental ADLs, and self-rated health (adjusted odds ratio [AOR], 0.49; AOR, 0.62; and AOR, 0.59, respectively). There was no difference between treatment types on declines in lower body function or depressive symptoms. CONCLUSION: The findings from this study suggest that chiropractic use in episodes of care for uncomplicated back conditions has protective effects against declines in ADLs, instrumental ADLs, and self-rated health for older Medicare beneficiaries over a 2-year period.
Keywords: Activities of Daily Living; Aged, 80 and over; Back Pain; Episode of Care; Female; Humans; Male; Manipulation, Chiropractic; Treatment Outcome

Cumulative inequality and racial disparities in health: private insurance coverage and black/white differences in functional limitations. - Ben Lennox Kail; Miles G Taylor (J Gerontol B Psychol Sci Soc Sci, 2014)
OBJECTIVES: To test different forms of private insurance coverage as mediators for racial disparities in onset, persistent level, and acceleration of functional limitations among Medicare age-eligible Americans. METHOD: Data come from 7 waves of the Health and Retirement Study (1996-2008). Onset and progression latent growth models were used to estimate racial differences in onset, level, and growth of functional limitations among a sample of 5,755 people aged 65 and older in 1996. Employer-provided insurance, spousal insurance, and market insurance were next added to the model to test how differences in private insurance mediated the racial gap in physical limitations. RESULTS: In baseline models, African Americans had larger persistent level of limitations over time. Although employer-provided, spousal provided, and market insurances were directly associated with lower persistent levels of limitation, only differences in market insurance accounted for the racial disparities in persistent level of limitations. DISCUSSION: Results suggest private insurance is important for reducing functional limitations, but market insurance is an important mediator of the persistently larger level of limitations observed among African Americans.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Black or African American; Cross-Sectional Studies; Female; Health Status Disparities; Hispanic or Latino; Humans; Insurance Coverage; Insurance, Health; Longitudinal Studies; Male; Medicare; Socioeconomic factors; United States

Depression and risk of hospitalization for pneumonia in a cohort study of older Americans. - Dimitry S Davydow; Catherine L Hough; Zivin, Kara; Kenneth M. Langa; Wayne J Katon (J Psychosom Res, 2014)
OBJECTIVE: The aim of this study is to determine if depression is independently associated with risk of hospitalization for pneumonia after adjusting for demographics, medical comorbidity, health-risk behaviors, baseline cognition and functional impairments. METHODS: This secondary analysis of prospectively collected data examined a population-based sample of 6704 Health and Retirement Study (HRS) (1998-2008) participants>50years old who consented to have their interviews linked to their Medicare claims and were without a dementia diagnosis. The eight-item Center for Epidemiologic Studies Depression Scale and/or International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) depression diagnoses were used to identify baseline depression. ICD-9-CM diagnoses were used to identify hospitalizations for which the principal discharge diagnosis was for bacterial or viral pneumonia. The odds of hospitalization for pneumonia for participants with depression relative to those without depression were estimated using logistic regression models. Population attributable fractions were calculated to determine the extent that hospitalizations for pneumonia could be attributable to depression. RESULTS: After adjusting for demographic characteristics, clinical factors, and health-risk behaviors, depression was independently associated with increased odds of hospitalization for pneumonia (odds ratio [OR]: 1.28, 95% confidence interval [95%CI]: 1.08, 1.53). This association persisted after adjusting for baseline cognition and functional impairments (OR: 1.24, 95%CI: 1.03, 1.50). In this cohort, 6% (95%CI: 2%, 10%) of hospitalizations for pneumonia were potentially attributable to depression. CONCLUSION: Depression is independently associated with increased odds of hospitalization for pneumonia. This study provides additional rationale for integrating mental health care into medical settings in order to improve outcomes for older adults.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Comorbidity; depression; Depressive Disorder; Female; Hospitalization; Humans; Logistic Models; Male; Middle Aged; Odds Ratio; Pneumonia; Risk Assessment; Risk Factors; United States

The disability burden associated with stroke emerges before stroke onset and differentially affects blacks: results from the health and retirement study cohort. - Benjamin D Capistrant; Nicte I Mejia; Sze Y Liu; Qianyi Wang; M. Maria Glymour (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Few longitudinal studies compare changes in instrumental activities of daily living (IADLs) among stroke-free adults to prospectively document IADL changes among adults who experience stroke. We contrast annual declines in IADL independence for older individuals who remain stroke free to those for individuals who experienced stroke. We also assess whether these patterns differ by sex, race, or Southern birthplace. METHODS: Health and Retirement Study participants who were stroke free in 1998 (n = 17,741) were followed through 2010 (average follow-up = 8.9 years) for self- or proxy-reported stroke. We used logistic regressions to compare annual changes in odds of self-reported independence in six IADLs among those who remained stroke free throughout follow-up (n = 15,888), those who survived a stroke (n = 1,412), and those who had a stroke and did not survive to participate in another interview (n = 442). We present models adjusted for demographic and socioeconomic covariates and also stratified on sex, race, and Southern birthplace. RESULTS: Compared with similar cohort members who remained stroke free, participants who developed stroke had faster declines in IADL independence and lower probability of IADL independence prior to stroke. After stroke, independence declined at an annual rate similar to those who did not have stroke. The black-white disparity in IADL independence narrowed poststroke. CONCLUSION: Racial differences in IADL independence are apparent long before stroke onset. Poststroke differences in IADL independence largely reflect prestroke disparities.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Black or African American; Cohort Studies; Disabled Persons; Female; Humans; Male; Prospective Studies; Stroke; United States; White People

Dysphoria and anhedonia as risk factors for disability or death in older persons: implications for the assessment of geriatric depression. - Kenneth E Covinsky; Irena Cenzer; Kristine Yaffe; Sarah O'Brien; Dan G. Blazer (Am J Geriatr Psychiatry, 2014)
OBJECTIVES: Either dysphoria (sadness) or anhedonia (loss of interest in usually pleasurable activities) is required for a diagnosis of major depression. Although major depression is a known risk factor for disability in older persons, few studies have examined the relationship between the two core symptoms of major depression and disability or mortality. Our objective was to examine the relationship between these two core symptoms and time to disability or death. METHODS: In a longitudinal cohort study, we used the nationally representative Health and Retirement Study to examine this relationship in 11,353 persons older than 62 years (mean: 73 years) followed for up to 13 years. Dysphoria and anhedonia were assessed with the Short Form Composite International Diagnostic Interview. Our outcome measure was time to either death or increased disability, defined as the new need for help in a basic activity of daily living. We adjusted for a validated disability risk index and other confounders. RESULTS: Compared with subjects without either dysphoria or anhedonia, the risk for disability or death was not elevated in elders with dysphoria without anhedonia (adjusted hazard ratio [HR]: 1.11; 95% confidence interval [CI]: 0.91-1.36). The risk was elevated in those with anhedonia without dysphoria (HR: 1.30; 95% CI: 1.06-1.60) and those with both anhedonia and dysphoria (HR: 1.28; 95% CI: 1.13-1.46). CONCLUSION: Our results highlight the need for clinicians to learn whether patients have lost interest in usually pleasurable activities, even if they deny sadness.
Keywords: Age Factors; Aged; Aged, 80 and over; Anhedonia; depression; Disabled Persons; Female; Humans; Interview, Psychological; Longitudinal Studies; Male; Middle Aged; Mortality; Risk Factors

Factors influencing the use of intensive procedures at the end of life. - Evan C Tschirhart; Qingling Du; Amy Kelley (J Am Geriatr Soc, 2014)
OBJECTIVES: To examine individual and regional factors associated with the use of intensive medical procedures in the last 6 months of life. DESIGN: Retrospective cohort study. SETTING: The Health and Retirement Study (HRS), a longitudinal nationally representative cohort of older adults. PARTICIPANTS: HRS decedents aged 66 and older (N = 3,069). MEASUREMENTS: Multivariable logistic regression was used to evaluate associations between individual and regional factors and receipt of five intensive procedures: intubation and mechanical ventilation, tracheostomy, gastrostomy tube insertion, enteral and parenteral nutrition, or cardiopulmonary resuscitation in the last 6 months of life. RESULTS: Approximately 18% of subjects (n = 546) underwent at least one intensive procedure in the last 6 months of life. Characteristics significantly associated with lower odds of an intensive procedure included aged 85-94 (vs 65-74, adjusted odds ratio (AOR) = 0.67, 95% confidence interval (CI) = 0.51-0.90), Alzheimer's disease (AOR = 0.71, 95% CI = 0.54-0.94), cancer (AOR = 0.60, 95% CI = 0.43-0.85), nursing home residence (AOR = 0.70, 95% CI = 0.50-0.97), and having an advance directive (AOR = 0.71, 95% CI = 0.57-0.89). In contrast, living in a region with higher hospital care intensity (AOR = 2.16, 95% CI = 1.48-3.13) and black race (AOR = 2.02, 95% CI = 1.52-2.69) each doubled one's odds of undergoing an intensive procedure. CONCLUSION: Individual characteristics and regional practice patterns are important determinants of intensive procedure use in the last 6 months of life. The effect of nonclinical factors highlights the need to better align treatments with individual preferences.
Keywords: Advance directives; Aged; Aged, 80 and over; Alzheimer disease; Cause of Death; Chronic disease; Critical Care; Female; Homes for the Aged; Humans; Life Support Care; Logistic Models; Male; Multivariate Analysis; Neoplasms; Nursing homes; Odds Ratio; Terminal Care; United States; Utilization Review

Fine particulate matter air pollution and cognitive function among older US adults. - Jennifer A Ailshire; Eileen M. Crimmins (Am J Epidemiol, 2014)
Existing research on the adverse health effects of exposure to pollution has devoted relatively little attention to the potential impact of ambient air pollution on cognitive function in older adults. We examined the cross-sectional association between residential concentrations of particulate matter with aerodynamic diameter of 2.5 μm or less (PM2.5) and cognitive function in older adults. Using hierarchical linear modeling, we analyzed data from the 2004 Health and Retirement Study, a large, nationally representative sample of US adults aged 50 years or older. We linked participant data with 2000 US Census tract data and 2004 census tract-level annual average PM2.5 concentrations. Older adults living in areas with higher PM2.5 concentrations had worse cognitive function (β = -0.26, 95% confidence interval: -0.47, -0.05) even after adjustment for community- and individual-level social and economic characteristics. Results suggest that the association is strongest for the episodic memory component of cognitive function. This study adds to a growing body of research highlighting the importance of air pollution to cognitive function in older adults. Improving air quality in large metropolitan areas, where much of the aging US population resides, may be an important mechanism for reducing age-related cognitive decline.
Ailshire, Jennifer A Crimmins, Eileen M eng K99 AG039528/AG/NIA NIH HHS/ K99AG039528/AG/NIA NIH HHS/ P30 AG017265/AG/NIA NIH HHS/ P30AG17265/AG/NIA NIH HHS/ R00 AG039528/AG/NIA NIH HHS/ R21 AG045625/AG/NIA NIH HHS/ T32 AG000037/AG/NIA NIH HHS/ T32AG0037/AG/NIA NIH HHS/ U01 AG009740/AG/NIA NIH HHS/ U01AG009740/AG/NIA NIH HHS/ Research Support, N.I.H., Extramural 2014/06/27 06:00 Am J Epidemiol. 2014 Aug 15;180(4):359-66. doi: 10.1093/aje/kwu155. Epub 2014 Jun 24.
Keywords: Aged; Aged, 80 and over; Cognition; Cognition Disorders; Cross-Sectional Studies; Female; Humans; Inhalation Exposure; Male; Memory, Episodic; Middle Aged; Neuropsychological tests; Particulate Matter; Socioeconomic factors; United States; Urban Population

Five-factor model personality traits and inflammatory markers: new data and a meta-analysis. - Martina Luchetti; James M Barkley; Yannick Stephan; Antonio Terracciano; Angelina R Sutin (Psychoneuroendocrinology, 2014)
The purpose of this research is to examine the association between five major dimensions of personality and systemic inflammation through (a) new data on C-reactive protein (CRP) from three large national samples of adults that together cover most of the adult lifespan and (b) a meta-analysis of published studies on CRP and interleukin-6 (IL-6). New data (total N=26,305) were drawn from the National Longitudinal Study of Adolescent Health, the Midlife in the United States study, and the Health and Retirement Study. PRISMA guidelines were used for the meta-analysis to combine results of up to seven studies on CRP (N=34,067) and six on IL-6 (N=7538). Across the three new samples, higher conscientiousness was associated with lower CRP. The conscientiousness-CRP relation was virtually identical controlling for smoking; controlling for body mass index attenuated this association but did not eliminate it. Compared to participants in the highest quartile of conscientiousness, participants in the lowest quartile had an up to 50% increased risk of CRP levels that exceeded the clinical threshold (≥3 mg/l). The meta-analysis supported the association between conscientiousness and both CRP and IL-6 and also suggested a negative association between openness and CRP; no associations were found for neuroticism, extraversion and agreeableness. The present work indicates a modest, but consistent, association between conscientiousness and a more favorable inflammatory profile, which may contribute to the role of conscientiousness in better health across the lifespan.
Keywords: Adult; Aged; Aged, 80 and over; Biomarkers; C-reactive protein; Female; Humans; Inflammation; Male; Middle Aged; Personality

Genetic susceptibility to accelerated cognitive decline in the US Health and Retirement Study. - Zhang, Chenan; Brandon L Pierce (Neurobiol Aging, 2014)
Age-related cognitive decline is a major public health concern facing a large segment of the US population. To identify genetic risk factors related to cognitive decline, we used nationally representative longitudinal data from the US Health and Retirement Study to conduct genome-wide association studies with 5765 participants of European ancestry, and 890 participants of African ancestry. Mixed effects models were used to derive cognitive decline phenotypes from data on repeated cognitive assessments and to perform single nucleotide polymorphism-based heritability estimation. We found 2 independent associations among European-Americans in the 19q13.32 region: rs769449 (APOE intron; p = 3.1 × 10(-20)) and rs115881343 (TOMM40 intron; p = 6.6 × 10(-11)). rs769449 was also associated with cognitive decline among African-Americans (p = 0.005), but rs115881343 was not. Cross-sectional cognitive function showed moderate heritability (15%-32%) across several age strata (50-59, 60-69, 70-79 years), but the cognitive decline heritability estimate was low (∼5%). These results indicate that despite multiple association signals for cognitive decline in the 19q13.32 region, inter-individual variation is likely influenced substantially by environmental factors.
Keywords: African Americans; Aged; Aged, 80 and over; Chromosomes, Human, Pair 9; Cognition; Cognition Disorders; Cross-Sectional Studies; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Membrane Transport Proteins; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; United States

Geographic variation in out-of-pocket expenditures of elderly Medicare beneficiaries. - Lena M. Chen; Edward C Norton; Kenneth M. Langa; Le, Sidney; Arnold M. Epstein (J Am Geriatr Soc, 2014)
OBJECTIVES: To examine whether out-of-pocket expenditures (OOPEs) exhibit the same geographic variation as Medicare claims, given wide variation in the costs of U.S. health care, but no information on how that translates into OOPEs or financial burden for older Americans. DESIGN: Retrospective cohort study. SETTING: Data from the Health and Retirement Study linked to Medicare claims. PARTICIPANTS: A nationally representative cohort of 4,657 noninstitutionalized, community-dwelling, fee-for-service elderly Medicare beneficiaries interviewed in 2006 and 2008. MEASUREMENTS: The primary predictor was per capita Medicare spending quintile according to hospital referral region. The primary outcome was a self-reported, validated measure of annual OOPEs excluding premiums. RESULTS: Mean and median adjusted per capita Medicare payments were $5,916 and $2,635, respectively; mean and median adjusted OOPEs were $1,525 and $779, respectively. Adjusted median Medicare payments were $3,474 in the highest cost quintile and $1,942 in the lowest cost quintile (ratio 1.79, P < .001 for difference). In contrast, adjusted median OOPEs were not higher in the highest than in the lowest Medicare cost quintile ($795 vs $764 for a Q5:Q1 ratio of 1.04, P = .42). The Q5:Q1 ratio was 1.48 for adjusted mean Medicare payments and 1.04 for adjusted mean OOPEs (both P < .001). CONCLUSION: Medicare payments vary widely between high- and low-cost regions, but OOPEs do not.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Geography; Health Care Costs; Health Expenditures; Humans; Male; Medicare; Retrospective Studies; United States

Heterogeneity in healthy aging. - David J Lowsky; S Jay Olshansky; Bhattacharya, Jay; Dana P Goldman (J Gerontol A Biol Sci Med Sci, 2014)
For a surprisingly large segment of the older population, chronological age is not a relevant marker for understanding, measuring, or experiencing healthy aging. Using the 2003 Medical Expenditure Panel Survey and the 2004 Health and Retirement Study to examine the proportion of Americans exhibiting five markers of health and the variation in health-related quality of life across each of eight age groups, we find that a significant proportion of older Americans is healthy within every age group beginning at age 51, including among those aged 85+. For example, 48% of those aged 51-54 and 28% of those aged 85+ have excellent or very good self-reported health status; similarly, 89% of those aged 51-54 and 56% of those aged 85+ report no health-based limitations in work or housework. Also, health-related quality of life ranges widely within every age group, yet there is only a comparatively small variation in median quality of life across age groups, suggesting that older Americans today may be experiencing substantially different age-health trajectories than their predecessors. Patterns are similar for medical expenditures. Several policy implications are explored.
Keywords: Aged; Aged, 80 and over; Aging; Female; Health Status; Humans; Male; Middle Aged; Population Surveillance; Quality of Life; Retrospective Studies; United States

Identifying diabetics in Medicare claims and survey data: implications for health services research. - Joseph W Sakshaug; David R Weir; Lauren Hersch Nicholas (BMC Health Serv Res, 2014)
BACKGROUND: Diabetes health services research often utilizes secondary data sources, including survey self-report and Medicare claims, to identify and study the diabetic population, but disagreement exists between these two data sources. We assessed agreement between the Chronic Condition Warehouse diabetes algorithm for Medicare claims and self-report measures of diabetes. Differences in healthcare utilization outcomes under each diabetes definition were also explored. METHODS: Claims data from the Medicare Beneficiary Annual Summary File were linked to survey and blood data collected from the 2006 Health and Retirement Study. A Hemoglobin A1c reading, collected on 2,028 respondents, was used to reconcile discrepancies between the self-report and Medicare claims measures of diabetes. T-tests were used to assess differences in healthcare utilization outcomes for each diabetes measure. RESULTS: The Chronic Condition Warehouse (CCW) algorithm yielded a higher rate of diabetes than respondent self-reports (27.3 vs. 21.2, p < 0.05). A1c levels of discordant claims-based diabetics suggest that these patients are not diabetic, however, they have high rates of healthcare spending and utilization similar to diabetics. CONCLUSIONS: Concordance between A1c and self-reports was higher than for A1c and the CCW algorithm. Accuracy of self-reports was superior to the CCW algorithm. False positives in the claims data have similar utilization profiles to diabetics, suggesting minimal bias in some types of claims-based analyses, though researchers should consider sensitivity analysis across definitions for health services research.
Keywords: Aged; Aged, 80 and over; Algorithms; Diabetes Mellitus; Female; Glycated Hemoglobin; Health Services Research; Humans; Insurance Claim Review; Male; Medicare; Prevalence; United States

Individualizing life expectancy estimates for older adults using the Gompertz Law of Human Mortality. - Sei J. Lee; W John Boscardin; Katharine A Kirby; Kenneth E Covinsky (PLoS One, 2014)
BACKGROUND: Guidelines recommend incorporating life expectancy (LE) into clinical decision-making for preventive interventions such as cancer screening. Previous research focused on mortality risk (e.g. 28% at 4 years) which is more difficult to interpret than LE (e.g. 7.3 years) for both patients and clinicians. Our objective was to utilize the Gompertz Law of Human Mortality which states that mortality risk doubles in a fixed time interval to transform the Lee mortality index into a LE calculator. METHODS: We examined community-dwelling older adults age 50 and over enrolled in the nationally representative 1998 wave of the Health and Retirement Study or HRS (response rate 81%), dividing study respondents into development (n = 11701) and validation (n = 8009) cohorts. In the development cohort, we fit proportional hazards Gompertz survival functions for each of the risk groups defined by the Lee mortality index. We validated our LE estimates by comparing our predicted LE with observed survival in the HRS validation cohort and an external validation cohort from the 2004 wave of the English Longitudinal Study on Ageing or ELSA (n = 7042). RESULTS: The ELSA cohort had a lower 8-year mortality risk (14%) compared to our HRS development (23%) and validation cohorts (25%). Our model had good discrimination in the validation cohorts (Harrell's c 0.78 in HRS and 0.80 in the ELSA). Our predicted LE's were similar to observed survival in the HRS validation cohort without evidence of miscalibration (Hosmer-Lemeshow, p = 0.2 at 8 years). However, our predicted LE's were longer than observed survival in the ELSA cohort with evidence of miscalibration (Hosmer-Lemeshow, p<0.001 at 8 years) reflecting the lower mortality rate in ELSA. CONCLUSION: We transformed a previously validated mortality index into a LE calculator that incorporated patient-level risk factors. Our LE calculator may help clinicians determine which preventive interventions are most appropriate for older US adults.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Female; Humans; Life Expectancy; Longevity; Longitudinal Studies; Male; Middle Aged; Mortality; Proportional Hazards Models; Risk Factors

An investigation of activity profiles of older adults. - Morrow-Howell, Nancy; Putnam, Michelle; Lee, Yung Soo; Jennifer C. Greenfield; Inoue, Megumi; Chen, Huajuan (J Gerontol B Psychol Sci Soc Sci, 2014)
OBJECTIVES: In this study, we advance knowledge about activity engagement by considering many activities simultaneously to identify profiles of activity among older adults. Further, we use cross-sectional data to explore factors associated with activity profiles and prospective data to explore activity profiles and well-being outcomes. METHOD: We used the core survey data from the years 2008 and 2010, as well as the 2009 Health and Retirement Study Consumption and Activities Mail Survey (HRS CAMS). The HRS CAMS includes information on types and amounts of activities. We used factor analysis and latent class analysis to identify activity profiles and regression analyses to assess antecedents and outcomes associated with activity profiles. RESULTS: We identified 5 activity profiles: Low Activity, Moderate Activity, High Activity, Working, and Physically Active. These profiles varied in amount and type of activities. Demographic and health factors were related to profiles. Activity profiles were subsequently associated with self-rated health and depression symptoms. DISCUSSION: The use of a 5-level categorical activity profile variable may allow more complex analyses of activity that capture the "whole person." There is clearly a vulnerable group of low-activity individuals as well as a High Activity group that may represent the "active ageing" vision.
Keywords: Aged; Aged, 80 and over; Aging; Black or African American; Cohort Studies; Cross-Sectional Studies; Employment; Female; Florida; Health Surveys; Hispanic or Latino; Human Activities; Humans; Male; Middle Aged; Models, Psychological; Motor Activity; Prospective Studies; Regression Analysis; United States

Longitudinal predictors of self-rated health and mortality in older adults. - Diane C Wagner; Jerome L Short (Prev Chronic Dis, 2014)
INTRODUCTION: Few studies have compared the effects of demographic, cognitive, and behavioral factors of health and mortality longitudinally. We examined predictors of self-rated health and mortality at 3 points, each 2 years apart, over 4 years. METHODS: We used data from the 2006 wave of the Health and Retirement Study and health and mortality indicators from 2006, 2008, and 2010. We analyzed data from 17,930 adults (aged 50-104 y) to examine predictors of self-rated health and data from a subgroup of 1,171 adults who died from 2006 through 2010 to examine predictors of mortality. RESULTS: Time 1 depression was the strongest predictor of self-rated health at all points, independent of age and education. Education, mild activities, body mass index, delayed word recall, and smoking were all associated with self-rated health at each point and predicted mortality. Delayed word recall mediated the relationships of mild activity with health and mortality. Bidirectional mediation was found for the effects of mild activity and depression on health. CONCLUSION: Medical professionals should consider screening for depression and memory difficulties in addition to conducting medical assessments. These assessments could lead to more effective biopsychosocial interventions to help older adults manage risks for mortality.
Keywords: Age Factors; Aged; Aged, 80 and over; Body Mass Index; Chronic disease; depression; Educational Status; Female; Health Behavior; Health Status Indicators; Humans; Longitudinal Studies; Male; Mental Recall; Middle Aged; Proportional Hazards Models; Psychometrics; Retirement; Self Report; Survival Analysis; United States

Neuropsychiatric disorders and potentially preventable hospitalizations in a prospective cohort study of older Americans. - Dimitry S Davydow; Zivin, Kara; Wayne J Katon; Gregory M Pontone; Lydia Chwastiak; Kenneth M. Langa; Theodore J Iwashyna (J Gen Intern Med, 2014)
BACKGROUND: The relative contributions of depression, cognitive impairment without dementia (CIND), and dementia to the risk of potentially preventable hospitalizations in older adults are not well understood. OBJECTIVE(S): To determine if depression, CIND, and/or dementia are each independently associated with hospitalizations for ambulatory care-sensitive conditions (ACSCs) and rehospitalizations within 30 days after hospitalization for pneumonia, congestive heart failure (CHF), or myocardial infarction (MI). DESIGN: Prospective cohort study. PARTICIPANTS: Population-based sample of 7,031 Americans > 50 years old participating in the Health and Retirement Study (1998-2008). MAIN MEASURES: The eight-item Center for Epidemiologic Studies Depression Scale and/or International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) depression diagnoses were used to identify baseline depression. The Modified Telephone Interview for Cognitive Status and/or ICD-9-CM dementia diagnoses were used to identify baseline CIND or dementia. Primary outcomes were time to hospitalization for an ACSC and presence of a hospitalization within 30 days after hospitalization for pneumonia, CHF, or MI. KEY RESULTS: All five categories of baseline neuropsychiatric disorder status were independently associated with increased risk of hospitalization for an ACSC (depression alone: Hazard Ratio [HR]: 1.33, 95% Confidence Interval [95%CI]: 1.18, 1.52; CIND alone: HR: 1.25, 95%CI: 1.10, 1.41; dementia alone: HR: 1.32, 95%CI: 1.12, 1.55; comorbid depression and CIND: HR: 1.43, 95%CI: 1.20, 1.69; comorbid depression and dementia: HR: 1.66, 95%CI: 1.38, 2.00). Depression (Odds Ratio [OR]: 1.37, 95%CI: 1.01, 1.84), comorbid depression and CIND (OR: 1.98, 95%CI: 1.40, 2.81), or comorbid depression and dementia (OR: 1.58, 95%CI: 1.06, 2.35) were independently associated with increased odds of rehospitalization within 30 days after hospitalization for pneumonia, CHF, or MI. CONCLUSIONS: Depression, CIND, and dementia are each independently associated with potentially preventable hospitalizations in older Americans. Older adults with comorbid depression and cognitive impairment represent a particularly at-risk group that could benefit from targeted interventions.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Cohort Studies; Dementia; depression; Female; Hospitalization; Humans; Male; Mental Disorders; Prospective Studies; Risk Factors; United States

Obesity and 1-year outcomes in older Americans with severe sepsis. - Hallie C Prescott; Virginia W Chang; James M. O'Brien Jr; Kenneth M. Langa; Theodore J Iwashyna (Crit Care Med, 2014)
OBJECTIVES: Although critical care physicians view obesity as an independent poor prognostic marker, growing evidence suggests that obesity is, instead, associated with improved mortality following ICU admission. However, this prior empirical work may be biased by preferential admission of obese patients to ICUs, and little is known about other patient-centered outcomes following critical illness. We sought to determine whether 1-year mortality, healthcare utilization, and functional outcomes following a severe sepsis hospitalization differ by body mass index. DESIGN: Observational cohort study. SETTING: U.S. hospitals. PATIENTS: We analyzed 1,404 severe sepsis hospitalizations (1999-2005) among Medicare beneficiaries enrolled in the nationally representative Health and Retirement Study, of which 597 (42.5%) were normal weight, 473 (33.7%) were overweight, and 334 (23.8%) were obese or severely obese, as assessed at their survey prior to acute illness. Underweight patients were excluded a priori. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Using Medicare claims, we identified severe sepsis hospitalizations and measured inpatient healthcare facility use and calculated total and itemized Medicare spending in the year following hospital discharge. Using the National Death Index, we determined mortality. We ascertained pre- and postmorbid functional status from survey data. Patients with greater body mass indexes experienced lower 1-year mortality compared with nonobese patients, and there was a dose-response relationship such that obese (odds ratio = 0.59; 95% CI, 0.39-0.88) and severely obese patients (odds ratio = 0.46; 95% CI, 0.26-0.80) had the lowest mortality. Total days in a healthcare facility and Medicare expenditures were greater for obese patients (p < 0.01 for both comparisons), but average daily utilization (p = 0.44) and Medicare spending were similar (p = 0.65) among normal, overweight, and obese survivors. Total function limitations following severe sepsis did not differ by body mass index category (p = 0.64). CONCLUSIONS: Obesity is associated with improved mortality among severe sepsis patients. Due to longer survival, obese sepsis survivors use more healthcare and result in higher Medicare spending in the year following hospitalization. Median daily healthcare utilization was similar across body mass index categories.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Comorbidity; Critical Illness; Delivery of Health Care; Female; Health Expenditures; Hospitalization; Humans; Male; Medicare; Middle Aged; Obesity; Sepsis; Survival Rate; Survivors; United States

Perceived neighbourhood social cohesion and myocardial infarction. - Eric S Kim; Armani M. Hawes; Jacqui Smith (J Epidemiol Community Health, 2014)
BACKGROUND: The main strategy for alleviating heart disease has been to target individuals and encourage them to change their health behaviours. Although important, emphasis on individuals has diverted focus and responsibility away from neighbourhood characteristics, which also strongly influence people's behaviours. Although a growing body of research has repeatedly demonstrated strong associations between neighbourhood characteristics and cardiovascular health, it has typically focused on negative neighbourhood characteristics. Only a few studies have examined the potential health enhancing effects of positive neighbourhood characteristics, such as perceived neighbourhood social cohesion. METHODS: Using multiple logistic regression models, we tested whether higher perceived neighbourhood social cohesion was associated with lower incidence of myocardial infarction. Prospective data from the Health and Retirement Study--a nationally representative panel study of American adults over the age of 50--were used to analyse 5276 participants with no history of heart disease. Respondents were tracked for 4 years and analyses adjusted for relevant sociodemographic, behavioural, biological and psychosocial factors. RESULTS: In a model that adjusted for age, gender, race, marital status, education and total wealth, each SD increase in perceived neighbourhood social cohesion was associated with a 22% reduced odds of myocardial infarction (OR=0.78, 95% CI 0.63 to 0.94. The association between perceived neighbourhood social cohesion and myocardial infarction remained even after adjusting for behavioural, biological and psychosocial covariates. CONCLUSIONS: Higher perceived neighbourhood social cohesion may have a protective effect against myocardial infarction.
Keywords: Aged; Aged, 80 and over; Confounding Factors, Epidemiologic; Female; Health Behavior; Health Status; Health Surveys; Humans; Incidence; Interviews as Topic; Male; Mental Health; Middle Aged; Multilevel Analysis; Myocardial Infarction; Perception; Prospective Studies; Protective factors; Residence Characteristics; Self Report; Social Environment; Socioeconomic factors; United States

A polygenic risk score associated with measures of depressive symptoms among older adults. - Morgan E. Levine; Eileen M. Crimmins; Carol A Prescott; Drystan F. Phillips; Thalida E. Arpawong; Jinkook Lee (Biodemography Soc Biol, 2014)
It has been suggested that depression is a polygenic trait, arising from the influences of multiple loci with small individual effects. The aim of this study is to generate a polygenic risk score (PRS) to examine the association between genetic variation and depressive symptoms. Our analytic sample included N = 10,091 participants aged 50 and older from the Health and Retirement Study (HRS). Depressive symptoms were measured by Center for Epidemiological Studies-Depression scale (CESD) scores assessed on up to nine occasions across 18 years. We conducted a genome-wide association analysis for a discovery set (n = 7,000) and used the top 11 single-nucleotide polymorphisms, all with p < 10(-5) to generate a weighted PRS for our replication sample (n = 3,091). Results showed that the PRS was significantly associated with mean CESD score in the replication sample (β = .08, p = .002). The R(2) change for the inclusion of the PRS was .003. Using a multinomial logistic regression model, we also examined the association between genetic risk and chronicity of high (4+) CESD scores. We found that a one-standard-deviation increase in PRS was associated with a 36 percent increase in the odds of having chronically high CESD scores relative to never having had high CESD scores. Our findings are consistent with depression being a polygenic trait and suggest that the cumulative influence of multiple variants increases an individual's susceptibility for chronically experiencing high levels of depressive symptoms.
Keywords: Aged; Aged, 80 and over; Depressive Disorder, Major; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Multifactorial Inheritance; Odds Ratio; Risk Factors

Preparedness for natural disasters among older US adults: a nationwide survey. - Tala M. Al-rousan; Linda M. Rubenstein; Robert B Wallace (Am J Public Health, 2014)
OBJECTIVES: We sought to determine natural disaster preparedness levels among older US adults and assess factors that may adversely affect health and safety during such incidents. METHODS: We sampled adults aged 50 years or older (n = 1304) from the 2010 interview survey of the Health and Retirement Study. The survey gathered data on general demographic characteristics, disability status or functional limitations, and preparedness-related factors and behaviors. We calculated a general disaster preparedness score by using individual indicators to assess overall preparedness. RESULTS: Participant (n = 1304) mean age was 70 years (SD = 9.3). Only 34.3% reported participating in an educational program or reading materials about disaster preparation. Nearly 15% reported using electrically powered medical devices that might be at risk in a power outage. The preparedness score indicated that increasing age, physical disability, and lower educational attainment and income were independently and significantly associated with worse overall preparedness. CONCLUSIONS: Despite both greater vulnerability to disasters and continuous growth in the number of older US adults, many of the substantial problems discovered are remediable and require attention in the clinical, public health, and emergency management sectors of society.
Keywords: Aged; Aged, 80 and over; Disaster Planning; Female; Humans; Male; Middle Aged; Surveys and Questionnaires; United States

Prospective study of the association between dispositional optimism and incident heart failure. - Eric S Kim; Jacqui Smith; Laura D Kubzansky (Circ Heart Fail, 2014)
BACKGROUND: Although higher optimism has been linked with an array of positive health behaviors, biological processes, and cardiovascular outcomes, the relationship between optimism and heart failure has not been examined. In the United States, 80% of heart failures occur in adults aged 65+ years. Therefore, we examined whether higher optimism was linked with a reduced incidence of heart failure among older adults. METHODS AND RESULTS: Prospective data were from the Health and Retirement Study, a nationally representative study of older US adults. Our sample included 6808 participants who were followed for 4 years. Multiple logistic regression models were used to assess whether optimism was independently associated with incident heart failure. We adjusted for sociodemographic, behavioral, biological, and psychological covariates. Higher optimism was associated with a lower risk of incident heart failure during the follow-up period. In a model that adjusted for sociodemographic factors, each SD increase in optimism had an odds ratio of 0.74 (95% confidence interval, 0.63-0.85) for heart failure. Effects of optimism persisted even after adjusting for a wide range of covariates. There was also evidence of a dose-response relationship. As optimism increased, risk of developing heart failure decreased monotonically, with a 48% reduced odds among people with the highest versus lowest optimism. CONCLUSIONS: This is the first study to suggest that optimism is associated with a lower risk of heart failure. If future studies confirm these findings, they may be used to inform new strategies for preventing or delaying the onset of heart failure.
Keywords: Affect; Aged; Aged, 80 and over; Emotions; Female; Heart Failure; Humans; Incidence; Logistic Models; Male; Middle Aged; Outcome Assessment, Health Care; Prospective Studies; Retrospective Studies; Risk Factors; Socioeconomic factors; United States

Purpose in life and use of preventive health care services. - Eric S Kim; Victor J Strecher; Carol D Ryff (Proc Natl Acad Sci U S A, 2014)
Purpose in life has been linked with better health (mental and physical) and health behaviors, but its link with patterns of health care use are understudied. We hypothesized that people with higher purpose would be more proactive in taking care of their health, as indicated by a higher likelihood of using preventive health care services. We also hypothesized that people with higher purpose would spend fewer nights in the hospital. Participants (n = 7,168) were drawn from the Health and Retirement Study, a nationally representative panel study of American adults over the age of 50, and tracked for 6 y. After adjusting for sociodemographic factors, each unit increase in purpose (on a six-point scale) was associated with a higher likelihood that people would obtain a cholesterol test [odds ratio (OR) = 1.18, 95% confidence interval (CI) = 1.08-1.29] or colonoscopy (OR = 1.06, 95% CI = 0.99-1.14). Furthermore, females were more likely to receive a mammogram/X-ray (OR = 1.27, 95% CI = 1.16-1.39) or pap smear (OR = 1.16, 95% CI = 1.06-1.28), and males were more likely to receive a prostate examination (OR = 1.31, 95% CI = 1.18-1.45). Each unit increase in purpose was also associated with 17% fewer nights spent in the hospital (rate ratio = 0.83, 95% CI = 0.77-0.89). An increasing number of randomized controlled trials show that purpose in life can be raised. Therefore, with additional research, findings from this study may inform the development of new strategies that increase the use of preventive health care services, offset the burden of rising health care costs, and enhance the quality of life among people moving into the ranks of our aging society.
Keywords: Aged; Aged, 80 and over; Early Detection of Cancer; Educational Status; ethnicity; Female; Habits; Hematologic Tests; Hospitalization; Humans; Influenza Vaccines; Insurance Coverage; Male; Marital Status; Middle Aged; Models, Psychological; Motivation; Patient Acceptance of Health Care; Preventive Health Services; Surveys and Questionnaires; Vaccination

Satisfaction with aging and use of preventive health services. - Eric S Kim; Kyle D Moored; Hannah L. Giasson; Jacqui Smith (Prev Med, 2014)
OBJECTIVE: Preventive health service use is relatively low among older age groups. We hypothesized that aging satisfaction would be associated with increased use of preventive health services four years later. METHOD: We conducted multiple logistic regression analyses on a sample of 6177 people from the Health and Retirement Study, a nationally representative study of U.S. adults over the age of 50 (M age=70.6; women n=3648; men n=2529). RESULTS: Aging satisfaction was not associated with obtaining flu shots. However, in fully-adjusted models, each standard deviation increase in aging satisfaction was associated with higher odds of reporting service use for cholesterol tests (OR=1.10, 95% CI=1.00-1.20). Further, women with higher aging satisfaction were more likely to obtain a mammogram/x-ray (OR=1.17, 95% CI=1.06-1.29) or Pap smear (OR=1.10, 95% CI=1.00-1.21). Among men, the odds of obtaining a prostate exam increased with higher aging satisfaction (OR=1.20 95% CI=1.09-1.34). CONCLUSION: These results suggest that aging satisfaction potentially influences preventive health service use after age 50.
Keywords: Aged; Aged, 80 and over; Aging; Chronic disease; Female; Health Behavior; Health Knowledge, Attitudes, Practice; Humans; Influenza Vaccines; Logistic Models; Male; Mammography; Middle Aged; Patient Acceptance of Health Care; Patient Satisfaction; Personal Satisfaction; Preventive Health Services; Prostatic Neoplasms; Surveys and Questionnaires; United States; Vaginal Smears

Self-rated health changes and oldest-old mortality. - Eric M Vogelsang (J Gerontol B Psychol Sci Soc Sci, 2014)
OBJECTIVES: This study explores how 2 measures of self-rated health (SRH) change are related to mortality among oldest-old adults. In doing so, it also considers how associations between SRH and mortality may depend on prior SRH. METHOD: Data come from the Asset and Health Dynamics survey--the oldest-old portion of the Health and Retirement Study-and follow 6,233 individuals across 13 years. I use parametric hazard models to examine relationships between death and 2 measures of short-term SRH change--a computed measure comparing SRH at time t-1 and t, and a respondent-provided retrospectively reported change. RESULTS: Respondents who demonstrate or report any SRH change between survey waves died at a greater rate than those with consistent SRH. After controlling for morbidity, individual characteristics, and SRH, those who changed SRH categories between survey waves and those who retrospectively reported an improvement in health continue to have a greater risk of death, when compared with those with no change. DISCUSSION: These findings suggest that the well-established associations between SRH status and mortality may understate the risk of death for oldest-old individuals with recent subjective health improvements.
Keywords: Aged; Aged, 80 and over; Diagnostic Self Evaluation; Female; Health Status; Humans; Longitudinal Studies; Male; Mortality; Proportional Hazards Models; Randomized Controlled Trials as Topic; Risk; United States

Self-rated health in the last 12 years of life compared to matched surviving controls: the Health and Retirement Study. - Stenholm, Sari; Pentti, Jaana; Ichiro Kawachi; Westerlund, Hugo; Mika Kivimäki; Vahtera, Jussi (PLoS One, 2014)
Self-rated health (SRH) is a valid measure of health status and associated with mortality. Based on individual-level biannual repeat data on SRH we sought to characterize the natural history of poor SRH during the 12 years prior to death in men and women in different age groups. We conducted a retrospective analysis of the Health and Retirement Study participants who died between 1998 and 2010 and had at least two SRH measurements in the 12 years prior to death. We used a nested case-control design to compare SRH trajectories of deceased men and women aged 30-64, 65-79 and 80 years versus surviving participants. The cases comprised 3,350 deceased participants who were matched to surviving controls (n = 8,127). SRH was dichotomized into good vs. poor health. Men and women dying at age 65-79 and ≥ 80 years had 1.5 to 3 times higher prevalence of poor SRH already 11-12 years prior to death compared to surviving controls. The risk estimates remained statistically significant even after adjusting for life-style related risk factors and diagnosed diseases. Prevalence of poor SRH before death was lowest among those aged ≥ 80 years and highest in 30-64 year-olds. In conclusion, men and women who subsequently die perceive their health worse already 11-12 years prior to death compared to their surviving controls.
Keywords: Adult; Aged; Aged, 80 and over; Diagnostic Self Evaluation; Female; health; Health Status; Humans; Life Style; Male; Middle Aged; Mortality; Retirement; Retrospective Studies

Social relationships, leisure activity, and health in older adults. - Chang, Po-Ju; Linda A. Wray; Lin, Yeqiang (Health Psychol, 2014)
OBJECTIVE: Although the link between enhanced social relationships and better health has generally been well established, few studies have examined the role of leisure activity in this link. This study examined how leisure influences the link between social relationships and health in older age. METHOD: Using data from the 2006 and 2010 waves of the nationally representative U.S. Health and Retirement Study and structural equation modeling analyses, we examined data on 2,965 older participants to determine if leisure activities mediated the link between social relationships and health in 2010, controlling for race, education level, and health in 2006. RESULTS: The results demonstrated that leisure activities mediate the link between social relationships and health in these age groups. Perceptions of positive social relationships were associated with greater involvement in leisure activities, and greater involvement in leisure activities was associated with better health in older age. CONCLUSION: The contribution of leisure to health in these age groups is receiving increasing attention, and the results of this study add to the literature on this topic, by identifying the mediating effect of leisure activity on the link between social relationships and health. Future studies aimed at increasing leisure activity may contribute to improved health outcomes in older adults.
Keywords: Aged; Aged, 80 and over; Female; Health Status; Humans; Interpersonal Relations; Leisure activities; Longitudinal Studies; Male; Middle Aged; United States

Validation of a polygenic risk score for dementia in black and white individuals. - Jessica R Marden; Stefan Walter; Eric J. Tchetgen Tchetgen; Ichiro Kawachi; M. Maria Glymour (Brain Behav, 2014)
OBJECTIVE: To determine whether a polygenic risk score for Alzheimer's disease (AD) predicts dementia probability and memory functioning in non-Hispanic black (NHB) and non-Hispanic white (NHW) participants from a sample not used in previous genome-wide association studies. METHODS: Non-Hispanic white and NHB Health and Retirement Study (HRS) participants provided genetic information and either a composite memory score (n = 10,401) or a dementia probability score (n = 7690). Dementia probability score was estimated for participants' age 65+ from 2006 to 2010, while memory score was available for participants age 50+. We calculated AD genetic risk scores (AD-GRS) based on 10 polymorphisms confirmed to predict AD, weighting alleles by beta coefficients reported in AlzGene meta-analyses. We used pooled logistic regression to estimate the association of the AD-GRS with dementia probability and generalized linear models to estimate its effect on memory score. RESULTS: Each 0.10 unit change in the AD-GRS was associated with larger relative effects on dementia among NHW aged 65+ (OR = 2.22; 95% CI: 1.79, 2.74; P < 0.001) than NHB (OR=1.33; 95% CI: 1.00, 1.77; P = 0.047), although additive effect estimates were similar. Each 0.10 unit change in the AD-GRS was associated with a -0.07 (95% CI: -0.09, -0.05; P < 0.001) SD difference in memory score among NHW aged 50+, but no significant differences among NHB (β = -0.01; 95% CI: -0.04, 0.01; P = 0.546). [Correction added on 29 July 2014, after first online publication: confidence intervalshave been amended.] The estimated effect of the GRS was significantly smaller among NHB than NHW (P < 0.05) for both outcomes. CONCLUSION: This analysis provides evidence for differential relative effects of the GRS on dementia probability and memory score among NHW and NHB in a new, national data set.
Keywords: African Americans; Aged; Aged, 80 and over; Dementia; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Multifactorial Inheritance; Polymorphism, Genetic; Reproducibility of Results; Risk Assessment; Risk Factors; Surveys and Questionnaires; United States

Why do older people change their ratings of childhood health? - Vuolo, Mike; Kenneth F Ferraro; Patricia M Morton; Ting-Ying Yang (Demography, 2014)
A growing number of studies in life course epidemiology and biodemography make use of a retrospective question tapping self-rated childhood health to assess overall physical health status. Analyzing repeated measures of self-rated childhood health from the Health and Retirement Study (HRS), this study examines several possible explanations for why respondents might change their ratings of childhood health. Results reveal that nearly one-half of the sample revised their rating of childhood health during the 10-year observation period. Whites and relatively advantaged older adults-those with more socioeconomic resources and better memory-were less likely to revise their rating of childhood health, while those who experienced multiple childhood health problems were more likely to revise their childhood health rating, either positively or negatively. Changes in current self-rated health and several incident physical health problems were also related to the revision of one's rating of childhood health, while the development of psychological disorders was associated with more negative revised ratings. We then illustrate the impact that these changes may have on an adult outcomes: namely, depressive symptoms. Whereas adult ratings of childhood health are likely to change over time, we recommend their use only if adjusting for factors associated with these changes, such as memory, psychological disorder, adult self-rated health, and socioeconomic resources.
Keywords: Adaptation, Psychological; Age Factors; Aged; Aged, 80 and over; Aging; Female; Health Status; Humans; Male; Memory; Middle Aged; Retrospective Studies; Self Report; Sex Factors; Socioeconomic factors

Advance care planning and the quality of end-of-life care in older adults. - Bischoff, Kara E; Rebecca L. Sudore; Yinghui Miao; W John Boscardin; Alexander K Smith (J Am Geriatr Soc, 2013)
OBJECTIVES: To determine whether advance care planning influences quality of end-of-life care. DESIGN: In this observational cohort study, Medicare data and survey data from the Health and Retirement Study (HRS) were combined to determine whether advance care planning was associated with quality metrics. SETTING: The nationally representative HRS. PARTICIPANTS: Four thousand three hundred ninety-nine decedent subjects (mean age 82.6 at death, 55% women). MEASUREMENTS: Advance care planning (ACP) was defined as having an advance directive (AD), durable power of attorney (DPOA) or having discussed preferences for end-of-life care with a next of kin. Outcomes included previously reported quality metrics observed during the last month of life (rates of hospital admission, in-hospital death, >14 days in the hospital, intensive care unit admission, >1 emergency department visit, hospice admission, and length of hospice ≤ 3 days). RESULTS: Seventy-six percent of subjects engaged in ACP. Ninety-two percent of ADs stated a preference to prioritize comfort. After adjustment, subjects who engaged in ACP were less likely to die in a hospital (adjusted relative risk (aRR) = 0.87, 95% confidence interval (CI) = 0.80-0.94), more likely to be enrolled in hospice (aRR = 1.68, 95% CI = 1.43-1.97), and less likely to receive hospice for 3 days or less before death (aRR = 0.88, 95% CI = 0.85-0.91). Having an AD, a DPOA or an ACP discussion were each independently associated with a significant increase in hospice use (P < .01 for all). CONCLUSION: ACP was associated with improved quality of care at the end of life, including less in-hospital death and increased use of hospice. Having an AD, assigning a DPOA and conducting ACP discussions are all important elements of ACP.
Keywords: Adaptation, Psychological; Advance care planning; Aged, 80 and over; Female; Humans; Male; Quality of Life; Terminal Care; United States

The apolipoprotein E genotype predicts longitudinal transitions to mild cognitive impairment but not to Alzheimer's dementia: findings from a nationally representative study. - Brainerd, C. J.; V. F. Reyna; Ronald C Petersen; Glenn E Smith; Kenney, A. E.; C. J. Gross; Taub, E. S.; Brenda L Plassman; Gwenith G Fisher (Neuropsychology, 2013)
OBJECTIVE: The ε4 allele of the apolipoprotein E (APOE) genotype is the most widely accepted genetic risk factor for Alzheimer's dementia (AD), but findings on whether it is a risk factor for the AD prodrome, mild cognitive impairment (MCI), have been inconsistent. In a prospective longitudinal design, we investigated (a) whether transitions to MCI and other forms of neurocognitive impairment without dementia (CIND) are more frequent among normal ε4 carriers than among noncarriers and (b) whether subsequent transitions to AD from MCI and from other forms of CIND are more frequent among ε4 carriers than among noncarriers. METHOD: The frequency of the ε4 allele was studied in older adults (mean age > 70), who had participated in two or more waves of neuropsychological testing and diagnosis in the Aging, Demographics, and Memory Study (ADAMS) of the United States Department of Health and Human Services, National Institutes of Health, National Institute on Aging's Health and Retirement Study, conducted by the University of Michigan. The association between ε4 and longitudinal transitions to specific types of CIND and dementia can be determined with this data set. RESULTS: Epsilon 4 increased the rate of progression from normal functioning to MCI (58% of new diagnoses were carriers) but not to other forms of CIND. The rate of progression to AD from MCI or from other forms of CIND was not increased by ε4. CONCLUSIONS: The results support the hypothesis that ε4 is a risk factor for transitions from normal functioning to MCI but not for subsequent transitions to AD. In the ADAMS sample, the reason ε4 is elevated in AD individuals is because it is already elevated in MCI individuals, who are the primary source of new AD diagnoses.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Apolipoproteins E; Cognitive Dysfunction; disease progression; Female; Genetic Predisposition to Disease; Genetic Testing; Genotype; Humans; Logistic Models; Longitudinal Studies; Male; National Institutes of Health (U.S.); Neuropsychological tests; Risk Factors; United States

Chiropractic use and changes in health among older medicare beneficiaries: a comparative effectiveness observational study. - Paula A Weigel; Jason Hockenberry; Suzanne E Bentler; Frederic D Wolinsky (J Manipulative Physiol Ther, 2013)
OBJECTIVE: The purpose of this study was to investigate the effect of chiropractic on 5 outcomes among Medicare beneficiaries: increased difficulties performing activities of daily living (ADLs), instrumental ADLs (IADLs), and lower body functions, as well as lower self-rated health and increased depressive symptoms. METHODS: Among all beneficiaries, we estimated the effect of chiropractic use on changes in health outcomes among those who used chiropractic compared with those who did not, and among beneficiaries with back conditions, we estimated the effect of chiropractic use relative to medical care, both during a 2- to 15-year period. Two analytic approaches were used--one assumed no selection bias, whereas the other adjusted for potential selection bias using propensity score methods. RESULTS: Among all beneficiaries, propensity score analyses indicated that chiropractic use led to comparable outcomes for ADLs, IADLs, and depressive symptoms, although there were increased risks associated with chiropractic for declines in lower body function and self-rated health. Propensity score analyses among beneficiaries with back conditions indicated that chiropractic use led to comparable outcomes for ADLs, IADLs, lower body function, and depressive symptoms, although there was an increased risk associated with chiropractic use for declines in self-rated health. CONCLUSION: The evidence in this study suggests that chiropractic treatment has comparable effects on functional outcomes when compared with medical treatment for all Medicare beneficiaries, but increased risk for declines in self-rated health among beneficiaries with back conditions.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Databases, Factual; Disability Evaluation; Female; Geriatric Assessment; Humans; Low Back Pain; Male; Manipulation, Chiropractic; Medicare; Mobility Limitation; Musculoskeletal Diseases; Patient Satisfaction; Quality of Life; Risk Assessment; Sex Factors; Treatment Outcome; United States

Cohorts based on decade of death: no evidence for secular trends favoring later cohorts in cognitive aging and terminal decline in the AHEAD study. - Hülür, Gizem; Frank J Infurna; Ram, Nilam; Denis Gerstorf (Psychol Aging, 2013)
Studies of birth-year cohorts examined over the same age range often report secular trends favoring later-born cohorts, who are cognitively fitter and show less steep cognitive declines than earlier-born cohorts. However, there is initial evidence that those advantages of later-born cohorts do not carry into the last years of life, suggesting that pervasive mortality-related processes minimize differences that were apparent earlier in life. Elaborating this work from an alternative perspective on cohort differences, we compared rates of cognitive aging and terminal decline in episodic memory between cohorts based on the year participants had died, earlier (between 1993 and 1999) or later in historical time (between 2000 and 2010). Specifically, we compared trajectories of cognitive decline in 2 death-year cohorts of participants in the Asset and Health Dynamics Among the Oldest Old study that were matched on age at death and education and controlled for a variety of additional covariates. Results revealed little evidence of secular trends favoring later cohorts. To the contrary, the cohort that died in the 2000s showed a less favorable trajectory of age-related memory decline than the cohort that died in the 1990s. In examinations of change in relation to time to death, the cohort dying in the 2000s experienced even steeper terminal declines than the cohort dying in the 1990s. We suggest that secular increases in "manufacturing" survival may exacerbate age- and mortality-related cognitive declines among the oldest old.
Keywords: Aged; Aged, 80 and over; Aging; Death; Epidemiologic Research Design; Female; Health Surveys; Humans; Longitudinal Studies; Male; Memory Disorders; Memory, Episodic; Time Factors; United States

Disability during the last two years of life. - Alexander K Smith; Louise C Walter; Yinghui Miao; W John Boscardin; Kenneth E Covinsky (JAMA Intern Med, 2013)
IMPORTANCE: Whereas many persons at advanced ages live independently and are free of disability, we know little about how likely older people are to be disabled in the basic activities of daily living that are necessary for independent living as they enter the last years of life. OBJECTIVE: To determine national estimates of disability during the last 2 years of life. DESIGN: Prospective cohort study. SETTING: A nationally representative study of older adults in the United States. PARTICIPANTS: Participants 50 years and older who died while enrolled in the Health and Retirement Study between 1995 and 2010. Each participant was interviewed once at a varying time point in the last 24 months of life. We used these interviews to calculate national estimates of the prevalence of disability across the 2 years prior to death. We modeled the prevalence of disability in the 2 years prior to death for groups defined by age at death and sex. MAIN OUTCOMES AND MEASURES: Disability was defined as need for help with at least 1 of the following activities of daily living: dressing, bathing, eating, transferring, walking across the room, and using the toilet. RESULTS: There were 8232 decedents (mean [SD] age at death, 79 [11] years; 52% women). The prevalence of disability increased from 28% (95% CI, 24%-31%) 2 years before death to 56% (95% CI, 52%-60%) in the last month of life. Those who died at the oldest ages were much more likely to have disability 2 years before death (ages 50-69 years, 14%; 70-79 years, 21%; 80-89 years, 32%; 90 years or more, 50%; P for trend, <.001). Disability was more common in women 2 years before death (32% [95% CI, 28%-36%]) than men (21% [95% CI, 18%-25%]; P < .001), even after adjustment for older age at death. CONCLUSIONS AND RELEVANCE: Those who live to an older age are likely to be disabled, and thus in need of caregiving assistance, many months or years prior to death. Women have a substantially longer period of end-of-life disability than men.
Copyright - Copyright American Medical Association Sep 9, 2013 Last updated - 2013-09-18 SubjectsTermNotLitGenreText - United States--US
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Disability Evaluation; Disabled Persons; Educational Status; Female; Frail Elderly; Humans; Income; Longitudinal Studies; Male; Marital Status; Middle Aged; Prospective Studies; Sex Distribution; Socioeconomic factors; United States

Former stepparents' contact with their stepchildren after midlife. - Claire Noël-Miller (J Gerontol B Psychol Sci Soc Sci, 2013)
OBJECTIVES: Based on the life course perspective and gender differences in stepparental roles, this study examines frequency of social contact between mid- to late-life stepparents and their stepchildren after stepparents' marriage to their stepchildren's biological parent has been dissolved through widowhood or divorce. METHOD: Using 5 waves of panel data on stepparent-stepchild pairs from the Health and Retirement Study (N = 12,947 stepchild observations on 4,063 stepchildren belonging to 1,663 stepparents) spanning 10 years (1998-2008), I estimate ordered logit multilevel models predicting former stepparent-stepchild contact frequency. RESULTS: Results indicate that former stepparents have notably less frequent contact with their stepchildren than current stepparents, particularly following divorce. Widowed stepparents' contact with their stepchildren diminishes gradually following union disruption, whereas divorced stepparents' contact frequency drops abruptly. Former stepfathers have less contact with their stepchildren than former stepmothers. Finally, I uncover evidence of the moderating role of (step)parents' marriage length and stepparents' number of biological children on widowed stepparent-stepchild contact frequency. DISCUSSION: Older stepparents' social contact with their stepchildren is largely conditional on stepparents' enduring marital bond to their stepchildren's biological parent. This study contributes to a growing literature portraying relatively weak ties between older adults and their stepchildren.
Copyright - Copyright Oxford University Press, UK May 2013 Last updated - 2013-04-19 DOI - 2948942401; 77441762; 9698; PGN2; INODPGN20000698908
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Child; Family Characteristics; Female; Health Surveys; Humans; Male; Marital Status; Middle Aged; Parent-Child Relations; Parents; Social Support; Young Adult

Functional disability, cognitive impairment, and depression after hospitalization for pneumonia. - Dimitry S Davydow; Catherine L Hough; Deborah A Levine; Kenneth M. Langa; Theodore J Iwashyna (Am J Med, 2013)
OBJECTIVE: The study objective was to examine whether hospitalization for pneumonia is associated with functional decline, cognitive impairment, and depression, and to compare this impairment with that seen after known disabling conditions, such as myocardial infarction or stroke. METHODS: We used data from a prospective cohort of 1434 adults aged more than 50 years who survived 1711 hospitalizations for pneumonia, myocardial infarction, or stroke drawn from the Health and Retirement Study (1998-2010). Main outcome measures included the number of Activities and Instrumental Activities of Daily Living requiring assistance and the presence of cognitive impairment and substantial depressive symptoms. RESULTS: Hospitalization for pneumonia was associated with 1.01 new impairments in Activities and Instrumental Activities of Daily Living (95% confidence interval [CI], 0.71-1.32) among patients without baseline functional impairment and 0.99 new impairments in Activities and Instrumental Activities of Daily Living (95% CI, 0.57-1.41) among those with mild-to-moderate baseline limitations, as well as moderate-to-severe cognitive impairment (odds ratio, 2.46; 95% CI, 1.60-3.79) and substantial depressive symptoms (odds ratio, 1.63; 95% CI, 1.06-2.51). Patients without baseline functional impairment who survived pneumonia hospitalization had more subsequent impairments in Activities and Instrumental Activities of Daily Living than those who survived myocardial infarction hospitalization. There were no significant differences in subsequent moderate-to-severe cognitive impairment or substantial depressive symptoms between patients who survived myocardial infarction or stroke and those who survived pneumonia. CONCLUSIONS: Hospitalization for pneumonia in older adults is associated with subsequent functional and cognitive impairment. Improved pneumonia prevention and interventions to ameliorate adverse sequelae during and after hospitalization may improve outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cognitive Dysfunction; depression; Hospitalization; Humans; Logistic Models; Longitudinal Studies; Middle Aged; Myocardial Infarction; Pneumonia; Stroke

Functional limitations in older adults who have cognitive impairment without dementia. - Tanya R Gure; Kenneth M. Langa; Gwenith G Fisher; John D Piette; Brenda L Plassman (J Geriatr Psychiatry Neurol, 2013)
OBJECTIVE: To characterize the prevalence of functional limitations among older adults with cognitive impairment without dementia (CIND). METHODS: Secondary data analysis was performed using the Aging, Demographics, and Memory Study data set. A total of 856 individuals aged ≥ 71 years were assigned to 3 diagnostic cognitive categories. A questionnaire was completed by a proxy informant regarding functional limitations for 744 of the 856 respondents. RESULTS: Of the 744 patients, 263 (13.9%) had dementia, 201 (21.3%) had CIND, and 280 (64.8%) had normal cognition. Informants reported ≥1 instrumental activities of daily living (ADLs) limitation in 45% of the patients with CIND compared to 13% of the patients with normal cognition and 85% of the patients with dementia (P < .001). The ADL impairments among individuals with CIND were primarily attributed to physical health problems (n = 41; 40%). CONCLUSIONS: Many individuals with CIND have impairment in a range of complex and basic daily activities, largely due to physical health problems.
NLM Title Abbreviation: J Geriatr Psychiatry Neurol
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Cognitive Dysfunction; Dementia; Female; Humans; Male; Neuropsychological tests; Severity of Illness Index; Surveys and Questionnaires

Heterogeneity in multidimensional health trajectories of late old years and socioeconomic stratification: a latent trajectory class analysis. - Kandauda Wickrama; Jay A. Mancini; Kwag, Kyunghwa; Kwon, Josephine (J Gerontol B Psychol Sci Soc Sci, 2013)
OBJECTIVES: This study examines (a) the heterogeneity in individual multidimensional health trajectories and (b) the socioeconomic stratification of individual multidimensional health trajectories during the late older years. METHOD: This study used prospective data from 1,945 adults, 75 to 85 years old, collected over an 8-year period from the Health and Retirement Study. To examine inconsistent findings in the research literature, a latent trajectory class analysis was performed. RESULTS: Multidimensional overall health trajectories showed three heterogeneous latent classes (maintaining, persistently high, and deteriorating), and profiles of ascribed and achieved socioeconomic characteristics of multidimensional health trajectory classes showed a significant social and racial/ethnic stratification in late older years. DISCUSSION: Past adverse socioeconomic circumstances, including childhood and adulthood adversity, are potential sources of unobserved heterogeneity of multidimensional health trajectories even in late older years. The identification of members of latent trajectory health classes and the associated antecedents linked to health class membership are consistent with a life-course conceptual framework. Thus, multidimensional health capturing the full range of health problems needs to be investigated for proper examination of socioeconomic correlates of health. This facilitates the understanding of the associations between life-course experiences and health in late old age that ultimately have implications for prevention and intervention.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; depression; Female; Health Status; Health Transition; Humans; Longitudinal Studies; Male; Marriage; Memory Disorders; Middle Aged; Socioeconomic factors

Hospital and nursing home use from 2002 to 2008 among U.S. older adults with cognitive impairment, not dementia in 2002. - Daniel O. Clark; Timothy E. Stump; Tu, Wanzhu; Douglas K Miller; Kenneth M. Langa; Frederick W Unverzagt; Christopher M. Callahan (Alzheimer Dis Assoc Disord, 2013)
Little is known about health care use in the cognitive impairment, not dementia (CIND) subpopulation. Using a cohort of 7130 persons aged 71 years or over from the Health and Retirement Survey, we compared mean and total health care use from 2002 to 2008 for those with no cognitive impairment, CIND, or dementia in 2002. Cognitive status was determined using a validated method based on self or proxy interview measures. Health care use was also based on self or proxy reports. On the basis of the Health and Retirement Survey, the CIND subpopulation in 2002 was 5.3 million or 23% of the total population 71 years of age or over. Mean hospital nights was similar and mean nursing home nights was less in persons with CIND compared with persons with dementia. The CIND subpopulation, however, had more total hospital and nursing home nights--71,000 total hospital nights and 223,000 total nursing home nights versus 32,000 hospital nights and 138,000 nursing home nights in the dementia subpopulation. A relatively large population and high health care use result in a large health care impact of the CIND subpopulation.
Keywords: Aged; Aged, 80 and over; Aging; Cognition Disorders; Dementia; Female; Homes for the Aged; Hospitalization; Humans; Male; Nursing homes; United States

Impact of cigarette smoking on utilization of nursing home services. - Kenneth E. Warner; Ryan J McCammon; Brant E Fries; Kenneth M. Langa (Nicotine Tob Res, 2013)
INTRODUCTION: Few studies have examined the effects of smoking on nursing home utilization, generally using poor data on smoking status. No previous study has distinguished utilization for recent from long-term quitters. METHODS: Using the Health and Retirement Study, we assessed nursing home utilization by never-smokers, long-term quitters (quit >3 years), recent quitters (quit ≤3 years), and current smokers. We used logistic regression to evaluate the likelihood of a nursing home admission. For those with an admission, we used negative binomial regression on the number of nursing home nights. Finally, we employed zero-inflated negative binomial regression to estimate nights for the full sample. RESULTS: Controlling for other variables, compared with never-smokers, long-term quitters have an odds ratio (OR) for nursing home admission of 1.18 (95% CI: 1.07-1.2), current smokers 1.39 (1.23-1.57), and recent quitters 1.55 (1.29-1.87). The probability of admission rises rapidly with age and is lower for African Americans and Hispanics, more affluent respondents, respondents with a spouse present in the home, and respondents with a living child. Given admission, smoking status is not associated with length of stay (LOS). LOS is longer for older respondents and women and shorter for more affluent respondents and those with spouses present. CONCLUSIONS: Compared with otherwise identical never-smokers, former and current smokers have a significantly increased risk of nursing home admission. That recent quitters are at greatest risk of admission is consistent with evidence that many stop smoking because they are sick, often due to smoking.
Keywords: Age Factors; Aged; Aged, 80 and over; Black or African American; Cross-Sectional Studies; Female; Hispanic or Latino; Humans; Length of Stay; Logistic Models; Longitudinal Studies; Male; Middle Aged; Nursing homes; Risk; Self Report; Smoking; Socioeconomic factors; United States; White People

Longer lived parents: protective associations with cancer incidence and overall mortality. - Ambarish Dutta; Henley, William; Robine, Jean-Marie; Kenneth M. Langa; Robert B Wallace; David Melzer (J Gerontol A Biol Sci Med Sci, 2013)
BACKGROUND: Children of centenarians have lower cardiovascular disease prevalence and live longer. We aimed to estimate associations between the full range of parental attained ages and health status in a middle-aged U.S. representative sample. METHODS: Using Health and Retirement Study data, models estimated disease incidence and mortality hazards for respondents aged 51-61 years at baseline, followed up for 18 years. Full adjustment included sex, race, smoking, wealth, education, body mass index, and childhood socioeconomic status. Mother's and father's attained age distributions were used to define short-, intermediate-, and long-lived groups, yielding a ranked parental longevity score (n = 6,055, excluding short-long discordance). Linear models (n = 8,340) tested mother's or father's attained ages, adjusted for each other. RESULTS: With increasing mother's or father's survival (>65 years), all-cause mortality declined 19% (hazard ratio [HR] = 0.81, 95% CI: 0.76-0.86, p < .001) and 14% per decade (HR = 0.87, 95% CI: 0.81-0.92, p < .001). Estimates changed only modestly when fully adjusted. Parent-in-law survival was not associated with mortality (n = 1,809, HR = 1.00, 95% CI: 0.90-1.12, p = .98). Offspring with one or two long-lived parents had lower cancer incidence (938 cases, HR per parental longevity score = 0.76, 95% CI: 0.61-0.94, p = .01) versus two intermediate parents. Similar HRs for diabetes (HR = 0.89, 95% CI: 0.84-0.96, p = .001), heart disease (HR = 0.88, 95% CI: 0.82-0.93, p < .001), and stroke (HR = 0.86, 95% CI: 0.78-0.95, p = .002) were significant, but there was no trend for arthritis. CONCLUSIONS: The results provide the first robust evidence that increasing parental attained age is associated with lower cancer incidence in offspring. Health advantages of having centenarian parents extend to a wider range of parental longevity and may provide a quantitative trait of slower aging.
Keywords: Aged; Aged, 80 and over; Female; Humans; Incidence; Longevity; Male; Middle Aged; Mortality; Neoplasms; Parents

Monetary costs of dementia in the United States. - Michael D Hurd; Martorell, Paco; Delavande, Adeline; Kathleen J Mullen; Kenneth M. Langa (N Engl J Med, 2013)
BACKGROUND: Dementia affects a large and growing number of older adults in the United States. The monetary costs attributable to dementia are likely to be similarly large and to continue to increase. METHODS: In a subsample (856 persons) of the population in the Health and Retirement Study (HRS), a nationally representative longitudinal study of older adults, the diagnosis of dementia was determined with the use of a detailed in-home cognitive assessment that was 3 to 4 hours in duration and a review by an expert panel. We then imputed cognitive status to the full HRS sample (10,903 persons, 31,936 person-years) on the basis of measures of cognitive and functional status available for all HRS respondents, thereby identifying persons in the larger sample with a high probability of dementia. The market costs associated with care for persons with dementia were determined on the basis of self-reported out-of-pocket spending and the utilization of nursing home care; Medicare claims data were used to identify costs paid by Medicare. Hours of informal (unpaid) care were valued either as the cost of equivalent formal (paid) care or as the estimated wages forgone by informal caregivers. RESULTS: The estimated prevalence of dementia among persons older than 70 years of age in the United States in 2010 was 14.7%. The yearly monetary cost per person that was attributable to dementia was either $56,290 (95% confidence interval [CI], $42,746 to $69,834) or $41,689 (95% CI, $31,017 to $52,362), depending on the method used to value informal care. These individual costs suggest that the total monetary cost of dementia in 2010 was between $157 billion and $215 billion. Medicare paid approximately $11 billion of this cost. CONCLUSIONS: Dementia represents a substantial financial burden on society, one that is similar to the financial burden of heart disease and cancer. (Funded by the National Institute on Aging.).
Keywords: Aged; Aged, 80 and over; Cost of Illness; Dementia; Female; Health Care Costs; Home Care Services; Home Nursing; Humans; Longitudinal Studies; Male; Medicare; Middle Aged; Nursing homes; United States

Pain as a risk factor for disability or death. - James S Andrews; Irena Cenzer; Yelin, Edward; Kenneth E Covinsky (J Am Geriatr Soc, 2013)
OBJECTIVES: To determine whether pain predicts future activity of daily living (ADL) disability or death in individuals aged 60 and older. DESIGN: Prospective cohort study. SETTING: The 1998 to 2008 Health and Retirement Study (HRS), a nationally representative study of older community-living individuals. PARTICIPANTS: Twelve thousand six hundred thirty-one participants in the 1998 HRS aged 60 and older who did not need help in any ADL. MEASUREMENTS: Participants reporting that they had moderate or severe pain most of the time were defined as having significant pain. The primary outcome was time to development of ADL disability or death over 10 yrs, assessed at five successive 2-year intervals. ADL disability was defined as needing help performing any ADL: bathing, dressing, transferring, toileting, eating, or walking across a room. A discrete hazards survival model was used to examine the relationship between pain and incident disability over each 2-year interval using only participants who started the interval with no ADL disability. Several potential confounders were adjusted for at the start of each interval: demographic factors, seven chronic health conditions, and functional limitations (ADL difficulty and difficulty with five measures of mobility). RESULTS: At baseline, 2,283 (18%) participants had significant pain. Participants with pain were more likely (all P < .001) to be female (65% vs 54%), have ADL difficulty (e.g., transferring 12% vs 2%, toileting 11% vs 2%), have difficulty walking several blocks (60% vs 21%), and have difficulty climbing one flight of stairs (40% vs 12%). Over 10 years, participants with pain were more likely to develop ADL disability or death (58% vs 43%, unadjusted hazard ratio (HR) = 1.67, 95% confidence interval (CI) = 1.57-1.79), although after adjustment for confounders, participants with pain were not at greater risk for ADL disability or death (HR = 0.98, 95% CI = 0.91-1.07). Adjustment for functional status almost entirely explained the difference between the unadjusted and adjusted results. CONCLUSION: Although there are strong cross-sectional relationships between pain and functional limitations, individuals with pain are not at higher risk of subsequent disability or death after accounting for functional limitations. Like many geriatric syndromes, pain and disability may represent interrelated phenomena that occur simultaneously and require unified treatment paradigms.
Date revised - 2013-05-01 Last updated - 2013-05-31 DOI - 0b2ff290-e53b-4073-a3d7csamfg102v; 17944301; 0002-8614; 1532-5415 SubjectsTermNotLitGenreText - Demography; Mortality; Mobility; Risk factors; Disabilities; Survival; Pain
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cohort Studies; Disabled Persons; Female; Geriatric Assessment; Health Status; Humans; Life Style; Male; Middle Aged; pain; Prevalence; Prognosis; Prospective Studies; Severity of Illness Index; Sex Distribution; Sex Factors; United States

Patterns of older Americans' health care utilization over time. - Richard J. Manski; John F Moeller; Haiyan Chen; Jody Schimmel; Patricia A St Clair; John V Pepper (Am J Public Health, 2013)
OBJECTIVES: We analyzed correlates of older Americans' continuous and transitional health care utilization over 4 years. METHODS: We analyzed data for civilian, noninstitutionalized US individuals older than 50 years from the 2006 and 2008 waves of the Health and Retirement Study. We estimated multinomial logistic models of persistent and intermittent use of physician, inpatient hospital, home health, and outpatient surgery over the 2004-2008 survey periods. RESULTS: Individuals with worse or worsening health were more likely to persistently use medical care and transition into care and not transition out of care over time. Financial variables were less often significant and, when significant, were often in an unexpected direction. CONCLUSIONS: Older individuals' health and changes in health are more strongly correlated with persistence of and changes in care-seeking behavior over time than are financial status and changes in financial status. The more pronounced sensitivity to health status and changes in health are important considerations in insurance and retirement policy reforms.
Keywords: Aged; Aged, 80 and over; Ambulatory Surgical Procedures; Delivery of Health Care; Female; Health Services; Health Status; Health Surveys; Home Care Services; Hospitalization; Humans; Income; Insurance Coverage; Logistic Models; Longitudinal Studies; Male; Middle Aged; Office Visits; Patient Acceptance of Health Care; Time Factors; United States

Predicting 10-year mortality for older adults. - Cruz, Marisa; Kenneth E Covinsky; Eric W Widera; Stijacic-Cenzer, Irena; Sei J. Lee (JAMA, 2013)
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Forecasting; Humans; Kaplan-Meier Estimate; Life Expectancy; Male; Middle Aged; Mortality; Risk Assessment; United States

A prospective study of volunteerism and hypertension risk in older adults. - Rodlescia S. Sneed; Cohen, Sheldon (Psychol Aging, 2013)
The purpose of the current study was to determine whether volunteerism is prospectively associated with hypertension risk among older adults. Participants provided data during the 2006 and 2010 waves of the Health and Retirement Study, a longitudinal panel survey using a nationally representative sample of community-dwelling older adults (age > 50 years). Volunteerism and blood pressure were measured at baseline and again 4 years later. Analyses excluded individuals hypertensive at baseline and controlled for age, race, sex, education, baseline systolic/diastolic blood pressure, and major chronic illnesses. Those who had volunteered at least 200 hr in the 12 months prior to baseline were less likely to develop hypertension (OR = 0.60; 95% CI [0.40, 0.90]) than nonvolunteers. There was no association between volunteerism and hypertension risk at lower levels of volunteer participation. Volunteering at least 200 hr was also associated with greater increases in psychological well-being (B = 0.99, β = .05, p = .006) and physical activity (B = 0.21, β = .05, p = .04) compared with nonvolunteers; however, these factors did not explain the association of volunteerism with hypertension risk.
Copyright - Copyright American Psychological Association Jun 2013 Last updated - 2013-06-30
Keywords: Aged; Aged, 80 and over; Female; Health Surveys; Humans; Hypertension; Male; Middle Aged; Prospective Studies; Risk Assessment; Time Factors; Volunteers

The role of pain in understanding racial/ethnic differences in the frequency of physical activity among older adults. - Grubert, Elizabeth; Tamara A. Baker; McGeever, Kelly; Benjamin A Shaw (J Aging Health, 2013)
OBJECTIVE: To evaluate racial/ethnic differences in physical activity among white, black, and Hispanic adults aged 65 years and older, and to assess the potential role of pain as a mediator. METHODS: Analyses were based on data from the 2008 Health and Retirement Study. Logistic regression was used to evaluate associations between race/ethnicity and pain and the odds of regular physical activity. RESULTS: Compared to Whites, the odds of both light physical activity and moderate/vigorous physical activity were lower among Blacks, but not Hispanics. A graded inverse association between levels of pain severity and the odds of physical activity was found, but pain did not mediate racial/ethnic differences in physical activity. DISCUSSION: When compared to Whites, older Blacks appear to have relatively low rates of physical activity even without comparatively high levels of pain, while older Hispanics experience relatively high rates of pain, but are perhaps more resilient to the effects of pain on physical activity.
Keywords: Aged; Aged, 80 and over; Black or African American; Female; Health Surveys; Hispanic or Latino; Humans; Male; Motor Activity; pain; Severity of Illness Index; United States; White People

The socioeconomic origins of physical functioning among older U.S. adults. - Jennifer Karas Montez (Adv Life Course Res, 2013)
Mounting evidence finds that adult health reflects socioeconomic circumstances (SES) in early life and adulthood. However, it is unclear how the health consequences of SES in early life and adulthood accumulate-for example, additively, synergistically. This study tests four hypotheses about how the health effects of early-life SES (measured by parental education) and adult SES (measured by own education) accumulate to shape functional limitations, whether the accumulation differs between men and women, and the extent to which key mechanisms explain the accumulation. It uses data from the 1994-2010 Health and Retirement Study on U.S. adults 50-100 years of age (N=24,026). The physical functioning benefits of parental and own education accumulated additively among men. While the physical functioning benefits generally accumulated among women, the functioning benefits from one's own education were dampened among women with low-educated mothers. The dampening partly reflected a strong tie between mothers' education level and women's obesity risk. Taken together, the findings reveal subtle differences between men and women in the life course origins of physical functioning. They also shed light on a key mechanism-obesity-that may help explain why a growing number of studies find that early-life SES is especially important for women's health.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Educational Status; Female; Health Behavior; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Obesity; Sex Factors; Socioeconomic factors; United States

Spouses of stroke survivors may be at risk for poor cognitive functioning: a cross-sectional population-based study. - Peii Chen; Amanda L. Botticello (Top Stroke Rehabil, 2013)
BACKGROUND: Stroke often results in chronic disability and the need for long-term assistance, which is provided in large part by spouses. Stroke caregivers experience poorer health and well-being compared with non-caregivers, but less is known about the specific toll that caregiving may exact on cognitive functioning. OBJECTIVE: To investigate whether persons caring for a spouse who experienced a recent stroke may be at risk for poor cognitive functioning compared with non-caregivers. METHODS: Existing data from the United States' Health and Retirement Study (HRS) were used to identify 146 caregivers from among couples in which 1 individual reported surviving a recent stroke and experiencing functional limitations. This cross-sectional population-based analysis compared the stroke caregivers with 3,416 non-caregivers in time orientation, working memory, semantic memory, learning, and episodic memory. RESULTS: Overall, the caregiver group was considerably more disadvantaged than the non-caregiver group in terms of background characteristics, socioeconomic status, health, and well-being. Results of weighted Poisson regression models indicated that stroke caregivers were at risk for poorer performance than non-caregivers in working memory, semantic memory, learning, and episodic memory. The gap between stroke caregivers and non-caregivers in episodic memory remained after adjusting for systematic differences between the 2 groups across an array of risk factors. CONCLUSIONS: Spousal caregivers of stroke survivors may be at risk for poor cognitive functioning. More work is needed to identify the processes that may contribute to the diminished cognitive capacity among these adults so that interventions may be developed to reduce caregiver burden and promote cognitive health.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Community Health Planning; Cross-Sectional Studies; Female; Humans; Male; Neuropsychological tests; Retrospective Studies; Spouses; Stroke; Survivors; United States

Stroke-associated differences in rates of activity of daily living loss emerge years before stroke onset. - Benjamin D Capistrant; Qianyi Wang; Sze Y Liu; M. Maria Glymour (J Am Geriatr Soc, 2013)
OBJECTIVES: To compare typical age-related changes in activities of daily living (ADLs) independence in stroke-free adults with long-term ADL trajectories before and after stroke. DESIGN: Prospective, observational study. SETTING: Community-dwelling Health and Retirement Study (HRS) cohort. PARTICIPANTS: HRS participants who were stroke free in 1998 and were followed through 2008 (average follow-up 7.9 years) (N = 18,441). MEASUREMENTS: Strokes were assessed using self- or proxy-report of a doctor's diagnosis and month and year of event. Logistic regression was used to compare within-person changes in odds of self-reported independence in five ADLs in those who remained stroke free throughout follow-up (n = 16,816), those who survived a stroke (n = 1,208), and those who had a stroke and did not survive to participate in another interview (n = 417). Models were adjusted for demographic and socioeconomic covariates. RESULTS: Even before stroke, those who later developed stroke had significantly lower ADL independence and were experiencing faster independence losses than similar-aged individuals who remained stroke free. Of those who developed a stroke, survivors experienced slower pre-stroke loss of ADL independence than those who died. ADL independence declined at the time of stroke and decline continued afterwards. CONCLUSION: In adults at risk of stroke, disproportionate ADL limitations emerge well before stroke onset. Excess disability in stroke survivors should not be entirely attributed to effects of acute stroke or quality of acute stroke care. Although there are many possible causal pathways between ADL and stroke, the association may be noncausal. For example, ADL limitations may be a consequence of stroke risk factors (e.g., diabetes mellitus) or early cerebrovascular ischemia.
Keywords: Activities of Daily Living; Age of Onset; Aged; Aged, 80 and over; Bayes Theorem; Disability Evaluation; Disabled Persons; Female; Follow-Up Studies; Geriatric Assessment; Humans; Male; Middle Aged; Morbidity; Prospective Studies; Risk Assessment; Risk Factors; Socioeconomic factors; Stroke; Stroke Rehabilitation; Survival Rate; Survivors; Time Factors; United States

Symptoms of depression in survivors of severe sepsis: a prospective cohort study of older Americans. - Dimitry S Davydow; Catherine L Hough; Kenneth M. Langa; Theodore J Iwashyna (Am J Geriatr Psychiatry, 2013)
OBJECTIVES: To examine if incident severe sepsis is associated with increased risk of subsequent depressive symptoms and to assess which patient characteristics are associated with increased risk of depressive symptoms. DESIGN: Prospective longitudinal cohort study. SETTING: Population-based cohort of older U.S. adults interviewed as part of the Health and Retirement Study (1998-2006). PARTICIPANTS: A total of 439 patients who survived 471 hospitalizations for severe sepsis and completed at least one follow-up interview. MEASUREMENTS: Depressive symptoms were assessed with a modified version of the Center for Epidemiologic Studies Depression Scale. Severe sepsis was identified using a validated algorithm in Medicare claims. RESULTS: The point prevalence of substantial depressive symptoms was 28% at a median of 1.2 years before sepsis, and remained 28% at a median of 0.9 years after sepsis. Neither incident severe sepsis (relative risk [RR]: 1.00; 95% confidence interval [CI]: 0.73, 1.34) nor severe sepsis-related clinical characteristics were significantly associated with subsequent depressive symptoms. These results were robust to potential threats from missing data or alternative outcome definitions. After adjustment, presepsis substantial depressive symptoms (RR: 2.20; 95% CI: 1.66, 2.90) and worse postsepsis functional impairment (RR: 1.08 per new limitation; 95% CI: 1.03, 1.13) were independently associated with substantial depressive symptoms after sepsis. CONCLUSIONS: The prevalence of substantial depressive symptoms in severe sepsis survivors is high but is not increased relative to their presepsis levels. Identifying this large subset of severe sepsis survivors at increased risk for major depression, and beginning interventions before hospital discharge, may improve outcomes.
Keywords: Aged; Aged, 80 and over; Cohort Studies; depression; Female; Hospitalization; Humans; Longitudinal Studies; Male; Poisson Distribution; Prospective Studies; Regression Analysis; Risk Factors; Sepsis; Severity of Illness Index; Survivors; United States

Trends in depressive symptom burden among older adults in the United States from 1998 to 2008. - Zivin, Kara; Paul A Pirraglia; Ryan J McCammon; Kenneth M. Langa; Sandeep Vijan (J Gen Intern Med, 2013)
CONTEXT: Diagnosis and treatment of depression has increased over the past decade in the United States. Whether self-reported depressive symptoms among older adults have concomitantly declined is unknown. OBJECTIVE: To examine trends in depressive symptoms among older adults in the US between 1998 and 2008. DESIGN: Serial cross-sectional analysis of six biennial assessments. SETTING: Health and Retirement Study (HRS), a nationally-representative survey. PATIENTS OR OTHER PARTICIPANTS Adults aged 55 and older (N = 16,184 in 1998). MAIN OUTCOME MEASURE: The eight-item Center for Epidemiologic Studies Depression scale (CES-D8) assessed three levels of depressive symptoms (none = 0, elevated = 4+, severe = 6+), adjusting for demographic and clinical characteristics. RESULTS: Having no depressive symptoms increased over the 10-year period from 40.9 % to 47.4 % (prevalence ratio [PR]: 1.16, 95 % CI: 1.13-1.19), with significant increases in those aged ≥ 60 relative to those aged 55-59. There was a 7 % prevalence reduction of elevated symptoms from 15.5 % to 14.2 % (PR: 0.93, 95 % CI: 0.88-0.98), which was most pronounced among those aged 80-84 in whom the prevalence of elevated symptoms declined from 14.3 % to 9.6 %. Prevalence of having severe depressive symptoms increased from 5.8 % to 6.8 % (PR: 1.17, 95 % CI: 1.06-1.28); however, this increase was limited to those aged 55-59, with the probability of severe symptoms increasing from 8.7 % to 11.8 %. No significant changes in severe symptoms were observed for those aged ≥ 60. CONCLUSIONS: Overall late-life depressive symptom burden declined significantly from 1998 to 2008. This decrease appeared to be driven primarily by greater reductions in depressive symptoms in the oldest-old, and by an increase in those with no depressive symptoms. These changes in symptom burden were robust to physical, functional, demographic, and economic factors. Future research should examine whether this decrease in depressive symptoms is associated with improved treatment outcomes, and if there have been changes in the treatment received for the various age cohorts.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Cost of Illness; Cross-Sectional Studies; depression; Female; Humans; Male; Middle Aged; United States

Trends in late-life activity limitations in the United States: an update from five national surveys. - Vicki A Freedman; Brenda C Spillman; Patricia Andreski; Jennifer C. Cornman; Eileen M. Crimmins; Kramarow, Ellen; Lubitz, James; Linda G Martin; Sharon S. Merkin; Robert F. Schoeni; Teresa Seeman; Timothy A Waidmann (Demography, 2013)
This article updates trends from five national U.S. surveys to determine whether the prevalence of activity limitations among the older population continued to decline in the first decade of the twenty-first century. Findings across studies suggest that personal care and domestic activity limitations may have continued to decline for those ages 85 and older from 2000 to 2008, but generally were flat since 2000 for those ages 65-84. Modest increases were observed for the 55- to 64-year-old group approaching late life, although prevalence remained low for this age group. Inclusion of the institutional population is important for assessing trends among those ages 85 and older in particular.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Disabled Persons; Female; Health Surveys; Humans; Male; Mobility Limitation; Models, Statistical; United States

Type of high-school credentials and older age ADL and IADL limitations: is the GED credential equivalent to a diploma? - Sze Y Liu; Chavan, Niraj R.; M. Maria Glymour (Gerontologist, 2013)
PURPOSE: Educational attainment is a robust predictor of disability in elderly Americans: older adults with high-school (HS) diplomas have substantially lower disability than individuals who did not complete HS. General Educational Development (GED) diplomas now comprise almost 20% of new HS credentials issued annually in the United States but it is unknown whether the apparent health advantages of HS diplomas extend to GED credentials. This study examines whether adults older than 50 years with GEDs have higher odds of incident instrumental or basic activities of daily living (IADLs) limitations compared with HS degree holders. METHODS: We compared odds of incident IADL limitations by HS credential type using discrete-time survival models among 9,426 Health and Retirement Study participants followed from 1998 through 2008. RESULTS: HS degree holders had lower odds of incident IADLs than GED holders (OR = 0.72, 95% CI = 0.58, 0.90 and OR = 0.69, 95% CI = 0.56, 0.86 for ADLs and IADLs, respectively). There was no significant difference in odds of incident IADL limitations between GED holders and respondents without HS credentials (OR = 0.89, 95% CI = 0.71, 1.11 for ADLs; OR = 0.88, 95% CI = 0.70, 1.12 for IADLs). IMPLICATIONS: Although GEDs are widely accepted as equivalent to high school diplomas, they are not associated with comparable health advantages for physical limitations in older age.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Aging; Disabled Persons; Educational Status; Female; Follow-Up Studies; Humans; Kaplan-Meier Estimate; Logistic Models; Male; Socioeconomic factors; United States

Understanding heterogeneity in price elasticities in the demand for alcohol for older individuals. - Padmaja Ayyagari; Deb, Partha; Jason M. Fletcher; William T Gallo; Jody L Sindelar (Health Econ, 2013)
This paper estimates the price elasticity of demand for alcohol using Health and Retirement Study data. To account for unobserved heterogeneity in price responsiveness, we use finite mixture models. We recover two latent groups, one is significantly responsive to price, but the other is unresponsive. The group with greater responsiveness is disadvantaged in multiple domains, including health, financial resources, education and perhaps even planning abilities. These results have policy implications. The unresponsive group drinks more heavily, suggesting that a higher tax would fail to curb the negative alcohol-related externalities. In contrast, the more disadvantaged group is more responsive to price, thus suffering greater deadweight loss, yet this group consumes fewer drinks per day and might be less likely to impose negative externalities.
Keywords: Adult; Aged; Aged, 80 and over; Alcohol Drinking; Alcoholic Beverages; Behavior; Body Height; Costs and Cost Analysis; Female; Health Status; Humans; Male; Middle Aged; Models, Econometric; Socioeconomic factors; Taxes; United States

Vascular depression: an early warning sign of frailty. - Daniel Paulson; Peter A Lichtenberg (Aging Ment Health, 2013)
OBJECTIVES: Frailty is a common geriatric disorder associated with activities of daily living (ADL) impairment, hospitalization, and death. Phenomenological evidence suggests that late-life depression (Katz, 2004 ), particularly vascular depression, may be a risk factor for frailty. This study tests that hypothesis. METHODS: We identified a sample of stroke-free women over the age of 80 from the Health and Retirement Survey. The sample included 984 respondents in 2000 (incidence sample). Of these, 459 were non-frail at baseline and still alive in 2004 (prevalence sample). Frail respondents experienced at least three of the following: wasting, exhaustion, weakness, slowness, and falls. Vascular depression was represented using two dummy variables. The first represented respondents with either high cerebrovascular burden (CVB; at least two cerebrovascular risk factors) or probable depression (score ≥3 on the 8-item Center for Epidemiological Studies Depression Scale (CES-D)), and the second represented respondents with both high CVB and probable depression. RESULTS: At baseline, the prevalence of frailty was 31.5%. Over four years the incidence of frailty was 31.8%. After controlling for age, education, ADL and IADL disability, arthritis, pulmonary disorders, cancer, and self-rated health, respondents with either high CVB or probable depression were more likely to be frail at baseline, and those with both were at even higher risk. Of those who were not frail at the 2000 wave, respondents who reported both high CVB and probable depression were more likely to become frail by 2004. DISCUSSION: These findings suggest that vascular depression is a prodrome for frailty.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cerebrovascular Disorders; depression; Disabled Persons; Female; Follow-Up Studies; Frail Elderly; Geriatric Assessment; Health Status; Humans; Incidence; Logistic Models; Male; Prevalence; Psychiatric Status Rating Scales; Risk Factors; Socioeconomic factors; United States

What do parents have to do with my cognitive reserve? Life course perspectives on twelve-year cognitive decline. - Hector M González; Wassim Tarraf; Mary E Bowen; Michelle D Johnson-Jennings; Gwenith G Fisher (Neuroepidemiology, 2013)
BACKGROUND/AIMS: To examine the cognitive reserve hypothesis by comparing the contribution of early childhood and life course factors related to cognitive functioning in a nationally representative sample of older Americans. METHODS: We examined a prospective, national probability cohort study (Health and Retirement Study; 1998-2010) of older adults (n=8,833) in the contiguous 48 United States. The main cognitive functioning outcome was a 35-point composite of memory (recall), mental status, and working memory tests. The main predictors were childhood socioeconomic position (SEP) and health, and individual-level adult achievement and health. RESULTS: Individual-level achievement indicators (i.e., education, income, and wealth) were positively and significantly associated with baseline cognitive function, while adult health was negatively associated with cognitive function. Controlling for individual-level adult achievement and other model covariates, childhood health presented a relatively small negative, but statistically significant association with initial cognitive function. Neither individual achievement nor childhood SEP was statistically linked to decline over time. CONCLUSIONS: Cognitive reserve purportedly acquired through learning and mental stimulation across the life course was associated with higher initial global cognitive functioning over the 12-year period in this nationally representative study of older Americans. We found little supporting evidence that childhood economic conditions were negatively associated with cognitive function and change, particularly when individual-level achievement is considered.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Cognitive Reserve; Cohort Studies; Female; Humans; Longevity; Longitudinal Studies; Male; Parents; Prospective Studies; Socioeconomic factors; United States

Antigenic challenge in the etiology of autoimmune disease in women. - Mary A M Rogers; Deborah A Levine; Neil Blumberg; Gwenith G Fisher; Mohammed U Kabeto; Kenneth M. Langa (J Autoimmun, 2012)
Infection has long been implicated as a trigger for autoimmune disease. Other antigenic challenges include receipt of allogeneic tissue or blood resulting in immunomodulation. We investigated antigenic challenges as possible risk factors for autoimmune disease in women using the Health and Retirement Study, a nationally representative longitudinal study, linked to Medicare files, years 1991-2007. The prevalence of autoimmune disease (rheumatoid arthritis, Hashimoto's disease, Graves' disease, systemic lupus erythematosus, celiac disease, systemic sclerosis, Sjögren syndrome and multiple sclerosis) was 1.4% in older women (95% CI: 1.3%, 1.5%) with significant variation across regions of the United States. The risk of autoimmune disease increased by 41% (95% CI of incidence rate ratio (IRR): 1.10, 1.81) with a prior infection-related medical visit. The risk of autoimmune disease increased by 90% (95% CI of IRR: 1.36, 2.66) with a prior transfusion without infection. Parity was not associated with autoimmune disease. Women less than 65 years of age and Jewish women had significantly elevated risk of developing autoimmune disease, as did individuals with a history of heart disease or end-stage renal disease. Antigenic challenges, such as infection and allogeneic blood transfusion, are significant risk factors for the development of autoimmune disease in older women.
Rogers, Mary A M Levine, Deborah A Blumberg, Neil Fisher, Gwenith G Kabeto, Mohammed Langa, Kenneth M 5R21HL093129-02/HL/NHLBI NIH HHS/ HL078603/HL/NHLBI NIH HHS/ HL095467/HL/NHLBI NIH HHS/ HL100051/HL/NHLBI NIH HHS/ R21 HL093129-01A1/HL/NHLBI NIH HHS/ R21 HL093129-02/HL/NHLBI NIH HHS/ U01AG009740/AG/NIA NIH HHS/ England J Autoimmun. 2012 May;38(2-3):J97-J102. Epub 2011 Aug 30.
Keywords: Aged; Aged, 80 and over; Antigens; Autoimmune Diseases; Female; Humans; Incidence; Middle Aged; Prevalence; Risk Factors; United States

Chemotherapy was not associated with cognitive decline in older adults with breast and colorectal cancer: findings from a prospective cohort study. - Victoria A. Shaffer; Edgar C. Merkle; Angela Fagerlin; Jennifer J Griggs; Kenneth M. Langa; Theodore J Iwashyna (Med Care, 2012)
OBJECTIVES: This study tested 2 hypotheses: (1) chemotherapy increases the rate of cognitive decline in breast and colorectal cancer patients beyond what is typical of normal aging and (2) chemotherapy results in systematic cognitive declines when compared with breast and colorectal cancer patients who did not receive chemotherapy. SUBJECTS: Data came from personal interviews with a prospective cohort of patients with breast (n=141) or colorectal cancer (n=224) with incident disease drawn from the nationally representative Health and Retirement Study (1998-2006) with linked Medicare claims. MEASURES: The 27-point modified Telephone Interview for Cognitive Status was used to assess cognitive functioning, focusing on memory and attention. We defined the smallest clinically significant change as 0.4 points per year. RESULTS: We used Bayesian hierarchical linear models to test the hypotheses, adjusting for multiple possible confounders. Eighty-eight patients were treated with chemotherapy; 277 were not. The mean age at diagnosis was 75.5. Patients were followed for a median of 3.1 years after diagnosis, with a range of 0 to 8.3 years. We found no differences in the rates of cognitive decline before and after diagnosis for patients who received chemotherapy in adjusted models (P=0.86, one-sided 95% posterior intervals lower bound: 0.09 worse after chemotherapy), where patients served as their own controls. Moreover, the rate of cognitive decline after diagnosis did not differ between patients who had chemotherapy and those who did not (P=0.84, one-sided 95% posterior intervals lower bound: 0.11 worse for chemotherapy group in adjusted model). CONCLUSIONS: There was no evidence of cognitive decline associated with chemotherapy in this sample of older adults with breast and colorectal cancer.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Antineoplastic Agents; Antineoplastic Protocols; Bayes Theorem; Breast Neoplasms; Cognition Disorders; Colorectal Neoplasms; Female; Health Behavior; Humans; Interviews as Topic; Male; Memory; Prospective Studies

Chiropractic episodes and the co-occurrence of chiropractic and health services use among older Medicare beneficiaries. - Paula A Weigel; Jason Hockenberry; Suzanne E Bentler; Kaskie, Brian; Frederic D Wolinsky (Journal of Manipulative & Physiological Therapeutics, 2012)
OBJECTIVE: The purpose of this study was to define and characterize episodes of chiropractic care among older Medicare beneficiaries and to evaluate the extent to which chiropractic services were used in tandem with conventional medicine. METHODS: Medicare Part B claims histories for 1991 to 2007 were linked to the nationally representative survey on Assets and Health Dynamics among the Oldest Old baseline interviews (1993-1994) to define episodes of chiropractic sensitive care using 4 approaches. Chiropractic and nonchiropractic patterns of service use were examined within these episodes of care. Of the 7447 Assets and Health Dynamics among the Oldest Old participants, 971 used chiropractic services and constituted the analytic sample. RESULTS: There were substantial variations in the number and duration of episodes and the type and volume of services used across the 4 definitions. Depending on how the episode was constructed, the mean number of episodes per chiropractic user ranged from 3.74 to 23.12, the mean episode duration ranged from 4.7 to 28.8 days, the mean number of chiropractic visits per episode ranged from 0.88 to 2.8, and the percentage of episodes with co-occurrent use of chiropractic and nonchiropractic providers ranged from 4.9% to 10.9% over the 17-year period. CONCLUSION: Treatment for back-related musculoskeletal conditions was sought from a variety of providers, but there was little co-occurrent service use or coordinated care across provider types within care episodes. Chiropractic treatment dosing patterns in everyday practice were much lower than that used in clinical trial protocols designed to establish chiropractic efficacy for back-related conditions.
Keywords: Age Factors; Aged; Aged, 80 and over; Chiropractic; Combined Modality Therapy; Episode of Care; Female; Geriatric Assessment; Health Care Surveys; Health Services; Humans; Incidence; Insurance Claim Reporting; Low Back Pain; Medicare Part B; Musculoskeletal Diseases; Primary Health Care; Retrospective Studies; Sex Factors; Treatment Outcome; United States

Cohort differences in the availability of informal caregivers: are the Boomers at risk? - Lindsay H Ryan; Jacqui Smith; Toni C Antonucci; James S Jackson (Gerontologist, 2012)
PURPOSE OF THE STUDY: We compare the close family resources of Baby Boomers (BBs) to previous cohorts of older adults at population level and then examine individual-level cohort comparisons of age-related trajectories of informal care availability from midlife into old age. DESIGN AND METHODS: Population data from the U.S. Census and from the Health and Retirement Study (HRS) are used to identify a cohort similar to the BBs on marital status and fertility rates. Using generalized linear mixed models and 10-year longitudinal data from Depression and WWII parents (DWP; n = 1,052) and the parents of BBs (PBB; n = 3,573) in the HRS, we examine cohort differences in the time-varying likelihoods of being married and of having an adult child living within 10 miles. RESULTS: The DWP had similar informal care resources at entry to old age as is expected in the BB. Longitudinal analyses of the DWP and PBB cohorts in HRS reveal that the availability of family changes over time and that the DWP cohort was significantly less likely to have a spouse or a grown child living nearby. IMPLICATIONS: These findings, and future projections based on them, have significant implications for institutions and public policy concerned with the informal caregiving needs of the Boomer cohort as they age.
Keywords: Aged; Aged, 80 and over; Aging; Caregivers; Censuses; Family Characteristics; Female; Health Status; Humans; Likelihood Functions; Longitudinal Studies; Male; Middle Aged; Nuclear Family; Population Growth; Residence Characteristics; Retirement; Risk; Socioeconomic factors

A comparison and cross-validation of models to predict basic activity of daily living dependency in older adults. - Daniel O. Clark; Timothy E. Stump; Tu, Wanzhu; Douglas K Miller (Medical Care, 2012)
BACKGROUND: A simple method of identifying elders at high risk for activity of daily living (ADL) dependence could facilitate essential research and implementation of cost-effective clinical care programs. OBJECTIVE: We used a nationally representative sample of 9446 older adults free from ADL dependence in 2006 to develop simple models for predicting ADL dependence at 2008 follow-up and to compare the models to the most predictive published model. Candidate predictor variables were those of published models that could be obtained from interview or medical record data. METHODS: Variable selection was performed using logistic regression with backward elimination in a two-third random sample (n = 6233) and validated in a one-third random sample (n = 3213). Model fit was determined using the c-statistic and evaluated vis-a-vis our replication of a published model. RESULTS: At 2-year follow-up, 8.0% and 7.3% of initially independent persons were ADL dependent in the development and validation samples, respectively. The best fitting, simple model consisted of age and number of hospitalizations in past 2 years, plus diagnoses of diabetes, chronic lung disease, congestive heart failure, stroke, and arthritis. This model had a c-statistic of 0.74 in the validation sample. A model of just age and number of hospitalizations achieved a c-statistic of 0.71. These compared with a c-statistic of 0.79 for the published model. Sensitivity analyses demonstrated model robustness. CONCLUSIONS: Models based on a widely available data achieve very good validity for predicting ADL dependence. Future work will assess the validity of these models using medical record data.
Keywords: Accidental Falls; Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Aging; Body Mass Index; Chronic disease; Female; Humans; Male; Mobility Limitation; Models, Statistical; Risk Assessment; Sex Factors

Current and long-term spousal caregiving and onset of cardiovascular disease. - Benjamin D Capistrant; J Robin Moon; Lisa F Berkman; M. Maria Glymour (J Epidemiol Community Health, 2012)
BACKGROUND: Prior evidence suggests that caregiving may increase risk of cardiovascular disease (CVD) onset. This association has never been examined in a nationally (USA) representative sample, and prior studies could not fully control for socioeconomic confounders. This paper seeks to estimate the association between spousal caregiving and incident CVD in older Americans. METHODS: Married, CVD-free Health and Retirement Study respondents aged 50+ years (n=8472) were followed up to 8 years (1669 new stroke or heart disease diagnoses). Current caregiving exposure was defined as assisting a spouse with basic or instrumental activities of daily living ≥14 h/week according to the care recipients' report in the most recent prior biennial survey; we define providing ≥14 h/week of care at two consecutive biennial surveys as 'long-term caregiving'. Inverse probability weighted discrete-time hazard models with time-updated exposure and covariate information (including socioeconomic and cardiovascular risk factors) were used to estimate the effect of caregiving on incident CVD. RESULTS: Caregiving significantly predicted CVD incidence (HR=1.35, 95% CI 1.06 to 1.68) in the population overall. Long-term caregiving was associated with double the risk of CVD onset (HR=1.95, 95% CI 1.19 to 3.18). This association for long-term care givers varied significantly by race (p<0.01): caregiving predicted CVD onset for white (HR=2.37, 95% CI 1.43 to 3.92) but not for non-white (HR=0.28, 95% CI 0.06 to 1.28). CONCLUSIONS: Spousal caregiving independently predicted risk of CVD in a large sample of US adults. There was significant evidence that the effect for long-term care givers differs for non-whites and white.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Caregivers; Female; Follow-Up Studies; Humans; Incidence; Interviews as Topic; Long-term Care; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Self Report; Socioeconomic factors; Spouses; Stress, Psychological; United States

Disability and decline in physical function associated with hospital use at end of life. - Amy Kelley; Susan L Ettner; R Sean Morrison; Qingling Du; Catherine A Sarkisian (J Gen Intern Med, 2012)
BACKGROUND: Hospital use near the end of life is often undesirable to patients, represents considerable Medicare cost, and varies widely across regions. OBJECTIVE: To concurrently examine regional and patient factors, including disability and functional decline, associated with end-of-life hospital use. DESIGN/PARTICIPANTS: We sampled decedents aged 65 and older (n = 2,493) from the Health and Retirement Study (2000-2006), and linked data from individual Medicare claims and the Dartmouth Atlas of Health Care. Two-part regression models estimated the relationship between total hospital days in the last 6 months and patient characteristics including physical function, while adjusting for regional resources and hospital care intensity (HCI). KEY RESULTS: Median hospital days was 7 (range = 0-183). 53% of respondents had functional decline. Compared with decedents without functional decline, those with severe disability or decline had more regression-adjusted hospital days (range 3.47-9.05, depending on category). Dementia was associated with fewer days (-3.02); while chronic kidney disease (2.37), diabetes (2.40), stroke or transient ischemic attack (2.11), and congestive heart failure (1.74) were associated with more days. African Americans and Hispanics had more days (5.91 and 4.61, respectively). Those with family nearby had 1.62 fewer days and hospice enrollees had 1.88 fewer days. Additional hospital days were associated with urban residence (1.74) and residence in a region with more specialists (1.97) and higher HCI (2.27). CONCLUSIONS: Functional decline is significantly associated with end-of-life hospital use among older adults. To improve care and reduce costs, health care programs and policies should address specific needs of patients with functional decline and disability.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Dementia; Disability Evaluation; Disabled Persons; Female; Frail Elderly; Geriatric Assessment; Hospitalization; Humans; Length of Stay; Longitudinal Studies; Male; Medicare; Socioeconomic factors; Terminal Care; United States

An examination of healthy aging across a conceptual continuum: prevalence estimates, demographic patterns, and validity. - Sara J McLaughlin; Alan M Jette; Cathleen M. Connell (J Gerontol A Biol Sci Med Sci, 2012)
BACKGROUND: Although the notion of healthy aging has gained wide acceptance in gerontology, measuring the phenomenon is challenging. Guided by a prominent conceptualization of healthy aging, we examined how shifting from a more to less stringent definition of healthy aging influences prevalence estimates, demographic patterns, and validity. METHODS: Data are from adults aged 65 years and older who participated in the Health and Retirement Study. We examined four operational definitions of healthy aging. For each, we calculated prevalence estimates and examined the odds of healthy aging by age, education, gender, and race-ethnicity in 2006. We also examined the association between healthy aging and both self-rated health and death. RESULTS: Across definitions, the prevalence of healthy aging ranged from 3.3% to 35.5%. For all definitions, those classified as experiencing healthy aging had lower odds of fair or poor self-rated health and death over an 8-year period. The odds of being classified as "healthy" were lower among those of advanced age, those with less education, and women than for their corresponding counterparts across all definitions. CONCLUSIONS: Moving across the conceptual continuum--from a more to less rigid definition of healthy aging--markedly increases the measured prevalence of healthy aging. Importantly, results suggest that all examined definitions identified a subgroup of older adults who had substantially lower odds of reporting fair or poor health and dying over an 8-year period, providing evidence of the validity of our definitions. Conceptualizations that emphasize symptomatic disease and functional health may be particularly useful for public health purposes.
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Female; health; Humans; Male; Odds Ratio; Prevalence; Reproducibility of Results

Gardening as a potential activity to reduce falls in older adults. - Tuo-Yu Chen; Megan C Janke (J Aging Phys Act, 2012)
This study examines whether participation in gardening predicts reduced fall risk and performance on balance and gait-speed measures in older adults. Data on adults age 65 and older (N = 3,237) from the Health and Retirement Study and Consumption and Activities Mail Survey were analyzed. Participants who spent 1 hr or more gardening in the past week were defined as gardeners, resulting in a total of 1,585 gardeners and 1,652 nongardeners. Independent t tests, chi square, and regression analyses were conducted to examine the relationship between gardening and health outcomes. Findings indicate that gardeners reported significantly better balance and gait speed and had fewer chronic conditions and functional limitations than nongardeners. Significantly fewer gardeners than nongardeners reported a fall in the past 2 yr. The findings suggest that gardening may be a potential activity to incorporate into future fall-prevention programs.
Keywords: Accidental Falls; Age Factors; Aged; Aged, 80 and over; Aging; Chi-Square Distribution; Confidence Intervals; Exercise Test; Female; Gait; Gardening; Humans; Leisure activities; Male; Motor Activity; Odds Ratio; Postural Balance; Risk Assessment; Self Report; Task Performance and Analysis

Half of older Americans seen in emergency department in last month of life; most admitted to hospital, and many die there. - Alexander K Smith; Ellen P McCarthy; Ellen Weber; Irena Cenzer; W John Boscardin; Jonathan Fisher; Kenneth E Covinsky (Health Aff (Millwood), 2012)
Emergency department use contributes to high end-of-life costs and is potentially burdensome for patients and family members. We examined emergency department use in the last months of life for patients age sixty-five or older who died while enrolled in a longitudinal study of older adults in the period 1992-2006. We found that 51 percent of the 4,158 [corrected] decedents visited the emergency department in the last month of life, and 75 percent in the last six months of life. Repeat visits were common. A total of 77 percent of the patients seen in the emergency department in the last month of life were admitted to the hospital, and 68 percent of those who were admitted died there. In contrast, patients who enrolled in hospice at least one month before death rarely visited the emergency department in the last month of life. Policies that encourage the preparation of patients and families for death and early enrollment in hospice may prevent emergency department visits at the end of life.
Keywords: Aged; Aged, 80 and over; Emergency Service, Hospital; Female; Hospital Mortality; Hospitalization; Humans; Insurance Claim Review; Male; Terminal Care; Terminally Ill; United States

Health behavior change following chronic illness in middle and later life. - Jason T Newsom; Nathalie Huguet; Michael J. McCarthy; Pamela Ramage-Morin; Mark S Kaplan; Julie Bernier; Bentson McFarland; Jillian Oderkirk (J Gerontol B Psychol Sci Soc Sci, 2012)
OBJECTIVES: Understanding lifestyle improvements among individuals with chronic illness is vital for targeting interventions that can increase longevity and improve quality of life. METHODS: Data from the U.S. Health and Retirement Study were used to examine changes in smoking, alcohol use, and exercise 2-14 years after a diagnosis of heart disease, diabetes, cancer, stroke, or lung disease. RESULTS: Patterns of behavior change following diagnosis indicated that the vast majority of individuals diagnosed with a new chronic condition did not adopt healthier behaviors. Smoking cessation among those with heart disease was the largest observed change, but only 40% of smokers quit. There were no significant increases in exercise for any health condition. Changes in alcohol consumption were small, with significant declines in excessive drinking and increases in abstention for a few health conditions. Over the long term, individuals who made changes appeared to maintain those changes. Latent growth curve analyses up to 14 years after diagnosis showed no average long-term improvement in health behaviors. DISCUSSION: Results provide important new information on health behavior changes among those with chronic disease and suggest that intensive efforts are required to help initiate and maintain lifestyle improvements among this population.
Keywords: Age Factors; Aged; Aged, 80 and over; Alcohol Drinking; Chi-Square Distribution; Chronic disease; Diabetes Mellitus; Exercise; Female; Health Behavior; Heart Diseases; Humans; Longitudinal Studies; Lung Diseases; Male; Middle Aged; Neoplasms; Smoking; Stroke; Time Factors

Health investment decisions in response to diabetes information in older Americans. - Alexander N Slade (J Health Econ, 2012)
Diabetes is a very common and serious chronic disease, and one of the fastest growing disease burdens in the United States. Further, health behaviors, such as exercise, smoking, drinking, as well as weight status, are instrumental to diabetes management and the reduction of its medical consequences. Nine waves of the Health and Retirement Study are used to model the role of a recent diabetes diagnosis and medication on present and subsequent weight status, exercise, drinking and smoking activity. Several non-linear dynamic population average probit models are estimated. Results suggest that compared to non-diagnosed individuals at risk for high blood sugar, diagnosed diabetics respond initially in terms of increasing exercise, losing weight, and curbing smoking and drinking behavior, but the effect diminishes after diagnosis. Evidence of recidivism is also found in these outcomes, especially weight status and physical activity, suggesting that some behavioral responses to diabetes may be short-lived.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alcohol Drinking; Body Weight; Decision making; Diabetes Mellitus; Empirical Research; Exercise; Female; Health Behavior; Health Surveys; Humans; Male; Middle Aged; Models, Psychological; Smoking; United States

How safe is your neighborhood? Perceived neighborhood safety and functional decline in older adults. - Vivien K Sun; Irena Cenzer; Helen Kao; Cyrus Ahalt; Brie A Williams (J Gen Intern Med, 2012)
BACKGROUND: Neighborhood characteristics are associated with health and the perception of safety is particularly important to exercise and health among older adults. Little is known about the relationship between perception of neighborhood safety and functional decline in older adults. OBJECTIVE: To determine the relationship between perceived neighborhood safety and functional decline in older adults. DESIGN/SETTING: Longitudinal, community-based. PARTICIPANTS: 18,043 persons, 50 years or older, who participated in the 1998 and 2008 Health and Retirement Study. MAIN MEASURES: The primary outcome was 10-year functional decline (new difficulty or dependence in any Activity of Daily Living, new mobility difficulty, and/or death). The primary predictor was perceived neighborhood safety categorized into three groups: "very safe", "moderately safe", and "unsafe." We evaluated the association between perceived neighborhood safety and 10-year functional decline using a modified Poisson regression to generate unadjusted and adjusted relative risks (ARR). KEY RESULTS: At baseline 11,742 (68.0%) participants perceived their neighborhood to be very safe, 4,477 (23.3%) moderately safe, and 1,824 (8.7%) unsafe. Over 10 years, 10,338 (53.9%) participants experienced functional decline, including 6,266 (50.2%) who had perceived their neighborhood to be very safe, 2,839 (61.2%) moderately safe, and 1,233 (63.6%) unsafe, P < 0.001. For the 11,496 (63.3%) of participants who were functionally independent at baseline, perceived neighborhood safety was associated with 10-year functional decline (moderately safe ARR 1.15 95% CI 1.09-1.20; unsafe ARR 1.21 95% CI: 1.03-1.31 compared to very safe group). The relationship between perceived neighborhood safety and 10-year functional decline was not statistically significant for participants who had baseline functional impairment. CONCLUSION: Asking older adults about their perceived neighborhood safety may provide important information about their risk of future functional decline. These findings also suggest that future studies might focus on assessing whether interventions that promote physical activity while addressing safety concerns help reduce functional decline in older adults.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Health Status Disparities; Humans; Longitudinal Studies; Male; Middle Aged; Perception; Residence Characteristics; Safety; Surveys and Questionnaires

Loneliness, health, and mortality in old age: a national longitudinal study. - Ye Luo; Louise C Hawkley; Linda J. Waite; John T. Cacioppo (Soc Sci Med, 2012)
This study examined the relationship between loneliness, health, and mortality using a U.S. nationally representative sample of 2101 adults aged 50 years and over from the 2002 to 2008 waves of the Health and Retirement Study. We estimated the effect of loneliness at one point on mortality over the subsequent six years, and investigated social relationships, health behaviors, and health outcomes as potential mechanisms through which loneliness affects mortality risk among older Americans. We operationalized health outcomes as depressive symptoms, self-rated health, and functional limitations, and we conceptualized the relationships between loneliness and each health outcome as reciprocal and dynamic. We found that feelings of loneliness were associated with increased mortality risk over a 6-year period, and that this effect was not explained by social relationships or health behaviors but was modestly explained by health outcomes. In cross-lagged panel models that tested the reciprocal prospective effects of loneliness and health, loneliness both affected and was affected by depressive symptoms and functional limitations over time, and had marginal effects on later self-rated health. These population-based data contribute to a growing literature indicating that loneliness is a risk factor for morbidity and mortality and point to potential mechanisms through which this process works.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Studies; depression; Female; Health Behavior; Health Status; Humans; Interpersonal Relations; Loneliness; Longitudinal Studies; Male; Middle Aged; Mortality; Social Support; Socioeconomic factors; United States

Loneliness in older persons: a predictor of functional decline and death. - Perissinotto, Carla M; Irena Cenzer; Kenneth E Covinsky (Arch Intern Med, 2012)
BACKGROUND: Loneliness is a common source of distress, suffering, and impaired quality of life in older persons. We examined the relationship between loneliness, functional decline, and death in adults older than 60 years in the United States. METHODS: This is a longitudinal cohort study of 1604 participants in the psychosocial module of the Health and Retirement Study, a nationally representative study of older persons. Baseline assessment was in 2002 and follow-up assessments occurred every 2 years until 2008. Subjects were asked if they (1) feel left out, (2) feel isolated, or (3) lack companionship. Subjects were categorized as not lonely if they responded hardly ever to all 3 questions and lonely if they responded some of the time or often to any of the 3 questions. The primary outcomes were time to death over 6 years and functional decline over 6 years on the following 4 measures: difficulty on an increased number of activities of daily living (ADL), difficulty in an increased number of upper extremity tasks, decline in mobility, or increased difficulty in stair climbing. Multivariate analyses adjusted for demographic variables, socioeconomic status, living situation, depression, and various medical conditions. RESULTS: The mean age of subjects was 71 years. Fifty-nine percent were women; 81% were white, 11%, black, and 6%, Hispanic; and 18% lived alone. Among the elderly participants, 43% reported feeling lonely. Loneliness was associated with all outcome measures. Lonely subjects were more likely to experience decline in ADL (24.8% vs 12.5%; adjusted risk ratio [RR], 1.59; 95% CI, 1.23-2.07); develop difficulties with upper extremity tasks (41.5% vs 28.3%; adjusted RR, 1.28; 95% CI, 1.08-1.52); experience decline in mobility (38.1% vs 29.4%; adjusted RR, 1.18; 95% CI, 0.99-1.41); or experience difficulty in climbing (40.8% vs 27.9%; adjusted RR, 1.31; 95% CI, 1.10-1.57). Loneliness was associated with an increased risk of death (22.8% vs 14.2%; adjusted HR, 1.45; 95% CI, 1.11-1.88). CONCLUSION: Among participants who were older than 60 years, loneliness was a predictor of functional decline and death.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Female; Humans; Loneliness; Longitudinal Studies; Male; Middle Aged; Mortality; United States; Upper Extremity; Walking

Long-term rate of change in memory functioning before and after stroke onset. - Qianyi Wang; Benjamin D Capistrant; Amy Ehntholt; M. Maria Glymour (Stroke, 2012)
BACKGROUND AND PURPOSE: Memory impairment is a predictor and a consequence of stroke, but memory decline is common even in healthy elderly individuals. We compared the long-term trajectory of memory functioning before and after stroke with memory change in stroke-free elderly individuals. METHODS: Health and Retirement Study participants aged 50 years and older (n=17 340) with no stroke history at baseline were interviewed biennially up to 10 years for first self-reported or proxy-reported stroke (n=1574). Age-, sex-, and race-adjusted segmented linear regression models were used to compare annual rates of change in a composite memory score before and after stroke among 3 groups: 1189 stroke survivors; 385 stroke decedents; and 15 766 cohort members who remained stroke-free. RESULTS: Before stroke onset, individuals who later survived stroke had significantly (P<0.001) faster average annual rates of memory decline (-0.143 points per year) than those who remained stroke-free throughout follow-up (-0.101 points per year). Stroke decedents had even faster prestroke memory decline (-0.212 points per year). At stroke onset, memory declined an average of -0.369 points among stroke survivors, comparable with 3.7 years of age-related decline in stroke-free cohort members. After stroke, memory in stroke survivors continued to decline at -0.142 points per year, similar to their prestroke rates (P=0.93). Approximately 50% of the memory difference between stroke survivors soon after stroke and age-matched stroke-free individuals was attributable to prestroke memory. CONCLUSIONS: Although stroke onset induced large decrements in memory, memory differences were apparent years before stroke. Memory declines before stroke, especially among those who did not survive the stroke, were faster than declines among stroke-free adults.
Keywords: Aged; Aged, 80 and over; Cohort Studies; disease progression; Female; Follow-Up Studies; Humans; Linear Models; Longitudinal Studies; Male; Memory; Memory Disorders; Middle Aged; Stroke; Survivors; Time Factors

Measurement equivalence in ADL and IADL difficulty across international surveys of aging: findings from the HRS, SHARE, and ELSA. - Kitty S. Chan; Judith D Kasper; Jason Brandt; Liliana E Pezzin (J Gerontol B Psychol Sci Soc Sci, 2012)
OBJECTIVE: To examine the measurement equivalence of items on disability across three international surveys of aging. METHOD: Data for persons aged 65 and older were drawn from the Health and Retirement Survey (HRS, n = 10,905), English Longitudinal Study of Aging (ELSA, n = 5,437), and Survey of Health, Ageing and Retirement in Europe (SHARE, n = 13,408). Differential item functioning (DIF) was assessed using item response theory (IRT) methods for activities of daily living (ADL) and instrumental activities of daily living (IADL) items. RESULTS: HRS and SHARE exhibited measurement equivalence, but 6 of 11 items in ELSA demonstrated meaningful DIF. At the scale level, this item-level DIF affected scores reflecting greater disability. IRT methods also spread out score distributions and shifted scores higher (toward greater disability). Results for mean disability differences by demographic characteristics, using original and DIF-adjusted scores, were the same overall but differed for some subgroup comparisons involving ELSA. DISCUSSION: Testing and adjusting for DIF is one means of minimizing measurement error in cross-national survey comparisons. IRT methods were used to evaluate potential measurement bias in disability comparisons across three international surveys of aging. The analysis also suggested DIF was mitigated for scales including both ADL and IADL and that summary indexes (counts of limitations) likely underestimate mean disability in these international populations.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Bias; Europe; Female; Health Surveys; Humans; Internationality; Longitudinal Studies; Male; United States

Predictors of self-report of heart failure in a population-based survey of older adults. - Tanya R Gure; Ryan J McCammon; Christine T Cigolle; Todd M Koelling; Caroline S Blaum; Kenneth M. Langa (Circ Cardiovasc Qual Outcomes, 2012)
BACKGROUND: Little research has been conducted on the predictors of self-report or patient awareness of heart failure (HF) in a population-based survey. The objective of this study was to (1) test the agreement between Medicare administrative and Health and Retirement Study (HRS) survey data and (2) determine predictors associated with self-report of HF, using a validated Medicare claims algorithm as the reference standard. We hypothesized that those who self-reported HF were more likely to have a higher number of HF-related claims. METHODS AND RESULTS: Secondary data analysis was conducted using the 2004 wave of the HRS linked to 2002 to 2004 Medicare claims (n=5573 respondents aged ≥ 67 years). Concordance between self-report of HF in the HRS and Medicare claims was calculated. Logistic regression was performed to identify predictors associated with self-report HF. HF prevalence by self-report was 4.6%. Self-report of HF and claims agreement was 87% (κ=0.34). The presence of >1 HF inpatient claims was associated with greater odds of self-report (odds ratio [OR], 1.92; 95% CI, 1.23-3.00). Greater odds of self-reporting HF was also associated with ≥ 4 HF claims (OR, 2.74; 95% CI, 1.36-5.52). Blacks (OR, 0.28; 95% CI, 0.14-0.55) and Hispanics (OR, 0.30; 95% CI, 0.11-0.83) were less likely to self-report HF compared with whites in the final model. CONCLUSIONS: Self-report of HF is an insensitive method for accurately identifying HF cases, especially in those with less-severe disease and who are nonwhite. There may be limited awareness of HF among older minority patients despite having clinical encounters during which HF is coded as a diagnosis.
Keywords: Age Factors; Aged; Aged, 80 and over; Algorithms; Awareness; Chi-Square Distribution; Comorbidity; Female; Health Knowledge, Attitudes, Practice; Health Status; Health Surveys; Heart Failure; Humans; Insurance Claim Review; Logistic Models; Male; Medicare; Odds Ratio; Patients; Predictive Value of Tests; Self Report; Socioeconomic factors; United States

Presepsis depressive symptoms are associated with incident cognitive impairment in survivors of severe sepsis: a prospective cohort study of older Americans. - Dimitry S Davydow; Catherine L Hough; Kenneth M. Langa; Theodore J Iwashyna (J Am Geriatr Soc, 2012)
OBJECTIVES: To test the hypothesis that presepsis depressive symptoms are associated with risk of new cognitive impairment in survivors of severe sepsis. DESIGN: Prospective longitudinal cohort study. SETTING: Population-based cohort of older U.S. adults interviewed as part of the Health and Retirement Study (1998-2006). PARTICIPANTS: Four hundred forty-seven individuals with normal presepsis cognition who survived 540 hospitalizations for severe sepsis and completed at least one follow-up interview. MEASUREMENTS: Severe sepsis was identified using a validated algorithm in Medicare claims. Depressive symptoms were assessed prospectively using a modified version of the Center for Epidemiologic Studies Depression Scale. Cognitive function was assessed using versions of the Telephone Interview for Cognitive Status (TICS). Logistic regression with robust standard errors was used to examine associations between substantial depressive symptoms at any interview before sepsis and incident cognitive impairment (mild or moderate to severe cognitive impairment) at any interview after sepsis. RESULTS: The prevalence of substantial depressive symptoms in participants with normal cognition before sepsis was 38% (95% confidence interval (CI) = 34-42%). After severe sepsis, 18% (95% CI = 15-20%) of survivors had incident cognitive impairment. In unadjusted analyses, presepsis substantial depressive symptoms were associated with postsepsis incident cognitive impairment (odds ratio (OR) = 2.56, 95% CI = 1.53-4.27). After adjustment for demographics, health-risk behaviors, clinical characteristics of the sepsis episode, and presepsis TICS scores, substantial presepsis depressive symptoms remained the strongest factor associated with postsepsis incident cognitive impairment (OR = 2.58, 95% CI = 1.45-4.59). CONCLUSION: Substantial presepsis depressive symptoms are independently associated with incident postsepsis cognitive impairment. Depressed older adults may be particularly at risk of developing cognitive impairment after a serious medical illness.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Cohort Studies; depression; Female; Humans; Longitudinal Studies; Male; Sepsis; Survivors

Prevalence of cognitive impairment in older adults with heart failure. - Tanya R Gure; Caroline S Blaum; Bruno J Giordani; Todd M Koelling; Andrzej T Galecki; Susan J Pressler; Scott L Hummel; Kenneth M. Langa (J Am Geriatr Soc, 2012)
OBJECTIVES: To determine the prevalence of cognitive impairment in older adults with heart failure (HF). DESIGN: Cross-sectional analysis of the 2004 wave of the nationally representative Health and Retirement Study linked to 2002 to 2004 Medicare administrative claims. SETTING: United States, community. PARTICIPANTS: Six thousand one hundred eighty-nine individuals aged 67 and older. MEASUREMENTS: An algorithm was developed using a combination of self- and proxy report of a heart problem and the presence of one or more Medicare claims in administrative files using standard HF diagnostic codes. On the basis of the algorithm, three categories were created to characterize the likelihood of a HF diagnosis: high or moderate probability of HF, low probability of HF, and no HF. Cognitive function was assessed using a screening measure of cognitive function or according to proxy rating. Age-adjusted prevalence estimates of cognitive impairment were calculated for the three groups. RESULTS: The prevalence of cognitive impairment consistent with dementia in older adults with HF was 15%, and the prevalence of mild cognitive impairment was 24%. The odds of dementia in those with HF were significantly higher, even after adjustment for age, education level, net worth, and prior stroke (odds ratio = 1.52, 95% confidence interval = 1.14-2.02). CONCLUSION: Cognitive impairment is common in older adults with HF and is independently associated with risk of dementia. A cognitive assessment should be routinely incorporated into HF-focused models of care.
Keywords: Aged; Aged, 80 and over; Algorithms; Chi-Square Distribution; Cognition Disorders; Cross-Sectional Studies; Demography; Female; Heart Failure; Humans; Logistic Models; Male; Medicare; Prevalence; United States

A prospective examination of the relationship between physical activity and dementia risk in later life. - Mary E Bowen (Am J Health Promot, 2012)
PURPOSE: To examine the relationship between vigorous physical activity and dementia risk. DESIGN: Prospective study design utilizing physical activity data from the Health and Retirement Study and cognitive outcome data from the Aging, Demographics, and Memory Study. SETTING: Community-based. SUBJECTS: Adults age 71 and over (N  =  808) with 3 to 7 years of physical activity information prior to dementia/no dementia diagnosis. MEASURES: Physical activity was measured by participation in vigorous activities such as aerobics, sports, running, bicycling, and heavy housework three or more times per week (yes/no). Dementia diagnosis was based on an expert panel (e.g., neuropsychologists, neurologists, geropsychiatrists) who performed and reviewed a battery of neuropsychological tests. ANALYSIS: Binary logistic regression models were used to account for demographic characteristics, genetic risk factors (one or two apolipoprotein E ε4 alleles), health behaviors (e.g., smoking, drinking alcohol), health indicators (body mass index), and health conditions (e.g., diabetes, heart disease) in a sequential model-building process. RESULTS: The relationship between vigorous physical activity and dementia risk remained robust across models. In the final model, older adults who were physically active were 21% (p ≤ .05) less likely than their counterparts to be diagnosed with dementia. CONCLUSION: Vigorous physical activity may reduce the risk for dementia independently of the factors examined here. This study's findings are important given that few preventative strategies for dementia have been explored beyond hormonal therapy and anti-inflammatory drugs.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Body Mass Index; Confidence Intervals; Dementia; disease progression; Exercise; Female; Health Promotion; Health Status Indicators; Health Surveys; Humans; Logistic Models; Male; Motor Activity; Multivariate Analysis; Odds Ratio; Prospective Studies; Psychometrics; Risk Factors; United States

Race/ethnic and nativity disparities in later life physical performance: the role of health and socioeconomic status over the life course. - Steven A Haas; Patrick M. Krueger; Leah Rohlfsen (J Gerontol B Psychol Sci Soc Sci, 2012)
OBJECTIVES: We examine race/ethnic and nativity differences in objective measures of physical performance (i.e., peak expiratory flow, grip strength, and gait speed) in a nationally representative sample of older Whites, Blacks, and Hispanics. We also examine whether detailed measures of childhood and adult health and socioeconomic status (SES) mediate race/ethnic differences in physical performance. METHOD: We use data from the Health and Retirement Study, a population-based sample of older Americans born before 1947, and 3 measures of physical performance. Nested ordinary least squares models examine whether childhood and adult health and SES mediate race/ethnic differences in performance. RESULTS: We find large and significant race/ethnic and nativity differences in lung function, grip strength, and gait speed. Adjusting for childhood and current adult health and SES reduces race/ethnic differences in physical performance but does not eliminate them entirely. Childhood health and SES as well as more proximal levels of SES are important determinants of race/ethnic disparities in later life physical performance. DISCUSSION: The analysis highlights that a large proportion of race/ethnic and nativity disparities result from health and socioeconomic disadvantages in both early life and adulthood and thus suggests multiple intervention points at which disparities can be reduced.
Keywords: Aged; Aged, 80 and over; Aging; ethnicity; Female; Gait; Hand Strength; Health Status; Health Status Disparities; Health Surveys; Humans; Male; Middle Aged; Racial Groups; Respiratory Function Tests; Social Class; United States

The relationship between cognitive impairment and diabetes self-management in a population-based community sample of older adults with Type 2 diabetes. - Denise G Feil; Carolyn Wei Zhu; David L Sultzer (J Behav Med, 2012)
Although nearly one-third of older diabetics are cognitively impaired, their diabetes management remains poorly understood. To examine the relationship between cognitive impairment and diabetes self-management in a population-based community sample of older adults with Type 2 diabetes. Cross-sectional observational analysis. 1,398 persons with diabetes, aged 60 years or older, who responded to the 2003 Health and Retirement Study Diabetes Survey. We conducted logistic regressions on the effects of cognitive impairment on respondents' self-management ability after controlling for diabetes comorbidities, demographics, and clinical characteristics. Participants with greater cognitive impairment were less likely to adhere to exercise (Adjusted Odds ratio [AOR] = 0.725 and 0.712 for moderate and severe cognitive impairment, both P < 0.05), and to diet (AOR = 0.906 and 0.618 for moderate and severe cognitive impairment, both P < 0.01). Cognitive impairment is associated with worse self-care and may pose challenges to diabetic older persons, notably in diet and exercise. Cognitive screening may be indicated in this high risk group.
Keywords: Aged; Aged, 80 and over; Blood Glucose; Cognition Disorders; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Exercise; Female; Health Surveys; Humans; Male; Middle Aged; Self Care

Restless legs syndrome and functional limitations among American elders in the Health and Retirement Study. - Dominic J Cirillo; Robert B Wallace (BMC Geriatr, 2012)
BACKGROUND: Restless legs syndrome (RLS) is a common condition associated with decreased quality of life in older adults. This study estimates the prevalence, risk factors, and functional correlates of among U.S. elders. METHODS: Subjects (n = 1,008) were sub-sampled from the 2002 cross-sectional interview survey of the Health and Retirement Study (HRS), a nationally representative study of U.S. elders. Symptoms and sleep disturbances consistent with RLS were identified. Activities of daily living (ADL), instrumental activities of daily living (IADL), and limitations for mobility, large muscle groups, gross and fine motor function were measured using standardized questions. Incident functional limitations were detected over six years of observation. RESULTS: The prevalence of RLS among U.S. elders born before 1947 was 10.6%. Factors associated with increased prevalence RLS at baseline included: overweight body mass index (multivariate adjusted prevalence ratio = 1.77; 95% confidence interval (CI) 1.05-2.99); mild-to-moderate pain (2.67, 1.47-4.84) or pain inferring with activity (3.44, 2.00-5.93); three or more chronic medications (2.54, 1.26-5.12), highest quartile of out-of-pocket medical expenses (2.12, 1.17-3.86), frequent falls (2.63, 1.49-4.66), health limiting ability to work (2.91, 1.75-4.85), or problems with early waking or frequent wakening (1.69, 1.09-2.62 and 1.55, 1.00-2.41, respectively). Current alcohol consumption (0.59, 0.37-0.92) and frequent healthcare provider visits (0.49, 0.27-0.90) were associated with decreased RLS prevalence. RLS did not predict incident disability for aggregate measures but was associated with increased risk for specific limitations, including: difficulty climbing several stair flights (multivariate-adjusted hazard ratio = 2.38, 95% CI 1.39-4.06), prolonged sitting (2.17, 1.25-3.75), rising from a chair (2.54, 1.62-3.99), stooping (2.66, 1.71-4.15), moving heavy objects (1.79, 1.08-2.99), carrying ten pounds (1.61, 1.05-2.97), raising arms (1.76, 1.05-2.97), or picking up a dime (1.97, 1.12-3.46). CONCLUSIONS: RLS sufferers are more likely to have functional disability, even after adjusting for health status and pain syndrome correlates.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Body Mass Index; Cross-Sectional Studies; Disabled Persons; Female; Humans; Male; Middle Aged; Prevalence; Restless Legs Syndrome; Risk Factors; United States

Risk factors of falls in community-dwelling older adults: logistic regression tree analysis. - Takashi Yamashita; Noe, Douglas A.; John A. Bailer (Gerontologist, 2012)
PURPOSE OF THE STUDY: A novel logistic regression tree-based method was applied to identify fall risk factors and possible interaction effects of those risk factors. DESIGN AND METHODS: A nationally representative sample of American older adults aged 65 years and older (N = 9,592) in the Health and Retirement Study 2004 and 2006 modules was used. Logistic Tree with Unbiased Selection, a computer algorithm for tree-based modeling, recursively split the entire group in the data set into mutually exclusive subgroups and fit a logistic regression model in each subgroup to generate an easily interpreted tree diagram. RESULTS: A subgroup of older adults with a fall history and either no activities of daily living (ADL) limitation and at least one instrumental activity of daily living or at least one ADL limitation was classified as at high risk of falling. Additionally, within each identified subgroup, the best predictor of falls varied over subgroups and was also evaluated. IMPLICATIONS: Application of tree-based methods may provide useful information for intervention program design and resource allocation planning targeting subpopulations of older adults at risk of falls.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Aged, 80 and over; Decision Trees; Female; Geriatric Assessment; Health Surveys; Humans; Logistic Models; Male; Predictive Value of Tests; Residence Characteristics; Risk Assessment; Socioeconomic factors; United States

Self- and other-oriented potential lifetime traumatic events as predictors of loneliness in the second half of life. - Yuval Palgi; Amit Shrira; Menachem Ben-Ezra; Sharon Shiovitz-Ezra; Liat Ayalon (Aging Ment Health, 2012)
OBJECTIVES: This study examined the relationship between self- and other-oriented potential lifetime traumatic events (PLTE) and loneliness at the second half of life. METHOD: The sample was comprised of 7446 respondents who completed the Health and Retirement Study (HRS) 2006 psychosocial questionnaire. PLTE were classified into self-oriented PLTE, defined as traumatic events that primarily inflict the self (e.g., being abused by parents) and other-oriented PLTE, defined as events that affect the self by primarily targeting others (e.g., death of one's child). We evaluated the role of self- and other-oriented PLTE as predictors of loneliness, as evaluated by the short R-UCLA. Analyses were stratified by age at which trauma happened categorized into four life periods (0-17, 18-30, 31-49, 50+). RESULTS: The results showed that PLTE is positively related to loneliness. Moreover, the number of other-oriented PLTE, and even more pronouncedly self-oriented PLTE, that happened up until adulthood were the strongest predictors of loneliness at the second half of life. CONCLUSION: The study suggests that self- and other-oriented PLTE reported to have occurred early in life are associated with perceived loneliness in the second half of life.
Keywords: Age Factors; Aged; Aged, 80 and over; Child; Child Abuse; Cross-Sectional Studies; depression; Female; Forecasting; Humans; Life Change Events; Loneliness; Male; Middle Aged; Self Psychology; Wounds and Injuries

Self-care and health outcomes of diabetes mellitus. - MinKyoung Song; Sarah J Ratcliffe; Nancy C Tkacs; Barbara Riegel (Clin Nurs Res, 2012)
Studies show that self-care improves diabetes mellitus (DM) outcomes; however, previous studies have focused on self-care maintenance, and little is known about self-care management. The objective of this study is to examine the influence of DM self-care maintenance and management on number of hospitalizations and hospitalization days. A cohort design with secondary analysis of data from the Health and Retirement Study 2002-2004 was used. Data from 726 adults with DM were analyzed with logistic regression and negative binomial regression adjusting for covariates. Self-care maintenance and management were significant determinants of hospitalization outcomes. Establishing a goal for HbA1c (self-care management) and eating ≥2 snacks or desserts per day (self-care maintenance) were associated with a decrease in hospitalizations (IRR = 0.860, p = .001; IRR = 0.914, p = .043, respectively). DM self-care maintenance and management influence health outcomes but in different ways. These data provide evidence that both elements are needed in the education of patients about DM.
Keywords: Adult; Aged; Aged, 80 and over; Clinical Nursing Research; Diabetes Mellitus; Female; Follow-Up Studies; Hospitalization; Humans; Length of Stay; Male; Middle Aged; Self Care; Treatment Outcome

The significance of education for mortality compression in the United States. - Dustin C. Brown; Mark D Hayward; Jennifer Karas Montez; Robert A Hummer; Chi-Tsun Chiu; Mira M Hidajat (Demography, 2012)
Recent studies of old-age mortality trends assess whether longevity improvements over time are linked to increasing compression of mortality at advanced ages. The historical backdrop of these studies is the long-term improvement in a population's socioeconomic resources that fueled longevity gains. We extend this line of inquiry by examining whether socioeconomic differences in longevity within a population are accompanied by old-age mortality compression. Specifically, we document educational differences in longevity and mortality compression for older men and women in the United States. Drawing on the fundamental cause of disease framework, we hypothesize that both longevity and compression increase with higher levels of education and that women with the highest levels of education will exhibit the greatest degree of longevity and compression. Results based on the Health and Retirement Study and the National Health Interview Survey Linked Mortality File confirm a strong educational gradient in both longevity and mortality compression. We also find that mortality is more compressed within educational groups among women than men. The results suggest that educational attainment in the United States maximizes life chances by delaying the biological aging process.
Keywords: Aged; Aged, 80 and over; Aging; Educational Status; Female; Health Status Disparities; Humans; Life Expectancy; Male; Middle Aged; Mortality; Mortality, Premature; Sex Distribution; Socioeconomic factors; United States

Spurious inferences about long-term outcomes: the case of severe sepsis and geriatric conditions. - Theodore J Iwashyna; Netzer, Giora; Kenneth M. Langa; Christine T Cigolle (Am J Respir Crit Care Med, 2012)
RATIONALE: Survivors of critical illness suffer significant limitations and disabilities. OBJECTIVES: Ascertain whether severe sepsis is associated with increased risk of so-called geriatric conditions (injurious falls, low body mass index [BMI], incontinence, vision loss, hearing loss, and chronic pain) and whether this association is measured consistently across three different study designs. METHODS: Patients with severe sepsis were identified in the Health and Retirement Study, a nationally representative cohort interviewed every 2 years, 1998 to 2006, and in linked Medicare claims. Three comparators were used to assess an association of severe sepsis with geriatric conditions in survivors: the prevalence in the United States population aged 65 years and older, survivors' own pre-sepsis levels assessed before hospitalization, or survivors' own pre-sepsis trajectory. MEASUREMENTS AND MAIN RESULTS: Six hundred twenty-three severe sepsis hospitalizations were followed a median of 0.92 years. When compared with the 65 years and older population, surviving severe sepsis was associated with increased rates of low BMI, injurious falls, incontinence, and vision loss. Results were similar when comparing survivors to their own pre-sepsis levels. The association of low BMI and severe sepsis persisted when controlling for patients' pre-sepsis trajectories, but there was no association of severe sepsis with injurious falls, incontinence, vision loss, hearing loss, and chronic pain after such controls. CONCLUSIONS: Geriatric conditions are common after severe sepsis. However, severe sepsis is associated with increased rates of only a subset of geriatric conditions, not all. In studying outcomes after acute illness, failing to measure and control for both preillness levels and trajectories may result in erroneous conclusions.
Iwashyna, Theodore J Netzer, Giora Langa, Kenneth M Cigolle, Christine K08 AG031837/AG/NIA NIH HHS/ K08 HL091249/HL/NHLBI NIH HHS/ K12 RR023250/RR/NCRR NIH HHS/ P30-AG028747/AG/NIA NIH HHS/ P60 DK-20572/DK/NIDDK NIH HHS/ R01 AG030155/AG/NIA NIH HHS/ U01 AG09740/AG/NIA NIH HHS/ UL1RR024986/RR/NCRR NIH HHS/ Am J Respir Crit Care Med. 2012 Apr 15;185(8):835-41. Epub 2012 Feb 9.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Chronic pain; Cohort Studies; Comorbidity; Critical Illness; Disabled Persons; disease progression; Female; Geriatric Assessment; Hearing Disorders; Hospitalization; Humans; Incidence; Male; Musculoskeletal Diseases; Prognosis; Retrospective Studies; Risk Assessment; Sepsis; Survival Analysis; Survivors; Thinness; Time; Treatment Outcome; Urinary incontinence; Vision Disorders

Variation in cognitive functioning as a refined approach to comparing aging across countries. - Skirbekk, V.; Loichinger, E.; Daniela Weber (Proc Natl Acad Sci U S A, 2012)
Comparing the burden of aging across countries hinges on the availability of valid and comparable indicators. The Old Age Dependency Ratio allows only a limited assessment of the challenges of aging, because it does not include information on any individual characteristics except age itself. Existing alternative indicators based on health or economic activity suffer from measurement and comparability problems. We propose an indicator based on age variation in cognitive functioning. We use newly released data from standardized tests of seniors' cognitive abilities for countries from different world regions. In the wake of long-term advances in countries' industrial composition, and technological advances, the ability to handle new job procedures is now of high and growing importance, which increases the importance of cognition for work performance over time. In several countries with older populations, we find better cognitive performance on the part of populations aged 50+ than in countries with chronologically younger populations. This variation in cognitive functioning levels may be explained by the fact that seniors in some regions of the world experienced better conditions during childhood and adult life, including nutrition, duration and quality of schooling, lower exposure to disease, and physical and social activity patterns. Because of the slow process of cohort replacement, those countries whose seniors already have higher cognitive levels today are likely to continue to be at an advantage for several decades to come.
Skirbekk, Vegard Loichinger, Elke Weber, Daniela 2R01AG017644/AG/NIA NIH HHS/United States 2R01AG7644-01A1/AG/NIA NIH HHS/United States P01 AG005842/AG/NIA NIH HHS/United States P01 AG08291/AG/NIA NIH HHS/United States P30 AG12815/AG/NIA NIH HHS/United States R21 AG025169/AG/NIA NIH HHS/United States U01 AG09740-13S2/AG/NIA NIH HHS/United States U01AG009740/AG/NIA NIH HHS/United States Y1-AG-4553-01/AG/NIA NIH HHS/United States Research Support, N.I.H., Extramural Research Support, Non-U.S. Gov't United States Proc Natl Acad Sci U S A. 2012 Jan 17;109(3):770-4. Epub 2011 Dec 19.
Keywords: Age Distribution; Aged; Aged, 80 and over; Aging; Cognition; Data collection; Databases as Topic; Humans; Internationality; Male; Middle Aged

Aging in a cultural context: cross-national differences in disability and the moderating role of personal control among older adults in the United States and England. - Philippa J Clarke; Jacqui Smith (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: We investigate cross-national differences in late-life health outcomes and focus on an intriguing difference in beliefs about personal control found between older adult populations in the U.K. and United States. We examine the moderating role of control beliefs in the relationship between physical function and self-reported difficulty with daily activities. METHOD: Using national data from the United States (Health and Retirement Study) and England (English Longitudinal Study on Ageing), we examine the prevalence in disability across the two countries and show how it varies according to the sense of control. Poisson regression was used to examine the relationship between objective measures of physical function (gait speed) and disability and the modifying effects of control. RESULTS: Older Americans have a higher sense of personal control than the British, which operates as a psychological resource to reduce disability among older Americans. However, the benefits of control are attenuated as physical impairments become more severe. DISCUSSION: These results emphasize the importance of carefully considering cross-national differences in the disablement process as a result of cultural variation in underlying psychosocial resources. This paper highlights the role of culture in shaping health across adults aging in different sociopolitical contexts.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cross-Cultural Comparison; Culture; Disabled Persons; England; Female; Gait; Health Status; Humans; Internal-External Control; Longitudinal Studies; Male; Mobility Limitation; Politics; Social Values; Socioeconomic factors; United States

Is the apolipoprotein e genotype a biomarker for mild cognitive impairment? Findings from a nationally representative study. - Brainerd, Charles J; V. F. Reyna; Ronald C Petersen; Glenn E Smith; Taub, Emily S (Neuropsychology, 2011)
OBJECTIVE: Although the ε4 allele of the apolipoprotein E (APOE) genotype is a known risk factor for Alzheimer's dementia (AD), prior findings on whether it is also a risk factor for mild cognitive impairment (MCI) have been inconsistent. We tested two contrasting explanations: (a) an ε4-AD specificity hypothesis, and (b) a measurement insensitivity hypothesis. METHOD: The frequency of the ε4 allele was investigated in older adults (mean age > 70) with various types of cognitive impairment (including MCI) and various types of dementia (including AD) with the aging, demographics, and memory study (ADAMS) of the National Institute on Aging's Health and Retirement Study (HRS). The ADAMS controls sources of Type I and Type II error that are posited in the ε4-AD specificity hypothesis and the measurement insensitivity hypothesis, and it is the only nationally representative data set on aging and cognitive impairment. RESULTS: ε4 was a reliable predictor of MCI, with a frequency of 32% in MCI subjects versus 20% in healthy control subjects. This link was specific to MCI because ε4 was not a risk factor for other forms of cognitive impairment without dementia. CONCLUSIONS: The results support the measurement insensitivity hypothesis rather than the ε4-AD specificity hypothesis and are consistent with recent research showing modest reductions in cognitive performance among normal functioning ε4 carriers.
Brainerd, Charles J Reyna, Valerie F Petersen, Ronald C Smith, Glenn E Taub, Emily S 1RC1AG036915-01/AG/NIA NIH HHS/United States U01AG009740/AG/NIA NIH HHS/United States Research Support, N.I.H., Extramural United States Neuropsychology. 2011 Nov;25(6):679-89.
Keywords: Aged; Aged, 80 and over; Aging; Analysis of Variance; Apolipoprotein E4; Cognitive Dysfunction; Dementia; Female; Gene Frequency; Genetic Markers; Genetic Testing; Genotype; Humans; Male; National Institute on Aging (U.S.); Neuropsychological tests; Reference Values; Reproducibility of Results; Risk Factors; United States

Assessment of cognition using surveys and neuropsychological assessment: the Health and Retirement Study and the Aging, Demographics, and Memory Study. - Eileen M. Crimmins; Jung K Kim; Kenneth M. Langa; David R Weir (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: This study examines the similarity of cognitive assessments using 1 interview in a large population study, the Health and Retirement Study (HRS), and a subsample in which a detailed neuropsychiatric assessment has been performed (Aging, Demographics, and Memory Study [ADAMS]). METHODS: Respondents are diagnosed in ADAMS as demented, cognitively impaired without dementia (CIND), or as having normal cognitive function. Multinomial logistic analysis is used to predict diagnosis using a variety of cognitive and noncognitive measures from the HRS and additional measures and information from ADAMS. RESULTS: The cognitive tests in HRS predict the ADAMS diagnosis in 74% of the sample able to complete the HRS survey on their own. Proxy respondents answer for a large proportion of HRS respondents who are diagnosed as demented in ADAMS. Classification of proxy respondents with some cognitive impairment can be predicted in 86% of the sample. Adding a small number of additional tests from ADAMS can increase each of these percentages to 84% and 93%, respectively. DISCUSSION: Cognitive assessment appropriate for diagnosis of dementia and CIND in large population surveys could be improved with more targeted information from informants and additional cognitive tests targeting other areas of brain function.
Crimmins, Eileen M Kim, Jung Ki Langa, Kenneth M Weir, David R P30 AG17265/AG/NIA NIH HHS/United States U01 AG009740/AG/NIA NIH HHS/United States Research Support, N.I.H., Extramural United States The journals of gerontology. Series B, Psychological sciences and social sciences J Gerontol B Psychol Sci Soc Sci. 2011 Jul;66 Suppl 1:i162-71.
Keywords: Age Factors; Aged; Aged, 80 and over; Cognition; Cognition Disorders; Dementia; Educational Status; Female; Humans; Interviews as Topic; Logistic Models; Longitudinal Studies; Male; Multivariate Analysis; Neuropsychological tests; Odds Ratio; Prevalence; Sex Factors; United States

Can Food Stamps help to reduce Medicare spending on diabetes? - Lauren Hersch Nicholas (Econ Hum Biol, 2011)
Diabetes is rapidly escalating amongst low-income, older adults at great cost to the Medicare program. We use longitudinal survey data from the Health and Retirement Study linked to administrative Medicare records and biomarker data to assess the relationship between Food Stamp receipt and diabetes health outcomes. We find no significant difference in Medicare spending, outpatient utilization, diabetes hospitalizations and blood sugar (HbA1c) levels between recipients and income-eligible non-recipients after controlling for a detailed set of covariates including individual fixed effects and measures of diabetes treatment compliance. As one-third of elderly Food Stamp recipients are currently diabetic, greater coordination between the Food Stamp, Medicare, and Medicaid programs may improve health outcomes for this group.
Keywords: Aged; Aged, 80 and over; Biomarkers; Confidence Intervals; Cross-Sectional Studies; Diabetes Mellitus; Female; Glycated Hemoglobin; Health Care Costs; Humans; Longitudinal Studies; Male; Medicare; Middle Aged; Odds Ratio; Outpatients; Poverty; Prevalence; Public Assistance; Regression Analysis; Social Welfare; Treatment Outcome; United States

Caregiver burden and neuropsychiatric symptoms in older adults with cognitive impairment: the Aging, Demographics, and Memory Study (ADAMS). - Okura, Toru; Kenneth M. Langa (Alzheimer Dis Assoc Disord, 2011)
OBJECTIVES: To estimate the quantity of informal care associated with neuropsychiatric symptoms in older adults with cognitive impairment. DESIGN: Cross-sectional analysis. SETTING: The Aging, Demographics, and Memory Study. PARTICIPANTS: A sample (n=450) of adults aged 71 years and older with cognitive impairment drawn form the Health and Retirement Study. MEASUREMENTS: The presence of neuropsychiatric symptoms (delusions, hallucinations, agitation, depression, apathy, elation, anxiety, disinhibition, irritation, and aberrant motor behaviors) was identified using the neuropsychiatric inventory. Cognitive category [normal, cognitive impairment without dementia (CIND), or dementia] was assigned by a consensus panel. The hours per week of active help and supervision were ascertained by informant questionnaire. RESULTS: Among older adults with CIND or dementia, those with no neuropsychiatric symptoms received an average of 10.2 hours of active help and 10.9 hours of supervision per week from informal caregivers. Those with 1 or 2 neuropsychiatric symptoms received an additional 10.0 hours of active help and 12.4 hours of supervision per week, while those with 3 or more symptoms received an additional 18.2 hours of active help and 28.7 hours of supervision per week (P<0.001). The presence of irritation (14.7 additional hours) was associated with the greatest number of additional hours of active help. The presence of aberrant motor behaviors (17.7 additional hours) and disinhibition (17.5 additional hours) were associated with the greatest number of additional hours of supervision. CONCLUSIONS: Neuropsychiatric symptoms among those with CIND or dementia are associated with a significant increase in the provision of informal care. This care represents a significant time commitment for families and a significant economic cost to society.
Okura, Toru Langa, Kenneth M R01 AG027010/AG/NIA NIH HHS/United States R01 AG030155-01/AG/NIA NIH HHS/United States R01 AG030155-02/AG/NIA NIH HHS/United States R01 AG030155-03/AG/NIA NIH HHS/United States R01 AG030155-04/AG/NIA NIH HHS/United States R01 AG030155-05/AG/NIA NIH HHS/United States U01 AG09740/AG/NIA NIH HHS/United States Research Support, N.I.H., Extramural United States Alzheimer disease and associated disorders Nihms259646 Alzheimer Dis Assoc Disord. 2011 Apr-Jun;25(2):116-21.
Keywords: Aged; Aged, 80 and over; Caregivers; Cognition Disorders; Cost of Illness; Cross-Sectional Studies; Female; Humans; Male; Neuropsychological tests

Determinants of death in the hospital among older adults. - Amy Kelley; Susan L Ettner; Neil S. Wenger; Catherine A Sarkisian (J Am Geriatr Soc, 2011)
OBJECTIVES: To investigate patient-level determinants of in-hospital death, adjusting for patient and regional characteristics. DESIGN: Using multivariable regression, the relationship between in-hospital death and participants' social, functional, and health characteristics was investigated, controlling for regional Hospital Care Intensity Index (HCI) from the Dartmouth Atlas of Health Care. SETTING: The Health and Retirement Study, a longitudinal nationally representative cohort of older adults. PARTICIPANTS: People aged 67 and older who died between 2,000 and 2,006 (N = 3,539) were sampled. MEASUREMENTS: In-hospital death. RESULTS: Thirty-nine percent (n = 1,380) of participants died in the hospital (range 34% in Midwest to 45% in Northeast). Nursing home residence, functional dependence, and cancer or dementia diagnosis, among other characteristics, were associated with lower adjusted odds of in-hospital death. Being black or Hispanic, living alone, and having more medical comorbidities were associated with greater adjusted odds, as was higher HCI. Sex, education, net worth, and completion of an advance directive did not correlate with in-hospital death. CONCLUSION: Black race, Hispanic ethnicity, and other functional and social characteristics are correlates of in-hospital death, even after controlling for the role of HCI. Further work must be done to determine whether preferences, provider characteristics and practice patterns, or differential access to medical and community services drive this difference.
Kelley, Amy S Ettner, Susan L Wenger, Neil S Sarkisian, Catherine A United States Journal of the American Geriatrics Society J Am Geriatr Soc. 2011 Dec;59(12):2321-5. doi: 10.1111/j.1532-5415.2011.03718.x. Epub 2011 Nov 8.
Keywords: Aged; Aged, 80 and over; Female; Hospital Mortality; Humans; Male; Multivariate Analysis; Risk Factors; Socioeconomic factors

Determinants of medical expenditures in the last 6 months of life. - Amy Kelley; Susan L Ettner; R Sean Morrison; Qingling Du; Neil S. Wenger; Catherine A Sarkisian (Annals of Internal Medicine, 2011)
BACKGROUND: End-of-life medical expenditures exceed costs of care during other years, vary across regions, and are likely to be unsustainable. Identifying determinants of expenditure variation may reveal opportunities for reducing costs. OBJECTIVE: To identify patient-level determinants of Medicare expenditures at the end of life and to determine the contributions of these factors to expenditure variation while accounting for regional characteristics. It was hypothesized that race or ethnicity, social support, and functional status are independently associated with treatment intensity and controlling for regional characteristics, and that individual characteristics account for a substantial proportion of expenditure variation. DESIGN: Using data from the Health and Retirement Study, Medicare claims, and The Dartmouth Atlas of Health Care, relationships were modeled between expenditures and patient and regional characteristics. SETTING: United States, 2000 to 2006. PARTICIPANTS: 2394 Health and Retirement Study decedents aged 65.5 years or older. MEASUREMENTS: Medicare expenditures in the last 6 months of life were estimated in a series of 2-level multivariable regression models that included patient, regional, and patient and regional characteristics. RESULTS: Decline in function (rate ratio [RR], 1.64 [95% CI, 1.46 to 1.83]); Hispanic ethnicity (RR, 1.50 [CI, 1.22 to 1.85]); black race (RR, 1.43 [CI, 1.25 to 1.64]); and certain chronic diseases, including diabetes (RR, 1.16 [CI, 1.06 to 1.27]), were associated with higher expenditures. Nearby family (RR, 0.90 [CI, 0.82 to 0.98]) and dementia (RR, 0.78 CI, 0.71 to 0.87]) were associated with lower expenditures, and advance care planning had no association. Regional characteristics, including end-of-life practice patterns (RR, 1.09 [CI, 1.06 to 1.14]) and hospital beds per capita (RR, 1.01 [CI, 1.00 to 1.02]), were associated with higher expenditures. Patient characteristics explained 10% of overall variance and retained statistically significant relationships with expenditures after regional characteristics were controlled for. LIMITATION: The study limitations include the decedent sample, proxy informants, and a large proportion of unexplained variation. CONCLUSION: Patient characteristics, such as functional decline, race or ethnicity, chronic disease, and nearby family, are important determinants of expenditures at the end of life, independent of regional characteristics. PRIMARY FUNDING SOURCE: The Brookdale Foundation.
Keywords: Aged; Aged, 80 and over; Chronic disease; Ethnic Groups; Female; Health Expenditures; Humans; Income; Independent Living; Male; Medicare; Regression Analysis; Social Support; Socioeconomic factors; Terminal Care; United States

Development and validation of a brief cognitive assessment tool: the sweet 16. - Tamara G Fong; Richard N Jones; James L Rudolph; Frances Margaret Yang; Tommet, Douglas; Habtemariam, Daniel; Edward R Marcantonio; Kenneth M. Langa; Sharon K Inouye (Arch Intern Med, 2011)
BACKGROUND: Cognitive impairment is often unrecognized among older adults. Meanwhile, current assessment instruments are underused, lack sensitivity, or may be restricted by copyright laws. To address these limitations, we created a new brief cognitive assessment tool: the Sweet 16. METHODS: The Sweet 16 was developed in a cohort from a large post-acute hospitalization study (n=774) and compared with the Mini-Mental State Examination (MMSE). Equipercentile equating identified Sweet 16 cut points that correlated with widely used MMSE cut points. Sweet 16 performance characteristics were independently validated in a cohort from the Aging, Demographics, and Memory Study (n=709) using clinical consensus diagnosis, the modified Blessed Dementia Rating Scale, and the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE). RESULTS: The Sweet 16 correlated highly with the MMSE (Spearman r, 0.94; P<.001). Validated against the IQCODE, the area under the curve was 0.84 for the Sweet 16 and 0.81 for the MMSE (P=.06). A Sweet 16 score of less than 14 (approximating an MMSE score <24) demonstrated a sensitivity of 80% and a specificity of 70%, whereas an MMSE score of less than 24 showed a sensitivity of 64% and a specificity of 86% against the IQCODE. When compared with clinical diagnosis, a Sweet 16 score of less than 14 showed a sensitivity of 99% and a specificity of 72% in contrast to an MMSE score with a sensitivity of 87% and a specificity of 89%. For education of 12 years or more, the area under the curve was 0.90 for the Sweet 16 and 0.84 for the MMSE (P=.03). CONCLUSIONS: The Sweet 16 is simple, quick to administer, and will be available open access. The performance of the Sweet 16 is equivalent or superior to that of the MMSE.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Cohort Studies; Dementia; Female; Humans; Male; Neuropsychological tests; Surveys and Questionnaires

Is diabetes-specific health literacy associated with diabetes-related outcomes in older adults? - Takashi Yamashita; Cary S Kart (J Diabetes, 2011)
BACKGROUND:  The present study examined the association between a measure of diabetes-specific health literacy and three different Type 2 diabetes outcome indicators in a national sample of older adults. METHODS: Data were taken from the Health and Retirement Study (HRS) 2003 Diabetes module and the HRS 2002 core wave. Analysis was performed on data from 1318 respondents aged 42-96 years [mean (±SD) 67.96 ± 8.65 years] who submitted responses on all relevant independent variable measures along with an HbA1c test kit. The index of diabetes-specific health literacy was constructed from responses to 10 diabetes self-care regimen items (α = 0.927). RESULTS: Using a multivariate regression strategy to analyze weighted data, the diabetes-specific health literacy index was significantly and positively associated with self-graded assessment of diabetes self-care (R2 = 0.231). However, diabetes-specific health literacy was not independently associated with the HbA1c level or the average number of days five recommended self-management behaviors were practiced each week. CONCLUSIONS:  No previous single study has focused on the relationship between diabetes-specific health literacy and multiple diabetes-related outcomes. The direct association of diabetes-specific health literacy with patients' assessment of their self-care practice acumen is useful information for the design of effective patient intervention and/or communication strategies. Health literacy is a broad, multidimensional construct that bridges basic literacy skills and various health and illness contexts. Because it is so important to adults engaged in the self-management of chronic illness, indicators of disease-specific knowledge and/or understanding should be included in efforts to measure health literacy.
Yamashita, Takashi Kart, Cary S Australia Journal of diabetes J Diabetes. 2011 Jun;3(2):138-46. doi: 10.1111/j.1753-0407.2011.00112.x.
Keywords: Adult; Aged; Aged, 80 and over; Blood Glucose; Diabetes Mellitus, Type 2; Glycated Hemoglobin; Health Literacy; Humans; Logistic Models; Middle Aged; Multivariate Analysis; Self Care; Socioeconomic factors; Surveys and Questionnaires; United States

Dispositional optimism protects older adults from stroke: the Health and Retirement Study. - Eric S Kim; Nansook Park; Christopher Peterson (Stroke, 2011)
BACKGROUND AND PURPOSE: Although higher optimism has been linked to an array of positive health outcomes, the association between optimism and incidence of stroke remains unclear, especially among older adults. We examined whether higher optimism was associated with a lower incidence of stroke. METHOD: Prospective data from the Health and Retirement Study--a nationally representative panel study of American adults aged>50 years--were used. Analyses were conducted for a 2-year follow-up on the subset of 6044 adults (2542 men, 3502 women) who were stroke-free at baseline. Analyses adjusted for chronic illnesses, self-rated health, and relevant sociodemographic, behavioral, biological, and psychological factors. RESULTS: Higher optimism was associated with a lower risk of stroke. On an optimism measure ranging from 3 to 18, each unit increase in optimism was associated with an age-adjusted OR of 0.90 for stroke (95% CI, 0.84 to 0.97; P<0.01). The effect of optimism remained significant even after fully adjusting for a comprehensive set of sociodemographic, behavioral, biological, and psychological stroke risk factors. CONCLUSIONS: Optimism may play an important role in protecting against stroke among older adults.
Kim, Eric S Park, Nansook Peterson, Christopher Research Support, Non-U.S. Gov't United States Stroke; a journal of cerebral circulation Stroke. 2011 Oct;42(10):2855-9. Epub 2011 Jul 21.
Keywords: Affect; Aged; Aged, 80 and over; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Personality; Prospective Studies; Risk Factors; Stroke

Does fall history influence residential adjustments? - Leland, Natalie; Frank Porell; Susan L Murphy (Gerontologist, 2011)
PURPOSE OF THE STUDY: To determine whether reported falls at baseline are associated with an older adult's decision to make a residential adjustment (RA) and the type of adjustment made in the subsequent 2 years. DESIGN AND METHODS: Observations (n = 25,036) were from the Health and Retirement Study, a nationally representative sample of community-living older adults, 65 years of age and older. At baseline, fall history (no fall, 1 fall no injury, 2 or more falls no injury, or 1 or more falls with an injury) and factors potentially associated with RA were used to predict the initiation of an RA (i.e., moving, home modifications, increased use of adaptive equipment, family support, or personal care assistance) during the subsequent 2 years. RESULTS: Compared with those with no history of falls, individuals with a history of falls had higher odds of making any RA. Among those making an RA, individuals with an injurious fall were more likely than those with no history of a fall to start using adaptive equipment or increase their use of personal care assistance. IMPLICATIONS: The higher initiation of RAs among fallers may indicate proactive steps to prevent future falls and may be influenced by interactions with the health care system. To optimize fall prevention efforts, older adults would benefit from education and interventions addressing optimal use of RAs before falls occur.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Decision making; Environment Design; Female; Geriatric Assessment; Humans; Male; Residential Facilities; Risk Factors

Does informal care attenuate the cycle of ADL/IADL disability and depressive symptoms in late life? - Lin, I-Fen; Wu, Hsueh-Sheng (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVE: Prior studies have extensively examined the reciprocal relation between disability and depressive symptoms in late life, but little is known about whether informal care attenuates the reciprocal relation over time. This study examined whether disability and depressive symptoms mobilize informal care and whether informal care, once mobilized, protects older adults against the progression of disability and depressive symptoms. METHODS: The analysis was based on 6,454 community-dwelling older adults who were interviewed in one or more waves of the Health and Retirement Study between 1998 and 2006. Extending an autoregressive cross-lagged model, we constructed 3 cycles of the relations among disability, depressive symptoms, and informal care. Comparing the relations across 3 cycles informs us about the attenuating effect of informal care on the relation between disability and depressive symptoms over time. RESULTS: Although older adults' disability and depressive symptoms mobilized informal care initially, worsening disability and depressive symptoms often exhausted support. Receipt of care generally increased, rather than decreased, disability and depressive symptoms, and the detrimental effects remained the same over time. DISCUSSION: We need to better understand the linkage between disability and depressive symptoms and seek effective interventions to reduce caregiver strain and enhance care receivers' well-being.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cohort Studies; Cost of Illness; depression; Disability Evaluation; Female; Humans; Longitudinal Studies; Male; Models, Psychological; United States

Does self-reported health bias the measurement of health inequalities in U.S. adults? Evidence using anchoring vignettes from the Health and Retirement Study. - Jennifer B Dowd; Todd, Megan (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: Measurement of health inequalities based on self-reports may be biased if individuals use response scales in systematically different ways. We use anchoring vignettes to test and adjust for reporting differences by education, race/ethnicity, and gender in self-reported health in 6 domains (pain, sleep, mobility, memory, shortness of breath, and depression). METHOD: Using data from the 2006 U.S. Health and Retirement Study (HRS) and the 2007 Disability Vignette Survey, we estimated generalized ordered probit models of the respondent's rating of each vignette character's health problem, allowing cut-points to vary by age, gender, education, and race/ethnicity. We then used one-step hierarchical ordered probit (HOPIT) models to jointly estimate the respondent's cut-points from the vignettes and the severity of the respondent's own health problems based on these vignette cut-points. RESULTS: We found strong evidence of reporting differences by age, gender, education, and race/ethnicity, with the magnitude depending on the specific health domain. Overall, traditional models not accounting for reporting differences underestimated the magnitude of health inequalities by education and race/ethnicity. DISCUSSION: These results suggest caution in relying on self-reported health measures to quantify and explain health disparities by socioeconomic status and race/ethnicity/ethnicity in the United States. The findings support expansion of the use of anchoring vignettes to properly account for reporting differences in self-reports of health.
Keywords: Adult; Aged; Aged, 80 and over; Attitude to Health; Bias; Black People; Disability Evaluation; Educational Status; Female; Geriatric Assessment; Health Status Indicators; Health Surveys; Hispanic or Latino; Humans; Longitudinal Studies; Male; Middle Aged; Socioeconomic factors; United States; White People

Dynamic links between memory and functional limitations in old age: longitudinal evidence for age-based structural dynamics from the AHEAD study. - Frank J Infurna; Denis Gerstorf; Lindsay H Ryan; Jacqui Smith (Psychol Aging, 2011)
This study examined competing substantive hypotheses about dynamic (i.e., time-ordered) links between memory and functional limitations in old age. We applied the Bivariate Dual Change Score Model to 13-year longitudinal data from the Asset and Health Dynamics Among the Oldest Old Study (AHEAD; N = 6,990; ages 70 - 95). Results revealed that better memory predicted shallower increases in functional limitations. Little evidence was found for the opposite direction that functional limitations predict ensuing changes in memory. Spline models indicated that dynamic associations between memory and functional limitations were substantively similar between participants aged 70-79 and those aged 80-95. Potential covariates (gender, education, health conditions, and depressive symptoms) did not account for these differential lead-lag associations. Applying a multivariate approach, our results suggest that late-life developments in two key components of successful aging are intrinsically interrelated. Our discussion focuses on possible mechanisms why cognitive functioning may serve as a source of age-related changes in health both among the young-old and the old-old.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognition; depression; Female; Health Status; Humans; Interviews as Topic; Longitudinal Studies; Male; Memory; Memory Disorders; Memory, Episodic; Models, Statistical; Neuropsychological tests

Gender differences in functional limitations in adults living with type 2 diabetes: biobehavioral and psychosocial mediators. - Chiu, Ching-Ju; Linda A. Wray (Ann Behav Med, 2011)
BACKGROUND: Differences in functional limitations between adults with and without diabetes are more evident in women than they are in men. PURPOSE: This study aims to investigate if there are gender differences in biological, behavioral, and psychosocial variables, and how these gender-related variables explain the gender-functional limitations relationship in adults with type 2 diabetes. METHODS: We drew data on 1,619 adults with type 2 diabetes from the Health and Retirement Study and its diabetes-specific mail survey. The fit of a series of mediation models to the data was assessed by structural equation modeling. RESULTS: Although women had better diet and blood glucose self-monitoring behaviors than did men, they reported less favorable body mass index, glycosylated hemoglobin (HbA1c) value, blood pressure, early complications, exercise behaviors, perceived control, self-efficacy, coping, depressive symptoms, and family support than did men. Psychosocial factors made an indirect contribution in the gender-functional limitations relationship by way of their strong association with biological and behavioral factors, two factors that directly and completely mediated the gender-functional limitations relationship. CONCLUSIONS: Interventions promoting psychosocial well-being and empowering perceived diabetes control, coping, and self-efficacy in women with type 2 diabetes may help improve biological and behavioral determinants, and further, their long-term functional health.
Keywords: Adult; Aged; Aged, 80 and over; Biomarkers; Blood Glucose Self-Monitoring; Body Mass Index; Diabetes Mellitus, Type 2; Exercise; Female; Health Behavior; Humans; Male; Middle Aged; Models, Psychological; Prospective Studies; Risk Factors; Self Report; Sex Characteristics; Socioeconomic factors; United States

Geriatric conditions develop in middle-aged adults with diabetes. - Christine T Cigolle; Pearl G. Lee; Kenneth M. Langa; Lee, Yuo-Yu; Zhiyi Tian; Caroline S Blaum (J Gen Intern Med, 2011)
BACKGROUND: Geriatric conditions, collections of symptoms common in older adults and not necessarily associated with a specific disease, increase in prevalence with advancing age. These conditions are important contributors to the complex health status of older adults. Diabetes mellitus is known to co-occur with geriatric conditions in older adults and has been implicated in the pathogenesis of some conditions. OBJECTIVE: To investigate the prevalence and incidence of geriatric conditions in middle-aged and older-aged adults with diabetes. DESIGN: Secondary analysis of nationally-representative, longitudinal health interview survey data (Health and Retirement Study waves 2004 and 2006). PARTICIPANTS: Respondents 51 years and older in 2004 (n=18,908). MAIN MEASURES: Diabetes mellitus. Eight geriatric conditions: cognitive impairment, falls, incontinence, low body mass index, dizziness, vision impairment, hearing impairment, pain. KEY RESULTS: Adults with diabetes, compared to those without, had increased prevalence and increased incidence of geriatric conditions across the age spectrum (p< 0.01 for each age group from 51-54 years old to 75-79 years old). Differences between adults with and without diabetes were most marked in middle-age. Diabetes was associated with the two-year cumulative incidence of acquiring new geriatric conditions (odds ratio, 95% confidence interval: 1.8, 1.6-2.0). A diabetes-age interaction was discovered: as age increased, the association of diabetes with new geriatric conditions decreased. CONCLUSIONS: Middle-aged, as well as older-aged, adults with diabetes are at increased risk for the development of geriatric conditions, which contribute substantially to their morbidity and functional impairment. Our findings suggest that adults with diabetes should be monitored for the development of these conditions beginning at a younger age than previously thought.
Keywords: Accidental Falls; Age Factors; Aged; Aged, 80 and over; Aging; Diabetes Mellitus; Dizziness; Female; Geriatric Assessment; Health Status; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; pain; Urinary incontinence

Health and medical services use: a matched case comparison between CCRC residents and national health and retirement study samples. - Gaines, Jean M; Judith L Poey; Marx, Katherine A; J. M. Parrish; Resnick, Barbara (J Gerontol Soc Work, 2011)
Little is known about the health status of adults living in continuing care retirement communities (CCRC). Using matched-case control, 458 adults from the Health and Retirement Study (HRS) or a CCRC-based sample were compared on total comorbidity, self-rated health, home health services use, and hospitalizations. At year 2, the CCRC sample reported more comorbidities (96%) but significantly better self-rated health (96% good/excellent) than the HRS sample (93% comorbidity, 73% good/excellent; p < .01). There were no significant differences in frequency of home health use or hospitalization. Living in a CCRC appears to be associated with higher self-ratings of health in this sample.
Gaines, Jean M Poey, Judith L Marx, Katherine A Parrish, John M Resnick, Barbara England Journal of gerontological social work J Gerontol Soc Work. 2011 Nov;54(8):788-802. doi: 10.1080/01634372.2011.595476.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Aging; Case-Control Studies; Chronic disease; depression; Female; Geriatric Assessment; Health Services; Health Services for the Aged; Health Status; Home Care Services; Hospitalization; Humans; Interview, Psychological; Male; Middle Aged; Multivariate Analysis; Psychometrics; Retirement

Higher education delays and shortens cognitive impairment: a multistate life table analysis of the US Health and Retirement Study. - Mieke Reuser; Frans J Willekens; Luc G Bonneux (Eur J Epidemiol, 2011)
Improved health may extend or shorten the duration of cognitive impairment by postponing incidence or death. We assess the duration of cognitive impairment in the US Health and Retirement Study (1992-2004) by self reported BMI, smoking and levels of education in men and women and three ethnic groups. We define multistate life tables by the transition rates to cognitive impairment, recovery and death and estimate Cox proportional hazard ratios for the studied determinants. 95% confidence intervals are obtained by bootstrapping. 55 year old white men and women expect to live 25.4 and 30.0 years, of which 1.7 [95% confidence intervals 1.5; 1.9] years and 2.7 [2.4; 2.9] years with cognitive impairment. Both black men and women live 3.7 [2.9; 4.5] years longer with cognitive impairment than whites, Hispanic men and women 3.2 [1.9; 4.6] and 5.8 [4.2; 7.5] years. BMI makes no difference. Smoking decreases the duration of cognitive impairment with 0.8 [0.4; 1.3] years by high mortality. Highly educated men and women live longer, but 1.6 years [1.1; 2.2] and 1.9 years [1.6; 2.6] shorter with cognitive impairment than lowly educated men and women. The effect of education is more pronounced among ethnic minorities. Higher life expectancy goes together with a longer period of cognitive impairment, but not for higher levels of education: that extends life in good cognitive health but shortens the period of cognitive impairment. The increased duration of cognitive impairment in minority ethnic groups needs further study, also in Europe.
Keywords: Age Factors; Aged; Aged, 80 and over; Body Mass Index; Cognition Disorders; Educational Status; Female; Health Surveys; Humans; Incidence; Life Expectancy; Life Tables; Male; Middle Aged; Prevalence; Proportional Hazards Models; Retirement; Sex Factors; Smoking; Time Factors; United States

How does the trajectory of multimorbidity vary across Black, White, and Mexican Americans in middle and old age? - Ana R Quiñones; Jersey Liang; Joan M. Bennett; Xiao Xu; Wen Ye (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: This research examines intra- and interpersonal differences in multiple chronic conditions reported by Americans aged 51 and older for a period up to 11 years. It focuses on how changes in multimorbidity vary across White, Black, and Mexican Americans. METHODS: Data came from 17,517 respondents of the Health and Retirement Study (1995-2006) with up to 5 repeated observations. Hierarchical linear models were employed to analyze ethnic variations in temporal changes of reported comorbidities. FINDINGS: Middle-aged and older Americans have on average nearly 2 chronic diseases at the baseline, which increased to almost 3 conditions in 11 years. White Americans differ from Black and Mexican Americans in terms of level and rate of change of multimorbidity. Mexican Americans demonstrate lower initial levels and slower accumulation of comorbidities relative to Whites. In contrast, Blacks showed an elevated level of multimorbidity throughout the 11-year period of observation, although their rate of change slowed relative to Whites. DISCUSSION: These results suggest that health differences between Black Americans and other ethnic groups including White and Mexican Americans persist in the trajectory of multimorbidity even when population heterogeneity is adjusted. Further research is needed concerning the impact of health disadvantages and differential mortality that may have occurred before middle age as well as exploring the role of nativity, the nature of self-reported diseases, and heterogeneity underlying the average trajectory of multimorbidity for ethnic elders.
Quinones, Ana R Liang, Jersey Bennett, Joan M Xu, Xiao Ye, Wen F31-AG029783/AG/NIA NIH HHS/United States R01-AG015124/AG/NIA NIH HHS/United States R01-AG028116/AG/NIA NIH HHS/United States Comparative Study Research Support, N.I.H., Extramural United States The journals of gerontology. Series B, Psychological sciences and social sciences J Gerontol B Psychol Sci Soc Sci. 2011 Nov;66(6):739-49. Epub 2011 Oct 3.
Keywords: Aged; Aged, 80 and over; Aging; Black or African American; Chronic disease; Female; Follow-Up Studies; Health Behavior; Health Status Disparities; Hispanic or Latino; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; United States; White People

The impact of private long-term care insurance on the use of long-term care. - Yong Li; Gail A Jensen (Inquiry, 2011)
This paper investigates the effects of privately purchased long-term care insurance (LTCI) on three major types of long-term care services: nursing home care, paid home care, and informal care received from Family and friends. Using 2002-2008 data from the ongoing Health and Retirement Study, we analyze the determinants of long-term care utilization simultaneously with the determinants of holding LTCI. We find that LTCI has modest effects on the likelihood of using long-term care services. For the very frail elderly, private LTCI enhances their access to nursing home care. For those with moderate disability, LTCI makes it more likely that they can remain at home and receive home care services, instead of going to a nursing home. We find no evidence that formal care substitutes for informal care in the presence of LTCI. These findings suggest that if LTCI becomes much more prevalent in the future, many older adults will be able to choose the type of long-term care arrangement that best suits their needs.
Keywords: Aged; Aged, 80 and over; Decision making; Female; Health Services Accessibility; Home Care Services; Home Nursing; Humans; Insurance, Long-Term Care; Likelihood Functions; Long-term Care; Male; Models, Econometric; Nursing homes; Private Sector; Regression Analysis; United States

Implementation of Medicare Part D and nondrug medical spending for elderly adults with limited prior drug coverage. - J. Michael McWilliams; Alan M. Zaslavsky; Haiden A. Huskamp (JAMA, 2011)
CONTEXT: Implementation of Medicare Part D was followed by increased use of prescription medications, reduced out-of-pocket costs, and improved medication adherence. Its effects on nondrug medical spending remain unclear. OBJECTIVE: To assess differential changes in nondrug medical spending following the implementation of Part D for traditional Medicare beneficiaries with limited prior drug coverage. DESIGN, SETTING, AND PARTICIPANTS: Nationally representative longitudinal survey data and linked Medicare claims from 2004-2007 were used to compare nondrug medical spending before and after the implementation of Part D by self-reported generosity of prescription drug coverage before 2006. Participants included 6001 elderly Medicare beneficiaries from the Health and Retirement Study, including 2538 with generous and 3463 with limited drug coverage before 2006. Comparisons were adjusted for sociodemographic and health characteristics and checked for residual confounding by conducting similar comparisons for a control cohort from 2002-2005. MAIN OUTCOME MEASURE: Nondrug medical spending assessed from claims, in total and by type of service (inpatient and skilled nursing facility vs physician services). RESULTS: Total nondrug medical spending was differentially reduced after January 1, 2006, for beneficiaries with limited prior drug coverage (-$306/quarter [95% confidence interval CI, -$586 to -$51]; P = .02), relative to beneficiaries with generous prior drug coverage. This differential reduction was explained mostly by differential changes in spending on inpatient and skilled nursing facility care (-$204/quarter [95% CI, -$447 to $2]; P = .05). Differential reductions in spending on physician services (-$67/quarter [95% CI, -$134 to -$5]; P = .03) were not associated with differential changes in outpatient visits (-0.06 visits/quarter [95% CI, -0.21 to 0.08]; P = .37), suggesting reduced spending on inpatient physician services for beneficiaries with limited prior drug coverage. In contrast, nondrug medical spending in the control cohort did not differentially change after January 1, 2004, for beneficiaries with limited prior drug coverage in 2002 ($14/quarter [95% CI, -$338 to $324]; P = .93), relative to beneficiaries with generous prior coverage. CONCLUSION: Implementation of Part D was associated with significant differential reductions in nondrug medical spending for Medicare beneficiaries with limited prior drug coverage.
McWilliams, J Michael Zaslavsky, Alan M Huskamp, Haiden A Comparative Study Research Support, Non-U.S. Gov't United States JAMA : the journal of the American Medical Association JAMA. 2011 Jul 27;306(4):402-9.
Keywords: Aged; Aged, 80 and over; Cost Control; Costs and Cost Analysis; Data collection; Female; Health Expenditures; Health Services; Humans; Insurance Claim Review; Longitudinal Studies; Male; Medicare Part D; Patient Care; Physicians; Skilled Nursing Facilities; United States

Incidence of dementia and cognitive impairment, not dementia in the United States. - Brenda L Plassman; Kenneth M. Langa; Ryan J McCammon; Gwenith G Fisher; Guy G Potter; James R Burke; David C Steffens; Norman L Foster; Bruno J Giordani; Frederick W Unverzagt; Kathleen A Welsh-Bohmer; Steven G Heeringa; et al. (Ann Neurol, 2011)
OBJECTIVE: Estimates of incident dementia, and cognitive impairment, not dementia (CIND) (or the related mild cognitive impairment) are important for public health and clinical care policy. In this paper, we report US national incidence rates for dementia and CIND. METHODS: Participants in the Aging, Demographic, and Memory Study (ADAMS) were evaluated for cognitive impairment using a comprehensive in-home assessment. A total of 456 individuals aged 72 years and older, who were not demented at baseline, were followed longitudinally from August 2001 to December 2009. An expert consensus panel assigned a diagnosis of normal cognition, CIND, or dementia and its subtypes. Using a population-weighted sample, we estimated the incidence of dementia, Alzheimer disease (AD), vascular dementia (VaD), and CIND by age. We also estimated the incidence of progression from CIND to dementia. RESULTS: The incidence of dementia was 33.3 (standard error [SE], 4.2) per 1,000 person-years and 22.9 (SE, 2.9) per 1,000 person-years for AD. The incidence of CIND was 60.4 (SE, 7.2) cases per 1,000 person-years. An estimated 120.3 (SE, 16.9) individuals per 1,000 person-years progressed from CIND to dementia. Over a 5.9-year period, about 3.4 million individuals aged 72 and older in the United States developed incident dementia, of whom approximately 2.3 million developed AD, and about 637,000 developed VaD. Over this same period, almost 4.8 million individuals developed incident CIND. INTERPRETATION: The incidence of CIND is greater than the incidence of dementia, and those with CIND are at high risk of progressing to dementia, making CIND a potentially valuable target for treatments aimed at slowing cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Cognition Disorders; Cohort Studies; Dementia; Diagnostic and Statistical Manual of Mental Disorders; disease progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Models, Statistical; United States

Long-term declines in ADLs, IADLs, and mobility among older Medicare beneficiaries. - Frederic D Wolinsky; Suzanne E Bentler; Jason Hockenberry; Michael P Jones; Maksym Obrizan; Paula A Weigel; Kaskie, Brian; Robert B Wallace (BMC Geriatr, 2011)
BACKGROUND: Most prior studies have focused on short-term (≤ 2 years) functional declines. But those studies cannot address aging effects inasmuch as all participants have aged the same amount. Therefore, the authors studied the extent of long-term functional decline in older Medicare beneficiaries who were followed for varying time lengths, and the authors also identified the risk factors associated with those declines. METHODS: The analytic sample included 5,871 self- or proxy-respondents who had complete baseline and follow-up survey data that could be linked to their Medicare claims for 1993-2007. Functional status was assessed using activities of daily living (ADLs), instrumental ADLs (IADLs), and mobility limitations, with declines defined as the development of two of more new difficulties. Multiple logistic regression analysis was used to focus on the associations involving respondent status, health lifestyle, continuity of care, managed care status, health shocks, and terminal drop. RESULTS: The average amount of time between the first and final interviews was 8.0 years. Declines were observed for 36.6% on ADL abilities, 32.3% on IADL abilities, and 30.9% on mobility abilities. Functional decline was more likely to occur when proxy-reports were used, and the effects of baseline function on decline were reduced when proxy-reports were used. Engaging in vigorous physical activity consistently and substantially protected against functional decline, whereas obesity, cigarette smoking, and alcohol consumption were only associated with mobility declines. Post-baseline hospitalizations were the most robust predictors of functional decline, exhibiting a dose-response effect such that the greater the average annual number of hospital episodes, the greater the likelihood of functional status decline. Participants whose final interview preceded their death by one year or less had substantially greater odds of functional status decline. CONCLUSIONS: Both the additive and interactive (with functional status) effects of respondent status should be taken into consideration whenever proxy-reports are used. Encouraging exercise could broadly reduce the risk of functional decline across all three outcomes, although interventions encouraging weight reduction and smoking cessation would only affect mobility declines. Reducing hospitalization and re-hospitalization rates could also broadly reduce the risk of functional decline across all three outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cohort Studies; Disabled Persons; Female; Follow-Up Studies; Geriatric Assessment; Health Surveys; Humans; Insurance Benefits; Longitudinal Studies; Male; Medicare; Mobility Limitation; Prospective Studies; Time Factors; United States

Memory predicts changes in depressive symptoms in older adults: a bidirectional longitudinal analysis. - Jajodia, Archana; Borders, Ashley (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: Although research indicates that depressive symptoms and memory performance are related in older adults, the temporal associations between these variables remain unclear. This study examined whether depressive symptoms predicted later memory change and whether memory predicted later change in depressive symptoms. METHODS: The sample consisted of more than 14,000 adults from the Health and Retirement Study, a biannual longitudinal study of health and retirement in Americans older than age 50 years. Measures of delayed recall and depressive symptoms served as the main study variables. We included age, sex, education, and history of vascular diseases as covariates. RESULTS: Using dynamic change models with latent difference scores, we found that memory performance predicted change in depressive symptoms 2 years later. Depressive symptoms did not predict later change in memory. The inclusion of vascular health variables diminished the size of the observed relationship, suggesting that biological processes may partially explain the effect of memory on depressive symptoms. IMPLICATIONS: Future research should explore both biological and psychological processes that may explain the association between worse memory performance and subsequent increases in depressive symptoms.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia, Vascular; depression; Female; Geriatric Assessment; Humans; Longitudinal Studies; Male; Mental Recall; Middle Aged; Models, Psychological; Retirement; Statistics as Topic; United States

Neuropsychiatric symptoms and the risk of institutionalization and death: the aging, demographics, and memory study. - Okura, Toru; Brenda L Plassman; David C Steffens; David J Llewellyn; Guy G Potter; Kenneth M. Langa (J Am Geriatr Soc, 2011)
OBJECTIVES: To examine the association between neuropsychiatric symptoms and risk of institutionalization and death. DESIGN: Analysis of longitudinal data. SETTING: The Aging, Demographics, and Memory Study (ADAMS). PARTICIPANTS: Five hundred thirty-seven adults aged 71 and older with cognitive impairment drawn from the Health and Retirement Study (HRS). MEASUREMENTS: Neuropsychiatric symptoms (delusions, hallucinations, agitation, depression, apathy, elation, anxiety, disinhibition, irritation, and aberrant motor behaviors) and caregiver distress were identified using the Neuropsychiatric Inventory. A consensus panel in the ADAMS assigned cognitive category. Date of nursing home placement and information on death, functional limitations, medical comorbidity, and sociodemographic characteristics were obtained from the HRS and ADAMS. RESULTS: Overall, the presence of one or more neuropsychiatric symptoms was not associated with a significantly higher risk for institutionalization or death during the 5-year study period, although when assessing each symptom individually, depression, delusions, and agitation were each associated with a significantly higher risk of institutionalization (hazard rate (HR)=3.06, 95% confidence interval (CI)=1.09-8.59 for depression; HR=5.74, 95% CI=1.94-16.96 for clinically significant delusions; HR=4.70, 95% CI=1.07-20.70 for clinically significant agitation). Caregiver distress mediated the association between delusions and agitation and institutionalization. Depression and hallucinations were associated with significantly higher mortality (HR=1.56, 95% CI=1.08-2.26 for depression; HR=2.59, 95% CI=1.09-6.16 for clinically significant hallucinations). CONCLUSION: Some, but not all, neuropsychiatric symptoms are associated with a higher risk of institutionalization and death in people with cognitive impairment, and caregiver distress also influences institutionalization. Interventions that better target and treat depression, delusions, agitation, and hallucinations, as well as caregiver distress, may help delay or prevent these negative clinical outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Behavioral Symptoms; Caregivers; Cognition Disorders; Female; Humans; Institutionalization; Male; Neuropsychological tests; Proportional Hazards Models

Physical disability trajectories in older Americans with and without diabetes: the role of age, gender, race or ethnicity, and education. - Chiu, Ching-Ju; Linda A. Wray (Gerontologist, 2011)
PURPOSE: This research combined cross-sectional and longitudinal data to characterize age-related trajectories in physical disability for adults with and without diabetes in the United States and to investigate if those patterns differ by age, gender, race or ethnicity, and education. DESIGN AND METHODS: Data were examined on 20,433 adults aged 51 and older from the 1998 to 2006 Health and Retirement Study. Multilevel models and a cohort-sequential design were applied to quantitatively depict the age norm of physical disability after age 50. RESULTS: Adults with diabetes not only experience greater levels of physical disability but also faster rates of deterioration over time. This pattern is net of attrition, time-invariant sociodemographic factors, and time-varying chronic disease conditions. Differences in physical disability between adults with and without diabetes were more pronounced in women, non-White, and those of lower education. The moderating effects of gender and education remained robust even after controlling for selected covariates in the model. IMPLICATIONS: This study highlighted the consistently greater development of disability over time in adults with diabetes and particularly in those who are women, non-White, or adults of lower education. Future studies are recommended to examine the mechanisms underlying the differential effects of diabetes on physical disability by gender and education.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Cross-Sectional Studies; Diabetes Mellitus; Disabled Persons; Educational Status; ethnicity; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Models, Theoretical; Racial Groups; Sex Distribution; Time Factors; United States

A prospective cohort study of long-term cognitive changes in older Medicare beneficiaries. - Frederic D Wolinsky; Suzanne E Bentler; Jason Hockenberry; Michael P Jones; Paula A Weigel; Kaskie, Brian; Robert B Wallace (BMC Public Health, 2011)
BACKGROUND: Promoting cognitive health and preventing its decline are longstanding public health goals, but long-term changes in cognitive function are not well-documented. Therefore, we first examined long-term changes in cognitive function among older Medicare beneficiaries in the Survey on Assets and Health Dynamics among the Oldest Old (AHEAD), and then we identified the risk factors associated with those changes in cognitive function. METHODS: We conducted a secondary analysis of a prospective, population-based cohort using baseline (1993-1994) interview data linked to 1993-2007 Medicare claims to examine cognitive function at the final follow-up interview which occurred between 1995-1996 and 2006-2007. Besides traditional risk factors (i.e., aging, age, race, and education) and adjustment for baseline cognitive function, we considered the reason for censoring (entrance into managed care or death), and post-baseline continuity of care and major health shocks (hospital episodes). Residual change score multiple linear regression analysis was used to predict cognitive function at the final follow-up using data from telephone interviews among 3,021 to 4,251 (sample size varied by cognitive outcome) baseline community-dwelling self-respondents that were ≥ 70 years old, not in managed Medicare, and had at least one follow-up interview as self-respondents. Cognitive function was assessed using the 7-item Telephone Interview for Cognitive Status (TICS-7; general mental status), and the 10-item immediate and delayed (episodic memory) word recall tests. RESULTS: Mean changes in the number of correct responses on the TICS-7, and 10-item immediate and delayed word recall tests were -0.33, -0.75, and -0.78, with 43.6%, 54.9%, and 52.3% declining and 25.4%, 20.8%, and 22.9% unchanged. The main and most consistent risks for declining cognitive function were the baseline values of cognitive function (reflecting substantial regression to the mean), aging (a strong linear pattern of increased decline associated with greater aging, but with diminishing marginal returns), older age at baseline, dying before the end of the study period, lower education, and minority status. CONCLUSIONS: In addition to aging, age, minority status, and low education, substantial and differential risks for cognitive change were associated with sooner vs. later subsequent death that help to clarify the terminal drop hypothesis. No readily modifiable protective factors were identified.
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Cognition Disorders; Cohort Studies; Female; Humans; Interviews as Topic; Male; Medicare; Mental Health; Outcome Assessment, Health Care; Prospective Studies; Regression Analysis; Risk Factors; United States

Recent trends in chronic disease, impairment and disability among older adults in the United States. - William W. Hung; Joseph S. Ross; Boockvar, Kenneth S; Albert L Siu (BMC Geriatr, 2011)
BACKGROUND: To examine concurrent prevalence trends of chronic disease, impairment and disability among older adults. METHODS: We analyzed the 1998, 2004 and 2008 waves of the Health and Retirement Study, a nationally representative survey of older adults in the United States, and included 31,568 community dwelling adults aged 65 and over. Measurements include: prevalence of chronic diseases including hypertension, heart disease, stroke, diabetes, cancer, chronic lung disease and arthritis; prevalence of impairments, including impairments of cognition, vision, hearing, mobility, and urinary incontinence; prevalence of disability, including activities of daily living (ADLs) and instrumental activities of daily living (IADLs). RESULTS: The proportion of older adults reporting no chronic disease decreased from 13.1% (95% Confidence Interval [CI], 12.4%-13.8%) in 1998 to 7.8% (95% CI, 7.2%-8.4%) in 2008, whereas the proportion reporting 1 or more chronic diseases increased from 86.9% (95% CI, 86.2%-89.6%) in 1998 to 92.2% (95% CI, 91.6%-92.8%) in 2008. In addition, the proportion reporting 4 or more diseases increased from 11.7% (95% CI, 11.0%-12.4%) in 1998 to 17.4% (95% CI, 16.6%-18.2%) in 2008. The proportion of older adults reporting no impairments was 47.3% (95% CI, 46.3%-48.4%) in 1998 and 44.4% (95% CI, 43.3%-45.5%) in 2008, whereas the proportion of respondents reporting 3 or more was 7.2% (95% CI, 6.7%-7.7%) in 1998 and 7.3% (95% CI, 6.8%-7.9%) in 2008. The proportion of older adults reporting any ADL or IADL disability was 26.3% (95% CI, 25.4%-27.2%) in 1998 and 25.4% (95% CI, 24.5%-26.3%) in 2008. CONCLUSIONS: Multiple chronic disease is increasingly prevalent among older U.S. adults, whereas the prevalence of impairment and disability, while substantial, remain stable.
Hung, William W Ross, Joseph S Boockvar, Kenneth S Siu, Albert L K08 AG032886/AG/NIA NIH HHS/United States U01AG009740/AG/NIA NIH HHS/United States Comparative Study Research Support, N.I.H., Extramural Research Support, Non-U.S. Gov't England BMC geriatrics BMC Geriatr. 2011 Aug 18;11:47.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Disabled Persons; Female; Health Surveys; Humans; Longitudinal Studies; Male; United States; Visually Impaired Persons

Regional variation in the association between advance directives and end-of-life Medicare expenditures. - Lauren Hersch Nicholas; Kenneth M. Langa; Theodore J Iwashyna; David R Weir (JAMA, 2011)
CONTEXT: It is unclear if advance directives (living wills) are associated with end-of-life expenditures and treatments. OBJECTIVE: To examine regional variation in the associations between treatment-limiting advance directive use, end-of-life Medicare expenditures, and use of palliative and intensive treatments. DESIGN, SETTING, AND PATIENTS: Prospectively collected survey data from the Health and Retirement Study for 3302 Medicare beneficiaries who died between 1998 and 2007 linked to Medicare claims and the National Death Index. Multivariable regression models examined associations between advance directives, end-of-life Medicare expenditures, and treatments by level of Medicare spending in the decedent's hospital referral region. MAIN OUTCOME MEASURES: Medicare expenditures, life-sustaining treatments, hospice care, and in-hospital death over the last 6 months of life. RESULTS: Advance directives specifying limits in care were associated with lower spending in hospital referral regions with high average levels of end-of-life expenditures (-$5585 per decedent; 95% CI, -$10,903 to -$267), but there was no difference in spending in hospital referral regions with low or medium levels of end-of-life expenditures. Directives were associated with lower adjusted probabilities of in-hospital death in high- and medium-spending regions (-9.8%; 95% CI, -16% to -3% in high-spending regions; -5.3%; 95% CI, -10% to -0.4% in medium-spending regions). Advance directives were associated with higher adjusted probabilities of hospice use in high- and medium-spending regions (17%; 95% CI, 11% to 23% in high-spending regions, 11%; 95% CI, 6% to 16% in medium-spending regions), but not in low-spending regions. CONCLUSION: Advance directives specifying limitations in end-of-life care were associated with significantly lower levels of Medicare spending, lower likelihood of in-hospital death, and higher use of hospice care in regions characterized by higher levels of end-of-life spending.
Keywords: Advance directives; Aged; Aged, 80 and over; Data collection; Female; Health Expenditures; Hospice Care; Hospital Mortality; Hospitals; Humans; Kidney Failure, Chronic; Male; Medicare; Palliative care; Prospective Studies; Regression Analysis; Terminal Care; United States

The relationships between major lifetime discrimination, everyday discrimination, and mental health in three racial and ethnic groups of older adults. - Liat Ayalon; Amber M Gum (Aging Ment Health, 2011)
OBJECTIVES: To evaluate the relationships between perceived exposure to major lifetime discrimination, everyday discrimination, and mental health in three racial/ethnic groups of older adults. DESIGN: The Health and Retirement Study is a nationally representative sample of individuals 50 years and older living in the United States. A total of 6455 Whites, 716 Latinos, and 1214 Blacks were eligible to complete a self-report psychosocial questionnaire in the year 2006. RESULTS: Whereas 30% of the general population reported at least one type of major lifetime discrimination, almost 45% of Black older adults reported such discrimination. Relative to the other two racial/ethnic groups (82% Whites, 82.6% Blacks), Latinos were significantly less likely to report any everyday discrimination (64.2%), whereas Blacks reported the greatest frequency of everyday discrimination. Whites reported the highest levels of life satisfaction and the lowest levels of depressive symptoms. Relative to major lifetime discrimination, everyday discrimination had a somewhat stronger correlation with mental health indicators. The relationships between discrimination and mental health outcomes were stronger for White compared to Black older adults, although everyday discrimination was still significantly associated with outcomes for Black older adults. CONCLUSIONS: Black older adults experience the greatest number of discriminative events, but weaker associated mental health outcomes. This could be because they have become accustomed to these experiences, benefit from social or cultural resources that serve as buffers, or selective survival, with the present sample capturing only the most resilient older adults who have learned to cope with the deleterious effects of discrimination.
Ayalon, Liat Gum, Amber M U01AG009740/AG/NIA NIH HHS/United States Evaluation Studies Research Support, N.I.H., Extramural England Aging and mental health Aging Ment Health. 2011 Jul 1;15(5):587-94.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Asian; Black or African American; Cross-Cultural Comparison; depression; Discrimination, Psychological; ethnicity; Hispanic or Latino; Humans; Longitudinal Studies; Mental Health; Middle Aged; Personal Satisfaction; Prejudice; Prevalence; Social Perception; Socioeconomic factors; Surveys and Questionnaires; United States; White People

Social characteristics and health status of exceptionally long-lived Americans in the Health and Retirement Study. - Jennifer A Ailshire; Hiram Beltrán-Sánchez; Eileen M. Crimmins (J Am Geriatr Soc, 2011)
OBJECTIVES: To characterize the social characteristics and physical, functional, mental, and cognitive health of exceptional survivors in the United States and how the experience of exceptional longevity differs according to social status. DESIGN: Nationally representative longitudinal study of older Americans. SETTING: United States. PARTICIPANTS: One thousand six hundred forty-nine men and women born from 1900 to 1911 from the Health and Retirement Study: 1,424 nonsurvivors who died before reaching the age of 97 and 225 exceptional survivors who survived to age 97 and older. MEASUREMENTS: Self-reported data on sociodemographic characteristics, social environment, physical and mental health, and physical and cognitive function. RESULTS: At baseline, exceptional survivors were more likely to live independently and had fewer diseases, better mental health, and better physical and cognitive function than those who did not survive to age 97. Exceptional survivors experienced declines from baseline in all health domains upon reaching 97 years of age, but between one-fifth and one-third of exceptional survivors remained disease free, with no functional limitations or depressive symptoms, and one-fifth retained high cognitive function. Of exceptional survivors, men were healthier than women, and whites were generally healthier than nonwhites. Highly educated exceptional survivors had better cognitive function than their less-educated counterparts. CONCLUSION: On average, exceptional survivors are relatively healthy and high functioning for most of their lives and experience health declines only upon reaching maximum longevity. Heterogeneity in the population of exceptionally old adults indicates that, although many individuals reach maximum longevity in a state of poor health and functioning, a considerable portion of exceptional survivors remain healthy and high-functioning even in very old age.
Ailshire, Jennifer A Beltran-Sanchez, Hiram Crimmins, Eileen M United States Journal of the American Geriatrics Society J Am Geriatr Soc. 2011 Dec;59(12):2241-8. doi: 10.1111/j.1532-5415.2011.03723.x.
Keywords: Age Factors; Aged, 80 and over; Female; Geriatric Assessment; Health Status; Humans; Longevity; Longitudinal Studies; Male; Social Class; Sociology; United States

Socioeconomic inequalities in old-age mortality: a comparison of Denmark and the USA. - Rasmus Hoffmann (Soc Sci Med, 2011)
Previous studies have reported important variations in the magnitude of health inequalities between countries that belong to different welfare systems. This suggests that there is scope for reducing health inequalities by means of country-level interventions. The present study adds to this literature by exploring whether the magnitude of socioeconomic inequalities in mortality is associated with social inequality levels. Denmark and the USA belong to fundamentally different welfare systems (social democratic and liberal) and our study thereby contributes to the ongoing debate on whether welfare systems are linked to health inequalities. We analyze Denmark and the USA in terms of socioeconomic differences in mortality above age 58. The data sources were Danish register data from 1980 to 2002 (n = 2,029,324), and survey data from the US Health and Retirement Study (HRS) from 1992 to 2006 (n = 9374). Survival analysis was used to study the impact of socioeconomic status on mortality and the magnitude of mortality differences between the two countries was compared. The results showed surprisingly that mortality differentials were larger in Denmark than in the USA even after controlling for a number of covariates: The poorest 10 percent of the Danish elderly population have a mortality rate ratio of 3.32 (men) and 3.70 (women) compared to the richest 25 percent. In the USA the corresponding rate ratios are 1.67 and 1.56. Low income seems to be a more powerful risk factor for mortality than low education. A number of possible explanations for higher mortality differences in Denmark are discussed: unintended positive correlation between generous health services and health inequality, early life influences, mortality selection, and relative deprivation.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cross-Cultural Comparison; Denmark; Educational Status; Female; Health Expenditures; Humans; Income; Life Expectancy; Male; Middle Aged; Mortality; Political Systems; Social Class; Social Welfare; United States

Socioeconomic status and race/ethnicity independently predict health decline among older diabetics. - Emily J Nicklett (BMC Public Health, 2011)
BACKGROUND: There are pervasive racial and socioeconomic differences in health status among older adults with type 2 diabetes. The extent to which racial/ethnic and socioeconomic disparities unfold to differential health outcomes has yet to be investigated among older adults with diabetes. This study examines whether or not race/ethnicity and SES are independent predictors of steeper rates of decline in self-rated health among older adults in the U.S. with type 2 diabetes. METHODS: The study population was a subset of diabetic adults aged 65 and older from the Health and Retirement Study. Respondents were followed up to 16 years. Multilevel cumulative logit regression models were used to examine the contributions of socioeconomic indicators, race/ethnicity, and covariates over time. Health decline was measured as a change in self-reported health status over the follow-up period. RESULTS: Relative to whites, blacks had a significantly lower cumulative odds of better health status over time (OR: 0.61, p < .0001). Hispanics reported significantly lower cumulative odds better health over time relative to whites (OR: 0.59, p < .05). Although these disparities narrowed when socioeconomic characteristics were added to the model, significant differences remained. Including socioeconomic status did not remove the health effects of race/ethnicity among blacks and Hispanics. CONCLUSIONS: The author found that race/ethnicity and some socioeconomic indicators were independent predictors of health decline among older adults with diabetes.
Nicklett, Emily J Research Support, N.I.H., Extramural Research Support, Non-U.S. Gov't Research Support, U.S. Gov't, P.H.S. England BMC public health BMC Public Health. 2011 Sep 2;11:684.
Keywords: Aged; Aged, 80 and over; Black People; Diabetes Mellitus, Type 2; Diagnostic Self Evaluation; Female; Follow-Up Studies; Health Status Disparities; Hispanic or Latino; Humans; Male; Social Class; United States; White People

Sources of variability in estimates of the prevalence of Alzheimer's disease in the United States. - Robert S Wilson; David R Weir; Sue E Leurgans; Denis A Evans; Liesi Hebert; Kenneth M. Langa; Brenda L Plassman; Brent J. Small; David A Bennett (Alzheimers Dement, 2011)
BACKGROUND: The prevalence of Alzheimer's disease (AD) in the United States was estimated at 2.3 million in 2002 by the Aging, Demographics, and Memory Study (ADAMS), which is almost 50% less than the estimate of 4.5 million in 2000 derived from the Chicago Health and Aging Project. METHODS: We considered how differences in diagnostic criteria may have contributed to these differences in AD prevalence. RESULTS: We identified several important differences in diagnostic criteria that may have contributed to the differing estimates of AD prevalence. Two factors were especially noteworthy. First, the Diagnostic and Statistical Manual of Mental Disorders III-R and IV criteria of functional limitation documented by an informant used in ADAMS effectively concentrated the diagnosis of dementia toward a relatively higher level of cognitive impairment. ADAMS separately identified a category of cognitive impairment not dementia and within that group there were a substantial number of cases with "prodromal" AD (a maximum of 1.95 million with upweighting). Second, a substantial proportion of dementia in ADAMS was attributed to either vascular disease (representing a maximum of 0.59 million with upweighting) or undetermined etiology (a maximum of 0.34 million), whereas most dementia, including mixed dementia, was attributed to AD in the Chicago Health and Aging Project. CONCLUSION: The diagnosis of AD in population studies is a complex process. When a diagnosis of AD excludes persons meeting criteria for vascular dementia, when not all persons with dementia are assigned an etiology, and when a diagnosis of dementia requires an informant report of functional limitations, the prevalence is substantially lower and the diagnosed cases most likely have a relatively higher level of impairment.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Community Health Planning; Comorbidity; Dementia; Diagnosis, Differential; Female; Humans; Incidence; Male; Prevalence; United States

Spousal associations between functional limitation and depressive symptom trajectories: Longitudinal findings from the study of Asset and Health Dynamics Among the Oldest Old (AHEAD). - Christiane A Hoppmann; Denis Gerstorf; Anita Hibbert (Health Psychol, 2011)
OBJECTIVE: To examine spousal associations between functional limitation and depressive symptom trajectories in a national sample of older long-term married couples. DESIGN: We used 14.5-year longitudinal data on functional limitations and depressive symptoms from 1,704 couples participating in the Study of Asset and Health Dynamics Among the Oldest Old (AHEAD). MAIN OUTCOME MEASURES: Activities of daily living and a short version of the Center for Epidemiologic Studies Depression scale were used. RESULTS: Between-person difference findings corroborate previous research by showing that levels and changes in functional limitations and depressive symptoms are closely interrelated among wives and husbands. Our results further demonstrate sizable associations in levels and changes in functional limitations and depressive symptoms between spouses. For example, functional limitation levels in one spouse were associated with depressive symptom levels in the other spouse. Spousal associations remained after controlling for individual (age, education, cognition) and spousal covariates (marriage duration, number of children) and did not differ between women and men. CONCLUSION: Our findings highlight the important role of marital relationships in shaping health trajectories in old age because they show that some of the well-documented between-person differences in functional limitations and depressive symptoms are in fact related to spouses.
Hoppmann, Christiane A Gerstorf, Denis Hibbert, Anita U01 AG009740-12/AG/NIA NIH HHS/United States U01AG009740/AG/NIA NIH HHS/United States Research Support, N.I.H., Extramural Research Support, Non-U.S. Gov't United States Nihms256806 Health Psychol. 2011 Mar;30(2):153-62.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; depression; Female; Humans; Longitudinal Studies; Male; Psychometrics; Spouses; United States

Utilization of blood transfusion among older adults in the United States. - Mary A M Rogers; Neil Blumberg; Heal, Joanna M; Kenneth M. Langa (Transfusion, 2011)
BACKGROUND: While there have been epidemiologic studies of blood donors, the characteristics of individuals who receive transfusions have not been well described for the US population. STUDY DESIGN AND METHODS: Subjects were from the nationally representative Health and Retirement Study whose data were linked to Medicare files from 1991 through 2007 (n = 16,377). A cohort study was conducted to assess the frequency of transfusion in older Americans over time and to describe the characteristics of blood recipients. RESULTS: Thirty-one percent (95% confidence interval [CI], 30%-33%) of older Americans received at least one transfusion within a 10-year period and 5.8% (95% CI, 5.4%-6.2%) experienced repeated transfusion-related visits within 30 days. The mean number of transfusion-related visits was 2.3 over a 10-year period (95% CI, 2.2-2.4). Older Americans who lived in the South were most likely to receive a transfusion (34%), independent of demographic and health-related factors, while those who lived in the western United States were the least likely (26%). Predictors of transfusion included smoking, low body mass index, and a history of cancer, diabetes mellitus, end-stage renal disease, and heart disease. African-Americans and Mexican-Americans had greater rates of blood utilization than other races and other Hispanics (respectively). There were also differences in transfusion utilization by education, marital status, religion, and alcohol use. CONCLUSIONS: Transfusion is common in older Americans. Regional variations in blood use are not explained by patient characteristics alone.
Keywords: Age Distribution; Aged; Aged, 80 and over; Black or African American; Blood Transfusion; Female; Humans; Male; United States; White People

Volunteering and hypertension risk in later life. - Jeffrey A Burr; Jane Tavares; Jan E Mutchler (J Aging Health, 2011)
OBJECTIVE: This study examined the relationship between volunteer activity and hypertension, a risk factor for cardiovascular disease, renal failure, and cognitive impairment. METHOD: Employing data from the Health and Retirement Study, we estimated regression models of hypertension status that include volunteer activity and psychosocial and health behavior risk factors for middle-aged and older persons. RESULTS: Multivariate analyses showed volunteers had lower hypertension risk and lower systolic and diastolic blood pressure than nonvolunteers and that a threshold effect was present, whereby a modest amount of volunteer time commitment (but not a high amount) was associated with lower risk of hypertension. We did neither find support that psychosocial and health behaviors mediated this relationship nor find support for a moderating effect of volunteering for the relationships among health behaviors and hypertension. DISCUSSION: The results of this study indicate that research is needed to determine what mediates the relationship between volunteering and hypertension.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Confidence Intervals; Female; Health Behavior; health policy; Health Status; Humans; Hypertension; Male; Middle Aged; Multivariate Analysis; Odds Ratio; Psychometrics; Regression Analysis; Risk Factors; Social Support; Surveys and Questionnaires; Volunteers

Advance directives and outcomes of surrogate decision making before death. - Maria J Silveira; Scott Y H Kim; Kenneth M. Langa (N Engl J Med, 2010)
BACKGROUND: Recent discussions about health care reform have raised questions regarding the value of advance directives. METHODS: We used data from survey proxies in the Health and Retirement Study involving adults 60 years of age or older who had died between 2000 and 2006 to determine the prevalence of the need for decision making and lost decision-making capacity and to test the association between preferences documented in advance directives and outcomes of surrogate decision making. RESULTS: Of 3746 subjects, 42.5% required decision making, of whom 70.3% lacked decision-making capacity and 67.6% of those subjects, in turn, had advance directives. Subjects who had living wills were more likely to want limited care (92.7%) or comfort care (96.2%) than all care possible (1.9%); 83.2% of subjects who requested limited care and 97.1% of subjects who requested comfort care received care consistent with their preferences. Among the 10 subjects who requested all care possible, only 5 received it; however, subjects who requested all care possible were far more likely to receive aggressive care as compared with those who did not request it (adjusted odds ratio, 22.62; 95% confidence interval [CI], 4.45 to 115.00). Subjects with living wills were less likely to receive all care possible (adjusted odds ratio, 0.33; 95% CI, 0.19 to 0.56) than were subjects without living wills. Subjects who had assigned a durable power of attorney for health care were less likely to die in a hospital (adjusted odds ratio, 0.72; 95% CI, 0.55 to 0.93) or receive all care possible (adjusted odds ratio, 0.54; 95% CI, 0.34 to 0.86) than were subjects who had not assigned a durable power of attorney for health care. CONCLUSIONS: Between 2000 and 2006, many elderly Americans needed decision making near the end of life at a time when most lacked the capacity to make decisions. Patients who had prepared advance directives received care that was strongly associated with their preferences. These findings support the continued use of advance directives.
Keywords: Advance directives; Aged; Aged, 80 and over; Decision making; Female; Humans; Living Wills; Logistic Models; Male; Mental Competency; Middle Aged; Proxy; Terminal Care; United States

Comparison study on functional outcomes and perceived quality of life between all-inclusive and fee-for-service continuing care retirement communities. - Young, Yuchi (J Am Med Dir Assoc, 2010)
OBJECTIVE: To examine the associations between 2 types of continuing care retirement communities' (CCRC) residents regarding physical function and perceived quality of life. METHODS: Cross-sectional study (n=406). Eligibility criteria include age 65 years or older, residents of independent living units, and intact cognition (MMSE>or=24). All-inclusive CCRCs provide unlimited access to home health services and nursing home care as needed in return for the entry and monthly fee. Fee-for-service CCRCs offer home health and nursing home services at a full fee-for-service rate. Outcomes were functional status (ADLs and IADLs) and perceived quality of life. Multivariate regressions were used to examine the associations between residents of different types of CCRCs on selected outcomes while adjusting for covariates. RESULTS: The all-inclusive CCRC sample was more likely to be married (53.8% versus 33.4%; P < .001), with more years of education (17.9 versus 14.4; P < .0001), and had few physician visits in the previous year in comparison to the FFS CCRC sample. Multivariate results indicate that the FFS group had worse ADL (beta=0.95; P=.0003), IADL (beta=0.57; P=.02) function than the all-inclusive group. There was no significant difference in perceived quality of life scores between the 2 groups. CONCLUSIONS: Residents of both CCRCs reported equally good quality of life scores. Residents of the all-inclusive CCRC seem to have had better ADL and IADL function than the FFS CCRC residents. Prepaid home health services and nursing home care in the all-inclusive CCRC may facilitate ADL and IADL functional independence.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cross-Sectional Studies; Fee-for-Service Plans; Female; Humans; Male; New York; Outcome Assessment, Health Care; Quality of Life; Residential Facilities

Cross-national comparison of sex differences in health and mortality in Denmark, Japan and the US. - Oksuzyan, Anna; Eileen M. Crimmins; Saito, Yasuhiko; Angela M O'Rand; James W Vaupel; Christensen, Kaare (Eur J Epidemiol, 2010)
The present study aims to compare the direction and magnitude of sex differences in mortality and major health dimensions across Denmark, Japan and the US. The Human Mortality Database was used to examine sex differences in age-specific mortality rates. The Danish twin surveys, the Danish 1905-Cohort Study, the Health and Retirement Study, and the Nihon University Japanese Longitudinal Study of Aging were used to examine sex differences in health. Men had consistently higher mortality rates at all ages in all three countries, but they also had a substantial advantage in handgrip strength compared with the same-aged women. Sex differences in activities of daily living (ADL) became pronounced among individuals aged 85+ in all three countries. Depression levels tended to be higher in women, particularly, in Denmark and the HRS, and only small sex differences were observed in the immediate recall test and Mini-Mental State Exam. The present study revealed consistent sex differentials in survival and physical health, self-rated health and cognition at older ages, whereas the pattern of sex differences in depressive symptoms was country-specific.
Keywords: Aged; Aged, 80 and over; Denmark; Disability Evaluation; Female; Health Status; Humans; Japan; Male; Middle Aged; Mortality; Sex Distribution; United States

Defining emergency department episodes by severity and intensity: A 15-year study of Medicare beneficiaries. - Kaskie, Brian; Maksym Obrizan; Elizabeth A Cook; Michael P Jones; Li Liu; Suzanne E Bentler; Robert B Wallace; John F Geweke; Kara B Wright; Elizabeth A Chrischilles; Claire E Pavlik; Robert L. Ohsfeldt; et al. (BMC Health Serv Res, 2010)
BACKGROUND: Episodes of Emergency Department (ED) service use among older adults previously have not been constructed, or evaluated as multi-dimensional phenomena. In this study, we constructed episodes of ED service use among a cohort of older adults over a 15-year observation period, measured the episodes by severity and intensity, and compared these measures in predicting subsequent hospitalization. METHODS: We conducted a secondary analysis of the prospective cohort study entitled the Survey on Assets and Health Dynamics among the Oldest Old (AHEAD). Baseline (1993) data on 5,511 self-respondents >or=70 years old were linked to their Medicare claims for 1991-2005. Claims then were organized into episodes of ED care according to Medicare guidelines. The severity of ED episodes was measured with a modified-NYU algorithm using ICD9-CM diagnoses, and the intensity of the episodes was measured using CPT codes. Measures were evaluated against subsequent hospitalization to estimate comparative predictive validity. RESULTS: Over 15 years, three-fourths (4,171) of the 5,511 AHEAD participants had at least 1 ED episode, with a mean of 4.5 episodes. Cross-classification indicated the modified-NYU severity measure and the CPT-based intensity measure captured different aspects of ED episodes (kappa = 0.18). While both measures were significant independent predictors of hospital admission from ED episodes, the CPT measure had substantially higher predictive validity than the modified-NYU measure (AORs 5.70 vs. 3.31; p < .001). CONCLUSIONS: We demonstrated an innovative approach for how claims data can be used to construct episodes of ED care among a sample of older adults. We also determined that the modified-NYU measure of severity and the CPT measure of intensity tap different aspects of ED episodes, and that both measures were predictive of subsequent hospitalization.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Emergency Service, Hospital; Humans; Insurance Claim Review; Medicare; Prospective Studies; Severity of Illness Index; United States

Depression among older adults in the United States and England. - Zivin, Kara; David J Llewellyn; Iain A Lang; Sandeep Vijan; Mohammed U Kabeto; Erin M Miller; Kenneth M. Langa (Am J Geriatr Psychiatry, 2010)
CONTEXT: Depression negatively affects health and well being among older adults, but there have been no nationally representative comparisons of depression prevalence among older adults in England and the United States. OBJECTIVE: The authors sought to compare depressive symptoms among older adults in these countries and identify sociodemographic and clinical correlates of depression in these countries. DESIGN AND SETTING: The authors assessed depressive symptoms in non-Hispanic whites aged 65 years and older in 2002 in two nationally representative, population-based studies: the U.S. Health and Retirement Study and English Longitudinal Study of Ageing. PARTICIPANTS: A total of 8,295 Health and Retirement Study respondents and 5,208 English Longitudinal Study of Ageing respondents. MAIN OUTCOME MEASURES: The authors measured depressive symptoms using the eight-item Center for Epidemiologic Studies Depression Scale. The authors determined whether depressive symptom differences between the United States and England were associated with sociodemographic characteristics, chronic health conditions, and health behaviors. RESULTS: Significant depressive symptoms (Center for Epidemiologic Studies Depression Scale score ≥4) were more prevalent in English than U.S. adults (17.6% versus 14.6%, adjusted Wald test F([1, 1593]) = 11.4, p < 0.001). Adjusted rates of depressive symptoms in England were 19% higher compared with the United States (odds ratio: 1.19, 95% confidence interval: 1.01-1.40). U.S. adults had higher levels of education, and net worth, but lower levels of activities of daily living/instrumental activities of daily living impairments, tobacco use, and cognitive impairment, which may have contributed to relatively lower levels of depressive symptoms in the United States. CONCLUSIONS: Older adults in the United States had lower rates of depressive symptoms than their English counterparts despite having more chronic health conditions. Future cross-national studies should identify how depression treatment influences outcomes in these populations.
Keywords: Aged; Aged, 80 and over; depression; England; Female; Health Behavior; Health Status; Health Surveys; Humans; Male; Prevalence; Risk Factors; United States; White People

Depressive symptoms predict incident stroke independently of memory impairments. - M. Maria Glymour; J Maselko; Gilman, S E; Kristen K Patton; Mauricio Avendano (Neurology, 2010)
BACKGROUND: We evaluated whether depressive symptoms predict the onset of first stroke independently of memory impairment. We conceptualized memory impairment as a marker of preexisting cerebrovascular disease. We hypothesized that if depressive symptoms are causally related to stroke through mechanisms unrelated to cerebrovascular disease, depressive symptoms should predict stroke independently of memory impairment. METHODS: Incidence of first stroke was assessed with self or proxy reports from 19,087 participants in the Health and Retirement Study cohort (1,864 events). Elevated depressive symptoms (3+ on an 8-item Centers for the Epidemiologic Study of Depression scale) and memory impairment (score of ≤6 on a combined immediate and delayed recall of a 10-word list) were used as predictors of incident stroke in Cox survival models with adjustment for sociodemographic and cardiovascular risk factors. RESULTS: After adjustment for sociodemographic and cardiovascular risk factors, elevated depressive symptoms (hazard ratio = 1.25; 95% confidence interval 1.12-1.39) and memory impairment (hazard ratio = 1.26; 95% confidence interval 1.13-1.41) each predicted stroke incidence in separate models. Hazard ratios were nearly unchanged and remained significant (1.23 for elevated depressive symptoms and 1.25 for memory impairment) when models were simultaneously adjusted for both elevated depressive symptoms and memory impairment. Elevated depressive symptoms also predicted stroke when restricting analyses to individuals with median memory score or better. CONCLUSIONS: Memory impairments and depressive symptoms independently predict stroke incidence. Memory impairment may reflect undiagnosed cerebrovascular disease. These results suggest that depressive symptoms might be directly related to stroke rather than merely indicating preexisting cerebrovascular disease.
Glymour, M M Maselko, J Gilman, S E Patton, K K Avendano, M 1R01MH087544/MH/NIMH NIH HHS/United States 1R21 AG34385-01A1/AG/NIA NIH HHS/United States 1R21AG037889-01/AG/NIA NIH HHS/United States 1R21HD066312-01/HD/NICHD NIH HHS/United States 1RC4MH092707-01/MH/NIMH NIH HHS/United States 5R03MH083335/MH/NIMH NIH HHS/United States Research Support, N.I.H., Extramural Research Support, Non-U.S. Gov't United States Neurology Neurology. 2010 Dec 7;75(23):2063-70.
Keywords: Aged; Aged, 80 and over; depression; Female; Health Surveys; Humans; Incidence; Kaplan-Meier Estimate; Longitudinal Studies; Male; Memory Disorders; Middle Aged; Neuropsychological tests; Predictive Value of Tests; Risk Factors; Statistics, Nonparametric; Stroke; United States

Disease prevalence, disease incidence, and mortality in the United States and in England. - James Banks; Muriel, Alastair; James P Smith (Demography, 2010)
We find that both disease incidence and disease prevalence are higher among Americans in age groups 55-64 and 70-80, indicating that Americans suffer from higher past cumulative disease risk and experience higher immediate risk of new disease onset compared with the English. In contrast, age-specific mortality rates are similar in the two countries, with an even higher risk among the English after age 65. We also examine reasons for the large financial gradients in mortality in the two countries. Among 55- to 64-year-olds, we estimate similar health gradients in income and wealth in both countries, but for 70- to 80-year-olds, we find no income gradient in the United Kingdom. Standard behavioral risk factors (work, marriage, obesity, exercise, and smoking) almost fully explain income gradients among those aged 55-64 in both countries and a significant part among Americans 70-80 years old. The most likely explanation of the absence of an English income gradient relates to the English income benefit system: below the median, retirement benefits are largely flat and independent of past income, and hence past health, during the working years. Finally, we report evidence using a long panel of American respondents that their subsequent mortality is not related to large changes in wealth experienced during the prior 10-year period.
Keywords: Aged; Aged, 80 and over; England; Health Status; Health Status Disparities; Humans; Incidence; Life Tables; Middle Aged; Morbidity; Mortality; Prevalence; Socioeconomic factors; United States

Dynamics and heterogeneity in the process of human frailty and aging: evidence from the U.S. older adult population. - Yang, Yang; Lee, Linda C (J Gerontol B Psychol Sci Soc Sci, 2010)
OBJECTIVES: This study investigated the dynamics and heterogeneity of the frailty index (FI) conceived as a systemic indicator of biological aging in the community-dwelling older adult population in the United States. METHODS: We used panel data on multiple birth cohorts from the Health and Retirement Survey 1993-2006 and growth curve models to estimate age trajectories of the FI and their differences by sex, race, and socioeconomic status (SES) within cohorts. RESULTS: The FI for cohorts born before 1942 exhibit quadratic increases with age and accelerated increases in the accumulation of health deficits. More recent cohorts exhibit higher average levels of and rates of increment in the FI than their predecessors do at the same ages. Females, non-Whites, and individuals with low education and income exhibit greater degrees of physiological deregulation than their male, White, and high-SES counterparts at any age. Patterns of sex, race, and SES differentials in rates of aging vary across cohorts. DISCUSSION: Adjusting for social behavioral factors, the analysis provides evidence for physiological differences in the aging process among recent cohorts of older adults, points to the need for biological explanations of female excess in general system damage, and reveals the insufficiency of any single mechanism for depicting the racial and SES differences in the process of physiological deterioration.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Frail Elderly; Humans; Male; Surveys and Questionnaires; United States

Early-life characteristics, psychiatric history, and cognition trajectories in later life. - Maria T. Brown (Gerontologist, 2010)
PURPOSE OF THE STUDY: Although considerable attention has been paid to the relationship between later-life depression and cognitive function, the relationship between a history of psychiatric problems and cognitive function is not very well documented. Few studies of relationships between childhood health, childhood disadvantage, and cognitive function in later life consider both childhood health and disadvantage, include measures for psychiatric history, or use nationally representative longitudinal data. DESIGN AND METHODS: This study uses growth curve models to analyze the relationships between childhood health and disadvantage, psychiatric history, and cognitive function using 6 waves of the Health and Retirement Study, controlling for demographics, health behavior, and health status. RESULTS: A history of psychiatric problems is associated with lower cognitive function and steeper declines in cognitive function with age. The influence of childhood health is mediated by later-life health status and behaviors. A combined history of childhood disadvantage and psychiatric problems more strongly affects cognitive function, but cognitive declines remain consistent with those associated with psychiatric history. These effects are partially mediated by later-life demographic, socioeconomic, or health characteristics. IMPLICATIONS: These findings demonstrate that cumulative disadvantage and a history of psychiatric problems shape later-life cognition and cognitive decline. This evidence can enhance public understanding of the trajectories of cognitive decline experienced by groups living with disadvantage and can enable policy makers and human services providers to better design and implement preventative interventions and support services for affected populations.
Using Smart Source Parsing pp. Oct Gerontological Society of America, Washington DC
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Cognition Disorders; Cohort Studies; Female; Health Status; Humans; Male; Mental Disorders; Middle Aged; Psychiatric Status Rating Scales; Social Environment; Socioeconomic factors; Time Factors

The effects of positive and negative support from children on widowed older adults' psychological adjustment: a longitudinal analysis. - Jung-Hwa Ha (Gerontologist, 2010)
PURPOSE: This article examines the extent to which positive and negative support from children prior to and after spousal loss and changes in support from pre- to post-loss affect widowed older adults' depressive symptoms, anxiety, and anger 18 months following widowhood. DESIGN AND METHODS: Analyses are based on the Changing Lives of Older Couples, a prospective study of 1,532 married individuals aged 65 years and older. The analytic sample includes 148 widowed persons who have at least one living child and participated in the baseline and two follow-up interviews conducted 6 and 18 months following widowhood. RESULTS: The analyses revealed that higher levels of positive support from children 6 months following widowhood were associated with fewer depressive symptoms at the 18-month follow-up, whereas higher levels of negative support 18 months after loss and a decrease in positive support following loss were associated with more depressive symptoms. Greater negative support both prior to and after loss was associated with greater anxiety, whereas greater negative support 6 months after loss and an increase in negative support following loss were related to greater anger. IMPLICATIONS: Given their differential impact on widowed persons' psychological adjustment, both positive and negative aspects of social support as well as its changing nature should be considered in working with bereaved older adults.
Using Smart Source Parsing pp. Aug Gerontological Society of America, Washington DC
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Female; Humans; Longitudinal Studies; Male; Middle Aged; Parent-Child Relations; Widowhood

The epidemiology of pain during the last 2 years of life. - Alexander K Smith; Irena Cenzer; Sara J Knight; Kathleen A Puntillo; Eric W Widera; Brie A Williams; W John Boscardin; Kenneth E Covinsky (Ann Intern Med, 2010)
BACKGROUND: The epidemiology of pain during the last years of life has not been well described. OBJECTIVE: To describe the prevalence and correlates of pain during the last 2 years of life. DESIGN: Observational study. Data from participants who died while enrolled in the Health and Retirement Study were analyzed. The survey interview closest to death was used. Each participant or proxy was interviewed once in the last 24 months of life and was classified into 1 of 24 cohorts on the basis of the number of months between the interview and death. The relationship between time before death and pain was modeled and was adjusted for age, sex, race or ethnicity, education level, net worth, income, terminal diagnosis category, presence of arthritis, and proxy status. SETTING: The Health and Retirement Study, a nationally representative survey of community-living older adults (1994 to 2006). PARTICIPANTS: Older adult decedents. MEASUREMENTS: Clinically significant pain, as indicated by a report that the participant was "often troubled" by pain of at least moderate severity. RESULTS: The sample included 4703 decedents. Mean age (SD) of participants was 75.7 years (SD, 10.8); 83.1% were white, 10.7% were black, 4.7% were Hispanic; and 52.3% were men. The adjusted prevalence of pain 24 months before death was 26% (95% CI, 23% to 30%). The prevalence remained flat until 4 months before death (28% [CI, 25% to 32%]), then it increased, reaching 46% (CI, 38% to 55%) in the last month of life. The prevalence of pain in the last month of life was 60% among patients with arthritis versus 26% among patients without arthritis (P < 0.001) and did not differ by terminal diagnosis category (cancer [45%], heart disease [48%], frailty [50%], sudden death [42%], or other causes [47%]; P = 0.195). LIMITATION: Data are cross-sectional; 19% of responses were from proxies; and information about cause, location, and treatment of pain was not available. CONCLUSION: Although the prevalence of pain increases in the last 4 months of life, pain is present in more than one quarter of elderly persons during the last 2 years of life. Arthritis is strongly associated with pain at the end of life. PRIMARY FUNDING SOURCE: National Institute on Aging, National Center for Research Resources, National Institute on Musculoskeletal and Skin Diseases, and National Palliative Care Research Center.
Keywords: Aged; Aged, 80 and over; Arthritis; Chronic disease; Cross-Sectional Studies; Death; Female; Humans; Male; pain; Palliative care; Prevalence; Quality of Life; Socioeconomic factors; Terminally Ill; Time Factors

Factors influencing cost-related nonadherence to medication in older adults: a conceptually based approach. - Zivin, Kara; Scott M Ratliff; Michele M Heisler; Kenneth M. Langa; John D Piette (Value Health, 2010)
OBJECTIVE: Although multiple noncost factors likely influence a patient's propensity to forego treatment in the face of cost pressures, little is known about how patients' sociodemographic characteristics, physical and behavioral health comorbidities, and prescription regimens influence cost-related nonadherence (CRN) to medications. We sought to determine both financial and nonfinancial factors associated with CRN in a nationally representative sample of older adults. METHODS: We used a conceptual model developed by Piette and colleagues that describes financial and nonfinancial factors that could increase someone's risk of CRN, including income, comorbidities, and medication regimen complexity. We used data from the 2004 wave of the Health and Retirement Study and the 2005 HRS Prescription Drug Study to examine the influence of factors within each of these domains on measures of CRN (including not filling, stopping, or skipping doses) in a nationally representative sample of Americans age 65+ in 2005. RESULTS: Of the 3071 respondents who met study criteria, 20% reported some form of CRN in 2005. As in prior studies, indicators of financial stress such as higher out-of-pocket payments for medications and lower net worth were significantly associated with CRN in multivariable analyses. Controlling for these economic pressures, relatively younger respondents (ages 65-74) and depressive symptoms were consistent independent risk factors for CRN. CONCLUSIONS: Noncost factors influenced patients' propensity to forego treatment even in the context of cost concerns. Future research encompassing clinician and health system factors should identify additional determinants of CRN beyond patients' cost pressures.
Keywords: Aged; Aged, 80 and over; Chronic disease; Female; Financing, Personal; Health Status; Humans; Logistic Models; Male; Medication Adherence; Models, Econometric; Multivariate Analysis; Prescription Fees; Risk Factors; Socioeconomic factors; United States

Health outcomes of Experience Corps: a high-commitment volunteer program. - S I Hong; Morrow-Howell, Nancy (Soc Sci Med, 2010)
Experience Corps (EC) is a high-commitment US volunteer program that brings older adults into public elementary schools to improve academic achievement of students. It is viewed as a health promotion program for the older volunteers. We evaluated the effects of the EC program on older adults' health, using a quasi-experimental design. We included volunteers from 17 EC sites across the US. They were pre-tested before beginning their volunteer work and post-tested after two years of service. We compared changes over time between the EC participants (n = 167) and a matched comparison group of people from the US Health and Retirement Study (2004, 2006). We developed the comparison group by using the nearest available Mahalanobis metric matching within calipers combined with the boosted propensity scores of those participating in the EC. We corrected for clustering effects via survey regression analyses with robust standard errors and calculated adjusted post-test means of health outcomes, controlling for all covariates and the boosted propensity score of EC participants. We found that compared to the comparison group, the EC group reported fewer depressive symptoms and functional limitations after two years of participation in the program, and there was a statistical trend toward the EC group reporting less decline in self-rated health. Results of this study add to the evidence supporting high-intensity volunteering as a social model of health promotion for older adults.
Using Smart Source Parsing pp. Jul Elsevier Science, Amsterdam The Netherlands
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; depression; Female; Health Promotion; Health Status; Humans; Male; Middle Aged; Program Evaluation; Regression Analysis; Self Concept; Volunteers

Health trajectories among older movers. - Janet M Wilmoth (J Aging Health, 2010)
OBJECTIVE: To examine health trajectories among older migrants by reason for move. METHOD: Data from the 1992 to 2006 Health and Retirement Study (HRS) are used to model trajectories of self-rated health and activity of daily living (ADL) limitations that occurred prior seven types of moves. RESULTS: There are substantial differences across the reason-for-move groups in initial levels of self-rated health. Declines in self-rated health among nursing home movers are more than two times steeper than the other reason-for-move groups. Employment, comfort, economic security, life crisis, and affiliation movers have low initial levels of ADL limitations and slow increases in ADL limitations. Health and nursing home movers have higher initial ADL limitations and increases in ADL limitations that are three and seven times higher respectively than the other groups. DISCUSSION: The results are consistent with the predictions of Litwak and Longino's (1987) typology of later-life migration and the extant literature on later-life migration. Implications for communities are considered.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Aging; Female; Health Status; Humans; Male; Middle Aged; Multivariate Analysis; Regression Analysis; Social Class; Transients and Migrants

Hospitalizations and deaths among adults with cardiovascular disease who underuse medications because of cost: a longitudinal analysis. - Michele M Heisler; Choi, Hwajung; Allison B Rosen; Sandeep Vijan; Mohammed U Kabeto; Kenneth M. Langa; John D Piette (Med Care, 2010)
CONTEXT: It is well-documented that the financial burden of out-of-pocket expenditures for prescription drugs often leads people with medication-sensitive chronic illnesses to restrict their use of these medications. Less is known about the extent to which such cost-related medication underuse is associated with increases in subsequent hospitalizations and deaths. OBJECTIVE: We compared the risk of hospitalizations among 5401 and of death among 6135 middle-aged and elderly adults with one or more cardiovascular diseases (diabetes, coronary artery disease, heart failure, and history of stroke) according to whether participants did or did not report restricting prescription medications because of cost. DESIGN AND SETTING: A retrospective biannual cohort study across 4 cross-sectional waves of the Health and Retirement Study, a nationally representative survey of adults older than age 50. Using multivariate logistic regression to adjust for baseline differences in sociodemographic and health characteristics, we assessed subsequent hospitalizations and deaths between 1998 and 2006 for respondents who reported that they had or had not taken less medicine than prescribed because of cost. RESULTS: Respondents with cardiovascular disease who reported underusing medications due to cost were significantly more likely to be hospitalized in the next 2 years, even after adjusting for other patient characteristics (adjusted predicted probability of 47% compared with 38%, P < 0.001). The more survey waves respondents reported cost-related medication underuse during 1998 to 2004, the higher the probability of being hospitalized in 2006 (adjusted predicted probability of 54% among respondents reporting cost-related medication underuse in all 4 survey waves compared with 42% among respondents reporting no underuse, P < 0.001). There was no independent association of cost-related medication underuse with death. CONCLUSIONS: In this nationally representative cohort, middle-aged and elderly adults with cardiovascular disease who reported cutting back on medication use because of cost were more likely to report being hospitalized over a subsequent 2-year period after they had reported medication underuse. The more extensively respondents reported cost-related underuse over time, the higher their adjusted predicted probability of subsequent hospitalization.
Using Smart Source Parsing Feb Comment In: Med Care. 2010 Feb;48(2):85-6 20057326 Index Medicus
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Financing, Personal; Health Care Costs; Health Services Accessibility; Health Status Disparities; Hospitalization; Humans; Logistic Models; Longitudinal Studies; Male; Medication Adherence; Middle Aged; Multivariate Analysis; Risk Factors; United States

Impact of cognitive impairment on screening mammography use in older US women. - Kala M. Mehta; Kathy Z Fung; Christine E Kistler; Chang, Anna; Louise C Walter (Am J Public Health, 2010)
OBJECTIVES: We evaluated mammography rates for cognitively impaired women in the context of their life expectancies, given that guidelines do not recommend screening mammography in women with limited life expectancies because harms outweigh benefits. METHODS: We evaluated Medicare claims for women aged 70 years or older from the 2002 wave of the Health and Retirement Study to determine which women had screening mammography. We calculated population-based estimates of 2-year screening mammography prevalence and 4-year survival by cognitive status and age. RESULTS: Women with severe cognitive impairment had lower rates of mammography (18%) compared with women with normal cognition (45%). Nationally, an estimated 120,000 screening mammograms were performed among women with severe cognitive impairment despite this group's median survival of 3.3 years (95% confidence interval = 2.8, 3.7). Cognitively impaired women who had high net worth and were married had screening rates approaching 50%. CONCLUSIONS: Although severe cognitive impairment is associated with lower screening mammography rates, certain subgroups with cognitive impairment are often screened despite lack of probable benefit. Given the limited life expectancy of women with severe cognitive impairment, guidelines should explicitly recommend against screening these women.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Female; Humans; Incidence; Longitudinal Studies; Mammography; Medicare; Patient Acceptance of Health Care; Social Class; United States

Length of stay for older adults residing in nursing homes at the end of life. - Kelly, Anne; Conell-Price, Jessamyn; Kenneth E Covinsky; Irena Cenzer; Chang, Anna; W John Boscardin; Alexander K Smith (J Am Geriatr Soc, 2010)
OBJECTIVES: To describe lengths of stay of nursing home decedents. DESIGN: Retrospective cohort study. SETTING: The Health and Retirement Study (HRS), a nationally representative survey of U.S. adults aged 50 and older. PARTICIPANTS: One thousand eight hundred seventeen nursing home residents who died between 1992 and 2006. MEASUREMENTS: The primary outcome was length of stay, defined as the number of months between nursing home admission and date of death. Covariates were demographic, social, and clinical factors drawn from the HRS interview conducted closest to the date of nursing home admission. RESULTS: The mean age of decedents was 83.3 ± 9.0; 59.1% were female, and 81.5% were white. Median and mean length of stay before death were 5 months (interquartile range 1-20) and 13.7 ± 18.4 months, respectively. Fifty-three percent died within 6 months of placement. Large differences in median length of stay were observed according to sex (men, 3 months vs women, 8 months) and net worth (highest quartile, 3 months vs lowest quartile, 9 months) (all P <.001). These differences persisted after adjustment for age, sex, marital status, net worth, geographic region, and diagnosed chronic conditions (cancer, hypertension, diabetes mellitus, lung disease, heart disease, and stroke). CONCLUSION: Nursing home lengths of stay are brief for the majority of decedents. Lengths of stay varied markedly according to factors related to social support.
Keywords: Advance care planning; Aged; Aged, 80 and over; Female; Follow-Up Studies; Humans; Length of Stay; Male; Middle Aged; Nursing homes; Palliative care; Retrospective Studies; United States

Longitudinal changes in disabled husbands' and wives' receipt of care. - Claire Noël-Miller (Gerontologist, 2010)
PURPOSE OF THE STUDY: This study contrasts 2-year adjustments in disabled husbands' and wives' amount of received care following both worsening and recovery in personal (activities of daily living [ADLs]) and routine care (instrumental activities of daily living [IADLs]) disability. DESIGN AND METHODS: Using longitudinal data on 789 husbands and 778 wives from the Health and Retirement Study (2000 and 2002), changes in marital partners' monthly hours of spousal and nonspousal care were jointly modeled using bivariate Tobit models. In addition, asymmetry in the magnitude of responses to worsening and improvement of function was examined. RESULTS: Disabled husbands receive more hours of spousal and nonspousal care following worsening in ADL function than wives. Conversely, disabled wives lose more spousal and nonspousal care hours following improvements in ADL disability than husbands. Moreover, wives recovering in ADL function lose more hours of spousal care than they receive following worsening in personal care disability. There is no evidence of corresponding gender differences in the dynamics of assistance received following changes in IADL function. IMPLICATIONS: Compared with husbands, disabled wives are disadvantaged in the adjustment of their personal care hours. Although disabled married community residents receive more hours of care than their unmarried counterparts, there are important gender differences in the advantages offered by marriage.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Disabled Persons; Female; Humans; Long-term Care; Longitudinal Studies; Male; Marriage; Middle Aged; Models, Theoretical; Sex Factors; Social Support; Socioeconomic factors; Spouses; Surveys and Questionnaires; Time Factors

Long-term cognitive impairment and functional disability among survivors of severe sepsis. - Theodore J Iwashyna; E Wesley Ely; Dylan M Smith; Kenneth M. Langa (JAMA, 2010)
CONTEXT: Cognitive impairment and functional disability are major determinants of caregiving needs and societal health care costs. Although the incidence of severe sepsis is high and increasing, the magnitude of patients' long-term cognitive and functional limitations after sepsis is unknown. OBJECTIVE: To determine the change in cognitive impairment and physical functioning among patients who survive severe sepsis, controlling for their presepsis functioning. DESIGN, SETTING, AND PATIENTS: A prospective cohort involving 1194 patients with 1520 hospitalizations for severe sepsis drawn from the Health and Retirement Study, a nationally representative survey of US residents (1998-2006). A total of 9223 respondents had a baseline cognitive and functional assessment and had linked Medicare claims; 516 survived severe sepsis and 4517 survived a nonsepsis hospitalization to at least 1 follow-up survey and are included in the analysis. MAIN OUTCOME MEASURES: Personal interviews were conducted with respondents or proxies using validated surveys to assess the presence of cognitive impairment and to determine the number of activities of daily living (ADLs) and instrumental ADLs (IADLs) for which patients needed assistance. RESULTS: Survivors' mean age at hospitalization was 76.9 years. The prevalence of moderate to severe cognitive impairment increased 10.6 percentage points among patients who survived severe sepsis, an odds ratio (OR) of 3.34 (95% confidence interval [CI], 1.53-7.25) in multivariable regression. Likewise, a high rate of new functional limitations was seen following sepsis: in those with no limits before sepsis, a mean 1.57 new limitations (95% CI, 0.99-2.15); and for those with mild to moderate limitations before sepsis, a mean of 1.50 new limitations (95% CI, 0.87-2.12). In contrast, nonsepsis general hospitalizations were associated with no change in moderate to severe cognitive impairment (OR, 1.15; 95% CI, 0.80-1.67; P for difference vs sepsis = .01) and with the development of fewer new limitations (mean among those with no limits before hospitalization, 0.48; 95% CI, 0.39-0.57; P for difference vs sepsis <.001 and mean among those with mild to moderate limits, 0.43; 95% CI, 0.23-0.63; P for difference = .001). The declines in cognitive and physical function persisted for at least 8 years. CONCLUSIONS: Severe sepsis in this older population was independently associated with substantial and persistent new cognitive impairment and functional disability among survivors. The magnitude of these new deficits was large, likely resulting in a pivotal downturn in patients' ability to live independently.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Case-Control Studies; Cognition Disorders; Disabled Persons; Female; Health Status; Hospitalization; Humans; Male; Prospective Studies; Sepsis; Severity of Illness Index; Survivors; United States

Modifiable risk factors for incidence of pain in older adults. - Yu Shi; Hooten, W Michael; Rosebud O. Roberts; David O. Warner (Pain, 2010)
Pain symptoms in aging populations have significant public health impact. The aim of this study was to determine risk factors for the incidence of pain in older adults, focusing on those factors that can be modified. Secondary analyses were performed of survey data from the nationally representative Health and Retirement Study of US adults older than 50 years. Generalized estimating equations logistic regressions were used to evaluate the effect of selected variables on the incidence of pain using biennial (1992 through 2006) data, determining the relationship between the incidence of pain and the potential risk factors. Of the 18,439 survey respondents in 2006, 34.1% (95% CI: 33.2%, 35.0%) reported that they were often troubled by pain; 24.3% reported having moderate to severe pain; and 22.3% reported that their daily life was affected by pain. Between 1992 and 2006, 7967 individuals reported new onset of pain in 169,762 person-years of follow-up, an incidence of 4.69 (4.59, 4.80) per 100 person-years. Depression and being overweight were independent predictors associated with an increased likelihood of incident pain. Current smoking increased the likelihood of incident pain only in those subjects who also reported depression. In conclusion, pain is a common symptom in older adults. Depression, smoking, and overweight are potentially modifiable risk factors and could be considered in the prevention and management of pain in older adults.
Keywords: Age Factors; Aged; Aged, 80 and over; Cross-Sectional Studies; Demography; depression; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Overweight; pain; Prevalence; Retrospective Studies; Risk Assessment; Risk Factors; Smoking; United States

Obesity and excess mortality among the elderly in the United States and Mexico. - Monteverde, Malena; Noronha, Kenya; Alberto Palloni; Beatriz Novak (Demography, 2010)
Increasing levels of obesity could compromise future gains in life expectancy in low- and high-income countries. Although excess mortality associated with obesity and, more generally, higher levels of body mass index (BAI) have been investigated in the United States, there is little research about the impact of obesity on mortality in Latin American countries, where very the rapid rate of growth of prevalence of obesity and overweight occur jointly with poor socioeconomic conditions. The aim of this article is to assess the magnitude of excess mortality due to obesity and overweight in Mexico and the United States. For this purpose, we take advantage of two comparable data sets: the Health and Retirement Study 2000 and 2004 for the United States, and the Mexican Health and Aging Study 2001 and 2003 for Mexico. We find higher excess mortality risks among obese and overweight individuals aged 60 and older in Mexico than in the United States. Yet, when analyzing excess mortality among different socioeconomic strata, we observe greater gaps by education in the United States than in Mexico. We also find that although the probability of experiencing obesity-related chronic diseases among individuals with high BMI is larger for the U.S. elderly, the relative risk of dying conditional on experiencing these diseases is higher in Mexico.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Chronic disease; Female; Humans; Logistic Models; Male; Mexico; Middle Aged; Mortality; Multivariate Analysis; Obesity; Risk Factors; Socioeconomic factors; United States

Older adults' expectations to move: do they predict actual community-based or nursing facility moves within 2 years? - Julie F. Sergeant; David J Ekerdt; Chapin, Rosemary K (J Aging Health, 2010)
OBJECTIVE: This study examined the relationship between older adults' expectations to move and actual residential relocation in the community or to a nursing facility within 2 years. METHOD: Two waves of data (2000, 2002) from the Health and Retirement Study were used to compare expectations with subsequent moves. Logistic regression techniques were used to analyze the association between decision outcomes and expectations to move, health and functioning, physical environment, informal supports, and formal services. RESULTS: Findings indicated that expectations to move did predict community-based moves but did not predict moves to nursing facilities. Additional factors had significant effects but did not diminish relationships between expectations and actual moves. DISCUSSION: Results support the residential decision process as a dynamic one based on the cumulative effect of factors from an ecological model. Findings will inform policy makers and practitioners as they work to support older adults' preferences to remain living in their homes.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Community Health Services; Decision making; Female; Humans; Logistic Models; Male; Odds Ratio; Residence Characteristics; Skilled Nursing Facilities; Social Support; Statistics as Topic; Time Factors; Transients and Migrants

Predicting positive well-being in older men and women. - Erin L. Waddell; Joy M Jacobs-Lawson (Int J Aging Hum Dev, 2010)
The purpose of this study was to examine the effects of background, psychological, and social variables on older adults' well-being, and how this may differ for men and women. Participants included 800 adults from the 2002 Health and Retirement Study (HRS), aged 60 to 101 years old (M = 71.22, SD = 8.46), who completed the optional positive well-being module. Gender-based regression models revealed that for men, marital status, self-rated health, and depression were significant predictors and accounted for 32% of the variability in positive well-being. Similar to men, self-rated health and depression were significant predictors of well-being for women. Additional significant predictors for women included age, the importance of religion, and volunteer work. Combined, these variables explained 35% of the variance in women's positive well-being. These results can help us understand which variables are important to target when developing interventions to improve the well-being of older men and women.
Keywords: Aged; Aged, 80 and over; Aging; depression; Female; Health Status; Humans; Male; Marriage; Middle Aged; Personal Satisfaction; Predictive Value of Tests; Quality of Life; Regression Analysis; Religion and Psychology; Self Concept; Sex Distribution; Social Behavior; Surveys and Questionnaires; Volunteers

Prevalence and predictors of fatigue in middle-aged and older adults: evidence from the health and retirement study. - Meng, Hongdao; Hale, Lauren; Friedberg, Fred (J Am Geriatr Soc, 2010)
Keywords: Aged; Aged, 80 and over; Fatigue; Female; Health Surveys; Humans; Male; Middle Aged; Prevalence; Retirement; Retrospective Studies; Survival Rate; United States

Prevalence of neuropsychiatric symptoms and their association with functional limitations in older adults in the United States: the aging, demographics, and memory study. - Okura, Toru; Brenda L Plassman; David C Steffens; David J Llewellyn; Guy G Potter; Kenneth M. Langa (J Am Geriatr Soc, 2010)
OBJECTIVES: To estimate the prevalence of neuropsychiatric symptoms and examine their association with functional limitations. DESIGN: Cross-sectional analysis. SETTING: The Aging, Demographics, and Memory Study (ADAMS). PARTICIPANTS: A sample of adults aged 71 and older (N=856) drawn from Health and Retirement Study (HRS), a nationally representative cohort of U.S. adults aged 51 and older. MEASUREMENTS: The presence of neuropsychiatric symptoms (delusions, hallucinations, agitation, depression, apathy, elation, anxiety, disinhibition, irritation, and aberrant motor behaviors) was identified using the Neuropsychiatric Inventory. A consensus panel in the ADAMS assigned a cognitive category (normal cognition; cognitive impairment, no dementia (CIND); mild, moderate, or severe dementia). Functional limitations, chronic medical conditions, and sociodemographic information were obtained from the HRS and ADAMS. RESULTS: Forty-three percent of individuals with CIND and 58% of those with dementia exhibited at least one neuropsychiatric symptom. Depression was the most common individual symptom in those with normal cognition (12%), CIND (30%), and mild dementia (25%), whereas apathy (42%) and agitation (41%) were most common in those with severe dementia. Individuals with three or more symptoms and one or more clinically significant symptoms had significantly higher odds of having functional limitations. Those with clinically significant depression had higher odds of activity of daily living limitations, and those with clinically significant depression, anxiety, or aberrant motor behaviors had significantly higher odds of instrumental activity of daily living limitations. CONCLUSION: Neuropsychiatric symptoms are highly prevalent in older adults with CIND and dementia. Of those with cognitive impairment, a greater number of total neuropsychiatric symptoms and some specific individual symptoms are strongly associated with functional limitations.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Behavioral Symptoms; Cognition Disorders; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Disorders; Prevalence; United States

The prospective relationship between binge drinking and physician visits among older adults. - Kristi Rahrig Jenkins; Robert A. Zucker (J Aging Health, 2010)
OBJECTIVES: The objectives are to (a) determine if binge drinking is related to physician visits and (b) estimate the degree to which the relationship between binge drinking and physician visits can be explained by other health characteristics. METHOD: Data on a sample of 4,960 older adults (70+ years of age in 2002) from the Health and Retirement Study (HRS) were used. Three linear regression models estimated the impact of binge drinking on physician visits. RESULTS: In the fully adjusted models, binge drinking did have an effect on the number of physician visits by older adults, with more frequent binge drinkers having fewer physician visits. This negative relationship exists even when demographic as well as other current health characteristics are controlled. DISCUSSION: The implications of these results are discussed in terms of more broadly communicating the risks associated with binge drinking and more effectively targeting interventions to older binge drinkers.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Alcoholic Intoxication; Female; Health Resources; Health Services Accessibility; Health Services Needs and Demand; Health Status Indicators; Humans; Linear Models; Male; Michigan; Multivariate Analysis; Patient Satisfaction; Physicians; Prospective Studies; Psychometrics; Risk Assessment; Risk Factors; Self Report

Reforming beneficiary cost sharing to improve Medicare performance. - Zuckerman, Stephen; Shang, Baoping; Timothy A Waidmann (Inquiry, 2010)
This paper explores options for reforming Medicare cost sharing in an effort to provide better financial protection for those beneficiaries with the greatest health care needs. Using data from the Health and Retirement Study (HRS) and the Medicare Current Beneficiary Survey (MCBS), we consider how unified annual deductibles, alternative coinsurance rates, and a limit on out-of-pocket spending would alter program spending, beneficiary cost sharing, and premiums for supplemental coverage. We show that adding an out-of-pocket limit and raising deductibles and coinsurance slightly would provide better safeguards to beneficiaries with high costs than the current Medicare benefit structure. Our estimates also suggest that policies protecting these beneficiaries could be structured in a way that would add little to overall program costs.
Keywords: Aged; Aged, 80 and over; Cost Sharing; Health Expenditures; Humans; Medicare; Middle Aged; Models, Economic; United States

Situational versus chronic loneliness as risk factors for all-cause mortality. - Sharon Shiovitz-Ezra; Liat Ayalon (Int Psychogeriatr, 2010)
BACKGROUND: Several international studies have substantiated the role of loneliness as a risk factor for mortality. Although both theoretical and empirical research has supported the classification of loneliness as either situational or chronic, research to date has not evaluated whether this classification has a differential impact upon mortality. METHODS: To establish the definition of situational vs. chronic loneliness, we used three waves of the Health and Retirement Study (HRS), a nationally representative sample of Americans over the age of 50 years. Baseline data for the present study were collected in the years 1996, 1998, and 2000. The present study concerns the 7,638 individuals who completed all three waves; their loneliness was classified as either not lonely, situational loneliness or chronic loneliness. Mortality data were available through to the year 2004. RESULTS: Those identified as "situationally lonely" (HR = 1.56; 95% CI: 1.52-1.62) as well as those identified as "chronically lonely" (HR = 1.83; 95% CI: 1.71-1.87) had a greater risk for all cause mortality net of the effect of possible demographic and health confounders. Nonetheless, relative to those classified as "situationally lonely," individuals classified as "chronically lonely" had a slightly greater mortality risk. CONCLUSIONS: The current study emphasizes the important role loneliness plays in older adults' health. The study further supports current division into situational vs. chronic loneliness, yet suggests that both types serve as substantial mortality risks.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Cause of Death; Female; Geriatric Assessment; Health Surveys; Humans; Israel; Life Change Events; Loneliness; Male; Middle Aged; Risk Factors; social isolation; Surveys and Questionnaires; Time Factors

Sociodemographic and health-related risks for loneliness and outcome differences by loneliness status in a sample of U.S. older adults. - Laurie A. Theeke (Res Gerontol Nurs, 2010)
This study assesses sociodemographic and health-related factors associated with loneliness and outcome differences between loneliness groups using a sample of 13,812 older adults from the U.S Health and Retirement Study. Descriptive and bivariate analyses were followed by logistic regression to evaluate risks and analysis of covariance testing to determine outcome differences. Overall, prevalence of loneliness was 16.9%. Nonmarried status, poorer self-report of health, lower educational level, functional impairment, increasing number of chronic illnesses, younger age, lower income, and less people living in the household were all associated with loneliness. The chronically lonely group reported less exercise, more tobacco use, less alcohol use, a greater number of chronic illnesses, higher depression scores, and greater average number of nursing home stays. Future research evaluating the effectiveness of both prevention and treatment interventions for loneliness in older adults would provide empirical data to further guide gerontological nursing practice.
Keywords: Aged; Aged, 80 and over; Female; Health Status; Humans; Logistic Models; Loneliness; Male; Middle Aged; Multivariate Analysis; Risk Factors; Socioeconomic factors; United States

Spousal loss, children, and the risk of nursing home admission. - Claire Noël-Miller (J Gerontol B Psychol Sci Soc Sci, 2010)
UNLABELLED: OBJECTIVES. Informed by a life course perspective, this study investigates the effects of spousal loss and availability of adult children on elderly husbands' and wives' risk of nursing home entry. METHODS: Based on longitudinal data from the Health and Retirement Study, we studied 2,116 couples who were community residents in 1998. We estimate proportional hazards models for husbands' and wives' duration to first nursing home admission during 8 years of follow-up. RESULTS: Overall, 438 (20.7%) husbands and 382 (18.1%) wives were institutionalized, and 362 (17.1%) husbands and 701 (33.1%) wives lost their spouse. Accounting for measured covariates, the risk of nursing home entry doubled for men following spousal death, but was unchanged for women. Results indicate that adult children reduced wives' risk of nursing home admission regardless of husbands' vital status, but buffered husbands' risk only after the death of their wives. We uncover suggestive evidence of parent-child gender concordance in children's buffering effect of widowed parents' risk of institutionalization. Discussion. Our findings are consistent with gender variations in spousal caregiving and in husbands' and wives' relative reliance on care from a partner and children. This study provides new evidence on the relationship between institutionalization and family structure among married elderly persons.
Keywords: Activities of Daily Living; Adult children; Aged; Aged, 80 and over; Aging; Bereavement; Caregivers; Family Characteristics; Female; Gender Identity; Homes for the Aged; Humans; Long-term Care; Male; Nursing homes; Parent-Child Relations; Patient Admission; Proportional Hazards Models; Social Support; Spouses; Utilization Review

Stability and changes in living arrangements: relationship to nursing home admission and timing of placement. - Judith D Kasper; Liliana E Pezzin; Rice, J Bradford (J Gerontol B Psychol Sci Soc Sci, 2010)
OBJECTIVES: To examine whether stability of living arrangements and changes in household composition-both types and frequency-influence nursing home placement or timing to entry among older people. METHODS: Data from the first 5 waves of the Assets and Health Dynamics of the Elderly (1993-2002) on 8,093 persons aged 70 years or older at baseline are used in probit and hazard models to predict nursing home entry and time to entry. RESULTS: Stable living arrangements carry different risks of institutionalization. Those living continuously alone or with others were at highest risk; at lowest risk were those living continuously with a spouse or the same child (lowest overall). Changes in household composition were protective against nursing home entry and slowed time to entry; types of change were not influential when number of changes was taken into account. DISCUSSION: Results suggest that stability of living arrangements in and of itself is not protective against institutionalization. Having options that allow one to change living arrangements over time in response to changing needs for assistance is of importance if the goal is to avoid institutional care or extend community residence prior to entry.
Keywords: Aged; Aged, 80 and over; Family Characteristics; Female; Health Status; Homes for the Aged; Humans; Institutionalization; Male; Marital Status; Multivariate Analysis; Nursing homes; Risk Factors; Single Person; Socioeconomic factors; Time Factors; United States

Surgery as a teachable moment for smoking cessation. - Yu Shi; David O. Warner (Anesthesiology, 2010)
BACKGROUND: A "teachable moment" is an event that motivates spontaneous behavior change. Some evidence suggests that major surgery for a smoking-related illness can serve as a teachable moment for smoking cessation. This study tested the hypotheses that surgery increases the likelihood of smoking cessation and that cessation is more likely after major surgical procedures compared with outpatient surgery. METHODS: Secondary analyses were performed of longitudinal biennial survey data (1992-2004) from the nationally representative Health and Retirement Study of U.S. adults older than 50 yr, determining the relationship between the incidence of smoking cessation and the occurrence of surgery. RESULTS: Five thousand four hundred ninety-eight individuals reported current smoking at enrollment, and 2,444 of them (44.5%) quit smoking during the period of examination. The incidence of quitting in smokers undergoing major surgery was 20.6/100 person-years of follow-up and 10.2/100 person-years in those undergoing outpatient surgery. In a multivariate negative binomial regression model, the incidence rate ratio of quitting associated with major surgery was 2.02 (95% CI: 1.67-2.44) and that of those associated with outpatient surgery was 1.28 (95% CI: 1.09-1.50). Estimates derived from national surgical utilization data show that approximately 8% of all quit events in the United States annually can be attributed to the surgical procedures analyzed. CONCLUSIONS: Undergoing surgery is associated with an increased likelihood of smoking cessation in the older U.S. population. Cessation is more likely in association with major procedures compared with outpatient surgery. These data support the concept that surgery is a teachable moment for smoking cessation.
Keywords: Aged; Aged, 80 and over; Ambulatory Surgical Procedures; Analysis of Variance; Cohort Studies; Female; Follow-Up Studies; General Surgery; Humans; Longitudinal Studies; Male; Middle Aged; Patient Education as Topic; Regression Analysis; Smoking cessation; Treatment Outcome; United States

Trading years for perfect health: results from the health and retirement study. - Liat Ayalon; King-Kallimanis, Bellinda L (J Aging Health, 2010)
OBJECTIVE: To evaluate the preferences of an ethnically diverse national sample of older Americans regarding length of life versus health quality. METHOD: A time trade-off task administered as part of the 2002 wave of the Health and Retirement Study. RESULTS: Respondents equated 6.86 (SD = 3.46) years of perfect health with 10 years of life in imperfect health. Women and those who ranked their health less favorably were more likely to give up years of life for perfect health. Relative to Whites, Blacks were more willing to live longer in imperfect health. Those of lower levels of education were more likely to prefer 10 years of life in imperfect health. DISCUSSION: There is wide variability in responses to the time trade-off task that is partially associated with self-rated health, gender, ethnicity, and education.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Aging; Community Participation; Confidence Intervals; Culture; Epidemiologic Methods; ethnicity; Female; Health Surveys; Humans; Longevity; Male; Multivariate Analysis; Psychometrics; Retirement; Self Report; Surveys and Questionnaires; Time Factors

Untreated poor vision: a contributing factor to late-life dementia. - Mary A M Rogers; Kenneth M. Langa (Am J Epidemiol, 2010)
Ophthalmologic abnormalities have been described in patients with dementia, but the extent to which poor vision and treatment for visual disorders affect cognitive decline is not well defined. Linked data from the Health and Retirement Study and Medicare files (1992-2005) were used to follow the experiences of 625 elderly US study participants with normal cognition at baseline. The outcome was a diagnosis of dementia, cognitively impaired but no dementia, or normal cognition. Poor vision was associated with development of dementia (P = 0.0048); individuals with very good or excellent vision at baseline had a 63% reduced risk of dementia (95% confidence interval (CI): 20, 82) over a mean follow-up period of 8.5 years. Participants with poorer vision who did not visit an ophthalmologist had a 9.5-fold increased risk of Alzheimer disease (95% CI: 2.3, 39.5) and a 5-fold increased risk of cognitively impaired but no dementia (95% CI: 1.6, 15.9). Poorer vision without a previous eye procedure increased the risk of Alzheimer disease 5-fold (95% CI: 1.5, 18.8). For Americans aged 90 years or older, 77.9% who maintained normal cognition had received at least one previous eye procedure compared with 51.7% of those with Alzheimer disease. Untreated poor vision is associated with cognitive decline, particularly Alzheimer disease.
Keywords: Aged, 80 and over; Cognition Disorders; Dementia; Female; Humans; Logistic Models; Male; Medicare; Ophthalmology; Patient Acceptance of Health Care; Risk Factors; United States; Vision Disorders

A 12-year prospective study of stroke risk in older Medicare beneficiaries. - Frederic D Wolinsky; Suzanne E Bentler; Elizabeth A Cook; Elizabeth A Chrischilles; Li Liu; Kara B Wright; John F Geweke; Maksym Obrizan; Claire E Pavlik; Robert L. Ohsfeldt; Michael P Jones; Robert B Wallace; et al. (BMC Geriatr, 2009)
BACKGROUND: 5.8 M living Americans have experienced a stroke at some time in their lives, 780K had either their first or a recurrent stroke this year, and 150K died from strokes this year. Stroke costs about $66B annually in the US, and also results in serious, long-term disability. Therefore, it is prudent to identify all possible risk factors and their effects so that appropriate intervention points may be targeted. METHODS: Baseline (1993-1994) interview data from the nationally representative Survey on Assets and Health Dynamics among the Oldest Old (AHEAD) were linked to 1993-2005 Medicare claims. Participants were 5,511 self-respondents >or= 70 years old. Two ICD9-CM case-identification approaches were used. Two approaches to stroke case-identification based on ICD9-CM codes were used, one emphasized sensitivity and the other emphasized specificity. Participants were censored at death or enrollment into managed Medicare. Baseline risk factors included sociodemographic, socioeconomic, place of residence, health behavior, disease history, and functional and cognitive status measures. A time-dependent marker reflecting post-baseline non-stroke hospitalizations was included to reflect health shocks, and sensitivity analyses were conducted to identify its peak effect. Competing risk, proportional hazards regression was used. RESULTS: Post-baseline strokes occurred for 545 (9.9%; high sensitivity approach) and 374 (6.8%; high specificity approach) participants. The greatest static risks involved increased age, being widowed or never married, living in multi-story buildings, reporting a baseline history of diabetes, hypertension, or stroke, and reporting difficulty picking up a dime, refusing to answer the delayed word recall test, or having poor cognition. Risks were similar for both case-identification approaches and for recurrent and first-ever vs. only first-ever strokes. The time-dependent health shock (recent hospitalization) marker did not alter the static model effect estimates, but increased stroke risk by 200% or more. CONCLUSION: The effect of our health shock marker (a time-dependent recent hospitalization indicator) was large and did not mediate the effects of the traditional risk factors. This suggests an especially vulnerable post-hospital transition period from adverse effects associated with both their underlying health shock (the reasons for the recent hospital admission) and the consequences of their treatments.
Keywords: Aged; Aged, 80 and over; Female; Humans; Insurance Benefits; Male; Medicare; Prospective Studies; Risk Factors; Socioeconomic factors; Stroke; United States

The accuracy of Medicare claims as an epidemiological tool: the case of dementia revisited. - Donald H. Taylor Jr.; Østbye, Truls; Kenneth M. Langa; David R Weir; Brenda L Plassman (J Alzheimers Dis, 2009)
Our study estimates the sensitivity and specificity of Medicare claims to identify clinically-diagnosed dementia, and documents how errors in dementia assessment affect dementia cost estimates. We compared Medicare claims from 1993-2005 to clinical dementia assessments carried out in 2001-2003 for the Aging Demographics and Memory Study (ADAMS) cohort (n = 758) of the Health and Retirement Study. The sensitivity and specificity of Medicare claims was 0.85 and 0.89 for dementia (0.64 and 0.95 for AD). Persons with dementia cost the Medicare program (in 2003) $7,135 more than controls (P < 0.001) when using claims to identify dementia, compared to $5,684 more when using ADAMS (P < 0.001). Using Medicare claims to identify dementia results in a 110% increase in costs for those with dementia as compared to a 68% increase when using ADAMS to identify disease, net of other variables. Persons with false positive Medicare claims notations of dementia were the most expensive group of subjects ($11,294 versus $4,065, for true negatives P < 0.001). Medicare claims overcount the true prevalence of dementia, but there are both false positive and negative assessments of disease. The use of Medicare claims to identify dementia results in an overstatement of the increase in Medicare costs that are due to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Cohort Studies; Dementia; Female; Health Care Costs; Humans; Insurance Claim Reporting; Male; Medicare; Prevalence; Sensitivity and Specificity; United States

The aftermath of hip fracture: discharge placement, functional status change, and mortality. - Suzanne E Bentler; Li Liu; Maksym Obrizan; Elizabeth A Cook; Kara B Wright; John F Geweke; Elizabeth A Chrischilles; Claire E Pavlik; Robert B Wallace; Robert L. Ohsfeldt; Michael P Jones; Gary E Rosenthal; et al. (Am J Epidemiol, 2009)
The authors prospectively explored the consequences of hip fracture with regard to discharge placement, functional status, and mortality using the Survey on Assets and Health Dynamics Among the Oldest Old (AHEAD). Data from baseline (1993) AHEAD interviews and biennial follow-up interviews were linked to Medicare claims data from 1993-2005. There were 495 postbaseline hip fractures among 5,511 respondents aged >or=69 years. Mean age at hip fracture was 85 years; 73% of fracture patients were white women, 45% had pertrochanteric fractures, and 55% underwent surgical pinning. Most patients (58%) were discharged to a nursing facility, with 14% being discharged to their homes. In-hospital, 6-month, and 1-year mortality were 2.7%, 19%, and 26%, respectively. Declines in functional-status-scale scores ranged from 29% on the fine motor skills scale to 56% on the mobility index. Mean scale score declines were 1.9 for activities of daily living, 1.7 for instrumental activities of daily living, and 2.2 for depressive symptoms; scores on mobility, large muscle, gross motor, and cognitive status scales worsened by 2.3, 1.6, 2.2, and 2.5 points, respectively. Hip fracture characteristics, socioeconomic status, and year of fracture were significantly associated with discharge placement. Sex, age, dementia, and frailty were significantly associated with mortality. This is one of the few studies to prospectively capture these declines in functional status after hip fracture.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; depression; Female; Health Status; Health Status Indicators; Hip Fractures; Humans; Interviews as Topic; Iowa; Length of Stay; Logistic Models; Medicare; Patient Discharge; Prospective Studies; Psychometrics; Socioeconomic factors; Time Factors; Treatment Outcome; United States

"Below average" self-assessed school performance and Alzheimer's disease in the Aging, Demographics, and Memory Study. - Kala M. Mehta; Anita L Stewart; Kenneth M. Langa; Kristine Yaffe; Sandra Y. Moody-Ayers; Brie A Williams; Kenneth E Covinsky (Alzheimers Dement, 2009)
BACKGROUND: A low level of formal education is becoming accepted as a risk factor for Alzheimer's disease (AD). Although increasing attention has been paid to differences in educational quality, no previous studies addressed participants' own characterizations of their overall performance in school. We examined whether self-assessed school performance is associated with AD beyond the effects of educational level alone. METHODS: Participants were drawn from the population-representative Aging, Demographics, and Memory Study (ADAMS, 2000-2002). The ADAMS participants were asked about their performance in school. Possible response options included "above average," "average," or "below average." The ADAMS participants also underwent a full neuropsychological battery, and received a research diagnosis of possible or probable AD. RESULTS: The 725 participants (mean age, 81.8 years; 59% female; 16% African-American) varied in self-assessed educational performance: 29% reported "above average," 64% reported "average," and 7% reported "below average" school performance. Participants with a lower self-assessed school performance had higher proportions of AD: 11% of participants with "above average" self-assessed performance had AD, as opposed to 12% of participants with "average" performance and 26% of participants with "below average" performance (P < 0.001). After controlling for subjects' years in school, a literacy test score (Wide-Range Achievement Test), age, sex, race/ethnicity, apolipoprotein E-epsilon4 status, socioeconomic status, and self-reported comorbidities, respondents with "below average" self-assessed school performance were four times more likely to have AD compared with those of "average" performance (odds ratio, 4.0; 95% confidence interval, 1.2-14). "Above average" and "average" self-assessed school performance did not increase or decrease the odds of having AD (odds ratio, 0.9; 95% confidence interval, 0.5-1.7). CONCLUSIONS: We suggest an association between "below average" self-assessed school performance and AD beyond the known association with formal education. Efforts to increase cognitive reserve through better school performance, in addition to increasing the number of years of formal education in early life, may be important in reducing vulnerability throughout the life course.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer disease; Apolipoprotein E4; Cognition Disorders; Educational Status; Female; Geriatric Assessment; Humans; Male; Memory; Neuropsychological tests; Risk Factors

Can self-reported strokes be used to study stroke incidence and risk factors?: evidence from the health and retirement study. - M. Maria Glymour; Mauricio Avendano (Stroke, 2009)
BACKGROUND AND PURPOSE: Most stroke incidence studies use geographically localized (community) samples with few national data sources available. Such samples preclude research on contextual risk factors, but national samples frequently collect only self-reported stroke. We examine whether incidence estimates from clinically verified studies are consistent with estimates from a nationally representative US sample assessing self-reported stroke. METHODS: Health and Retirement Study (HRS) participants (n=17 056) age 50+ years were followed for self- or proxy-reported first stroke (1293 events) from 1998 to 2006 (average, 6.8 years). We compared incidence rates by race, sex, and age strata with those previously documented in leading geographically localized studies with medically verified stroke. We also examined whether cardiovascular risk factor effect estimates in HRS are comparable to those reported in studies with clinically verified strokes. RESULTS: The weighted first-stroke incidence rate was 10.0 events/1000 person-years. Total age-stratified incidence rates in whites were mostly comparable with those reported elsewhere and were not systematically higher or lower. However, among blacks in HRS, incidence rates generally appeared higher than those previously reported. HRS estimates were most comparable with those reported in the Cardiovascular Health Study. Incidence rates approximately doubled per decade of age and were higher in men and blacks. After demographic adjustment, all risk factors predicted stroke incidence in whites. Smoking, hypertension, diabetes, and heart disease predicted incident stroke in blacks. CONCLUSIONS: Associations between known risk factors and stroke incidence were verified in HRS, suggesting that misreporting is nonsystematic. HRS may provide valuable data for stroke surveillance and examination of classical and contextual risk factors.
Keywords: Age Factors; Aged; Aged, 80 and over; Algorithms; Epidemiologic Methods; ethnicity; Female; Humans; Longitudinal Studies; Male; Middle Aged; Retirement; Risk Factors; Sex Factors; Stroke; Treatment Outcome; United States

Childhood socioeconomic status and racial differences in disability: evidence from the Health and Retirement Study (1998-2006). - Mary E Bowen (Soc Sci Med, 2009)
This study used a life course approach to examine the ways in which childhood socioeconomic status (SES) may account for some of the racial differences in disability in later life. Eight years (5 waves) of longitudinal data from the US Health and Retirement Study (HRS; 1998-2006), a nationally representative sample of community-dwelling Black and White Americans over age 50 (N=14,588), were used in nonlinear multilevel models. Parental education and father's occupation were used to predict racial differences in activities of daily living (ADL) and instrumental activities of daily living (IADL). The role of adult SES (education, income, and wealth) and health behaviors (smoking, drinking alcohol, exercising, and being obese) were also examined and models were adjusted for health conditions (heart problems, diabetes, stroke, hypertension, cancer, lung disease, and arthritis). With the inclusion of childhood SES indicators, racial differences in ADL and IADL disability were reduced. Adult SES and health behaviors mediated some of the relationship between low childhood SES and disability, though low childhood SES continued to be associated with disability net of these. In support of a life course approach, these findings suggest that socioeconomic conditions in early life may have implications for racial differences in disability between older Black and older White adults.
PMID: 19541400
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Black or African American; Disabled Persons; Female; Health Behavior; Humans; Male; Middle Aged; Models, Statistical; Prejudice; Prospective Studies; Racial Groups; Social Justice; Socioeconomic factors; Statistics as Topic; United States; White People

Cognitive health among older adults in the United States and in England. - Kenneth M. Langa; David J Llewellyn; Iain A Lang; David R Weir; Robert B Wallace; Mohammed U Kabeto; Felicia A Huppert (BMC Geriatr, 2009)
BACKGROUND: Cognitive function is a key determinant of independence and quality of life among older adults. Compared to adults in England, US adults have a greater prevalence of cardiovascular risk factors and disease that may lead to poorer cognitive function. We compared cognitive performance of older adults in the US and England, and sought to identify sociodemographic and medical factors associated with differences in cognitive function between the two countries. METHODS: Data were from the 2002 waves of the US Health and Retirement Study (HRS) (n = 8,299) and the English Longitudinal Study of Ageing (ELSA) (n = 5,276), nationally representative population-based studies designed to facilitate direct comparisons of health, wealth, and well-being. There were differences in the administration of the HRS and ELSA surveys, including use of both telephone and in-person administration of the HRS compared to only in-person administration of the ELSA, and a significantly higher response rate for the HRS (87% for the HRS vs. 67% for the ELSA). In each country, we assessed cognitive performance in non-hispanic whites aged 65 and over using the same tests of memory and orientation (0 to 24 point scale). RESULTS: US adults scored significantly better than English adults on the 24-point cognitive scale (unadjusted mean: 12.8 vs. 11.4, P < .001; age- and sex-adjusted: 13.2 vs. 11.7, P < .001). The US cognitive advantage was apparent even though US adults had a significantly higher prevalence of cardiovascular risk factors and disease. In a series of OLS regression analyses that controlled for a range of sociodemographic and medical factors, higher levels of education and wealth, and lower levels of depressive symptoms, accounted for some of the US cognitive advantage. US adults were also more likely to be taking medications for hypertension, and hypertension treatment was associated with significantly better cognitive function in the US, but not in England (P = .014 for treatment x country interaction). CONCLUSION: Despite methodological differences in the administration of the surveys in the two countries, US adults aged >/= 65 appeared to be cognitively healthier than English adults, even though they had a higher burden of cardiovascular risk factors and disease. Given the growing number of older adults worldwide, future cross-national studies aimed at identifying the medical and social factors that might prevent or delay cognitive decline in older adults would make important and valuable contributions to public health.
PMID: 19555494
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Cognition Disorders; Cohort Studies; Cross-Sectional Studies; England; Female; Health Status; Humans; Longitudinal Studies; Male; Neuropsychological tests; United States

Cognitive performance and informant reports in the diagnosis of cognitive impairment and dementia in African Americans and whites. - Guy G Potter; Brenda L Plassman; James R Burke; Mohammed U Kabeto; Kenneth M. Langa; David J Llewellyn; Mary A M Rogers; David C Steffens (Alzheimers Dement, 2009)
BACKGROUND: The diagnosis of cognitive impairment and dementia must reflect an increasingly diverse and aging United States population. This study compared direct testing and informant reports of cognition with clinical diagnoses of cognitive impairment and dementia between African Americans and whites. METHODS: Participants in the Aging, Demographics, and Memory Study completed in-person dementia evaluations, and were assigned clinical diagnoses (by a consensus panel of dementia experts) of normal; cognitive impairment, not demented (CIND); and dementia. The Consortium to Establish a Registry for Alzheimer's Disease (CERAD) total score and the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) were used to assess cognitive performance and reported cognitive decline. RESULTS: A higher CERAD total score was associated with lower odds of CIND and dementia, at comparable ratios between African Americans and whites. Higher IQCODE scores were associated with increased odds of dementia in both African Americans and whites. Higher IQCODE scores were associated with increased odds of CIND among whites, but not among African Americans. CONCLUSIONS: Cultural differences may influence informant reports of prevalent CIND and dementia. Our findings also highlight the need for more comparative research to establish the cultural validity of measures used to diagnose these conditions.
Keywords: Activities of Daily Living; Age of Onset; Aged; Aged, 80 and over; Black or African American; Caregivers; Cognition Disorders; Cohort Studies; Culture; Dementia; Disability Evaluation; Female; Geriatric Assessment; Health Surveys; Humans; Male; Neuropsychological tests; Observer Variation; Population Surveillance; Predictive Value of Tests; Prevalence; Psychiatric Status Rating Scales; Psychometrics; Registries; Sensitivity and Specificity; Surveys and Questionnaires; White People

Comparing models of frailty: the Health and Retirement Study. - Christine T Cigolle; Mary Beth Ofstedal; Zhiyi Tian; Caroline S Blaum (J Am Geriatr Soc, 2009)
OBJECTIVES: To operationalize and compare three models of frailty, each representing a distinct theoretical view of frailty: as deficiencies in function (Functional Domains model), as an index of health burden (Burden model), and as a biological syndrome (Biologic Syndrome model). DESIGN: Cross-sectional analysis. SETTING: 2004 wave of the Health and Retirement Study, a nationally representative, longitudinal health interview survey. PARTICIPANTS: Adults aged 65 and older (N=11,113) living in the community and in nursing homes in the United States. MEASUREMENTS: The outcome measure was the presence of frailty, as defined according to each frailty model. Covariates included chronic diseases and sociodemographic characteristics. RESULTS: Almost one-third (30.2%) of respondents were frail according to at least one model; 3.1% were frail according to all three models. The Functional Domains model showed the least overlap with the other models. In contrast, 76.1% of those classified as frail according to the Biologic Syndrome model and 72.1% of those according to the Burden model were also frail according to at least one other model. Older adults identified as frail according to the different models differed in sociodemographic and chronic disease characteristics. For example, the Biologic Syndrome model demonstrated substantial associations with older age (adjusted odds ratio (OR)=10.6, 95% confidence interval (CI)=6.1-18.5), female sex (OR=1.7, 95% CI=1.2-2.5), and African-American ethnicity (OR=2.1, % CI=1.0-4.4). CONCLUSION: Different models of frailty, based on different theoretical constructs, capture different groups of older adults. The different models may represent different frailty pathways or trajectories to adverse outcomes such as disability and death.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Cross-Sectional Studies; Demography; Disability Evaluation; Frail Elderly; Geriatric Assessment; Health Surveys; Humans; Interviews as Topic; Logistic Models; Models, Theoretical; United States

Compensatory conscientiousness and health in older couples. - Brent W Roberts; Jacqui Smith; Joshua J Jackson; Edmonds, Grant (Psychol Sci, 2009)
The present study tested the effect of conscientiousness and neuroticism on health and physical limitations in a representative sample of older couples (N= 2,203) drawn from the Health and Retirement Study. As in past research, conscientiousness predicted better health and physical functioning, whereas neuroticism predicted worse health and physical functioning. Unique to this study was the finding that conscientiousness demonstrated a compensatory effect, such that husbands' conscientiousness predicted wives' health outcomes above and beyond wives' own personality. The same pattern held true for wives' conscientiousness as a predictor of husbands' health outcomes. Furthermore, conscientiousness and neuroticism acted synergistically, such that people who scored high for both traits were healthier than others. Finally, we found that the combination of high conscientiousness and high neuroticism was also compensatory, such that the wives of men with this combination of personality traits reported better health than other women.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Aging; Conscience; Female; Health Status; Humans; Longevity; Longitudinal Studies; Male; Middle Aged; Neurotic Disorders; Personality Inventory; Social Conformity; Spouses

The co-occurrence of chronic diseases and geriatric syndromes: the health and retirement study. - Pearl G. Lee; Christine T Cigolle; Caroline S Blaum (J Am Geriatr Soc, 2009)
OBJECTIVES: To analyze the co-occurrence, in adults aged 65 and older, of five conditions that are highly prevalent, lead to substantial morbidity, and have evidence-based guidelines for management and well-developed measures of medical care quality. DESIGN: Secondary data analysis of the 2004 wave of the Health and Retirement Study (HRS). SETTING: Nationally representative health interview survey. PARTICIPANTS: Respondents in the 2004 wave of the HRS aged 65 and older. MEASUREMENTS: Self-reported presence of five index conditions (three chronic diseases (coronary artery disease, congestive heart failure, and diabetes mellitus) and two geriatric syndromes (urinary incontinence and injurious falls)) and demographic information (age, sex, race, living situation, net worth, and education). RESULTS: Eleven thousand one hundred thirteen adults, representing 37.1 million Americans aged 65 and older, were interviewed. Forty-five percent were aged 76 and older, 58% were female, 8% were African American, and 4% resided in a nursing home. Respondents with more conditions were older and more likely to be female, single, and residing in a nursing home (all P<.001). Fifty-six percent had at least one of the five index conditions, and 23% had two or more. Of respondents with one condition, 20% to 55% (depending on the index condition) had two or more additional conditions. CONCLUSION: Five common conditions (3 chronic diseases, 2 geriatric syndromes) often co-occur in older adults, suggesting that coordinated management of comorbid conditions, both diseases and geriatric syndromes, is important. Care guidelines and quality indicators, rather than considering one condition at a time, should be developed to address comprehensive and coordinated management of co-occurring diseases and geriatric syndromes.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Aged, 80 and over; Angina Pectoris; Comorbidity; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Geriatric Assessment; Health Surveys; Heart Failure; Humans; Male; Myocardial Infarction; Sick Role; Syndrome; United States; Urinary incontinence

Correlates of improvement in walking ability in older persons in the United States. - Joseph Feinglass; Song, Jing; Larry M Manheim; Semanik, Pamela; Rowland W Chang; Dorothy D Dunlop (Am J Public Health, 2009)
OBJECTIVES: We analyzed factors associated with improvement in walking ability among respondents to the nationally representative Health and Retirement Study. METHODS: We analyzed data from 6574 respondents aged 53 years or older who reported difficulty walking several blocks, 1 block, or across the room in 2000 or 2002. We examined associations between improvement (versus no change, deterioration, or death) and baseline health status, chronic conditions, baseline walking difficulty, demographic characteristics, socioeconomic status, and behavioral risk factors. RESULTS: Among the 25% of the study population with baseline walking limitations, 29% experienced improved walking ability, 40% experienced no change in walking ability, and 31% experienced deteriorated walking ability or died. In a multivariate analysis, we found positive associations between walking improvement and more recent onset and more severe walking difficulty, being overweight, and engaging in vigorous physical activity. A history of diabetes, having any difficulty with activities of daily living, and being a current smoker were all negatively associated with improvement in walking ability. After we controlled for baseline health, improvement in walking ability was equally likely among racial and ethnic minorities and those with lower socioeconomic status. CONCLUSIONS: Interventions to reduce smoking and to increase physical activity may help improve walking ability in older Americans.
Keywords: Age Factors; Aged; Aged, 80 and over; Confidence Intervals; Female; Health Promotion; Humans; Male; Middle Aged; Motor Activity; Multivariate Analysis; Odds Ratio; Overweight; Smoking Prevention; Social Marketing; Socioeconomic factors; United States; Walking

The effect of depression and cognitive impairment on enrollment in Medicare Part D. - Zivin, Kara; Mohammed U Kabeto; Helen C Kales; Kenneth M. Langa (J Am Geriatr Soc, 2009)
OBJECTIVES: To examine concerns that vulnerable populations, such as depressed or cognitively impaired beneficiaries would have challenges accessing Part D coverage. DESIGN: Logistic regression analysis was used to assess whether elderly Medicare beneficiaries with depression or cognitive impairment differentially planned to and actually signed up for Part D. SETTING: 2004 and 2006 data from the Health and Retirement Study (HRS) were used, including a subsample that completed the Prescription Drug Study (PDS) in 2005. PARTICIPANTS: Nine thousand five hundred ninety-three HRS respondents and 3,567 PDS respondents. MEASUREMENTS: The outcome variables of interest were planned and actual enrollment in Part D. The independent variables were depression and cognitive impairment status. The analyses were adjusted using clinical and demographic predictors including age, sex, race or ethnicity, educational attainment, net worth, marital status, health status, number of health conditions being treated with prescription medications, and presence of a caregiver. RESULTS: Although having depression or cognitive impairment was associated with a higher likelihood of planning to and actually signing up for Part D in unadjusted analyses, in adjusted analyses, having depression or cognitive impairment was not significantly associated with whether Medicare beneficiaries planned to enroll in or actually enrolled in Part D. CONCLUSION: Vulnerable Medicare beneficiaries with depression or cognitive impairment were able to access Part D benefits to the same extent as nonvulnerable beneficiaries. More research is needed to determine how well Part D meets the needs of these populations.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cognition Disorders; depression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Medicare Part D; Middle Aged; Patient Participation; Risk Factors; United States

Is the effect of reported physical activity on disability mediated by cognitive performance in white and african american older adults? - Mihaela A. Popa; Sandra L Reynolds; Brent J. Small (J Gerontol B Psychol Sci Soc Sci, 2009)
This study examined if reported physical activity has beneficial outcomes on disability through cognitive performance-mediated effects and if these mediation effects are comparable for White and African American elders. Longitudinal data from the Assets and Health Dynamics among the Oldest Old study (N = 4,472) are used to test mediation in multilevel models. During the 7-year follow-up, cognitive performance mediated the effects of reported physical activity on disability in the entire sample and in Whites but not in African Americans. Our results indicate that reported physical activity may delay the disability development through improvement in cognitive performance. Unmeasured education and comorbidity influences may have obscured the mediation effects in African Americans. Reported physical activity plays a key role in the independence of older adults and should be particularly promoted in African Americans and during the entire life course.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Black or African American; Cognition Disorders; Cohort Studies; Disability Evaluation; Exercise; Female; Follow-Up Studies; Health Status Disparities; Humans; Male; Motor Activity; Neuropsychological tests; Socioeconomic factors; United States; White People

The effects of developing a dual sensory loss on depression in older adults: a longitudinal study. - Michele Capella McDonnall (J Aging Health, 2009)
OBJECTIVE: To determine the effect of developing a dual sensory loss (DSL) on depression over time and evaluate the impact of preexisting single sensory loss on this effect. METHOD: Multilevel modeling was used to analyze data (N = 2,689) from the Health and Retirement Study. RESULTS: A significant increase in depression at the first report of DSL occurred, and depression increased at a significantly faster rate following DSL, in a curvilinear pattern. In addition, persons who eventually developed DSL began the study with a depression score significantly higher than persons who did not experience sensory loss. A preexisting single sensory loss did not alter the effect of DSL on depression. DISCUSSION: Two sources of disparity in depression between persons with and without DSL were identified: preexisting differences and differences that occurred due to the DSL. The relationship exhibited between depression and developing a DSL indicated an adjustment process.
Keywords: Adaptation, Psychological; Adult; Aged; Aged, 80 and over; Black or African American; depression; Depressive Disorder; Female; Health Surveys; Hearing loss; Hispanic or Latino; Humans; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Multivariate Analysis; Rehabilitation; Retirement; Risk Factors; Sensation Disorders; United States; Vision Disorders; White People

Estimating the quantity and economic value of family caregiving for community-dwelling older persons in the last year of life. - Rhee, YongJoo; Howard B Degenholtz; Anthony T. Lo Sasso; Linda L Emanuel (J Am Geriatr Soc, 2009)
OBJECTIVES: To estimate the quantity and economic value of informal care provided to older persons during their final year of life in the community. DESIGN: Retrospective analysis of publicly available nationally representative survey data. SETTING: This retrospective study used data from the Health and Retirement Study, a nationally representative, longitudinal study of community-dwelling older people. PARTICIPANTS: Older people who died between 2000 and 2002. MEASUREMENTS: Data were extracted from the 2002 "exit survey" and linked with characteristics of caregivers from the helper file. Ordinary least squares regression was used to estimate hours of informal caregiving for community-dwelling older people (N=990). Adjusted hours were multiplied by the 2002 national average home aide wage (9.16 USD per hour). Sensitivity tests were performed using the 10th percentile wage rate (6.56 USD) and 90th percentile wage rate (12.34 USD). RESULTS: Older people who died in the community received on average 65.8 hours per week of informal care in the last year of life. The estimated economic value ranges from 22,514 USD to 42,351 USD, which is equivalent to the annual direct replacement cost with a home aide in 2002. CONCLUSION: Family members provide substantial assistance during the last year of life for older people who die in the community. If the informal care provided in the last year of life is replaced with a home aide, the total economic value for the United States would be approximately 1.4 billion USD (in 2002).
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Caregivers; Costs and Cost Analysis; Disability Evaluation; Female; Health Surveys; Home Health Aides; Home Nursing; Humans; Independent Living; Male; Middle Aged; Retrospective Studies; Terminal Care; United States

Factors associated with long-stay nursing home admissions among the U.S. elderly population: comparison of logistic regression and the Cox proportional hazards model with policy implications for social work. - Cai, Qian; J. Warren Salmon; Mark E. Rodgers (Soc Work Health Care, 2009)
Two statistical methods were compared to identify key factors associated with long-stay nursing home (LSNH) admission among the U.S. elderly population. Social Work's interest in services to the elderly makes this research critical to the profession. Effectively transitioning the "baby boomer" population into appropriate long-term care will be a great societal challenge. It remains a challenge paramount to the practice of social work. Secondary data analyses using four waves (1995, 1998, 2000, and 2002) of the Health Retirement Study (HRS) coupled with the Assets and Health Dynamics among the Oldest Old (AHEAD) surveys were conducted. Multivariable logistic regression and Cox proportional hazards model were performed and compared. Older age, lower self-perceived health, worse instrumental activities of daily living (IADL), psychiatric problems, and living alone were found significantly associated with increased risk of LSNH admission. In contrast, being female, African American, or Hispanic; owning a home; and having lower level of cognitive impairment reduced the admission risk. Home ownership showed a significant effect in logistic regression, but a marginal effect in the Cox model. The Cox model generally provided more precise parameter estimates than logistic regression. Logistic regression, used frequently in analyses, can provide a good approximation to the Cox model in identifying factors of LSNH admission. However, the Cox model gives more information on how soon the LSNH admission may happen. Our analyses, based on two models, dually identified the factors associated with LSNH admission; therefore, results discussed confidently provide implications for both public and private long-term care policies, as well as improving the assessment capabilities of social work practitioners for development of screening programs among at-risk elderly. Given the predicted surge in this population, significant factors found from this study can be utilized in a strengths-based empowerment approach by social workers to aid in avoiding LSNH utilization.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Female; Geriatric Assessment; Health Status; Homes for the Aged; Humans; Logistic Models; Male; Mental Health; Nursing homes; Proportional Hazards Models; Risk Factors; Sex Factors; Social work; Socioeconomic factors; United States

Fall risk in older adults: roles of self-rated vision, home modifications, and limb function. - Bernard A Steinman; Pynoos, Jon; Anna Q D Nguyen (J Aging Health, 2009)
Objective. To assess direct effects of self-rated vision, home modifications, and limb functioning, and moderating effects of self-rated vision on change in functioning of upper and lower limbs on fall risk in older adults. Method. Logistic regression was used to analyze 2004 and 2006 waves of the Health and Retirement Study. Results. Effects of self-rated vision and home modifications in predicting falls decreased after controlling functioning in upper and lower extremities. Declines/gains in functioning across short periods of time superseded self-rated vision in predicting falls. No evidence was found for a moderating effect of vision status on limb functioning. Discussion. Poor self-rated vision may not be a good indicator of fall risk in older adults. Thus, for older adults with visual impairments, preserving residual limb functioning through exercise and activity has the important potential to reduce fall risk in addition to improving muscle and bone strength as well as improving balance and gait.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Aged, 80 and over; Black or African American; Disabled Persons; Educational Status; Female; Health Status; Health Surveys; Humans; Logistic Models; Longitudinal Studies; Male; Musculoskeletal Physiological Phenomena; Risk; Risk Factors; Self-Assessment; Self-Help Devices; Surveys and Questionnaires; Vision, Low; Visual Acuity; White People

Financial status, employment, and insurance among older cancer survivors. - Norredam, Marie; Meara, Ellen; Landrum, Mary Beth; Haiden A. Huskamp; Nancy L. Keating (J Gen Intern Med, 2009)
BACKGROUND: Few data are available about the socioeconomic impact of cancer for long-term cancer survivors. OBJECTIVES: To investigate socioeconomic outcomes among older cancer survivors compared to non-cancer patients. DATA SOURCE: 2002 Health and Retirement Study. STUDY DESIGN: We studied 964 cancer survivors of > 4 years and 14,333 control patients who had never had cancer from a population-based sample of Americans ages >or= 55 years responding to the 2002 Health and Retirement Study. MEASURES: We compared household income, housing assets, net worth, insurance, employment, and future work expectations. ANALYSES: Propensity score methods were used to control for baseline differences between cancer survivors and controls. RESULTS: Female cancer survivors did not differ from non-cancer patients in terms of income, housing assets, net worth, or likelihood of current employment (all P > 0.20); but more were self-employed (25.0% vs. 17.7%; P = 0.03), and fewer were confident that if they lost their job they would find an equally good job in the next few months (38.4% vs. 45.9%; P = 0.03). Among men, cancer survivors and noncancer patients had similar income and housing assets (both P >or= 0.10) but differed somewhat in net worth (P = 0.04). Male cancer survivors were less likely than other men to be currently employed (25.2% vs. 29.7%) and more likely to be retired (66.9% vs. 62.2%), although the P value did not reach statistical significance (P = 0.06). Men were also less optimistic about finding an equally good job in the next few months if they lost their current job (33.5% vs. 46.9%), although this result was not significant (P = 0.11). CONCLUSIONS: Despite generally similar socioeconomic outcomes for cancer survivors and noncancer patients ages >or=55 years, a better understanding of employment experience and pessimism regarding work prospects may help to shape policies to benefit cancer survivors.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Data collection; Employment; Female; Financing, Personal; Humans; Income; Insurance Coverage; Insurance, Health; Longitudinal Studies; Male; Middle Aged; Neoplasms; Socioeconomic factors; Survivors

Individual well-being in middle and older adulthood: do spousal beliefs matter? - Tim D Windsor; Lindsay H Ryan; Jacqui Smith (J Gerontol B Psychol Sci Soc Sci, 2009)
Associations between health, control beliefs, and well-being in later life are frequently conceptualized in terms of the characteristics of individuals. However, spousal interdependencies in psychosocial characteristics are also likely to be relevant for well-being. The present study investigated associations of self-rated health, control, and relationship closeness with life satisfaction and positive and negative affect in a sample of 2,235 spousal dyads. A significant proportion of variance in health, control, closeness, and well-being occurred between dyads. Individuals' self-rated health, control, and relationship closeness were associated with higher well-being. Spouses' self-rated health and control beliefs were consistently and positively associated with individuals' well-being; however, effect sizes were small. Some evidence for individual's control beliefs buffering the association between health and well-being emerged, whereas spouses' perceived control was not a significant moderator of the health-well-being association. Results highlight the importance of couple interdependencies for contextualizing health and well-being in older adulthood.
Keywords: Adult; Affect; Aged; Aged, 80 and over; Aging; Attitude to Health; Culture; Female; Humans; Individuality; Internal-External Control; Male; Marriage; Middle Aged; Quality of Life; Spouses

The influence of long-term care insurance on the likelihood of nursing home admission. - Tanya R Gure; Mohammed U Kabeto; Kenneth M. Langa (J Am Geriatr Soc, 2009)
OBJECTIVES: To determine the effect of long-term care (LTC) insurance on nursing home use. DESIGN: Longitudinal analysis, 1998 to 2006 waves of the Health Retirement Study. SETTING: Community-dwelling nationally representative sample. PARTICIPANTS: Nineteen thousand one hundred seventy adults aged 50 and older, 1998 wave. METHODS: Two groups of respondents were created at baseline: those with and without an LTC insurance policy. Respondents admitted to the nursing home from 1998 to 2006 were identified. Propensity scores were used to control for known predictors of LTC insurance possession. A Cox proportional hazards model was used to compare the probability of nursing home admission over 8 years of follow-up for respondents possessing LTC insurance and those without a policy. RESULTS: Of the 19,170 respondents aged 50 and older in 1998, 1,767 (9.2%) possessed LTC insurance. A total of 1,778 (8.5%) were admitted to a nursing home during the 8-year period: 149 (8.7%) of those with LTC insurance and 1,629 (8.4%) of those without LTC insurance. The hazard ratio, adjusted for propensity score, for those with LTC insurance entering a nursing home compared with those without was 1.07 (95% confidence interval=0.83-1.38). Likelihood of nursing home admission was relatively low because the low-risk population included in the study, limiting the power to detect small differences in risk of nursing home utilization between groups. CONCLUSION: There was no difference in nursing home utilization between low-risk older adults who did and did not possess an LTC insurance policy.
Keywords: Aged; Aged, 80 and over; Female; Humans; Insurance, Long-Term Care; Longitudinal Studies; Male; Middle Aged; Nursing homes

Level and change in cognitive test scores predict risk of first stroke. - Triveni DeFries; Mauricio Avendano; M. Maria Glymour (J Am Geriatr Soc, 2009)
OBJECTIVES: To determine whether cognitive test scores and cognitive decline predict incidence of first diagnosed stroke. DESIGN: Stroke-free Health and Retirement Study participants were followed on average 7.6 years for self- or proxy-reported first stroke (1,483 events). Predictors included baseline performance on a modified Telephone Interview for Cognitive Status (Mental Status) and Word Recall test and decline between baseline and second assessment in either measure. Hazard ratios (HRs) were estimated using Cox proportional hazards models for the whole sample and stratified according to five major cardiovascular risk factors. SETTING: National cohort study of noninstitutionalized adults with a mean baseline age of 64+/-9.9. PARTICIPANTS: Health and Retirement Study participants (n=19,699) aged 50 and older. RESULTS: Word Recall (HR for 1 standard deviation difference=0.92, 95% confidence interval (CI)=0.86-0.97)) and Mental Status (HR=0.89, 95% CI=0.84-0.95) predicted incident stroke. Mental Status predicted stroke risk in those with (HR=0.93, 95%=0.87-0.99) and without (HR=0.81, 95% CI=0.72-.91) one or more vascular risk factors. Word Recall declines predicted a 16% elevation in subsequent stroke risk (95% CI=1.01-1.34). Declines in Mental Status predicted a 37% elevation in stroke risk (95% CI=1.11-1.70). CONCLUSION: Cognitive test scores predict future stroke risk, independent of other major vascular risk factors.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Cohort Studies; Dementia, Vascular; Female; Follow-Up Studies; Humans; Interviews as Topic; Kaplan-Meier Estimate; Male; Mental Status Schedule; Middle Aged; Predictive Value of Tests; Psychometrics; Risk; Stroke; United States

Measuring socioeconomic differences in use of health care services by wealth versus by income. - Allin, Sara; Masseria, Cristina; Elias Mossialos (Am J Public Health, 2009)
OBJECTIVES: We compared the extent of socioeconomic differences in use of health care services based on wealth (i.e., accumulated assets) as the socioeconomic ranking variable with the extent of differences based on income to explore the sensitivity of the estimates of equity to the choice of the socioeconomic indicator. METHODS: We used data from the Health and Retirement Study in the United States and the Survey of Health, Ageing, and Retirement in Europe to estimate levels of income- and wealth-related disparity in use of physician and dental services among adults 50 or older in 12 countries. RESULTS: We found socioeconomic differences in use of physician services after standardizing for need in about half of the countries studied. No consistent pattern in levels of disparity measured by wealth versus those measured by income was found. However, the rich were significantly more likely to use dental services in all countries. Wealth-related differences in dental service use were consistently higher than were income-related differences. CONCLUSIONS: We found some support for wealth as a more sensitive indicator of socioeconomic status among older adults than was income. Wealth may thus allow more accurate measurements of socioeconomic differences in use of health care services for this population.
Keywords: Aged; Aged, 80 and over; Aging; Data collection; Europe; Female; Health Services; Health Services Accessibility; Health Status Disparities; Humans; Income; Male; Middle Aged; Odds Ratio; Pensions; Retirement; Socioeconomic factors; Statistics as Topic; United Kingdom

Memory and depressive symptoms are dynamically linked among married couples: longitudinal evidence from the AHEAD study. - Denis Gerstorf; Christiane A Hoppmann; Kelly M Kadlec; John J McArdle (Dev Psychol, 2009)
This study examined dyadic interrelations between episodic memory and depressive symptom trajectories of change in old and advanced old age. The authors applied dynamic models to 10-year incomplete longitudinal data of initially 1,599 married couples from the study of Asset and Health Dynamics Among the Oldest Old (M(age) = 75 years at Time 1). The authors found domain-specific lead-lag associations (time lags of 2 years) among wives and husbands as well as between spouses. For memory, better performance among husbands protected against subsequent memory decline among wives, with no evidence of a directed effect in the other direction. For depressive symptoms, wives' scores predicted subsequent depression increase and memory decline among husbands. Possible individual covariates (age, education, functional limitations) and spousal covariates (length of marriage, number of children, and whether the couple remained intact over the study period) did not account for differential lead-lag associations. The findings of antecedent-consequent relations between wives and husbands are consistent with life-span notions that individual development both influences and is influenced by contextual factors such as close social relationships.
PMID: 19899917
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Aging; Cognition; depression; Female; Health Status; Humans; Interpersonal Relations; Longitudinal Studies; Male; Marriage; Mental Recall; Models, Psychological; Quality of Life; Spouses

Neighborhood safety, socioeconomic status, and physical activity in older adults. - Reginald D. Tucker-Seeley; Subramanian, S V; Li, Yi; Sorensen, Glorian (Am J Prev Med, 2009)
BACKGROUND: Neighborhood environment can have a substantial influence on the level of physical activity among older adults. Yet, the moderating influence of various measures of SES on the association between perceived neighborhood safety and leisure-time physical activity (LTPA) among older adults remains unknown. PURPOSE: The study was designed to investigate the association between perceived neighborhood safety and LTPA in a nationally representative sample of older adults, and to evaluate SES characteristics as potential effect modifiers in the association between perceived neighborhood safety and LTPA. METHODS: Cross-sectional data from the 2004 Health and Retirement Study of older adults aged >or=50 years were used to examine the association between perceived neighborhood safety and LTPA. Differences in LTPA were evaluated across three measures of SES: education, household income, and household wealth. SES was also evaluated as a potential effect modifier in the association between perceived neighborhood safety and LTPA. The analysis was conducted in 2008. RESULTS: An SES gradient in LTPA was noted across measures of SES used in this study. After controlling for SES and demographic characteristics and functional limitations, older adults who perceived their neighborhood as safe had an 8% higher mean rate of LTPA compared to older adults who perceived their neighborhood as unsafe. The association was no longer significant when self-rated health was added. Additionally, SES was not a significant effect modifier in the association between perceived neighborhood safety and LTPA. CONCLUSIONS: SES, demographic characteristics, and functional limitations substantially attenuated the positive association between perceived neighborhood safety and LTPA; however, with the inclusion of self-rated health, the association was no longer present. This finding suggests that self-rated health may mediate this association. The lack of significance in the interaction between perceived neighborhood safety and SES suggests that prevention efforts to increase physical activity among older adults should consider perceptions of neighborhood safety as a potential barrier regardless of SES.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Florida; Health Status; Humans; Leisure activities; Male; Middle Aged; Motor Activity; Recreation; Residence Characteristics; Safety; Sex Distribution; Social Support; Socioeconomic factors; Surveys and Questionnaires

Pain, functional limitations, and aging. - Kenneth E Covinsky; Lindquist, Karla; Dorothy D Dunlop; Yelin, Edward (J Am Geriatr Soc, 2009)
OBJECTIVES: To examine the relationship between functional limitations and pain across a spectrum of age, ranging from mid life to advanced old age. DESIGN: Cross-sectional study. SETTING: The 2004 Health and Retirement Study (HRS), a nationally representative study of community-living persons aged 50 and older. PARTICIPANTS: Eighteen thousand five hundred thirty-one participants in the 2004 HRS. MEASUREMENTS: Participants who reported that they were often troubled by pain that was moderate or severe most of the time were defined as having significant pain. For each of four functional domains, subjects were classified according to their degree of functional limitation: mobility (able to jog 1 mile, able to walk several blocks, able to walk one block, unable to walk one block), stair climbing (able to climb several flights, able to climb one flight, not able to climb a flight), upper extremity tasks (able to do 3, 2, 1, or 0), and activity of daily living (ADL) function (able to do without difficulty, had difficulty but able to do without help, need help). RESULTS: Twenty-four percent of participants had significant pain. Across all four domains, participants with pain had much higher rates of functional limitations than subjects without pain. Participants with pain were similar in terms of their degree of functional limitation to participants 2 to 3 decades older. For example, for mobility, of subjects aged 50 to 59 without pain, 37% were able to jog 1 mile, 91% were able to walk several blocks, and 96% were able to walk one block without difficulty. In contrast, of subjects aged 50 to 59 with pain, 9% were able to jog 1 mile, 50% were able to walk several blocks, and 69% were able to walk one block without difficulty. Subjects aged 50 to 59 with pain were similar in terms of mobility limitations to subjects aged 80 to 89 without pain, of whom 4% were able to jog 1 mile, 55% were able to walk several blocks, and 72% were able to walk one block without difficulty. After adjustment for demographic characteristics, socioeconomic status, comorbid conditions, depression, obesity, and health habits, across all four measures, participants with significant pain were at much higher risk for having functional limitations (adjusted odds ratio (AOR)=2.85, 95% confidence interval (CI)=2.20-3.69, for mobility; AOR=2.84, 95% CI=2.48-3.26, for stair climbing; AOR=3.96, 95% CI=3.43-4.58, for upper extremity tasks; and AOR=4.33; 95% CI=3.71-5.06, for ADL function). CONCLUSION: Subjects with pain develop the functional limitations classically associated with aging at much earlier ages.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Comorbidity; Cross-Sectional Studies; Disability Evaluation; Female; Geriatric Assessment; Health Behavior; Health Surveys; Humans; Life Style; Male; Middle Aged; Mobility Limitation; pain; Pain Measurement; Quality of Life; Risk Factors

Parental education and late-life dementia in the United States. - Mary A M Rogers; Brenda L Plassman; Mohammed U Kabeto; Gwenith G Fisher; John J McArdle; David J Llewellyn; Guy G Potter; Kenneth M. Langa (J Geriatr Psychiatry Neurol, 2009)
We investigated the relation between parental education and dementia in the United States. Participants in the Aging, Demographics, and Memory Study were included, with information regarding parental education obtained from the Health and Retirement Study. The odds of dementia in elderly Americans whose mothers had less then 8 years of schooling were twice (95% CI, 1.1-3.8) that of individuals with higher maternal education, when adjusted for paternal education. Of elderly Americans with less educated mothers, 45.4% (95% CI, 37.4-53.4%) were diagnosed with dementia or ;;cognitive impairment, no dementia'' compared to 31.2% (95% CI, 25.0-37.4%) of elderly Americans whose mothers had at least an 8th grade education. The population attributable risk of dementia due to low maternal education was 18.8% (95% CI, 9.4-28.2%). The education of girls in a population may be protective of dementia in the next generation.
Keywords: Age Distribution; Aged; Aged, 80 and over; Apolipoproteins E; Biomarkers; Cognition Disorders; Dementia; Educational Status; Fathers; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Mothers; Odds Ratio; Parents; Prevalence; Prospective Studies; Racial Groups; Risk Factors; Sex Distribution; United States

Physician outpatient contacts and hospitalizations among cognitively impaired elderly. - Caspi, Eilon; Nina M Silverstein; Frank Porell; Kwan, Ngai (Alzheimers Dement, 2009)
BACKGROUND: This study examined how physician contacts and hospitalizations vary in relation to cognitive function level among community-residing older adults. METHODS: Analysis of the 1998 wave of the Health and Retirement Survey (HRS) was conducted to create three levels of cognitive function among 6,991 older adults by using direct measures for self-respondents and proxy evaluations. Ordinary least square regression analyses were used to estimate the probability of physician outpatient contacts, number of hospitalizations, and nights hospitalized during the last 2 years. RESULTS: Lower cognitive function level was found to be associated with decreasing levels of physician contacts and increasing levels of hospitalizations as well as nights hospitalized. In addition, lower cognitive function levels were consistently related to a variety of comorbidities. Moreover, many older adults with low cognitive function levels reported or were reported by their proxies as not having a diagnosis of a memory-related disease (MRD). Finally, having a diagnosis of an MRD was found to be associated with more physician contacts but fewer hospital nights compared with those who had never received such a diagnosis. CONCLUSIONS: The findings suggest the need for increased outreach targeted at identification of community-dwelling older adults with decline in cognitive function who are in need of care but are underdiagnosed, underutilize physician care, and are overhospitalized.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Ambulatory Care; Cognition Disorders; Community-Institutional Relations; Comorbidity; Female; Hospitalization; Housing for the Elderly; Humans; Male; Memory Disorders; Physicians; Prevalence; Severity of Illness Index

Predictors of loneliness in U.S. adults over age sixty-five. - Laurie A. Theeke (Arch Psychiatr Nurs, 2009)
The purpose of this study was to examine sociodemographic and health-related risks for loneliness among older adults using Health and Retirement Study Data. Overall prevalence of loneliness was 19.3%. Marital status, self-report of health, number of chronic illnesses, gross motor impairment, fine motor impairment, and living alone were predictors of loneliness. Age, female gender, use of home care, and frequency of healthcare visits were not predictive. Loneliness is a prevalent problem for older adults in the United States with its own health-related risks. Future research of interventions targeting identified risks would enhance the evidence base for nursing and the problem of loneliness.
Keywords: Aged; Aged, 80 and over; Female; Health Status; Humans; Likelihood Functions; Logistic Models; Loneliness; Male; Prevalence; Risk Factors; Single Person; Socioeconomic factors; United States

Prevalence of depression among older Americans: the Aging, Demographics and Memory Study. - David C Steffens; Gwenith G Fisher; Kenneth M. Langa; Guy G Potter; Brenda L Plassman (Int Psychogeriatr, 2009)
BACKGROUND: Previous studies have attempted to provide estimates of depression prevalence in older adults. The Aging, Demographics and Memory Study (ADAMS) is a population-representative study that included a depression assessment, providing an opportunity to estimate the prevalence of depression in late life in the U.S.A. METHODS: The ADAMS sample was drawn from the larger Health and Retirement Study. A total of 851 of 856 ADAMS participants aged 71 and older had available depression data. Depression was measured using the Composite International Diagnostic Interview - Short Form (CIDI-SF) and the informant depression section of the Neuropsychiatric Inventory (NPI). We estimated the national prevalence of depression, stratified by age, race, sex, and cognitive status. Logistic regression analyses were performed to examine the association of depression and previously reported risk factors for the condition. RESULTS: When combining symptoms of major or minor depression with reported treatment for depression, we found an overall depression prevalence of 11.19%. Prevalence was similar for men (10.19%) and women (11.44%). Whites and Hispanics had nearly three times the prevalence of depression found in African-Americans. Dementia diagnosis and pain severity were associated with increased depression prevalence, while black race was associated with lower rates of depression. CONCLUSIONS: The finding of similar prevalence estimates for depression in men and women was not consistent with prior research that has shown a female predominance. Given the population-representativeness of our sample, similar depression rates between the sexes in ADAMS may result from racial, ethnic and socioeconomic diversity.
PMID: 19519984
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Black People; Cohort Studies; Comorbidity; Cross-Sectional Studies; Depressive Disorder; Female; Health Status; Hispanic or Latino; Humans; Male; Neuropsychological tests; Personality Assessment; Sex Factors; Socioeconomic factors; United States; White People

Proximity to death and participation in the long-term care market. - Weaver, France; Sally C. Stearns; Edward C Norton; Spector, William (Health Econ, 2009)
The extent to which increasing longevity increases per capita demand for long-term care depends on the degree to which utilization is concentrated at the end of life. We estimate the marginal effect of proximity to death, measured by being within 2 years of death, on the probabilities of nursing home and formal home care use, and we determine whether this effect differs by availability of informal care--i.e. marital status and co-residence with an adult child. The analysis uses a sample of elderly aged 70+ from the 1993-2002 Health and Retirement Study. Simultaneous probit models address the joint decisions to use long-term care and co-reside with an adult child. Overall, proximity to death significantly increases the probability of nursing home use by 50.0% and of formal home care use by 12.4%. Availability of informal support significantly reduces the effect of proximity to death. Among married elderly, proximity to death has no effect on institutionalization. In conclusion, proximity to death is one of the main drivers of long-term care use, but changes in sources of informal support, such as an increase in the proportion of married elderly, may lessen its importance in shaping the demand for long-term care.
PMID: 18770873
Keywords: Aged; Aged, 80 and over; Caregivers; Female; Health Services Needs and Demand; Home Care Services; Humans; Interviews as Topic; Longevity; Male; Models, Statistical; Nursing homes; Terminal Care; United States

Recent hospitalization and the risk of hip fracture among older Americans. - Frederic D Wolinsky; Suzanne E Bentler; Li Liu; Maksym Obrizan; Elizabeth A Cook; Kara B Wright; John F Geweke; Elizabeth A Chrischilles; Claire E Pavlik; Robert L. Ohsfeldt; Michael P Jones; Kelly K Richardson; et al. (J Gerontol A Biol Sci Med Sci, 2009)
BACKGROUND: We identified hip fracture risks in a prospective national study. METHODS: Baseline (1993-1994) interview data were linked to Medicare claims for 1993-2005. Participants were 5,511 self-respondents aged 70 years and older and not in managed Medicare. ICD9-CM 820.xx (International Classification of Diseases, 9th Edition, Clinical Modification) codes identified hip fracture. Participants were censored at death or enrollment into managed Medicare. Static risk factors included sociodemographic, socioeconomic, place of residence, health behavior, disease history, and functional and cognitive status measures. A time-dependent marker reflecting postbaseline hospitalizations was included. RESULTS: A total of 495 (8.9%) participants suffered a postbaseline hip fracture. In the static proportional hazards model, the greatest risks involved age (adjusted hazard ratios [AHRs] of 2.01, 2.82, and 4.91 for 75-79, 80-84, and > or =85 year age groups vs those aged 70-74 years; p values <.001), sex (AHR = 0.45 for men vs women; p < .001), race (AHRs of 0.37 and 0.46 for African Americans and Hispanics vs whites; p values <.001 and <.01), body mass (AHRs of 0.40, 0.77, and 1.73 for obese, overweight, and underweight vs normal weight; p values <.001, <.05, and <.01), smoking status (AHRs = 1.49 and 1.52 for current and former smokers vs nonsmokers; p values <.05 and <.001), and diabetes (AHR = 1.99; p < .001). The time-dependent recent hospitalization marker did not alter the static model effect estimates, but it did substantially increase the risk of hip fracture (AHR = 2.51; p < .001). CONCLUSIONS: Enhanced discharge planning and home care for non-hip fracture hospitalizations could reduce subsequent hip fracture rates.
Keywords: Accidental Falls; Age Distribution; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Follow-Up Studies; Geriatric Assessment; Hip Fractures; Hospitalization; Humans; Logistic Models; Male; Multivariate Analysis; Probability; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Distribution; Survival Analysis; United States

Risk factors associated with injury attributable to falling among elderly population with history of stroke. - Afshin A Divani; Vazquez, Gabriela; Anna M Barrett; Asadollahi, Marjan; Andreas R Luft (Stroke, 2009)
BACKGROUND AND PURPOSE: Stroke survivors are at high risk for falling. Identifying physical, clinical, and social factors that predispose stroke patients to falls may reduce further disability and life-threatening complications, and improve overall quality of life. METHODS: We used 5 biennial waves (1998-2006) from the Health and Retirement Study to assess risk factors associated with falling accidents and fall-related injuries among stroke survivors. We abstracted demographic data, living status, self-evaluated general health, and comorbid conditions. We analyzed the rate ratio (RR) of falling and the OR of injury within 2 follow-up years using a multivariate random effects model. RESULTS: We identified 1174 stroke survivors (mean age+/-SD, 74.4+/-7.2 years; 53% female). The 2-year risks of falling, subsequent injury, and broken hip attributable to fall were 46%, 15%, and 2.1% among the subjects, respectively. Factors associated with an increased frequency of falling were living with spouse as compared to living alone (RR, 1.4), poor general health (RR, 1.1), time from first stroke (RR, 1.2), psychiatric problems (RR, 1.7), urinary incontinence (RR, 1.4), pain (RR, 1.4), motor impairment (RR, 1.2), and past frequency of > or = 3 falls (RR, 1.3). Risk factors associated with fall-related injury were female gender (OR, 1.5), poor general health (OR, 1.2), past injury from fall (OR, 3.2), past frequency of > or = 3 falls (OR, 3.1), psychiatric problems (OR, 1.4), urinary incontinence (OR, 1.4), impaired hearing (OR, 1.6), pain (OR, 1.8), motor impairment (OR, 1.3), and presence of multiple strokes (OR, 3.2). CONCLUSIONS: This study demonstrates the high prevalence of falls and fall-related injuries in stroke survivors, and identifies factors that increase the risk. Modifying these factors may prevent falls, which could lead to improved quality of life and less caregiver burden and cost in this population.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Aging; Causality; Cohort Studies; Comorbidity; disease progression; Female; Health Status; Humans; Male; Marital Status; Mental Disorders; Movement Disorders; Prevalence; Risk Factors; Risk Reduction Behavior; Sex Distribution; Stroke; Urinary incontinence; Wounds and Injuries

Risk perception and preference for prevention of Alzheimer's disease. - Chung, Sukyung; Kala M. Mehta; Shumway, Martha; Alvidrez, Jennifer; Eliseo J Perez-Stable (Value Health, 2009)
OBJECTIVES: To understand how older adults perceive their risk of Alzheimer's Disease (AD) and how this may shape their medical care decisions, we examined whether presence of established risk factors of AD is associated with individuals' perceived risk of AD, and with preference for preventing AD. PARTICIPANTS: Data came from the US Health and Retirement Study participants who were asked questions on AD risk perception (N = 778). MEASUREMENTS: Perceived risk of AD was measured by respondents' estimate of their percent chance (0-100) developing AD in the next 10 years. Preference for AD prevention was measured with questions eliciting willingness to pay for a drug to prevent AD. ANALYSIS: Multivariate linear regressions were used to estimate correlates of perceived risk and preference for prevention. RESULTS: Better cognitive functioning and physical activity are associated with decreased perceived risk. Neither age nor cardiovascular disease is associated with perceived risk. African Americans have lower perceived risk than non-Latino whites; the difference is wider among people age 65 and above. Only 4% to 7% of the variation in perceived risk was explained by the model. Preference for prevention is stronger with increased perceived risk, but not with the presence of risk factors. Persons with better cognitive functioning, physical functioning, or wealth status have a stronger preference for prevention. CONCLUSION: Some known risk factors appear to inform, but only modestly, individuals' perceived risk of AD. Furthermore, decisions about AD prevention may not be determined by objective needs alone, suggesting a potential discrepancy between need and demand for AD preventive care.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer disease; Cognition; Female; Health education; Health Knowledge, Attitudes, Practice; Health Surveys; Humans; Linear Models; Male; Multivariate Analysis; Psychometrics; Risk Assessment; Risk Factors; Social Perception; Statistics as Topic; United States

Smoking and weight change after new health diagnoses in older adults. - Patricia S Keenan (Arch Intern Med, 2009)
BACKGROUND: Smoking and patterns of diet and activity are the 2 leading underlying causes of death in the United States, yet the factors that prompt individuals to adopt healthier habits are not well understood. METHODS: This study was undertaken to determine whether individuals who have experienced recent adverse health events are more likely to quit smoking or to lose weight than those without recent events using Health and Retirement Study panel survey data for 20 221 overweight or obese individuals younger than 75 years and 7764 smokers from 1992 to 2000. RESULTS: In multivariate analyses, adults with recent diagnoses of stroke, cancer, lung disease, heart disease, or diabetes mellitus were 3.2 times more likely to quit smoking than were individuals without new diagnoses (P < .001). Among overweight or obese individuals younger than 75 years, those with recent diagnoses of lung disease, heart disease, or diabetes mellitus lost -0.35 U of body mass index (calculated as weight in kilograms divided by height in meters squared) compared with those without these new diagnoses (P < .001). Smokers with multiple new diagnoses were 6 times more likely to quit smoking compared with those with no new diagnoses. The odds of quitting smoking were 5 times greater in individuals with a new diagnosis of heart disease, and body mass index declined by 0.6 U in overweight or obese individuals with a new diagnosis of diabetes mellitus (P < .001). CONCLUSIONS: Across a range of health conditions, new diagnoses can serve as a window of opportunity that prompts older adults to change health habits, in particular, to quit smoking. Quality improvement efforts targeting secondary as well as primary prevention through the health care system are likely well founded.
Keywords: Age Factors; Aged; Aged, 80 and over; Body Mass Index; Diabetes Mellitus, Type 2; Health Behavior; Health Surveys; Heart Diseases; Humans; Longitudinal Studies; Lung Diseases; Middle Aged; Multivariate Analysis; Neoplasms; Overweight; Racial Groups; Smoking; Smoking cessation; Stroke; United States; Weight Loss

Smoking kills, obesity disables: a multistate approach of the US Health and Retirement Survey. - Mieke Reuser; Luc G Bonneux; Frans J Willekens (Obesity (Silver Spring), 2009)
Increasing BMI causes concerns about the consequences for health care. Decreasing cardiovascular mortality has lowered obesity-related mortality, extending duration of disability. We hypothesized increased duration of disability among overweight and obese individuals. We estimated age-, risk-, and state-dependent probabilities of activities of daily living (ADL) disability and death and calculated multistate life tables, resulting in the comprehensive measure of life years with and without ADL disability. We used prospective data of 16,176 white adults of the Health and Retirement Survey (HRS). Exposures were self-reported BMI and for comparison smoking status and levels of education. Outcomes were years to live with and without ADL disability at age 55. The reference categories were high normal weight (BMI: 23-24.9), nonsmoking and high education. Mild obesity (BMI: 30-34.9) did not change total life expectancy (LE) but exchanged disabled for disability-free years. Mild obesity decreased disability-free LE with 2.7 (95% confidence limits 1.2; 3.2) year but increased LE with disability with 2.0 (0.6; 3.4) years among men. Among women, BMI of 30 to 34.9 decreased disability-free LE with 3.6 (2.1; 5.1) year but increased LE with disability with 3.2 (1.6;4.8) years. Overweight (BMI: 25-29.9) increases LE with disability for women only, by 2.1 (0.8; 3.3) years). Smoking compressed disability by high mortality. Smoking decreased LE with 7.2 years, and LE with disability with 1.3 (0.5; 2.5) years (men) and 1.4 (0.3; 2.6) years (women). A lower education decreased disability-free life, but not duration of ADL disability. In the aging baby boom, higher BMI will further increase care dependence.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Body Mass Index; Disability Evaluation; Educational Status; Female; Health Surveys; Humans; Life Expectancy; Life Tables; Male; Middle Aged; Obesity; Proportional Hazards Models; Prospective Studies; Smoking; United States; White People

Statistical design and estimation for the national social life, health, and aging project. - O'Muircheartaigh, Colm; Eckman, Stephanie; Smith, Stephen (J Gerontol B Psychol Sci Soc Sci, 2009)
OBJECTIVES: The paper discusses the sample design of the National Social Life, Health, and Aging Project (NSHAP) and how the design affects how estimates should be calculated from the survey data. The NSHAP study allows researchers to study the links between sexuality and health in older adults. The goal of the design was to represent adults aged 57-85 years in six demographic domains. METHODS: The sample design begins with a national area probability sample of households, carried out jointly with the 2004 round of the Health and Retirement Study. Selection of respondents for NSHAP balanced age and gender subgroups and oversampled African Americans and Latinos. Data collection was carried out from July 2005 to March 2006. RESULTS: The survey obtained an overall response rate of 75.5%. DISCUSSION: The complex sample design requires that the selection probabilities and the field implementation be accounted for in estimating population parameters. The data set contains weights to compensate for differential probabilities of selection and response rates among demographic groups. Analysts should use weights in constructing estimates from the survey and account for the complex sample design in estimating standard errors for survey estimates.
Keywords: Aged; Aged, 80 and over; Aging; Bias; Data collection; Data Interpretation, Statistical; Female; Health Status; Health Surveys; Humans; Longitudinal Studies; Male; Mass Screening; Middle Aged; Research Design; Sampling Studies; Sexual Behavior; Social Behavior; United States

Surrogate consent for dementia research: a national survey of older Americans. - Scott Y H Kim; H.M. Kim; Kenneth M. Langa; Jason H. Karlawish; David S Knopman; Appelbaum, P S (Neurology, 2009)
BACKGROUND: Research in novel therapies for Alzheimer disease (AD) relies on persons with AD as research subjects. Because AD impairs decisional capacity, informed consent often must come from surrogates, usually close family members. But policies for surrogate consent for research remain unsettled after decades of debate. METHODS: We designed a survey module for a random subsample (n = 1,515) of the 2006 wave of the Health and Retirement Study, a biennial survey of a nationally representative sample of Americans aged 51 and older. The participants answered questions regarding one of four randomly assigned surrogate-based research (SBR) scenarios: lumbar puncture study, drug randomized control study, vaccine study, and gene transfer study. Each participant answered three questions: whether our society should allow family surrogate consent, whether one would want to participate in the research, and whether one would allow one's surrogate some or complete leeway to override stated personal preferences. RESULTS: Most respondents stated that our society should allow family surrogate consent for SBR (67.5% to 82.5%, depending on the scenario) and would themselves want to participate in SBR (57.4% to 79.7%). Most would also grant some or complete leeway to their surrogates (54.8% to 66.8%), but this was true mainly of those willing to participate. There was a trend toward lower willingness to participate in SBR among those from ethnic or racial minority groups. CONCLUSIONS: Family surrogate consent-based dementia research is broadly supported by older Americans. Willingness to allow leeway to future surrogates needs to be studied further for its ethical significance for surrogate-based research policy.
PMID 19139366
Keywords: Advance directives; Age Factors; Aged; Aged, 80 and over; Alzheimer disease; Biomedical Research; Caregivers; Clinical Trials as Topic; Data collection; ethnicity; Female; Humans; Informed Consent; Legal Guardians; Male; Mental Competency; Middle Aged; Patient Participation; Proxy; Research Subjects; Surveys and Questionnaires; Therapeutic Human Experimentation; Third-Party Consent

Telephone interview for cognitive status: Creating a crosswalk with the Mini-Mental State Examination. - Tamara G Fong; Michael A Fearing; Richard N Jones; Peilin Shi; Edward R Marcantonio; James L Rudolph; Frances Margaret Yang; Dan K Kiely; Sharon K Inouye (Alzheimers Dement, 2009)
BACKGROUND: Brief cognitive screening measures are valuable tools for both research and clinical applications. The most widely used instrument, the Mini-Mental State Examination (MMSE), is limited in that it must be administered face-to-face, cannot be used in participants with visual or motor impairments, and is protected by copyright. Screening instruments such as the Telephone Interview for Cognitive Status (TICS) were developed to provide a valid alternative, with comparable cut-point scores to rate global cognitive function. METHODS: The MMSE, TICS-30, and TICS-40 scores from 746 community-dwelling elders who participated in the Aging, Demographics, and Memory Study (ADAMS) were analyzed with equipercentile equating, a statistical process of determining comparable scores based on percentile equivalents for different forms of an examination. RESULTS: Scores from the MMSE and TICS-30 and TICS-40 corresponded well, and clinically relevant cut-point scores were determined. For example, an MMSE score of 23 is equivalent to 17 and 20 on the TICS-30 and TICS-40, respectively. CONCLUSIONS: These findings indicate that TICS and MMSE scores can be linked directly. Clinically relevant and important MMSE cut points and the respective ADAMS TICS-30 and TICS-40 cut-point scores are included, to identify the degree of cognitive impairment among respondents with any type of cognitive disorder. These results will help in the widespread application of TICS in both research and clinical practice.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Cognition Disorders; Disability Evaluation; Female; Geriatric Assessment; Health Status; Humans; Interviews as Topic; Male; Mass Screening; Models, Statistical; Neuropsychological tests; Predictive Value of Tests; Psychiatric Status Rating Scales; Remote Consultation; Reproducibility of Results; Sensitivity and Specificity

Trajectories of cognitive function in late life in the United States: demographic and socioeconomic predictors. - Arun S Karlamangla; Miller-Martinez, Dana; Carol S Aneshensel; Teresa Seeman; Richard G Wight; Joshua Chodosh (Am J Epidemiol, 2009)
This study used mixed-effects modeling of data from a national sample of 6,476 US adults born before 1924, who were tested 5 times between 1993 and 2002 on word recall, serial 7's, and other mental status items to determine demographic and socioeconomic predictors of trajectories of cognitive function in older Americans. Mean decline with aging in total cognition score (range, 0-35; standard deviation, 6.00) was 4.1 (0.68 standard deviations) per decade (95% confidence interval: 3.8, 4.4) and in recall score (range, 0-20; standard deviation, 3.84) was 2.3 (0.60 standard deviations) per decade (95% confidence interval: 2.1, 2.5). Older cohorts (compared with younger cohorts), women (compared with men), widows/widowers, and those never married (both compared with married individuals) declined faster, and non-Hispanic blacks (compared with non-Hispanic whites) and those in the bottom income quintile (compared with the top quintile) declined slower. Race and income differences in rates of decline were not sufficient to offset larger differences in baseline cognition scores. Educational level was not associated with rate of decline in cognition scores. The authors concluded that ethnic and socioeconomic disparities in cognitive function in older Americans arise primarily from differences in peak cognitive performance achieved earlier in the life course and less from declines in later life.
Keywords: Aged; Aged, 80 and over; Aging; Black or African American; Cognition; Confidence Intervals; Education; Female; Geriatric Assessment; Hispanic or Latino; Humans; Income; Male; Marital Status; Mexican Americans; Poverty; Sampling Studies; Socioeconomic factors; Surveys and Questionnaires; United States; White People

Urban neighborhood context and change in depressive symptoms in late life. - Richard G Wight; Janet R. Cummings; Arun S Karlamangla; Carol S Aneshensel (J Gerontol B Psychol Sci Soc Sci, 2009)
OBJECTIVES: This study examines associations between urban neighborhood sociodemographic characteristics and change over time in late-life depressive symptoms. METHODS: Survey data are from three waves (1993, 1995, and 1998) of the Study of Assets and Health Dynamics Among the Oldest Old, a U.S. national probability sample of noninstitutionalized persons aged 70 years or older in 1993. Neighborhoods are 1990 U.S. Census tracts. Hierarchical linear regression is used to estimate multilevel models. RESULTS: The average change over time in depressive symptoms varies significantly across urban neighborhoods. Change in depressive symptoms is significantly associated with neighborhood-level socioeconomic disadvantage and ethnic composition in unadjusted models but not in models that control for individual-level characteristics. CONCLUSIONS: Findings indicate that apparent neighborhood-level effects on change in depressive symptoms over time among urban-dwelling older adults reflect, for the most part, differences in characteristics of the neighborhood residents.
Keywords: Aged; Aged, 80 and over; Aging; Cultural Diversity; depression; Disability Evaluation; Educational Status; Female; Humans; Longitudinal Studies; Los Angeles; Male; Personality Inventory; Poverty; Psychosocial Deprivation; Residence Characteristics; Risk Factors; Urban Population

The burden of mortality of obesity at middle and old age is small. A life table analysis of the US Health and Retirement Survey. - Mieke Reuser; Luc G Bonneux; Frans J Willekens (Eur J Epidemiol, 2008)
The evidence of effect of overweight and obesity on mortality at middle and old age is conflicting. The increased relative risk of cardiovascular disease and diabetes for overweight and obese individuals compared to normal weight is well documented, but the absolute risk of cardiovascular death has decreased spectacularly since the 1980s. We estimate the burden of mortality of obesity among middle and old aged adults in the Health and Retirement Survey (HRS), a US prospective longitudinal study. We calculate univariate and multivariate age-specific probabilities and proportional hazard ratios of death in relation to self-reported body mass index (BMI), smoking and education. The life table translates age specific adjusted event rates in survival times, dependent on risk factor distributions (smoking, levels of education and self reported BMI). 95% confidence intervals are calculated by bootstrapping. The highest life expectancy at age 55 was found in overweight (BMI 25-29.9), highly educated non smokers: 30.7 (29.5-31.9) years (men) and 33.2 (32.1-34.3) (women), slightly higher than a BMI 23-24.9 in both sexes. Smoking decreased the population life expectancy with 3.5 (2.7-4.4) years (men) and 1.8 (1.0-2.5) years (women). Less than optimal education cost men and women respectively 2.8 (2.1-3.6) and 2.6 (1.6-3.6) years. Obesity and low normal weight decreased population life expectancy respectively by 0.8 (0.2-1.3) and 0.8 (0.0-1.5) years for men and women in a contemporary, US population. The burden of mortality of obesity is limited, compared to smoking and low education.
PMID: 18584293
Keywords: Aged; Aged, 80 and over; Body Mass Index; Educational Status; Female; Health Surveys; Humans; Life Expectancy; Life Tables; Male; Middle Aged; Multivariate Analysis; Obesity; Proportional Hazards Models; Smoking; United States; Weight Gain; Weight Loss

Changes in weight among U.S. adults aged 70 and over, 1993 to 2002. - Xiaoxing He; Meng, Hongdao (Prev Med, 2008)
OBJECTIVE: To describe the patterns and predictors of weight change among U.S. adults aged 70 and over. METHOD: The study is a retrospective cohort study of 7441 community-dwelling U.S. adults aged 70 years and over during 1993-2002. We examined changes in weight for men and women, and by race/ethnicity groups. We used multivariate linear regression analysis to determine predictors of weight change while controlling for key covariates at baseline. RESULTS: The mean body weight decreased in both genders and all ethnic groups. Unadjusted average weight loss was 3.41 kg for men and 3.29 kg for women over nine years. Black women had higher mean body weight at baseline and were more likely to report weight gains of 5 kg or more. Multivariate analysis showed that age and baseline weight were major predictors of weight loss. Physical activity was associated with less weight loss among men. CONCLUSION: The trends of weight change among U.S. adults aged 70 and over were more prone to weight loss than weight gain, with substantial variations. Public health messages regarding weight control should take into account the heterogeneity of this population and target weight loss as well as weight gain to meet diverse needs of the population.
Keywords: Aged; Aged, 80 and over; Aging; Female; Humans; Interviews as Topic; Linear Models; Male; Multivariate Analysis; Population Growth; Retrospective Studies; United States; Weight Gain; Weight Loss

Chronic conditions and mortality among the oldest old. - Sei J. Lee; Alan S Go; Lindquist, Karla; Bertenthal, Daniel; Kenneth E Covinsky (Am J Public Health, 2008)
OBJECTIVES: We sought to determine whether chronic conditions and functional limitations are equally predictive of mortality among older adults. METHODS: Participants in the 1998 wave of the Health and Retirement Study (N=19430) were divided into groups by decades of age, and their vital status in 2004 was determined. We used multivariate Cox regression to determine the ability of chronic conditions and functional limitations to predict mortality. RESULTS: As age increased, the ability of chronic conditions to predict mortality declined rapidly, whereas the ability of functional limitations to predict mortality declined more slowly. In younger participants (aged 50-59 years), chronic conditions were stronger predictors of death than were functional limitations (Harrell C statistic 0.78 vs. 0.73; P=.001). In older participants (aged 90-99 years), functional limitations were stronger predictors of death than were chronic conditions (Harrell C statistic 0.67 vs. 0.61; P=.004). CONCLUSIONS: The importance of chronic conditions as a predictor of death declined rapidly with increasing age. Therefore, risk-adjustment models that only consider comorbidities when comparing mortality rates across providers may be inadequate for adults older than 80 years.
PMID 18511714
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Female; Health Behavior; Health Status; Humans; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Proportional Hazards Models; Reproducibility of Results; Risk Adjustment; Severity of Illness Index; Socioeconomic factors; Survival Analysis; United States

Declines in late-life disability: the role of early- and mid-life factors. - Vicki A Freedman; Linda G Martin; Robert F. Schoeni; Jennifer C. Cornman (Soc Sci Med, 2008)
Investigations into the reasons for declines in late-life disability have largely focused on the role of contemporaneous factors. Adopting a life-course perspective as a backdrop, in this paper we ask whether there also has been a role for selected early- and mid-life factors in the decline, and if so whether these factors have been operating through changes in the risks of disability onset or recovery. Drawing on five waves from 1995 to 2004 of the U.S. Health and Retirement Study, we found for the 75 years and older population in the United States that the prevalence of difficulty with activities of daily living (ADL) declined from 30.2% in 1995 to 26.0% in 2004, whereas the trend in difficulty with instrumental activities of daily living (IADL) was flat. Onset of ADL limitations also was reduced during this period while recovery increased. Changes in the educational composition of the older population were linked to declines in the prevalence of ADL limitations, but there were also modest contributions of changes in mother's education, self-rated childhood health, and lifetime occupation. Declines in late-life vision impairments and increases in wealth also contributed substantially to the downward trend, and had chronic conditions not increased, it would have been even larger. Reductions in the onset of ADL limitations were partly driven by changes in educational attainment of respondents and their mothers and, in late-life, better vision and wealth. In contrast, the recovery trend was not accounted for by changes in early- or mid-life factors. We conclude that early- and mid-life factors have contributed along with late-life factors to U.S. late-life disability trends mainly through their influence on the onset of, rather than recovery from, limitations.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Chronic disease; Cross-Sectional Studies; Disabled Persons; Female; Frail Elderly; Health Behavior; Health Status; Health Surveys; Humans; Life Style; Logistic Models; Male; Morbidity; Population Surveillance; Socioeconomic factors; United States

Degree of disability and patterns of caregiving among older Americans with congestive heart failure. - Tanya R Gure; Mohammed U Kabeto; Caroline S Blaum; Kenneth M. Langa (J Gen Intern Med, 2008)
OBJECTIVES: Although congestive heart failure (CHF) is a common condition, the extent of disability and caregiving needs for those with CHF are unclear. We sought to determine: (1) prevalence of physical disability and geriatric conditions, (2) whether CHF is independently associated with disability, (3) rates of nursing home admission, and (4) formal and informal in-home care received in the older CHF population. METHODS: We used cross-sectional data from the 2000 wave of the Health and Retirement Study. We compared outcomes among three categories of older adults: (1) no coronary heart disease (CHD), (2) CHD, without CHF, and (3) CHF. Compared to those without CHF, respondents reporting CHF were more likely to be disabled (P < 0.001) and to have geriatric conditions (P < 0.001). Respondents reporting CHF were more likely to have been admitted to a nursing home (P < 0.05). CHF respondents were more functionally impaired than respondents without CHF. RESULTS: The adjusted average weekly informal care hours for respondents reporting CHF was higher than for those reporting CHD but without CHF and those reporting no CHD (6.7 vs 4.1 vs 5.1, respectively; P < 0.05). Average weekly formal caregiving hours also differed among the three groups (1.3 CHF vs 0.9 CHD without CHF vs 0.7 no CHD; P > 0.05). CONCLUSIONS: CHF imposes a significant burden on patients, families, and the long-term care system. Older adults with CHF have higher rates of disability, geriatric conditions, and nursing home admission.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Coronary Disease; Cross-Sectional Studies; Disabled Persons; Female; Health Surveys; Heart Failure; Hospitalization; Humans; Male; Nursing homes; United States

Economic theory and evidence on smoking behavior of adults. - Frank A Sloan; Wang, Yang (Addiction, 2008)
AIMS: To describe: (i) three alternative conceptual frameworks used by economists to study addictive behaviors: rational, imperfectly rational and irrational addiction; (ii) empirical economic evidence on each framework and specific channels to explain adult smoking matched to the frameworks; and (iii) policy implications for each framework. METHODS: A systematic review and appraisal of important theoretical and empirical economic studies on smoking. RESULTS: There is some empirical support for each framework. For rational and imperfectly rational addiction there is some evidence that anticipated future cigarette prices influence current cigarette consumption, and quitting costs are high for smokers. Smokers are more risk-tolerant in the financial domain than are others and tend to attach a lower value to being in good health. Findings on differences in rates of time preference by smoking status are mixed; however, short-term rates are higher than long-term rates for both smokers and non-smokers, a stylized fact consistent with hyperbolic discounting. The economic literature lends no empirical support to the view that mature adults smoke because they underestimate the probability of harm to health from smoking. In support of the irrationality framework, smokers tend to be more impulsive than others in domains not related directly to smoking, implying that they may be sensitive to cues that trigger smoking. CONCLUSIONS: Much promising economic research uses the imperfectly rational addiction framework, but empirical research based on this framework is still in its infancy.
Keywords: Adult; Aged; Aged, 80 and over; Choice Behavior; Costs and Cost Analysis; health policy; Humans; Impulsive Behavior; Middle Aged; Risk Factors; Smoking; Smoking cessation; Time Factors

Educational differentials in life expectancy with cognitive impairment among the elderly in the United States. - Agnès Lièvre; Dawn E Alley; Eileen M. Crimmins (J Aging Health, 2008)
OBJECTIVE: This article provides estimates of education differentials in life expectancy with and without cognitive impairment for the noninstitutionalized population aged 70 years and older in the United States. METHOD: Life expectancy with cognitive impairment was calculated using multistate models, allowing transitions between cognitively intact and cognitively impaired states and from each of these states to death and allowing transition rates to vary across age and education. Four waves of the Assets and Health Dynamics of the Oldest Old survey were used. RESULTS: Those with low levels of education are more likely to become cognitively impaired and do so at an earlier age. After age 70, persons with low educational levels can expect to live 11.6 years, and persons with high education 14.1 years, without cognitive impairment. Length of life with cognitive impairment differs by education (1.6 years and 1.0 years at age 70, respectively) but differs little by age. DISCUSSION: Although those with higher education have lower rates of both cognitive impairment and mortality, those who do become cognitively impaired appear to be in poorer health, leading to a reduced probability of improved cognition and increased probability of mortality relative to those with lower educational levels.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Educational Status; Female; Humans; Life Expectancy; Male; United States

Effects of social integration on preserving memory function in a nationally representative US elderly population. - Karen A Ertel; M. Maria Glymour; Lisa F Berkman (Am J Public Health, 2008)
OBJECTIVES: We tested whether social integration protects against memory loss and other cognitive disorders in late life in a nationally representative US sample of elderly adults, whether effects were stronger among disadvantaged individuals, and whether earlier cognitive losses explained the association (reverse causation). METHODS: Using data from the Health and Retirement Study (N = 16,638), we examined whether social integration predicted memory change over 6 years. Memory was measured by immediate and delayed recall of a 10-word list. Social integration was assessed by marital status, volunteer activity, and frequency of contact with children, parents, and neighbors. We examined growth-curve models for the whole sample and within subgroups. RESULTS: The mean memory score declined from 11.0 in 1998 to 10.0 in 2004. Higher baseline social integration predicted slower memory decline in fully adjusted models (P<.01). Memory among the least integrated declined at twice the rate as among the most integrated. This association was largest for respondents with fewer than 12 years of education. There was no evidence of reverse causation. CONCLUSIONS: Our study provides evidence that social integration delays memory loss among elderly Americans. Future research should focus on identifying the specific aspects of social integration most important for preserving memory.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Female; Health Behavior; Health Status; Humans; Interpersonal Relations; Male; Mental Health; Mental Recall; Predictive Value of Tests; Reproducibility of Results; Severity of Illness Index; social isolation; Social Support; Socioeconomic factors; United States

Exploring the determinants of racial and ethnic disparities in total knee arthroplasty: health insurance, income, and assets. - Amresh D Hanchate; Zhang, Yuqing; David T Felson; Arlene S Ash (Med Care, 2008)
OBJECTIVE: To estimate national total knee arthroplasty (TKA) rates by economic factors, and the extent to which differences in insurance coverage, income, and assets contribute to racial and ethnic disparities in TKA use. DATA SOURCE: US longitudinal Health and Retirement Study survey data for the elderly and near-elderly (biennial rounds 1994-2004) from the Institute of Social Research, University of Michigan. STUDY DESIGN: The outcome is dichotomous, whether the respondent received first TKA in the previous 2 years. Longitudinal, random-effects logistic regression models are used to assess associations with lagged economic indicators. SAMPLE: Sample was 55,469 person-year observations from 18,439 persons; 663, with first TKA. RESULTS: Racial/ethnic disparities in TKA were more prominent among men than women. For example, relative to white women, odds ratios (ORs) were 0.94, 0.46, and 0.79, for white, black, and Hispanic men, respectively (P < 0.05 for black men). After adjusting for economic factors, racial/ethnic differences in TKA rates for women essentially disappeared, while the deficit for black men remained large. Among Medicare-enrolled elderly, those with supplemental insurance may be more likely to have first TKA compared with those without it, whether the supplemental coverage was private [OR: 1.27; 95% confidence interval (CI): 0.82-1.96] or Medicaid (OR: 1.18; 95% CI: 0.93-1.49). Among the near-elderly (age 47-64), compared with the privately insured, the uninsured were less likely (OR: 0.61; 95% CI: 0.40-0.92) and those with Medicaid more likely (OR: 1.53; 95% CI: 1.03-2.26) to have first TKA. CONCLUSIONS: Limited insurance coverage and financial constraints explain some of the racial/ethnic disparities in TKA rates.
Keywords: Aged; Aged, 80 and over; Arthroplasty, Replacement, Knee; Comorbidity; ethnicity; Female; Healthcare Disparities; Humans; Income; Insurance, Health; Logistic Models; Longitudinal Studies; Male; Middle Aged; Sex Distribution; Socioeconomic factors; United States

Gender differences in functional status in middle and older age: are there any age variations? - Jersey Liang; Joan M. Bennett; Benjamin A Shaw; Ana R Quiñones; Wen Ye; Xiao Xu; Mary Beth Ofstedal (J Gerontol B Psychol Sci Soc Sci, 2008)
OBJECTIVES: The present study examines gender differences in changes in functional status after age 50 and how such differences vary across different age groups. METHODS: Data came from the Health and Retirement Study, involving up to six repeated observations of a national sample of Americans older than 50 years of age between 1995 and 2006. We employed hierarchical linear models with time-varying covariates in depicting temporal variations in functional status between men and women. RESULTS: As a quadratic function, the worsening of functional status was more accelerated in terms of the intercept and rate of change among women and those in older age groups. In addition, gender differences in the level of functional impairment were more substantial in older persons than in younger individuals, although differences in the rate of change between men and women remained constant across age groups. DISCUSSION: A life course perspective can lead to new insights regarding gender variations in health within the context of intrapersonal and interpersonal differences. Smaller gender differences in the level of functional impairment in the younger groups may reflect improvement of women's socioeconomic status, greater rate of increase in chronic diseases among men, and less debilitating effects of diseases.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Disabled Persons; Female; Health Status; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Sex Factors; United States

Lifecourse social conditions and racial disparities in incidence of first stroke. - M. Maria Glymour; Mauricio Avendano; Steven A Haas; Lisa F Berkman (Ann Epidemiol, 2008)
PURPOSE: Some previous studies found excess stroke rates among black subjects persisted after adjustment for socioeconomic status (SES), fueling speculation regarding racially patterned genetic predispositions to stroke. Previous research was hampered by incomplete SES assessments, without measures of childhood conditions or adult wealth. We assess the role of lifecourse SES in explaining stroke risk and stroke disparities. METHODS: Health and Retirement Study participants age 50+ (n = 20,661) were followed on average 9.9 years for self- or proxy-reported first stroke (2175 events). Childhood social conditions (southern state of birth, parental SES, self-reported fair/poor childhood health, and attained height), adult SES (education, income, wealth, and occupational status) and traditional cardiovascular risk factors were used to predict first stroke onset using Cox proportional hazards models. RESULTS: Black subjects had a 48% greater risk of first stroke incidence than whites (95% confidence interval, 1.33-1.65). Childhood conditions predicted stroke risk in both blacks and whites, independently of adult SES. Adjustment for both childhood social conditions and adult SES measures attenuated racial differences to marginal significance (hazard ratio, 1.13; 95% CI, 1.00-1.28). CONCLUSIONS: Childhood social conditions predict stroke risk in black and White American adults. Additional adjustment for adult SES, in particular wealth, nearly eliminated the disparity in stroke risk between black and white subjects.
Keywords: Aged; Aged, 80 and over; Black or African American; Cardiovascular Diseases; ethnicity; Female; Health Status Disparities; Humans; Incidence; Interviews as Topic; Life Style; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Risk Factors; Social Environment; Socioeconomic factors; Stroke; United States; White People

Measurement differences in depression: chronic health-related and sociodemographic effects in older Americans. - Frances Margaret Yang; Richard N Jones (Psychosom Med, 2008)
OBJECTIVE: To evaluate the influence of five chronic health conditions (high blood pressure, heart conditions, stroke, diabetes, and lung diseases) and four sociodemographic characteristics (age, gender, education, and race/ethnicity) on the endorsement patterns of depressive symptoms in a sample of community-dwelling older adults. METHOD: Participants were adults aged >or=65 years from the 2004 Health and Retirement Study (n = 9448). Depressive symptoms were measured with a nine-item Center for Epidemiologic Studies-Depression scale. Measurement differences attributable to health and sociodemographic factors were assessed with a multidimensional model based on item response theory. RESULTS: Evidence for unidimensionality was equivocal. We used a bifactor model to express symptom endorsement patterns as resulting from a general factor and three specific factors ("dysphoria," "psychosomatic," and "lack of positive affect"). Even after controlling for the effects of health on the psychosomatic factor, heart conditions, stroke, diabetes, and lung diseases had significant positive effects on the general factor. Significant effects due to gender and educational levels were observed on the "lack of positive affect" factor. Older adults self-identifying as Latinos had higher levels of general depression. On the symptom level, meaningful measurement noninvariance due to race/ethnic differences were found in the following five items: depressed, effort, energy, happy, and enjoy life. CONCLUSIONS: The increased tendency to endorse depressive symptoms among persons with specific health conditions is, in part, explained by specific associations among symptoms belonging to the psychosomatic domain. Differences attributable to the effects of health conditions may reflect distinct phenomenological features of depression. The bifactor model serves as a vehicle for testing such hypotheses.
Keywords: Aged; Aged, 80 and over; Chronic disease; Cohort Studies; Comorbidity; Confounding Factors, Epidemiologic; Culture; depression; Diabetes Mellitus; Educational Status; ethnicity; Factor Analysis, Statistical; Female; Heart Diseases; Humans; Hypertension; Interviews as Topic; Lung Diseases; Male; Self-Assessment; Sex Factors; Stroke; United States

Memory decline and depressive symptoms in a nationally representative sample of older adults: the Health and Retirement Study (1998-2004). - Hector M González; Mary E Bowen; Gwenith G Fisher (Dement Geriatr Cogn Disord, 2008)
BACKGROUND/AIMS: Inconsistencies in the relationship between depression and cognitive decline may exist because the expected cognitive domains at risk have not been specified in previous study designs. We aimed to examine the relationship between depressive symptoms and verbal episodic memory functioning over time. METHODS: Data from a prospective cohort study (Health and Retirement Study; 1998-2004; n = 18,465), a multistage national probability sample of older adults in the United States, were analyzed. Verbal learning and memory of a 10-word list learning task were the main outcomes. Depressive symptoms (Center for Epidemiologic Studies - Depression Scale) constituted the main predictor. RESULTS: Depressive symptoms were associated with significantly lower immediate (-0.05; p < 0.001) and delayed (-0.06; p < 0.001) word list recall scores after controlling for demographics and baseline and time-varying cardiovascular disease risks and diseases. CONCLUSIONS: In this US national study of older adults, elevated depressive symptoms were associated with declines in episodic learning and memory over time. These associations were little affected by the demographic or medical conditions considered in this study. The results suggest that learning and memory decline may be a long-term feature associated with depressive symptoms among the nation's older adult population.
Keywords: Aged; Aged, 80 and over; depression; Female; Health Status; Humans; Incidence; Male; Memory Disorders; Neuropsychological tests; Prevalence; Retirement; United States

Place of death among older Americans: does state spending on home- and community-based services promote home death? - Muramatsu, Naoko; Ruby L Hoyem; yin, Hongjun; Richard T. Campbell (Med Care, 2008)
BACKGROUND: The majority of Americans die in institutions although most prefer to die at home. States vary greatly in their proportion of home deaths. Although individuals' circumstances largely determine where they die, health policies may affect the range of options available to them. OBJECTIVE: To examine whether states' spending on home- and community-based services (HCBS) affects place of death, taking into consideration county health care resources and individuals' family, sociodemographic, and health factors. METHODS: Using exit interview data from respondents in the Health and Retirement Study born in 1923 or earlier who died between 1993 and 2002 (N = 3362), we conducted discrete-time survival analysis of the risk of end-of-life nursing home relocation to examine whether states' HCBS spending would delay or prevent end-of-life nursing home admission. Then we ran logistic regression analysis to investigate the HCBS effects on place of death separately for those who relocated to a nursing home and those who remained in the community. RESULTS: Living in a state with higher HCBS spending was associated with lower risk of end-of-life nursing home relocation, especially among people who had Medicaid. However, state HCBS support was not directly associated with place of death. CONCLUSIONS: States' generosity for HCBS increases the chance of dying at home via lowering the risk of end-of-life nursing home relocation. State-to-state variation in HCBS spending may partly explain variation in home deaths. Our findings add to the emerging encouraging evidence for continued efforts to enhance support for HCBS.
Keywords: Aged; Aged, 80 and over; Community Health Services; Death; Humans; Logistic Models; Nursing homes; Residence Characteristics; Terminal Care

Prevalence of cognitive impairment without dementia in the United States. - Brenda L Plassman; Kenneth M. Langa; Gwenith G Fisher; Steven G Heeringa; David R Weir; Mary Beth Ofstedal; James R Burke; Michael D Hurd; Guy G Potter; Willard L Rodgers; David C Steffens; John J McArdle; et al. (Ann Intern Med, 2008)
BACKGROUND: Cognitive impairment without dementia is associated with increased risk for disability, increased health care costs, and progression to dementia. There are no population-based prevalence estimates of this condition in the United States. OBJECTIVE: To estimate the prevalence of cognitive impairment without dementia in the United States and determine longitudinal cognitive and mortality outcomes. DESIGN: Longitudinal study from July 2001 to March 2005. SETTING: In-home assessment for cognitive impairment. PARTICIPANTS: Participants in ADAMS (Aging, Demographics, and Memory Study) who were age 71 years or older drawn from the nationally representative HRS (Health and Retirement Study). Of 1770 selected individuals, 856 completed initial assessment, and of 241 selected individuals, 180 completed 16- to 18-month follow-up assessment. MEASUREMENTS: Assessments, including neuropsychological testing, neurologic examination, and clinical and medical history, were used to assign a diagnosis of normal cognition, cognitive impairment without dementia, or dementia. National prevalence rates were estimated by using a population-weighted sample. RESULTS: In 2002, an estimated 5.4 million people (22.2%) in the United States age 71 years or older had cognitive impairment without dementia. Prominent subtypes included prodromal Alzheimer disease (8.2%) and cerebrovascular disease (5.7%). Among participants who completed follow-up assessments, 11.7% with cognitive impairment without dementia progressed to dementia annually, whereas those with subtypes of prodromal Alzheimer disease and stroke progressed at annual rates of 17% to 20%. The annual death rate was 8% among those with cognitive impairment without dementia and almost 15% among those with cognitive impairment due to medical conditions. LIMITATIONS: Only 56% of the nondeceased target sample completed the initial assessment. Population sampling weights were derived to adjust for at least some of the potential bias due to nonresponse and attrition. CONCLUSION: Cognitive impairment without dementia is more prevalent in the United States than dementia, and its subtypes vary in prevalence and outcomes.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Dementia; disease progression; Humans; Longitudinal Studies; Prevalence; United States

Racial and ethnic differences in activities of daily living disability among the elderly: the case of Spanish speakers. - Manasi A. Tirodkar; Song, Jing; Rowland W Chang; Dorothy D Dunlop; Huan J. Chang (Arch Phys Med Rehabil, 2008)
OBJECTIVE: To compare incident disability patterns across racial and ethnic groups. DESIGN: Prospective cohort study with 6-year follow-up (1998-2004). SETTING: National probability sample. PARTICIPANTS: A 1998 Health and Retirement Study sample of 12,288 non-Hispanic whites, 1952 African Americans, 575 Hispanics interviewed in Spanish (Hispanic-Spanish), and 518 Hispanics interviewed in English (Hispanic-English), older than 51 years, and free of disability at baseline. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURE: Disability in activities of daily living (ADL) tasks (walking, dressing, transferring, bathing, toileting, feeding). RESULTS: Hispanic-Spanish reported disproportionately lower rates of walking disability (standardized rates, 4.31% vs Hispanic-English [8.57%], black [7.54%], white [7.20%]) despite higher reported Hispanic-Spanish frequencies of lower-extremity dysfunction than other racial and ethnic groups. Across the 6 ADL tasks, the development of walking disability was most frequent among Hispanic-English subjects, African Americans, and whites. In contrast, Hispanic-Spanish subjects reported dressing as the most frequent ADL task disability, whereas walking ranked fourth. CONCLUSIONS: Aggregating all Hispanics, regardless of interview language, may be inappropriate. Future research on linguistic group differences in self-reported health outcomes is necessary to ensure that health status measures will be appropriate for use in diverse racial and ethnic groups.
Keywords: Acculturation; Activities of Daily Living; Aged; Aged, 80 and over; Disability Evaluation; Disabled Persons; Female; Geriatric Assessment; Health Status Indicators; Hispanic or Latino; Humans; Male; Middle Aged

Spousal caregiving in late midlife versus older ages: implications of work and family obligations. - Julie C Lima; Susan M Allen; Goldscheider, Frances; Intrator, Orna (J Gerontol B Psychol Sci Soc Sci, 2008)
OBJECTIVES: This study examined life-stage differences in the provision of care to spouses with functional impairment. METHODS: We examined 1,218 married adults aged 52 and older from the 2000 wave of the Health and Retirement Study who received impairment-related help with at least one activity of daily living. We examined the differential likelihood that spouses served as primary caregiver and the hours of care provided by spousal primary caregivers by life stage. RESULTS: We found that late middle-aged care recipients were more likely than their older counterparts to receive the majority of their care from their spouse but received fewer hours of spousal care, mostly when spouses worked full time. Competing demands of caring for children or parents did not affect the amount of care provided by a spouse. DISCUSSION: Late middle-aged adults with functional limitations are more likely than older groups to be married and cared for primarily by spouses; however, they may be particularly vulnerable to unmet need for care. As the baby boom generation ages, retirement ages increase, and federal safety nets weaken, people with health problems at older ages may soon find themselves in the same caregiving predicament as those in late middle age.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Caregivers; Employment; Family Relations; Female; Gender Identity; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Mobility Limitation; Spouses; Time Factors; United States

Trends in the prevalence and mortality of cognitive impairment in the United States: is there evidence of a compression of cognitive morbidity? - Kenneth M. Langa; Eric B Larson; Jason H. Karlawish; David M Cutler; Mohammed U Kabeto; Scott Y H Kim; Allison B Rosen (Alzheimers Dement, 2008)
BACKGROUND: Recent medical, demographic, and social trends might have had an important impact on the cognitive health of older adults. To assess the impact of these multiple trends, we compared the prevalence and 2-year mortality of cognitive impairment (CI) consistent with dementia in the United States in 1993 to 1995 and 2002 to 2004. METHODS: We used data from the Health and Retirement Study (HRS), a nationally representative population-based longitudinal survey of U.S. adults. Individuals aged 70 years or older from the 1993 (N = 7,406) and 2002 (N = 7,104) waves of the HRS were included. CI was determined by using a 35-point cognitive scale for self-respondents and assessments of memory and judgment for respondents represented by a proxy. Mortality was ascertained with HRS data verified by the National Death Index. RESULTS: In 1993, 12.2% of those aged 70 or older had CI compared with 8.7% in 2002 (P < .001). CI was associated with a significantly higher risk of 2-year mortality in both years. The risk of death for those with moderate/severe CI was greater in 2002 compared with 1993 (unadjusted hazard ratio, 4.12 in 2002 vs 3.36 in 1993; P = .08; age- and sex-adjusted hazard ratio, 3.11 in 2002 vs 2.53 in 1993; P = .09). Education was protective against CI, but among those with CI, more education was associated with higher 2-year mortality. CONCLUSIONS: These findings support the hypothesis of a compression of cognitive morbidity between 1993 and 2004, with fewer older Americans reaching a threshold of significant CI and a more rapid decline to death among those who did. Societal investment in building and maintaining cognitive reserve through formal education in childhood and continued cognitive stimulation during work and leisure in adulthood might help limit the burden of dementia among the growing number of older adults worldwide.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Female; Humans; Male; Neurology; Prevalence; Quality of Life; Socioeconomic factors; United States

Using subjective expectations to forecast longevity: do survey respondents know something we don't know? - Maria Perozek (Demography, 2008)
Old-age mortality is notoriously difficult to predict because it requires not only an understanding of the process of senescence-which is influenced by genetic, environmental, and behavioral factors-but also a prediction of how these factors will evolve. In this paper I argue that individuals are uniquely qualified to predict their own mortality based on their own genetic background, as well as environmental and behavioral risk factors that are often known only to the individual. Given this private information, individuals form expectations about survival probabilities that may provide additional information to demographers and policymakers in their challenge to predict mortality. From expectations data from the 1992 Health and Retirement Study (HRS), I construct subjective, cohort life tables that are shown to predict the unusual direction of revisions to U.S. life expectancy by gender between 1992 and 2004: that is, for these cohorts, the Social Security Actuary (SSA) raised male life expectancy in 2004 and at the same lowered female life expectancy, narrowing the gender gap in longevity by 25% over this period. Further, although the subjective life expectancies for men appear to be roughly in line with the 2004 life tables, the subjective expectations of women suggest that female life expectancies estimated by the SSA might still be on the high side.
Keywords: Aged; Aged, 80 and over; Aging; Data collection; Demography; Female; health policy; Humans; Life Expectancy; Life Tables; Longevity; Male; Middle Aged; Mortality; Risk Factors; Sex Factors; United States

Age group differences in depressive symptoms among older adults with functional impairments. - Namkee G Choi; Kim, Johnny S. (Health Soc Work, 2007)
This study used data from the 2000 interview wave of the Health and Retirement Study to examine age group differences in the likelihood of self-reported depressive symptomatology among a nationally representative sample of 3,035 adults age 55 years or older who had at least one activities of daily living (ADL) or instrumental activities of daily living (IADL) limitation. Depression was defined as scoring three points or higher on the eight-point Center for Epidemiological Studies Depression Scale. The results show that respondents age 75 years or older with one ADL/IADL impairment or more were significantly less likely to be depressed than were those between ages 55 and 64 with the same degree of functional impairment. It is recommended that doctors, social workers, and other health care and social services providers pay special attention to younger old adults with health problems and functional limitations because they have a greater risk of being depressed.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Demography; depression; Disabled Persons; Female; Health Status; Humans; Interviews as Topic; Logistic Models; Male; Middle Aged; United States

All in the family: the impact of caring for grandchildren on grandparents' health. - Mary Elizabeth Hughes; Linda J. Waite; Tracey A. LaPierre; Ye Luo (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVES: The purpose of this study was to examine the effects of caring for grandchildren on health behaviors and mental and physical health among older adults. METHODS: Using a sample of 12,872 grandparents aged 50 through 80 from the Health and Retirement Study, we examined the relationship between stability and change in various types of grandchild care and subsequent health, controlling for covariates and earlier health. RESULTS: We found no evidence to suggest that caring for grandchildren has dramatic and widespread negative effects on grandparents' health and health behavior. We found limited evidence that grandmothers caring for grandchildren in skipped-generation households are more likely to experience negative changes in health behavior, depression, and self-rated health. We also found some evidence of benefits to grandmothers who babysit. DISCUSSION: Our findings suggest that the health disadvantages found previously among grandparent caregivers arise from grandparents' prior characteristics, not as a consequence of providing care. Health declines as a consequence of grandchild care appear to be the exception rather than the rule. These findings are important given continuing reliance on grandparents for day care and increasing reliance on grandparents for custodial care. However, the findings should be tempered by the recognition that for a minority of grandparents, coresidential grandchild care may compromise health.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Aging; Caregivers; Child Care; Child, Preschool; Family Relations; Female; Health Status; Humans; Intergenerational Relations; Male; Middle Aged; Parenting; Risk Assessment; Stress, Psychological

Baseline health, socioeconomic status, and 10-year mortality among older middle-aged Americans: findings from the Health and Retirement Study, 1992 2002. - Joseph Feinglass; Lin, Suru; Jason A. Thompson; Joseph J Sudano; Dorothy D Dunlop; Song, Jing; David W. Baker (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVE: This study analyzed whether socioeconomic status in older middle age continues to be associated with 10-year survival after data are controlled for baseline health status. METHODS: We confirmed deaths through 2002 for 9,759 participants in the Health and Retirement Study, aged 51 to 61 in 1992. We used discrete time survival models to examine hazard ratios over 10 years of follow-up. We examined associations of demographic characteristics and socioeconomic status measures before and after adjustment by health status and behavioral risk factors. RESULT: The 10-year mortality rate was 10.9%, ranging from 4.7% for respondents reporting excellent health to 35.8% for those reporting poor health at baseline. Lower levels of education, income, and wealth were strongly associated with higher mortality risk after we controlled for just demographic characteristics. After further adjustment for health status and behavioral risk factors, only household income remained significant. DISCUSSION: Baseline health by age 50 is an important pathway in the association between midlife socioeconomic status and mortality risk to age 70. The continuing effect of low household income on mortality risk was concentrated among respondents reporting excellent to good health at baseline. Socioeconomic disparities in middle-age health continue to limit disability-free life expectancy at older ages.
Keywords: Adult; Aged; Aged, 80 and over; Economics; Education; Follow-Up Studies; Health Status; Humans; Income; Middle Aged; Mortality; Motor Activity; Pilot Projects; Proportional Hazards Models; Retirement; Risk Factors; Risk-Taking; Smoking; Social Class; Thinness; United States

Change in depression of spousal caregivers of dementia patients following patient's death. - Tweedy, Maureen P.; Charles A Guarnaccia (Omega (Westport), 2007)
Caring for an elderly spouse with dementia places a heavy burden on spousal caregivers and often results in chronic depression. Little has been written about change in depression caregivers experience from before to after the death of the spouse with dementia. This longitudinal study examines change in depression of spousal caregivers that occurs following death of the dementia patient. Two theoretical models, the Relief and Stress Models, are discussed in terms of caregiver depression after the death of the dementia-patient care-recipient spouse. These two theoretical models were tested using longitudinal data from the National Institute on Aging sponsored Health and Retirement Study. Both male and female spousal caregivers report an increase in depression after the death of the dementia-patient care-recipient spouse. As time passed following the spouse's death, the conjugally bereaved husbands showed a decrease in depression while the conjugally bereaved wives continued to report increased depression.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Bereavement; Caregivers; Dementia; depression; Female; Humans; Life Change Events; Long-term Care; Longitudinal Studies; Male; Sex Factors; Spouses; Surveys and Questionnaires; United States

Childhood social and economic well-being and health in older age. - Sandra Y. Moody-Ayers; Lindquist, Karla; Sen, Saunak; Kenneth E Covinsky (Am J Epidemiol, 2007)
Childhood socioeconomic status (SES) acts over a lifetime to influence adult health outcomes. Whether the impact of childhood SES differs by age or race/ethnicity is unclear. The authors studied 20,566 community-living US adults aged > or =50 years. Parental education was the main predictor. Outcomes evaluated (1998-2002) included self-reported health and functional limitation. The influence of childhood SES on later-life health was also examined in groups stratified by age and race/ethnicity, with adjustment for demographic factors and current SES. Participants' mean age was 67 years; 57% were women. By race/ethnicity, 76% were White, 14% were Black, and 8% were Latino. The relation between low parental education and fair/poor self-rated health declined with advancing age (age 50-64 years: adjusted odds ratio (AOR) = 1.42, 95% confidence interval (CI): 1.24, 1.63; age > or =80 years: AOR = 1.14, 95% CI: 0.96, 1.36). The relation between low parental education and fair/poor self-rated health differed across racial/ethnic groups and was significant in White (AOR = 1.33, 95% CI: 1.21, 1.47) and Black (AOR = 1.37, 95% CI: 1.14, 1.64) participants but not Latinos. These findings suggest that childhood SES affects health status through midlife but the effects may abate in late life; its effects also may be weaker in Latinos than in Whites or Blacks.
Keywords: Aged; Aged, 80 and over; Black or African American; Child; Confidence Intervals; Educational Status; Female; Frail Elderly; Health Status; Health Status Indicators; Hispanic or Latino; Humans; Male; Middle Aged; Mobility Limitation; Odds Ratio; Poverty; Retrospective Studies; Sampling Studies; San Francisco; Socioeconomic factors; Surveys and Questionnaires; White People

Educational disparities in the prevalence and consequence of physical vulnerability. - Daniel O. Clark; Timothy E. Stump; Douglas K Miller; Long, J. Scott (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVES: The purpose of this study was to estimate educational differences in the prevalence and mortality consequence of physical vulnerability among older adults in the United States. METHODS: Data came from the 1998 and 2000 waves of the Health and Retirement Study, a nationally representative cross-sectional and prospective cohort study of community-based adults aged 65 and older. We created a physical vulnerability score from age, gender, and self-reported disability measures and measured socioeconomic status via educational attainment. Mortality data came from the National Death Index. RESULTS: In the 1998 cohort, high physical vulnerability was more than 3 times more prevalent in individuals with less than 12 years of education compared to those with 16 or more years of education. Although less educated older adults had a higher probability of death overall, evidence of educational differences in the mortality consequence of high physical vulnerability was limited. In 2000, 2.16 million older adults had high physical vulnerability, and more than one half (53%) of these adults had less than 12 years of education. DISCUSSION: In persons 65 years of age or older, educational differences are more apparent in the prevalence of physical vulnerability than in the mortality consequence of that vulnerability.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Cohort Studies; Cross-Sectional Studies; Educational Status; Female; Geriatric Assessment; Health Surveys; Humans; Male; Mobility Limitation; Risk Factors; Socioeconomic factors; Survival Analysis; United States

Exploring the association of dual use of the VHA and Medicare with mortality: separating the contributions of inpatient and outpatient services. - Frederic D Wolinsky; An, Hyonggin; Li Liu; Thomas R Miller; Gary E Rosenthal (BMC Health Serv Res, 2007)
BACKGROUND: Older veterans may use both the Veterans Health Administration (VHA) and Medicare, but the association of dual use with health outcomes is unclear. We examined the association of indirect measures of dual use with mortality. METHODS: Our secondary analysis used survey, claims, and National Death Index data from the Survey on Assets and Health Dynamics among the Oldest Old. The analytic sample included 1,521 men who were Medicare beneficiaries. Veterans were classified as dual users when their self-reported number of hospital episodes or physician visits exceeded that in their Medicare claims. Veterans reporting inpatient or outpatient visits but having no Medicare claims were classified as VHA-only users. Proportional hazards regression was used. RESULTS: 897 (59%) of the men were veterans, of whom 134 (15%) were dual users. Among dual users, 60 (45%) met the criterion based on inpatient services, 54 (40%) based on outpatient services, and 20 (15%) based on both. 766 men (50%) died. Adjusting for covariates, the independent effect of any dual use was a 38% increased mortality risk (AHR = 1.38; p = .02). Dual use based on outpatient services marginally increased mortality risk by 45% (AHR = 1.45; p = .06), and dual use based on both inpatient and outpatient services increased the risk by 98% (AHR = 1.98; p = .02). CONCLUSION: Indirect measures of dual use were associated with increased mortality risk. New strategies to better coordinate care, such as shared medical records, should be considered.
Keywords: Aged; Aged, 80 and over; Ambulatory Care; Cluster Analysis; Continuity of Patient Care; Emergency Service, Hospital; Episode of Care; Hospital Mortality; Hospitals, Veterans; Humans; Male; Medicare; Proportional Hazards Models; United States; Veterans

Geriatric conditions and disability: the Health and Retirement Study. - Christine T Cigolle; Kenneth M. Langa; Mohammed U Kabeto; Zhiyi Tian; Caroline S Blaum (Ann Intern Med, 2007)
BACKGROUND: Geriatric conditions, such as incontinence and falling, are not part of the traditional disease model of medicine and may be overlooked in the care of older adults. The prevalence of geriatric conditions and their effect on health and disability in older adults has not been investigated in population-based samples. OBJECTIVE: To investigate the prevalence of geriatric conditions and their association with dependency in activities of daily living by using nationally representative data. DESIGN: Cross-sectional analysis. SETTING: Health and Retirement Study survey administered in 2000. PARTICIPANTS: Adults age 65 years or older (n = 11 093, representing 34.5 million older Americans) living in the community and in nursing homes. MEASUREMENTS: Geriatric conditions (cognitive impairment, falls, incontinence, low body mass index, dizziness, vision impairment, hearing impairment) and dependency in activities of daily living (bathing, dressing, eating, transferring, toileting). RESULTS: Of adults age 65 years or older, 49.9% had 1 or more geriatric conditions. Some conditions were as prevalent as common chronic diseases, such as heart disease and diabetes. The association between geriatric conditions and dependency in activities of daily living was strong and significant, even after adjustment for demographic characteristics and chronic diseases (adjusted risk ratio, 2.1 [95% CI, 1.9 to 2.4] for 1 geriatric condition, 3.6 [CI, 3.1 to 4.1] for 2 conditions, and 6.6 [CI, 5.6 to 7.6] for > or =3 conditions). LIMITATIONS: The study was cross-sectional and based on self-reported data. Because measures were limited by the survey questions, important conditions, such as delirium and frailty, were not assessed. Survival biases may influence the estimates. CONCLUSIONS: Geriatric conditions are similar in prevalence to chronic diseases in older adults and in some cases are as strongly associated with disability. The findings suggest that geriatric conditions, although not a target of current models of health care, are important to the health and function of older adults and should be addressed in their care.
Keywords: Accidental Falls; Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Body Mass Index; Chronic disease; Cognition Disorders; Comorbidity; Cross-Sectional Studies; Disability Evaluation; Dizziness; Female; Geriatric Assessment; Geriatrics; Hearing Disorders; Humans; Male; Prevalence; Retirement; Urinary incontinence; Vision Disorders

Informal caregiving and Body Mass Index among older adults. - Kristi Rahrig Jenkins; Mohammed U Kabeto; Fultz, Nancy H.; Kenneth M. Langa (J Gerontol Nurs, 2007)
The authors sought to obtain nationally representative estimates of the time of informal caregiving provided to older adults classified into the four standard Body Mass Index (BMI) classifications. They estimated multivariate regression models using data from the 2000 Health and Retirement Study to determine the weekly hours of informal caregiving for older adults classified into the four standard BMI classifications. In the fully adjusted models, being underweight was associated with receiving significantly more informal care, however, obesity was not associated with more informal care. The implications of these findings are discussed in terms of nursing practice and research to prevent weight loss and frailty.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Body Mass Index; Body Weight; Caregivers; Female; Geriatric Assessment; Humans; Male; Social Class

An interpersonal continuity of care measure for Medicare Part B claims analyses. - Frederic D Wolinsky; Thomas R Miller; John F Geweke; Elizabeth A Chrischilles; An, Hyonggin; Robert B Wallace; Claire E Pavlik; Kara B Wright; Robert L. Ohsfeldt; Gary E Rosenthal (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVES: This article presents an interpersonal continuity of care measure. METHODS: We operationalized continuity of care as no more than an 8-month interval between any two visits during a 2-year period to either (a) the same primary care physician or (b) the same physician regardless of specialty. Sensitivity analyses evaluated two interval censoring algorithms and two alternative intervals. We linked Medicare Part A and B claims to baseline survey data for 4,596 respondents to the Survey on Asset and Health Dynamics Among the Oldest Old. We addressed the potential for selection bias by using propensity score methods, and we explored construct validity. RESULTS: Interpersonal continuity with a primary care physician was 17.3%, and interpersonal continuity of care with any physician was 26.1%. Older participants; men; individuals who lived alone; people who had difficulty walking; and respondents with medical histories of arthritis, cancer, diabetes, heart conditions, hypertension, and stroke were most likely to have continuity. Individuals who had never married, were widowed, were working, or had low subjective life expectancy were least likely to have continuity. DISCUSSION: Researchers can measure interpersonal continuity of care using Medicare Part B claims. Replication of these findings and further construct validation, however, are needed prior to widespread adoption of this method.
Keywords: Aged; Aged, 80 and over; Continuity of Patient Care; Disability Evaluation; Female; Health Services Accessibility; Health Surveys; Humans; Insurance Claim Review; Male; Medicare Part B; Mobility Limitation; Physician-Patient Relations; Primary Health Care; United States

Latent variable analyses of age trends of cognition in the Health and Retirement Study, 1992-2004. - John J McArdle; Gwenith G Fisher; Kelly M Kadlec (Psychol Aging, 2007)
The present study was conducted to better describe age trends in cognition among older adults in the longitudinal Health and Retirement Study (HRS) from 1992 to 2004 (N = 17,000). The authors used contemporary latent variable models to organize this information in terms of both cross-sectional and longitudinal inferences about age and cognition. Common factor analysis results yielded evidence for at least 2 common factors, labeled Episodic Memory and Mental Status, largely separable from vocabulary. Latent path models with these common factors were based on demographic characteristics. Multilevel models of factorial invariance over age indicated that at least 2 common factors were needed. Latent curve models of episodic memory were based on age at testing and showed substantial age differences and age changes, including impacts due to retesting as well as several time-invariant and time-varying predictors.
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Female; Health Surveys; Humans; Individuality; Longitudinal Studies; Male; Mental Recall; Mental Status Schedule; Middle Aged; Models, Statistical; Neuropsychological tests; Psychometrics; Retention, Psychology; Sex Factors; United States

Mechanisms for racial and ethnic disparities in glycemic control in middle-aged and older Americans in the health and retirement study. - Michele M Heisler; Jessica Faul; Rodney A. Hayward; Kenneth M. Langa; Caroline S Blaum; David R Weir (Arch Intern Med, 2007)
BACKGROUND: Mechanisms for racial/ethnic disparities in glycemic control are poorly understood. METHODS: A nationally representative sample of 1901 respondents 55 years or older with diabetes mellitus completed a mailed survey in 2003; 1233 respondents completed valid at-home hemoglobin A(1c) (HbA(1c)) kits. We constructed multivariate regression models with survey weights to examine racial/ethnic differences in HbA(1c) control and to explore the association of HbA(1c) level with sociodemographic and clinical factors, access to and quality of diabetes health care, and self-management behaviors and attitudes. RESULTS: There were no significant racial/ethnic differences in HbA(1c) levels in respondents not taking antihyperglycemic medications. In 1034 respondents taking medications, the mean HbA(1c) value (expressed as percentage of total hemoglobin) was 8.07% in black respondents and 8.14% in Latino respondents compared with 7.22% in white respondents (P < .001). Black respondents had worse medication adherence than white respondents, and Latino respondents had more diabetes-specific emotional distress (P < .001). Adjusting for hypothesized mechanisms accounted for 14.0% of the higher HbA(1c) levels in black respondents and 19.0% in Latinos, with the full model explaining 22.0% of the variance. Besides black and Latino ethnicity, only insulin use (P < .001), age younger than 65 years (P = .007), longer diabetes duration (P = .004), and lower self-reported medication adherence (P = .04) were independently associated with higher HbA(1c) levels. CONCLUSIONS: Latino and African American respondents had worse glycemic control than white respondents. Socioeconomic, clinical, health care, and self-management measures explained approximately a fifth of the HbA(1c) differences. One potentially modifiable factor for which there were racial disparities--medication adherence--was among the most significant independent predictors of glycemic control.
Keywords: Aged; Aged, 80 and over; Black People; Diabetes Mellitus; Female; Glycated Hemoglobin; Health Services Accessibility; Hispanic or Latino; Humans; Longitudinal Studies; Male; Middle Aged; Patient Compliance; Socioeconomic factors; Treatment Refusal; United States; White People

Pain in aging community-dwelling adults in the United States: non-Hispanic whites, non-Hispanic blacks, and Hispanics. - Reyes-Gibby, Cielito C.; Aday, Lu Ann; Todd, Knox H.; Cleeland, Charles S.; Anderson, Karen O. (J Pain, 2007)
UNLABELLED: Racial and ethnic disparities in healthcare persist in the U.S. Although pain is one of the most prevalent and disabling symptoms of disease, only a few studies have assessed disparities in pain in large racially and ethnically diverse, middle- to late aged community samples, thus limiting the generalizability of study findings in broader populations. With data from the 2000 Health and Retirement Study, we assessed the prevalence and impact of pain in a community sample of aging (> or =51 years old) non-Hispanic whites (n = 11,021), non-Hispanic blacks (n = 1,804), and Hispanics (n = 952) in the U.S. Pain, pain severity, activity limitation as a result of pain, comorbid conditions, and sociodemographic variables were assessed. Results showed that pain prevalence was 28%, and 17% of the sample reported activity limitation as a result of pain. Non-Hispanic blacks (odds ratio [OR], 1.78; 99% confidence interval [CI], 1.33-2.37) and Hispanics (OR, 1.80; 99% CI, 1.26-2.56) had higher risk for severe pain compared with non-Hispanic whites. Analyses of respondents with pain (n = 3,811) showed that having chronic diseases (2 comorbid conditions, OR, 1.5; 99% CI, 1.09-2.17), psychological distress (OR, 1.99; 99% CI, 1.54-2.43), being a Medicaid recipient (OR, 1.63; 99% CI, 1.17-2.25), and lower educational level (OR, 1.45; 99% CI, 1.14-1.85) were significant predictors for severe pain and helped to explain racial/ethnic differences in pain severity. PERSPECTIVE: This study, which used a large racially and ethnically diverse community sample, provided empirical evidence that racial/ethnic difference in pain severity in aging community adults in the U.S. can be accounted for by differential vulnerability in terms of chronic disease, socioeconomic conditions, and access to care.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Aging; Black People; Chronic disease; Data collection; ethnicity; Female; Hispanic or Latino; Humans; Insurance, Health; Logistic Models; Male; Middle Aged; pain; Pain Measurement; Population; Socioeconomic factors; United States; White People

Prevalence of dementia in the United States: the aging, demographics, and memory study. - Brenda L Plassman; Kenneth M. Langa; Gwenith G Fisher; Steven G Heeringa; David R Weir; Mary Beth Ofstedal; James R Burke; Michael D Hurd; Guy G Potter; Willard L Rodgers; David C Steffens; Robert J. Willis; et al. (Neuroepidemiology, 2007)
AIM: To estimate the prevalence of Alzheimer's disease (AD) and other dementias in the USA using a nationally representative sample. METHODS: The Aging, Demographics, and Memory Study sample was composed of 856 individuals aged 71 years and older from the nationally representative Health and Retirement Study (HRS) who were evaluated for dementia using a comprehensive in-home assessment. An expert consensus panel used this information to assign a diagnosis of normal cognition, cognitive impairment but not demented, or dementia (and dementia subtype). Using sampling weights derived from the HRS, we estimated the national prevalence of dementia, AD and vascular dementia by age and gender. RESULTS: The prevalence of dementia among individuals aged 71 and older was 13.9%, comprising about 3.4 million individuals in the USA in 2002. The corresponding values for AD were 9.7% and 2.4 million individuals. Dementia prevalence increased with age, from 5.0% of those aged 71-79 years to 37.4% of those aged 90 and older. CONCLUSIONS: Dementia prevalence estimates from this first nationally representative population-based study of dementia in the USA to include subjects from all regions of the country can provide essential information for effective planning for the impending healthcare needs of the large and increasing number of individuals at risk for dementia as our population ages.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cohort Studies; Dementia; Female; Geriatric Assessment; Health Surveys; Humans; Logistic Models; Male; Prevalence; Sex Distribution; United States

The relationship between self-rated health and mortality in older black and white Americans. - Sei J. Lee; Sandra Y. Moody-Ayers; C. Seth Landefeld; Louise C Walter; Lindquist, Karla; Mark Segal; Kenneth E Covinsky (J Am Geriatr Soc, 2007)
OBJECTIVES: To determine whether the association between self-rated health (SRH) and 4-year mortality differs between black and white Americans and whether education affects this relationship. DESIGN: Prospective cohort. SETTING: Communities in the United States. PARTICIPANTS: Sixteen thousand four hundred thirty-two subjects (14,004 white, 2,428 black) enrolled in the 1998 wave of the Health and Retirement Study (HRS), a population-based study of community-dwelling U.S. adults aged 50 and older. MEASUREMENTS: Subjects were asked to self-identify their race and their overall health by answering the question, "Would you say your health is excellent, very good, good, fair, or poor?" Death was determined according to the National Death Index. RESULTS: SRH is a much stronger predictor of mortality in whites than blacks (c-statistic 0.71 vs 0.62). In whites, poor SRH resulted in a markedly higher risk of mortality than excellent SRH (odds ratio (OR)=10.4, 95% confidence interval (CI)=8.0-13.6). In blacks, poor RSH resulted in a much smaller increased risk of mortality (OR=2.9, 95% CI=1.5-5.5). SRH was a stronger predictor of death in white and black subjects with higher levels of education, but differences in education could not account for the observed race differences in the prognostic effect of SRH. CONCLUSION: This population-based study found that the relationship between SRH and mortality is stronger in white Americans and in subjects with higher levels of education. Because the association between SRH and mortality appears weakest in traditionally disadvantaged groups, SRH may not be the best measure to identify vulnerable older subjects.
Keywords: Age Distribution; Aged; Aged, 80 and over; Black People; Educational Status; Female; Health Status; Humans; Male; Middle Aged; Mortality; Population Surveillance; Prognosis; Self Disclosure; Sex Distribution; United States; White People

Risk of nursing home admission among older americans: does states' spending on home- and community-based services matter? - Muramatsu, Naoko; yin, Hongjun; Richard T. Campbell; Ruby L Hoyem; Martha A. Jacob; Christopher Ross (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVE: States vary greatly in their support for home- and community-based services (HCBS) that are intended to help disabled seniors live in the community. This article examines how states' generosity in providing HCBS affects the risk of nursing home admission among older Americans and how family availability moderates such effects. METHODS: We conducted discrete time survival analysis of first long-term (90 or more days) nursing home admissions that occurred between 1995 and 2002, using Health and Retirement Study panel data from respondents born in 1923 or earlier. RESULT: State HCBS effects were conditional on child availability among older Americans. Living in a state with higher HCBS expenditures was associated with lower risk of nursing home admission among childless seniors (p <.001). However, the association was not statistically significant among seniors with living children. Doubling state HCBS expenditures per person aged 65 or older would reduce the risk of nursing home admission among childless seniors by 35%. DISCUSSION: Results provided modest but important evidence supportive of increasing state investment in HCBS. Within-state allocation of HCBS resources, however, requires further research and careful consideration about fairness for individual seniors and their families as well as cost effectiveness.
Keywords: Aged; Aged, 80 and over; Caregivers; Cohort Studies; Cost Savings; Cost-Benefit Analysis; Female; Financing, Government; Health Expenditures; Home Care Services; Homes for the Aged; Humans; Insurance Coverage; Long-term Care; Male; Medicaid; Medicare; Nursing homes; Patient Admission; Patient Readmission; Risk Assessment; Risk Factors; State Health Plans; United States

Self-rated health trajectories and mortality among older adults. - Thomas R Miller; Frederic D Wolinsky (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVES: For this article, we evaluated whether measures of prior self-rated health (SRH) trajectories had associations with subsequent mortality that were independent of current SRH assessment and other covariates. METHODS: We used multivariable logistic regression that incorporated four waves of interview data (1993, 1995, 1998, and 2000) from the Asset and Health Dynamics Among the Oldest Old Survey in order to predict mortality during 2000-2002. We defined prior SRH trajectories for each individual based on the slope estimated from a simple linear regression of their own SRH between 1993 and 1998 and the variance around that slope. In addition to SRH reported in 2000, other covariates included in the mortality models reflected health status, health-related behaviors, and individual resources. RESULTS: Among the 3,129 respondents in the analytic sample, SRH in 2000 was significantly (p <.0001) associated with mortality, but the measures of prior SRH trajectories were not. Prior SRH trajectory was, however, a significant determinant of current SRH. We observed significant independent associations with mortality for age, sex, education, lung disease, and having ever smoked. DISCUSSION: Although measures of prior SRH trajectories did not have significant direct associations with mortality, they did have important indirect effects via their influence on current SRH.
Keywords: Age Factors; Aged; Aged, 80 and over; Attitude to Health; Cardiovascular Diseases; Cause of Death; Female; Follow-Up Studies; Health Status; Health Status Indicators; Humans; Logistic Models; Longitudinal Studies; Lung Diseases; Male; Mortality; Multivariate Analysis; Risk Factors; Sex Factors; Smoking; Socioeconomic factors; Survival Analysis; United States

Urban neighborhoods and depressive symptoms among older adults. - Carol S Aneshensel; Richard G Wight; Miller-Martinez, Dana; Amanda L. Botticello; Arun S Karlamangla; Teresa Seeman (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVE: This study seeks to determine whether depressive symptoms among older persons systematically vary across urban neighborhoods such that experiencing more symptoms is associated with low socioeconomic status (SES), high concentrations of ethnic minorities, low residential stability and low proportion aged 65 years and older. METHODS: Survey data are from the Study of Assets and Health Dynamics Among the Oldest Old (AHEAD), a 1993 U.S. national probability sample of noninstitutionalized persons born in 1923 or earlier (i.e. people aged 70 or older). Neighborhood data are from the 1990 Census at the tract level. Hierarchical linear regression is used to estimate multilevel models. RESULT: The average number of depressive symptoms varies across Census tracts independent of individual-level characteristics. Symptoms are not significantly associated with neighborhood SES, ethnic composition, or age structure when individual-level characteristics are controlled statistically. However, net of individual-level characteristics, symptoms are positively associated with neighborhood residential stability, pointing to a complex meaning of residential stability for the older population. DISCUSSION: This study shows that apparent neighborhood-level socioeconomic effects on depressive symptoms among urban-dwelling older adults are largely if not entirely compositional in nature. Further, residential stability in the urban neighborhood may not be emotionally beneficial to its aged residents.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Comorbidity; Cross-Sectional Studies; Depressive Disorder; Female; Health Status Indicators; Health Surveys; Humans; Incidence; Male; Minority Groups; Peer Group; Population Dynamics; Risk Factors; Social Environment; United States; Urban Population

Weight and depressive symptoms in older adults: direction of influence? - Valerie L Forman-Hoffman; Jon W. Yankey; Stephen L Hillis; Robert B Wallace (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVE: . The purpose of this study was to clarify the direction of the relationship between changes in depressive symptoms and changes in weight in older adults. Methods. The sample included a prospective cohort of individuals aged 53-63 (n = 9,130) enrolled in the Health and Retirement Study. We used separate cross-lagged models for men and women in order to study the impact of weight change on subsequent increases in depressive symptoms 2 years later and vice versa. RESULT: . Weight gain did not lead to increased depressive symptoms, and weight loss preceded increased depressive symptoms only in unadjusted models among men (odds ratio [OR] = 1.26, 95% confidence interval [CI] = 1.04-1.53). Increased depressive symptoms were not predictive of subsequent weight loss, but they were predictive of subsequent weight gain in unadjusted models only (men: OR = 1.24, 95% CI = 1.00-1.54; women: OR = 1.12, 95% CI = 1.00-1.26). In adjusted models, baseline depressive symptoms predicted both weight loss and weight gain among both men and women. Increase in functional limitations and medical conditions were significant predictors of both weight loss and weight gain. Baseline functional limitations also predicted increased depressive symptoms. Discussion. Based on our findings, it is apparent that researchers need to examine the pathways between changes in weight and increases in depressive symptoms in the context of functional limitations and medical comorbidity.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Comorbidity; Depressive Disorder; Female; Health Status Indicators; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Odds Ratio; Prospective Studies; Sex Factors; Statistics as Topic; United States; Weight Gain; Weight Loss

Dual use of Medicare and the Veterans Health Administration: are there adverse health outcomes? - Frederic D Wolinsky; Thomas R Miller; An, Hyonggin; Paul R Brezinski; Thomas E Vaughn; Gary E Rosenthal (BMC Health Serv Res, 2006)
BACKGROUND: Millions of veterans are eligible to use the Veterans Health Administration (VHA) and Medicare because of their military service and age. This article examines whether an indirect measure of dual use based on inpatient services is associated with increased mortality risk. METHODS: Data on 1,566 self-responding men (weighted N = 1,522) from the Survey of Assets and Health Dynamics among the Oldest Old (AHEAD) were linked to Medicare claims and the National Death Index. Dual use was indirectly indicated when the self-reported number of hospital episodes in the 12 months prior to baseline was greater than that observed in the Medicare claims. The independent association of dual use with mortality was estimated using proportional hazards regression. RESULTS: 96 (11%) of the veterans were classified as dual users. 766 men (50.3%) had died by December 31, 2002, including 64.9% of the dual users and 49.3% of all others, for an attributable mortality risk of 15.6% (p < .003). Adjusting for demographics, socioeconomics, comorbidity, hospitalization status, and selection bias at baseline, as well as subsequent hospitalization for ambulatory care sensitive conditions, the independent effect of dual use was a 56.1% increased relative risk of mortality (AHR = 1.561; p = .009). CONCLUSION: An indirect measure of veterans' dual use of the VHA and Medicare systems, based on inpatient services, was associated with an increased risk of death. Further examination of dual use, especially in the outpatient setting, is needed, because dual inpatient and dual outpatient use may be different phenomena.
Keywords: Aged; Aged, 80 and over; Deductibles and Coinsurance; Episode of Care; Health Services Research; Hospitals, Veterans; Humans; Male; Medicare; Mortality; Outcome Assessment, Health Care; Proportional Hazards Models; Quality Indicators, Health Care; Risk Assessment; Selection Bias; Surveys and Questionnaires; United States; United States Department of Veterans Affairs; Veterans

Postretirement earnings relative to preretirement earnings: gender and racial differences. - Martha N. Ozawa; Hong, Baeg-Eui (J Gerontol Soc Work, 2006)
As the social security program comes under increasing financial pressure in the coming decades, the federal government will encourage elderly people to continue to work. Data from the Social Security Administration indicate that earnings are already a sizable component of retirement income. But there is public concern about how women and minorities will fare economically in this changing policy environment. To what extent can women and minorities keep earning money after they reach retirement age? This article presents the results of a study that investigated the postretirement earnings, relative to the preretirement earnings, of women and minorities, and compared the results with those for men and whites. The major finding, based on regression analyses, was that women's postretirement earnings, relative to their preretirement earnings, were greater than those of men. Furthermore, the regression results indicate that nonwhites' postretirement earnings could not be predicted by their preretirement earnings or by any of the independent variables used in the study, including age, gender, education, marital status, number of children, occupation, and preretirement earnings.
Using Smart Source Parsing pp. May Sage Publications, Thousand Oaks CA
Keywords: Age Factors; Aged; Aged, 80 and over; Data collection; Employment; Female; Humans; Income; Male; Men; Minority Groups; Pensions; Retirement; Salaries and Fringe Benefits; Sex Factors; Social Security; Time Factors; United States; White People; women

Retirement patterns from career employment. - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn (Gerontologist, 2006)
PURPOSE: This article investigates how older Americans leave their career jobs and estimates the extent of intermediate labor force activity (bridge jobs) between full-time work on a career job and complete labor-force withdrawal. DESIGN AND METHODS: Using data from the Health and Retirement Study, we explored the work histories and retirement patterns of a cohort of retirees aged 51 to 61 in 1992 during a 10-year period in both cross-sectional and longitudinal contexts. We examined determinants of retirement patterns in a multinomial logistic regression model. RESULTS: We found that a majority of older Americans with career jobs retire gradually, in stages, rather than all at once. We also found that the utilization of bridge jobs was more common among younger respondents, respondents without defined-benefit pension plans, and respondents at both the lower and upper ends of the wage distribution. IMPLICATIONS: Older Americans are now working longer than pre-1980s trends would have predicted. Given concerns about the traditional sources of retirement income (Social Security, employer pensions, and prior savings), older Americans may have to rely more on earnings. This article suggests that many are already doing so by moving to bridge jobs after leaving their career employment.
Keywords: Aged; Aged, 80 and over; Aging; Career Choice; Employment; Female; Health Status; Humans; Income; Male; Middle Aged; Pensions; Retirement; Social Security; United States

The tide to come: elderly health in Latin America and the Caribbean. - Alberto Palloni; Mary McEniry; Rebeca Wong; Pelaez, M. (J Aging Health, 2006)
This article introduces a conjecture and reviews partial evidence about peculiarities in the aging of populations in Latin America and the Caribbean (LAC) that may impact future elderly health status. Using Survey on Health and Well-Being of Elders data (SABE; n = 10,902), the authors estimated effects of early childhood conditions on adult diabetes and heart disease. Using Waaler-type surfaces, the authors obtained expected mortality risks for SABE and also U.S. elderly (Health and Retirement System, n = 12,527). Expected mortality risks using Waaler-type surfaces among elderly in LAC reflected excesses supporting our conjecture. There was partial evidence of a relation between various indicators of early childhood nutritional status (knee height, waist-to-hip ratio) and diabetes and even stronger evidence of a relation between rheumatic fever and adult heart disease. There is some evidence, albeit weak, to suggest that the conjecture regarding elderly health status' connection to early conditions has some merit.
Article English
Keywords: Aged; Aged, 80 and over; Caribbean Region; Child; Diabetes Mellitus; Forecasting; Health Status; Heart Diseases; Humans; Latin America; Malnutrition; Middle Aged; Mortality; Nutritional Status; United States

Urban neighborhood context, educational attainment, and cognitive function among older adults. - Richard G Wight; Carol S Aneshensel; Miller-Martinez, Dana; Amanda L. Botticello; Janet R. Cummings; Arun S Karlamangla; Teresa Seeman (Am J Epidemiol, 2006)
Existing research has not addressed the potential impact of neighborhood context--educational attainment of neighbors in particular--on individual-level cognition among older adults. Using hierarchical linear modeling, the authors analyzed data from the 1993 Study of Assets and Health Dynamics Among the Oldest Old (AHEAD), a large, nationally representative sample of US adults born before 1924. Data from participants residing in urban neighborhoods (n = 3,442) were linked with 1990 US Census tract data. Findings indicate that 1) average cognitive function varies significantly across US Census tracts; 2) older adults living in low-education areas fare less well cognitively than those living in high-education areas, net of individual characteristics, including their own education; 3) this association is sustained when controlling for contextual-level median household income; and 4) the effect of individual-level educational attainment differs across neighborhoods of varying educational profiles. Promoting educational attainment among the general population living in disadvantaged neighborhoods may prove cognitively beneficial to its aging residents because it may lead to meliorations in stressful life conditions and coping deficiencies.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cognition Disorders; Educational Status; Female; Humans; Linear Models; Male; Residence Characteristics; Risk Factors; Socioeconomic factors; United States; Urban Population

The validation of the Texas revised inventory of grief on an older Latino sample. - Wilson, Steve (J Soc Work End Life Palliat Care, 2006)
PURPOSE: Bereavement is considered to be one of the most profound experiences in older adulthood. However, assessments of emotional reactions to grief and loss have often been based on measures tested on primarily Anglo samples. This study examined the validity and factor structure of a commonly used bereavement measure on an older Latino sample. DESIGN AND METHODS: Using convergent and discriminant validation procedures, this instrument was tested using a purposive sample of 134 older, recently bereaved Latinos. RESULTS: While the instrument was originally designed to measure two domains of grief: Past Behaviors and Present Feelings, confirmatory and exploratory factor analysis revealed a three-factor solution for this sample which included also Disbelief of the loss. Items within this domain included anger, rejection, and a sense of injustice. IMPLICATIONS: This study underscores the need for improved measures in research on grief and bereavement to capture the intensity and severity of grief in a cross-cultural context.
Keywords: Aged; Aged, 80 and over; Bereavement; Culture; Factor Analysis, Statistical; Female; Grief; Hispanic or Latino; Humans; Male; Middle Aged; Psychometrics; Reproducibility of Results; Socioeconomic factors; Surveys and Questionnaires; Texas

Disparities among older adults in measures of cognitive function by race or ethnicity. - Frank A Sloan; Wang, Jingshu (J Gerontol B Psychol Sci Soc Sci, 2005)
This study examined racial or ethnic differences in cognitive function, cross-sectionally and longitudinally, using survey data from the Asset and Health Dynamics Among the Oldest Old. A version of the Telephone Interview for Cognitive Status (TICS), proxy assessments of cognition, and difficulties in performing daily tasks were assessed. Blacks performed below Whites on the TICS at baseline and on proxy assessments of cognition. TICS score declined with age for Whites and Blacks, with some relative gains for Blacks. At baseline, Blacks more often had difficulties in performing daily tasks, with some increase in difficulties relative to Whites with age. Differences between other groups and Whites were smaller than those between Blacks and Whites.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Black or African American; Case-Control Studies; Cognition; Cognition Disorders; Cross-Sectional Studies; Female; Hispanic or Latino; Humans; Linear Models; Longitudinal Studies; Male; Racial Groups; United States

Functional impairment as a risk factor for urinary incontinence among older Americans. - Kristi Rahrig Jenkins; Fultz, Nancy H. (Neurourol Urodyn, 2005)
AIMS: Using a large nationally representative sample of older Americans we investigate four domains of functional impairment as possible risk factors for the subsequent development of urinary incontinence (UI) symptoms. METHODS: Data from three waves (1993, 1995, 1998) of the Asset and Health Dynamics among the Oldest Old (AHEAD) survey were used to model the effects of functional impairment on the onset of UI symptoms. RESULTS: A greater number of serious chronic conditions and functional impairment in the lower body mobility domain increased the odds of the onset of mild UI (vs. remaining continent). Factors that contributed to greater odds of the onset of severe UI (vs. remaining continent) were older age, being represented by a proxy respondent, and functional impairment in the strength domain. CONCLUSIONS: Understanding the possible relationship between functional impairment and UI is an important step toward developing appropriate interventions for the prevention, treatment, or management of urine loss.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Disability Evaluation; Female; Humans; Longitudinal Studies; Male; Motor Activity; Risk Factors; Socioeconomic factors; Urinary incontinence

Net worth predicts symptom burden at the end of life. - Maria J Silveira; Mohammed U Kabeto; Kenneth M. Langa (J Palliat Med, 2005)
OBJECTIVES: To explore the predictors of symptom burden at the end of life. DESIGN: Observational, secondary analysis of Health and Retirement Study (HRS) data. SETTING: USA. PARTICIPANTS: Two thousand six hundred four deceased, older adults. METHODS: Multivariate Poisson and logistic regression to explore the relationship between sociodemographic and clinical factors with symptoms. RESULTS: Fatigue, pain, dyspnea, depression, and anorexia were common and severe; 58% of participants experienced more than 3 of these during their last year of life. Sociodemographic and clinical factors were associated with the number of symptoms as well as the presence of pain, depression, and dyspnea alone. Decedents in the highest quartile of net worth had fewer symptoms (incident rate ratio [IRR] 0.90, confidence interval [CI] 0.85-0.96) and less pain (odds ratio [OR] 0.66, CI 0.51-0.85) than comparisons did. Patients with cancer experienced more pain (OR 2.02, CI 1.62-2.53) and depression (OR 1.31, CI 1.07-1.61). Patients experienced more depression (OR 2.37, CI 1.85-3.03) and dyspnea (OR 1.40, CI 1.09-1.78). LIMITATION: Use of proxy reports for primary data. CONCLUSION: Older Americans experience a large symptom burden in the last year of life, largely with treatable symptoms such as pain, dyspnea, and depression. The adequacy of symptom control relates to clinical factors as well as net worth. This association between symptoms and wealth suggests that access to health care and other social services beyond those covered by Medicare may be important in decreasing symptom burden at the end of life.
Keywords: Aged; Aged, 80 and over; Data collection; Female; Humans; Logistic Models; Male; Severity of Illness Index; Social Class; Terminally Ill; United States

Physical and mental health status of older long-term cancer survivors. - Nancy L. Keating; Norredam, Marie; Landrum, Mary Beth; Haiden A. Huskamp; Meara, Ellen (J Am Geriatr Soc, 2005)
OBJECTIVES: To assess the physical and mental health status of older long-term cancer survivors. DESIGN: Cohort study using propensity score methods to control for baseline differences between cancer survivors and controls. SETTING: General community population in the United States. PARTICIPANTS: Nine hundred sixty-four cancer patients who had survived for more than 4 years and 14,333 control patients who had never had cancer from a population-based sample of Americans aged 55 and older responding to the 2002 Health and Retirement Study. MEASUREMENTS: Medical conditions, symptoms, health behaviors, health status, mobility, activities of daily living, mental health diagnoses, self-rated memory, depressive symptoms, cognitive function, and self-reported life expectancy. RESULTS: Cancer survivors reported higher rates of lung disease (13.9% vs 9.6%; P=.001), heart condition (29.3% vs 22.9%; P<.001), arthritis (69.4% vs 59.4%; P<.001), incontinence (26.6% vs 19.7%; P=.001), frequent pain (36.4% vs 29.4%; P=.005), and obesity (27.0% vs 24.2%; P=.001) than individuals without cancer but lower rates of smoking (12.0% vs 14.8%; P=.03). Cancer survivors were less likely than persons without cancer to report excellent or very good health status (37.2% vs 44.6%; P<.001) and had more mobility (P<.001) and activity of daily living (P=.01) limitations. Cancer survivors did not differ from persons without cancer in rates of depression or cognitive function (both P>.2) but were less optimistic about their life expectancy (P=.004). CONCLUSION: The physical health status of older long-term cancer survivors is somewhat worse than that of comparable persons who have never had cancer, but they have surprisingly similar mental health status. Future research is needed to understand factors contributing to poorer health status and identify patients at highest risk of long-term cancer-related problems.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Chronic disease; Cohort Studies; Female; Health Behavior; Health Status; Humans; Logistic Models; Male; Mental Health; Middle Aged; Neoplasms; Survivors; United States

Setting eligibility criteria for a care-coordination benefit. - Christine T Cigolle; Kenneth M. Langa; Mohammed U Kabeto; Caroline S Blaum (J Am Geriatr Soc, 2005)
OBJECTIVES: To examine different clinically relevant eligibility criteria sets to determine how they differ in numbers and characteristics of individuals served. DESIGN: Cross-sectional analysis of the 2000 wave of the Health and Retirement Study (HRS), a nationally representative longitudinal health interview survey of adults aged 50 and older. SETTING: Population-based cohort of community-dwelling older adults, subset of an ongoing longitudinal health interview survey. PARTICIPANTS: Adults aged 65 and older who were respondents in the 2000 wave of the HRS (n=10,640, representing approximately 33.6 million Medicare beneficiaries). MEASUREMENTS: Three clinical criteria sets were examined that included different combinations of medical conditions, cognitive impairment, and activity of daily living/instrumental activity of daily living (ADL/IADL) dependency. RESULTS: A small portion of Medicare beneficiaries (1.3-5.8%) would be eligible for care coordination, depending on the criteria set chosen. A criteria set recently proposed by Congress (at least four severe complex medical conditions and one ADL or IADL dependency) would apply to 427,000 adults aged 65 and older in the United States. Criteria emphasizing cognitive impairment would serve an older population. CONCLUSION: Several criteria sets for a Medicare care-coordination benefit are clinically reasonable, but different definitions of eligibility would serve different numbers and population groups of older adults.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Case Management; Chronic disease; Cognition Disorders; Comorbidity; Cross-Sectional Studies; Disability Evaluation; Disease Management; Eligibility Determination; Female; Geriatric Assessment; Health Surveys; Humans; Longitudinal Studies; Male; Medicare; Middle Aged; Retirement; United States

Supplemental private health insurance and depressive symptoms in older married couples. - Min, Meeyoung O.; Aloen L. Townsend; Baila Miller; Rovine, Michael J. (Int J Aging Hum Dev, 2005)
Stress process theory is applied to examine lack of supplemental private health insurance as a risk factor for depressive symptomatology among older married couples covered by Medicare. Dyadic data from 130 African-American couples and 1,429 White couples in the 1993 Asset and Health Dynamics Among the Oldest-Old Survey were analyzed using hierarchical generalized linear modeling. Lack of supplemental insurance is operationalized at the household level in terms of neither spouse covered, one spouse covered, or both spouses covered. Controlling for covariates at both individual and couple levels, supplemental insurance has significant impact on depression, but the pattern differs by race. White couples report the highest depression when neither spouse is covered by private health insurance; African-American couples report the highest depression when only one spouse is covered. Results suggest lack of supplemental private health insurance coverage is a stressor that significantly affects depressive symptoms.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Black People; Chi-Square Distribution; depression; Female; Humans; Insurance Coverage; Insurance, Health; Linear Models; Male; Risk Factors; Spouses; United States; White People

A variables associated with occupational and physical therapy stroke rehabilitation utilization and outcomes. - Chad Cook; Stickley, Lois; Ramey, Kevin; Knotts, Valerie J. (J Allied Health, 2005)
Many studies have reported the benefits of a comprehensive stroke team including occupational therapy/physical therapy (OT/PT) services; however, factors associated with access to these services are less known. This study used a subsample of the Health and Retirement Study database, a cross-sectional survey of more than 11,126 Americans aged 65 to 106 years within the contiguous United States. The purposes of this study were to determine the associational factors that contribute to attending OT/PT and determine if attending OT/PT leads to a reduced report of stroke-related problems. The findings indicated that fewer than 10% of stroke survivors in a noninstitutionalized, community-based setting were currently accessing OT/PT. Additionally, access to OT/PT services was highly associated with report of having an attending physician, report of stroke-related weakness, higher monthly income, and older age. The increased odds of reported continued problems associated with a past stroke were associated with failure to access OT/PT services, lower monthly income, Hispanic culture, and age. OT/PT services were typically provided to patients who reported a higher level of physical dysfunction. Despite the greater degree of severity, OT/PT intervention led to reports of lower levels of disability and problems over time.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Disability Evaluation; Female; Health Services Accessibility; Humans; Male; Occupational therapy; Physical Therapy Modalities; Risk Factors; Socioeconomic factors; Stroke Rehabilitation; United States

What is perfect health to an 85-year-old?: evidence for scale recalibration in subjective health ratings. - Peter A. Ubel; Jankovic, Aleksandra; Dylan M Smith; Kenneth M. Langa; Angela Fagerlin (Med Care, 2005)
BACKGROUND: If an 85-year-old man rates his health as 90 on a scale in which 100 represents "perfect health," would his rating mean the same thing as a 90 rating from a 25-year-old? We conducted a randomized trial of 3 different ways of eliciting subjective health ratings from participants in the Health and Retirement Study to test whether the meaning of perfect health changes as people age, causing people to recalibrate their self-reported health ratings to account for their age. METHODS: The Health and Retirement Study (HRS) is a nationally representative, prospective study of 22,000 persons born in 1947 or earlier. The data analyzed in this study come from the self-assessed health utilities module administered in 2002 to 1031 randomly selected HRS respondents. Respondents were randomized to receive one of 3 versions of a subjective health rating task. In the perfect health version, they were asked how they would rate their "current health on a scale from 0 to 100, in which 0 represents death and 100 represents perfect health." In the your-age version, the phrase "for someone your age" was added to the end of the question to encourage people to recalibrate their responses based on age, and in the 20-year-old version, the phrase "for a 20-year-old" was added to minimize recalibration. RESULTS: A total of 1015 subjects responded to the rating task (98% response rate). Health ratings varied significantly across versions, with subjects responding to the 20-year-old version reporting lower health (mean rating 66 of 100) than those responding to the your-age version (mean rating of 73, P<0.001) or the perfect health version (mean rating of 73, P<0.001). This result suggests that subjects interpret perfect health to mean "perfect health for someone your age." However, additional analysis showed that the interpretation of the phrase perfect health lies somewhere between the other 2 versions. For example, responses to the perfect health and 20-year-old versions varied significantly by respondent age (both P's<0.075), whereas responses to the your-age scale did not (P=0.8). CONCLUSION: The phrase "perfect health" is ambiguous, causing some people to recalibrate their responses based on their age. Such ambiguity threatens the validity of common subjective health ratings, thereby reducing the comparability of responses across people of different ages or different circumstances.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Analysis of Variance; Attitude to Health; Calibration; Female; Geriatric Assessment; Health Status; Humans; Interviews as Topic; Male; Prospective Studies; Psychometrics; Self Concept

The effect of equipment usage and residual task difficulty on use of personal assistance, days in bed, and nursing home placement. - Donald H. Taylor Jr.; Hoenig, H. (J Am Geriatr Soc, 2004)
OBJECTIVES: To determine whether residual difficulty in functioning in spite of equipment use is linked with increased use of personal assistance. DESIGN: Longitudinal. Two waves of the Asset and Health Dynamics Among the Oldest Old (AHEAD) database were used to test the effect of residual difficulty on hours of personal assistance and bed days at Wave 1 on hours of personal assistance, bed days, and nursing home placement at Waves 1 and 2. SETTING: A nationally representative setting of community-dwelling persons aged 70 and older and their spouses, regardless of age at Wave 1 AHEAD. There was movement of some respondents into nursing homes by the Wave 2 interview. PARTICIPANTS: Respondents to the AHEAD survey, N=8,222 at Wave 1. MEASUREMENTS: The dependent variables were hours of personal assistance in the month before the AHEAD survey (Waves 1 and 2), number of days in month before the survey in which the person did not get out of bed (Waves 1 and 2), and residence in a nursing home at Wave 2. The key explanatory variable was a mutually exclusive (four category) variable that specified whether there was residual difficulty (yes/no) in indoor mobility in spite of using equipment to aid specifically with indoor mobility. The four-category variable was defined by the four categories created by a cross-tabulation of equipment use (yes/no) and difficulty with indoor mobility (yes/no). A similar four-category variable was also defined for transferring in the home. RESULTS: In cross section, equipment users with residual difficulty reported more hours of personal assistance in the case of indoor mobility impairment and were more likely to have some hours of personal assistance than those without residual difficulty with indoor mobility and transferring. Longitudinally, those with residual difficulty at Wave 1 were more likely to need some personal assistance hours at Wave 2 (odds ratio=1.67, 95% confidence interval= 1.23-2.26 for indoor mobility). For transferring, those with residual difficulty had 43 more hours of personal assistance per month (P=.001) than those for whom equipment resolved their disability. Residual disability was linked to more bed days for users of indoor mobility and transferring equipment, but it was not predictive of nursing home placement by Wave 2. CONCLUSION: Equipment for indoor mobility or transfers apparently resolves difficulty for some users of the equipment but not for others. Residual task difficulty in spite of equipment for indoor mobility and transferring is linked with worse outcomes, including increased dependency on personal assistance and more days in bed. This shows that more attention is needed to determine whether equipment prescribed is appropriate for a patient's difficulty and that follow-up assessment is crucial after equipment is prescribed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Bed Rest; Cross-Sectional Studies; Disability Evaluation; Female; Homemaker Services; Humans; Least-Squares Analysis; Logistic Models; Longitudinal Studies; Male; Nursing homes; Risk Factors; Self-Help Devices

The effect of heavy drinking on social security old-age and survivors insurance contributions and benefits. - Ostermann, Jan; Frank A Sloan (Milbank Q, 2004)
This article estimates the effects of heavy alcohol consumption on Social Security Old-Age and Survivor Insurance (OASI) contributions and benefits. The analysis accounts for differential earnings and mortality experiences of individuals with different alcohol consumption patterns and controls for other characteristics, including smoking. Relative to moderate drinkers, heavy drinkers receive fewer OASI benefits relative to their contributions. Ironically, for each cohort of 25-year-olds, eliminating heavy drinking costs the program an additional $3 billion over the cohort's lifetime. Public health campaigns are designed to improve individual health-relevant behaviors and, in the long run, increase longevity. Therefore, if programs for the elderly are structured as longevity-independent defined benefit programs, their success will reward healthier behaviors but increase these programs' outlays and worsen their financial condition.
RDA 1996-024
Keywords: Accidents, Traffic; Adolescent; Adult; Aged; Aged, 80 and over; Alcoholism; Cost Sharing; Female; Health Behavior; Humans; Insurance Coverage; Life Expectancy; Male; Middle Aged; Old Age Assistance; Social Security; United States

The effect of smoking on years of healthy life (YHL) lost among middle-aged and older Americans. - Truls Ostbye; Donald H. Taylor Jr. (Health Serv Res, 2004)
OBJECTIVE: To estimate the effects of smoking on quality of life over time, using the Years of Healthy Life (YHL) construct. DATA SOURCES/STUDY SETTING: The Health and Retirement Study (HRS) survey (N=12,652) of persons 50 to 60 years old and the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey (N=8,124) of persons > or =70 years old, plus spouses regardless of age, followed from 1992/1993 to 2000. STUDY DESIGN: Years of healthy life from baseline to death were estimated. Regression models were developed with smoking as the main explanatory variable and with both YHL and years of life remaining as the outcome variables. PRINCIPAL FINDINGS: Smoking was strongly and consistently related to YHL lost. In HRS, individuals who had quit smoking at least 15 years prior to baseline had a similar number of YHL left as never smokers. CONCLUSIONS: Efforts to encourage smoking cessation should emphasize the impact of these factors on quality of life.
Keywords: Age Distribution; Aged; Aged, 80 and over; Female; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Quality of Life; Quality-Adjusted Life Years; Regression Analysis; Sex Distribution; Smoking; Smoking cessation; United States

Elders who delay medication because of cost: health insurance, demographic, health, and financial correlates. - Klein, Dawn; Carolyn L. Turvey; Robert B Wallace (Gerontologist, 2004)
PURPOSE: Prescription medication use is essential to the health and well-being of many elderly persons. However, the cost of medications may be prohibitive and contribute to noncompliance with medical recommendations. This study identifies community-dwelling elders who reported a delay in medication use because of prescription medication cost. DESIGN AND METHODS: This was a cross-sectional study of a nationwide sample of 6,535 elders participating in the Asset and Health Dynamics Among the Oldest Old (AHEAD) study. Participants reported if they had taken less medication than prescribed or if they had not filled prescriptions because of cost in the past 2 years. This response was then compared with the self-report of multiple variables, including demographic, health status, health insurance coverage, and financial variables. RESULTS: Elders who were most vulnerable to medication delay as a result of cost included those with Medicare coverage only, low income, high out-of-pocket prescription costs, and poor health as well as African American elders and those aged 65-80 years. IMPLICATIONS: This study provides important information about community-dwelling elders that reported a delay in medication use because of cost. As a Medicare prescription benefit has been passed, it will be important to monitor how these changes affect the elders identified at risk for medication delay.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Drug Therapy; Fees, Pharmaceutical; Female; Health Status; Humans; Insurance, Pharmaceutical Services; Logistic Models; Male; Medicare; Multivariate Analysis; Patient Compliance; Self Administration; Socioeconomic factors; United States

Extent and cost of informal caregiving for older Americans with symptoms of depression. - Kenneth M. Langa; Marcia A. Valenstein; A. Mark Fendrick; Mohammed U Kabeto; Sandeep Vijan (Am J Psychiatry, 2004)
OBJECTIVE: The purpose of this study was to obtain nationally representative estimates of the additional time and cost associated with informal caregiving for older Americans with depressive symptoms. METHOD: Data from the 1993 Asset and Health Dynamics Among the Oldest Old Study, a nationally representative survey of people age 70 years or older (N=6,649), were used to determine the weekly hours and imputed costs of informal caregiving for elderly people with no depressive symptoms in the last week, one to three depressive symptoms in the last week, and four to eight depressive symptoms in the last week. RESULTS: Forty-four percent of survey respondents reported one to three depressive symptoms, and 18% reported four to eight depressive symptoms. In multivariate regression analyses that adjusted for sociodemographics, caregiver network, and coexisting chronic health conditions, respondents with no depressive symptoms received an average of 2.9 hours per week of informal care, compared with 4.3 hours per week for those with one to three symptoms and 6.0 hours per week for those with four to eight symptoms. Caregiving associated with depressive symptoms in elderly Americans represented a yearly cost of about $9 billion. CONCLUSIONS: Depressive symptoms in elderly persons are independently associated with significantly higher levels of informal caregiving, even after the effects of major coexisting chronic conditions are adjusted. The additional hours of care attributable to depressive symptoms represent a significant time commitment for family members and, therefore, a significant societal economic cost. Further research should evaluate the causal pathways by which depressive symptoms lead to high levels of caregiving and should examine whether successful treatment of depression reduces the need for informal care.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Comorbidity; Costs and Cost Analysis; Depressive Disorder; Fees and Charges; Female; Health Care Costs; Home Nursing; Humans; Longitudinal Studies; Male; Personality Inventory; Workload

Heart disease, comorbidity, and activity limitation in community-dwelling elderly. - Oldrige, Neil B.; Timothy E. Stump (Eur J Cardiovasc Prev Rehabil, 2004)
PURPOSE: The purpose of this study was to describe the impact of self-report heart disease, other chronic comorbidities, and perceived health status on activity limitation among community dwelling persons older than 50 years of age. METHODS: Odds ratios for activity limitation in activities of daily living, mobility, and other activities were estimated for respondents with self-report heart disease, eight other chronic comorbid conditions, and perceived health status using data generated in two nationally representative cross-sectional surveys, the Health and Retirement Survey (HRS; respondents aged 51 to 60 years) and the Assets and Health Dynamics of the Oldest Old study (AHEAD; respondents aged 70 years and older). RESULTS: The prevalence of activity limitation increased significantly across the spectrum from activities of daily living to mobility to other activities in both surveys in respondents with and without heart disease. There was a significantly increased likelihood of mobility and other activity limitation among those with heart disease. Among the HRS respondents with heart disease, five or more of the eight comorbid conditions plus poor or fair perceived health were associated with a significantly increased limitation in each activity category. Among the AHEAD respondents with heart disease, three comorbid conditions plus perceived health were associated with a significantly increased limitation in activities of daily living whereas six comorbid conditions plus perceived health were associated with a significantly increased limitation in mobility and in other activities. CONCLUSIONS: As a prime objective of cardiac rehabilitation is to reduce activity limitation, the strong associations between comorbidity and activity limitation observed in this study among persons older than 50 years with heart disease suggest that the burden of comorbidity-associated is considerable but should not be an automatic exclusion criterion for referral to cardiac rehabilitation. The lack of rigorous scientific information on how these associations may influence clinicians who refer patients to rehabilitation and those who manage these programs strongly reinforces the need for more research to explore the real-world spectrum of comorbidity among persons with heart disease and the impact on activity limitation.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Cross-Sectional Studies; Female; Health Status; Heart Diseases; Humans; Male; Middle Aged; Motor Activity; Residence Characteristics; Self Concept; Socioeconomic factors

Nonmetro residence and impaired vision among elderly Americans. - Nan E. Johnson (J Rural Health, 2004)
PURPOSE: Nonmetro and metro elderly people are contrasted in their risk of having (relative to lacking) an impairment in distance vision and in near vision. METHODS: Using the 1995-1996 panel (Wave 2) of the Asset and Health Dynamics Among the Oldest Old (AHEAD) Survey, the prevalence of 5 eye-threatening conditions (cardiovascular disease, cataract, diabetes, glaucoma, and hypertension), a variety of medical treatments for these conditions, the number of talks/visits with doctors in the 2 years before Wave 2, and several relevant demographic characteristics of the 6,817 respondents were controlled. FINDINGS: Nonmetro and metro elders have the same risk of impairment in distance vision. After controlling for other factors, nonmetro elders have a higher risk than their metro peers of an uncorrected impairment in near vision (probably presbyopia). CONCLUSIONS: Nonmetro elders may confront more impediments to updating their corrective lenses for presbyopia. Implications for public health policy are discussed.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cataract; Chronic disease; Comorbidity; Diabetes Mellitus; Humans; Hypertension; Prevalence; Risk Assessment; Rural Health; United States; Urban Health; Vision Disorders

Nonmetro residence, hearing loss, and its accommodation among elderly people. - Nan E. Johnson (J Rural Health, 2004)
BACKGROUND: No previous studies compare the prevalence of physiological hearing loss among older adults by nonmetro/metro residence. Also, there is little information on their relative successes in accommodating hearing loss with a hearing aid. PURPOSE: This study sought to bridge these gaps by analyzing the 8,222 respondents to Wave 1 (1993-1994) of the national Asset and Health Dynamics Among the Oldest Old (AHEAD) Survey. METHODS: Respondents were classified into 4 categories of hearing status: (1) physiologically normal hearing; and physiologically abnormal hearing with (2) full accommodation of lost hearing with a hearing aid, (3) partial accommodation, and (4) no hearing aid. A multinomial logistic regression was used to predict the odds of having any of the 3 statuses of physiologically abnormal hearing rather than normal hearing. FINDINGS: Nonmetro residents had the same odds as metro residents of having no residual hearing loss when a hearing aid was worn (versus having physiologically normal hearing). But nonmetro residents had a much greater risk than their metro counterparts of having a hearing loss but no hearing aid or a residual hearing loss even when wearing an aid. The association of nonmetro residence with either of these latter hearing-loss statuses was greater than that of age, a more traditionally acknowledged hearing-risk factor. CONCLUSION: Future studies should add nonmetro residence to the list of risk factors for negative hearing outcomes, especially since the percentage of elderly nonmetro residents is expected to grow over the next 2 decades.
Keywords: Aged; Aged, 80 and over; Comorbidity; Female; Health Surveys; Hearing aids; Hearing loss; Humans; Male; Memory Disorders; Odds Ratio; Rural Health; United States; Urban Population

Obesity's effects on the onset of functional impairment among older adults. - Kristi Rahrig Jenkins (Gerontologist, 2004)
PURPOSE: This study has two purposes. First, it determines if there is a relationship between body weight and the onset of functional impairment across time among this sample of older adults. More specifically, it examines if obese older adults are more likely to experience the onset of functional impairment. Second, it explores how health behaviors and health conditions may explain the relationship between body weight and the onset of functional impairment. DESIGN AND METHODS: With the use of longitudinal data from the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey, logistic regression models on the onset of functional impairment over two time points are estimated for older adults. RESULTS: Results indicate that body weight (more specifically being overweight or obese) makes one more likely to experience the onset of functional impairment across various domains of impairment. Outside of health behaviors and health conditions, obesity has an independent effect on the onset of impairment in strength, lower body mobility, and activities of daily living. IMPLICATIONS: Study findings support the active treatment of weight problems in older adults. Future directions for research in this area should address effective weight management interventions targeting issues related to older individuals.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Body Weight; Chronic disease; Disabled Persons; Exercise; Female; Humans; Longitudinal Studies; Male; Motor Activity; Movement; Obesity; Risk-Taking; United States

Out-of-pocket health care expenditures among older Americans with dementia. - Kenneth M. Langa; Eric B Larson; Robert B Wallace; A. Mark Fendrick; Norman L Foster; Mohammed U Kabeto; David R Weir; Robert J. Willis; A. Regula Herzog (Alzheimer Dis Assoc Disord, 2004)
The number of older individuals with dementia will likely increase significantly in the next decades, but there is currently limited information regarding the out-of-pocket expenditures (OOPE) for medical care made by cognitively impaired individuals and their families. We used data from the 1993 and 1995 Asset and Health Dynamics Study, a nationally representative longitudinal survey of older Americans, to determine the OOPE for individuals with and without dementia. Dementia was identified in 1993 using a modified version of the Telephone Interview for Cognitive Status for self-respondents, and proxy assessment of memory and judgment for proxy respondents. In 1995, respondents reported OOPE over the prior 2 years for: 1) hospital and nursing home stays, 2) outpatient services, 3) home care, and 4) prescription medications. The adjusted mean annual OOPE was 1,350 US dollars for those without dementia, 2,150 US dollars for those with mild/moderate dementia, and 3,010 US dollars for those with severe dementia (p < 0.01). Expenditures for hospital/nursing home care (1,770 per year US dollars) and prescription medications (800 per year US dollars) were the largest OOPE components for those with severe dementia. We conclude that dementia is independently associated with significantly higher OOPE for medical care compared with those with normal cognitive function. Severe dementia is associated with a doubling of OOPE, mainly due to higher payments for long-term care. Given that the number of older Americans with dementia will likely increase significantly in the coming decades, changes in public funding aimed at reducing OOPE for both long-term care and prescription medications would have considerable impact on individuals with dementia and their families.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Costs and Cost Analysis; Data Interpretation, Statistical; Female; Financing, Personal; Health Care Costs; Health Expenditures; Health Surveys; Humans; Insurance Coverage; Longitudinal Studies; Male

Out-of-pocket health-care expenditures among older Americans with cancer. - Kenneth M. Langa; A. Mark Fendrick; M.E. Chernew; Mohammed U Kabeto; Paisley, Kerry L.; Hayman, James A. (Value Health, 2004)
OBJECTIVE: There is currently limited information regarding the out-of-pocket expenditures (OOPE) for medical care made by elderly individuals with cancer. We sought to quantify OOPE for community-dwelling individuals age 70 or older with: 1) no cancer (No CA), 2) a history of cancer, not undergoing current treatment (CA/No Tx), and 3) a history of cancer, undergoing current treatment (CA/Tx). METHODS: We used data from the 1995 Asset and Health Dynamics Study, a nationally representative survey of community-dwelling elderly individuals. Respondents identified their cancer status and reported OOPE for the prior 2 years for: 1) hospital and nursing home stays, 2) outpatient services, 3) home care, and 4) prescription medications. Using a multivariable two-part regression model to control for differences in sociodemographics, living situation, functional limitations, comorbid chronic conditions, and insurance coverage, the additional cancer-related OOPE were estimated. RESULTS: Of the 6370 respondents, 5382 (84%) reported No CA, 812 (13%) reported CA/No Tx, and 176 (3%) reported CA/Tx. The adjusted mean annual OOPE for the No CA, CA/No Tx, and CA/Tx groups were 1210 dollars, 1450 dollars, and 1880 dollars, respectively (P < .01). Prescription medications (1120 dollars per year) and home care services (250 dollars) accounted for most of the additional OOPE associated with cancer treatment. Low-income individuals undergoing cancer treatment spent about 27% of their yearly income on OOPE compared to only 5% of yearly income for high-income individuals with no cancer history (P < .01). CONCLUSIONS: Cancer treatment in older individuals results in significant OOPE, mainly for prescription medications and home care services. Economic evaluations and public policies aimed at cancer prevention and treatment should take note of the significant OOPE made by older Americans with cancer.
Keywords: Aged; Aged, 80 and over; Cost of Illness; Family Characteristics; Female; Financing, Personal; Health Expenditures; Health Services Research; Humans; Insurance, Health; Longitudinal Studies; Male; Medicaid; Medicare; Michigan; Neoplasms

Race, gender, and the retirement decisions of people ages 60 to 80: prospects for age integration in employment. - Tay K. McNamara; Williamson, John B. (Int J Aging Hum Dev, 2004)
UNLABELLED: Demographic projections have prompted concerns about the potential economic burden of an aging population. This article, drawing on the 1998 Health and Retirement Study, explores ways in which race, gender, and age moderate the effects of various factors on labor force participation among people ages 60 to 80. Key findings center on health, education, and non-wage income. First, the effect of low non-wage income is weaker at older ages due to higher levels of functional disability. Second, the effect of low education is stronger for women, who perceive their chances of finding employment as low. Third, the effect of health is weaker for blacks, as they are less likely to find steady employment regardless of health. POLICY IMPLICATIONS: Employer flexibility in number of hours worked might make sense for workers close to retirement age, while job search and training programs might be preferable for workers past the typical retirement age.
Keywords: Age Distribution; Aged; Aged, 80 and over; Black People; Educational Status; Employment; Female; Health Status; Humans; Income; Logistic Models; Male; Middle Aged; Retirement; Sex Distribution; White People

Religion and preventative health care utilization among the elderly. - Benjamins, Maureen Reindl; Brown, Carolyn (Soc Sci Med, 2004)
Evidence supporting a relationship between religion and physical health has increased substantially in the recent past. One possible explanation for this relationship that has not received much attention in the literature is that health care utilization may differ by religious involvement or religious denomination. A nationally representative sample of older adults was used to estimate the effects of religious salience and denomination on six different types of preventative health care (i.e. flu shots, cholesterol screening, breast self-exams, mammograms, pap smears, and prostate screening). Findings show that both men and women who report high levels of religiosity are more likely to use preventative services. Denominational differences show that affiliated individuals, especially those who are Jewish, are significantly more likely to use each type of preventative care than non-affiliated individuals. The results of this study open the door to further exploration of this potentially important, but relatively neglected, link between religion and health.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Catholicism; Diagnostic Tests, Routine; Female; Health Services for the Aged; Health Status; Humans; Interviews as Topic; Jews; Logistic Models; Longitudinal Studies; Male; Patient Acceptance of Health Care; Preventive Health Services; Primary Health Care; Protestantism; Religion and Psychology; Socioeconomic factors; United States

Resolving inconsistencies in trends in old-age disability: report from a technical working group. - Vicki A Freedman; Eileen M. Crimmins; Robert F. Schoeni; Brenda C Spillman; Aykan, Hakan; Kramarow, Ellen; Land, Kenneth; Lubitz, James; Kenneth G. Manton; Linda G Martin; Shinberg, Diane; Timothy A Waidmann (Demography, 2004)
In September 2002, a technical working group met to resolve previously published inconsistencies across national surveys in trends in activity limitations among the older population. The 12-person panel prepared estimates from five national data sets and investigated methodological sources of the inconsistencies among the population aged 70 and older from the early 1980s to 2001. Although the evidence was mixed for the 1980s and it is difficult to pinpoint when in the 1990s the decline began, during the mid- and late 1990s, the panel found consistent declines on the order of 1%-2.5% per year for two commonly used measures in the disability literature: difficulty with daily activities and help with daily activities. Mixed evidence was found for a third measure: the use of help or equipment with daily activities. The panel also found agreement across surveys that the proportion of older persons who receive help with bathing has declined at the same time as the proportion who use only equipment (but not personal care) to bathe has increased. In comparing findings across surveys, the panel found that the period, definition of disability, treatment of the institutionalized population, and age standardizing of results were important to consider. The implications of the findings for policy, national survey efforts, and further research are discussed.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Chronic disease; Disabled Persons; Female; Health Surveys; Homemaker Services; Humans; Male; Models, Statistical; Self-Help Devices; United States

Urinary incontinence and its association with death, nursing home admission, and functional decline. - Holroyd-Leduc, Jayna M.; Kala M. Mehta; Kenneth E Covinsky (J Am Geriatr Soc, 2004)
OBJECTIVES: To determine whether urinary incontinence (UI) is an independent predictor of death, nursing home admission, decline in activities of daily living (ADLs), or decline in instrumental activities of daily living (IADLs). DESIGN: A population-based prospective cohort study from 1993 to 1995. SETTING: Community-dwelling within the United States. PARTICIPANTS: Six thousand five hundred six of the 7,447 subjects aged 70 and older in the Asset and Health Dynamics Among the Oldest Old study who had complete information on continence status and did not require a proxy interview at baseline. MEASUREMENTS: The predictor was UI, and the outcomes were death, nursing home admission, ADL decline, and IADL decline. Potential confounders considered were comorbid conditions, baseline function, sensory impairment, cognition, depressive symptoms, body mass index, smoking and alcohol, demographics, and socioeconomic status. RESULTS: The prevalence of UI was 14.8% (18.5% in women; 8.5% in men). At 2-year follow-up, subjects incontinent at baseline were more likely to have died (10.9% vs 8.7%; unadjusted odds ratio (OR)=1.29, 95% confidence interval (CI)=1.02-1.64), be admitted to a nursing home (4.4% vs 2.6%, OR=1.77; 95% CI=1.18-2.63), and to have declined in ADL function (13.6% vs 8.1%; OR=1.78, 95% CI=1.36-2.33) and IADL function (21.2% vs 13.8%; OR 1.69, 95% CI 1.39-2.05). However, after adjusting for confounders, UI was not an independent predictor of death (adjusted OR (AOR)= 0.90, 95% CI=0.67-1.21), nursing home admission (AOR=1.33, 95% CI=0.86-2.04), or ADL decline (AOR=1.24, 95% CI=0.92-1.68). Incontinence remained a predictor of IADL decline (AOR=1.31; 95% CI=1.05-1.63), although adjustment markedly reduced the strength of this association. CONCLUSION: Higher levels of baseline illness severity and functional impairment appear to mediate the relationship between UI and adverse outcomes. The results suggest that, although UI appears to be a marker of frailty in community-dwelling elderly, it is not a strong independent risk factor for death, nursing home admission, or functional decline.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Body Mass Index; Female; Follow-Up Studies; Frail Elderly; Health Status; Humans; Male; Nursing homes; Outcome Assessment, Health Care; Risk Factors; Smoking; Socioeconomic factors; Time Factors; Urinary incontinence

County-level income inequality and depression among older Americans. - Muramatsu, Naoko (Health Serv Res, 2003)
OBJECTIVES: To examine (1) whether county-level income inequality is associated with depression among Americans aged 70 and older, taking into consideration county-level mean household income and individual-level socioeconomic status (SES), demographic characteristics, and physical health, and (2) whether income inequality effects are stronger among people with lower SES and physical health. DATA SOURCES: The individual-level data from the first wave of the Assets and Health Dynamics among the Oldest Old survey (1993-1994) were linked with the county-level income inequality and mean household income data from the 1990 Census. STUDY DESIGN: Multilevel analysis was conducted to examine the association between income inequality (the Gini coefficient) and depression. PRINCIPAL FINDINGS: Income inequality was significantly associated with depression among older Americans. Those living in counties with higher income inequality were more depressed, independent of their demographic characteristics, SES, and physical health. The association was stronger among those with more illnesses. CONCLUSIONS: While previous empirical research on income inequality and physical health is equivocal, evidence for income inequality effects on mental health seems to be strong.
Keywords: Age Factors; Aged; Aged, 80 and over; depression; Female; Health Status Indicators; Humans; Income; Male; Socioeconomic factors; United States

Health care utilization among older adults with arthritis. - Dorothy D Dunlop; Larry M Manheim; Song, Jing; Rowland W Chang (Arthritis Rheum, 2003)
OBJECTIVE: To evaluate the effect of arthritis on subsequent 2-year use of health care services and out-of-pocket costs among older adults and determine if comorbidities or economic resources mitigate that effect. METHODS: Data were analyzed from 6230 participants interviewed in 1993 and 1995 in the Asset and Health Dynamic Survey Among the Oldest Old (AHEAD), a national probability sample of community-dwelling adults. Baseline arthritis status was ascertained from the report of an arthritis-related physician's visit or a joint replacement not associated with a hip fracture. The effect of baseline arthritis on the odds of subsequent 2-year health care utilization and high out-of-pocket expenses were estimated from multiple logistic regression controlling for demographic factors, comorbidity, and economic resources. RESULTS: Older adults with arthritis are significantly more likely to have a physician visit (odds ratio [OR] 3.0), hospital admission (OR 1.6), outpatient surgery (OR 1.3), receive home health care (OR 1.6), and have out-of-pocket cost >5000 US dollars (OR 1.6) compared with contemporaries having similar demographics (age, sex, racial/ethnic group, marital status), comorbid conditions, and economic resources (education, income, wealth, health insurance), but not reporting arthritis. CONCLUSIONS: Older adults with symptomatic arthritis reported greater medical utilization and cost compared with people not reporting arthritis. These disparities persisted after accounting for differences in demographics, comorbidities, and economic factors. These findings document greater economic burdens on a personal and societal level among people with arthritis. As individuals, older adults with arthritis spend more out-of-pocket dollars for health care than their contemporaries without arthritis. On a societal level, these findings of greater health care utilization among people with arthritis point to increasing future demands on the US health care system due to demographic increases in the numbers of older adults with arthritis and support policies aimed at improving arthritis prevention and treatment as well as reducing the economic disparities between those with and without arthritis.
Keywords: Aged; Aged, 80 and over; Ambulatory Surgical Procedures; Arthritis; Comorbidity; Cost of Illness; Female; Health Services; Home Care Services; Hospitals; Humans; Insurance, Health; Longitudinal Studies; Male; Nursing homes; Physicians' Offices; Social Class

Life expectancy with cognitive impairment in the older population of the United States. - Suthers, Kristen; Jung K Kim; Eileen M. Crimmins (J Gerontol B Psychol Sci Soc Sci, 2003)
OBJECTIVES: This article provides estimates of the prevalence of cognitive impairment by age and sex for a nationally representative sample of the U.S. population aged 70 and over. From these estimates, years of life with and without cognitive impairment are calculated. METHODS: Using data from the Assets and Health Dynamics of the Oldest Old (AHEAD) survey, the prevalence of cognitive impairment is estimated for a sample representing both the community-dwelling and institutionalized older American population. Sullivan's method is used to calculate the average number of years an elderly person can expect to live with and without cognitive impairment. RESULTS: The prevalence of moderate to severe cognitive impairment in the total U.S. population aged 70 and over is 9.5%. At age 70, the average American can expect 1.5 years with cognitive impairment. Expected length of life with cognitive impairment is longer for women than men because of their longer life expectancy. DISCUSSION: As total life expectancy continues to increase, the length of life with cognitive impairment for the American population will increase unless age-specific prevalence is reduced. There is great potential for improvement in future early treatment and diagnosis of this condition.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Cross-Sectional Studies; Female; Humans; Life Expectancy; Male; Neuropsychological tests; Probability; Psychometrics; Sex Factors; Survival Analysis; United States

Medication costs, adherence, and health outcomes among Medicare beneficiaries. - Ramin Mojtabai; Mark Olfson (Health Aff (Millwood), 2003)
In a two-year period more than two million elderly Medicare beneficiaries did not adhere to drug treatment regimens because of cost. This poor adherence tended to be more common among beneficiaries with no or partial medication coverage and was associated with poorer health and higher rates of hospitalization. The risk for cost-related poor adherence was especially pronounced among lower-income beneficiaries with high out-of-pocket drug spending. We argue that this pattern of cost-related poor medication adherence should inform the design of Medicare prescription drug benefit legislation.
Keywords: Aged; Aged, 80 and over; Chronic disease; Continuity of Patient Care; Family Characteristics; Female; Financing, Personal; Health Services Research; Humans; Income; Insurance, Pharmaceutical Services; Longitudinal Studies; Male; Medicare; Patient Compliance; Prevalence; Probability; Self Administration; Treatment Outcome; United States

Racial disparities in joint replacement use among older adults. - Dorothy D Dunlop; Larry M Manheim; Song, Jing; Rowland W Chang (Med Care, 2003)
BACKGROUND: Although joint replacement can restore function for arthritis patients with severe joint disease, this procedure has not been used equally across racial groups. Differences in joint replacement use are assessed from a national sample. OBJECTIVE: This study evaluates the role of health conditions and economic access to explain differences in joint replacement among older black and Hispanic minorities relative to white persons. DESIGN: Longitudinal (1993-1995) Asset and Health Dynamics Among the Oldest Old (AHEAD) study. SETTING: National probability sample of US community-dwelling older adults. PATIENT POPULATION: AHEAD participants (n = 6159) aged 69 to 103 years. MEASUREMENTS: The outcome is subject-reported 2-year use of any arthritis-related joint-replacement. Independent variables are demographics, health needs (arthritis, other medical conditions, functional health), and economic access (income, assets, education, and health insurance). RESULTS: Older minorities reported arthritis-related joint replacements (black: 0.98%; Hispanic: 0.97%, annually) less frequently compared with white persons (1.48% annually). Older minorities were significantly less likely to use joint replacement compared with white persons (OR, 0.37; 95% CI, 0.20, 0.71) controlling for demographics, and arthritis and other health needs. Disparities remained significant (OR, 0.46; 95% CI, 0.22, 0.98) after additionally controlling for economic medical access. Use was lower among people who depended solely on Medicare compared with those with supplemental health insurance (OR, 0.46; 95% CI, 0.22, 0.95). CONCLUSIONS: These national data document low rates of arthritis-related joint replacement among older Hispanic persons comparable to black persons. Less use among older minorities compared with white persons is not explained by differences in health needs or economic access. Other cultural and attitudinal factors merit investigation to explain disparities.
Keywords: Aged; Aged, 80 and over; Arthroplasty, Replacement; Black or African American; Cohort Studies; Data Interpretation, Statistical; Health Services Accessibility; Health Services Needs and Demand; Health Status; Health Surveys; Hispanic or Latino; Humans; Interviews as Topic; Osteoarthritis; Sampling Studies; United States; White People

Screening mammography and Pap tests among older American women 1996-2000: results from the Health and Retirement Study (HRS) and Asset and Health Dynamics Among the Oldest Old (AHEAD). - Truls Ostbye; Gary N. Greenberg; Donald H. Taylor Jr.; Lee, Ann Marie M. (Ann Fam Med, 2003)
BACKGROUND: We wanted to determine the frequency of self-reported receipt of screening mammography and Papanicolaou (Pap) tests in older women and investigate important predictors of utilization, based on 2 national longitudinal surveys. METHODS: This cohort study includes participants from 4 waves (1994-2000) of the Health and Retirement Study (HRS)--5,942 women aged 50 to 61 years, and 4 waves (1993-2000) of the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey--4,543 women aged 70 years and older. The self-reported receipt of screening mammograms and Pap smears in the most recent 2 years were reported in 1996 and 2000 for HRS, with predictors of receipt measured in 1994 and 1998. In AHEAD, the self-reported receipt of screening mammograms and Pap smears in the most recent 2 years were reported in 1995 and 2000, with predictors of receipt measured in 1993 and 1998. RESULTS: Receipt of mammography is stable at 70% to 80% among women aged 50 to 64 years, then declines to around 40% among those aged 85 to 90 years. For Pap tests there is a decline from 75% among women aged 50 to 54 years to 25% in those aged 85 to 90 years. For both mammography and Pap tests, the rates increased in all groups from 1995/1996 to 2000. Higher education, being married, higher income, not smoking, and vigorous exercise were consistently associated with higher rates of receipt. CONCLUSIONS: Although the use of mammography and Pap tests for screening declines into old age, use has been increasing recently. The large and increasing number of tests performed might not be justified given the lack of evidence of effect in older age-groups.
Keywords: Age Factors; Aged; Aged, 80 and over; Breast Neoplasms; Cost-Benefit Analysis; Female; Health Services for the Aged; Humans; Longitudinal Studies; Mammography; Middle Aged; Multivariate Analysis; Papanicolaou Test; Patient Acceptance of Health Care; Risk; United States; Uterine Cervical Neoplasms; Vaginal Smears

Driving life expectancy of persons aged 70 years and older in the United States. - Foley, Daniel J.; Heimovitz, Harley K.; Jack M. Guralnik; Brock, Dwight B. (Am J Public Health, 2002)
OBJECTIVES: We estimated total life expectancy and driving life expectancy of US drivers aged 70 years and older. METHODS: Life table methods were applied to 4699 elderly persons who were driving in 1993 and reassessed in a 1995 survey. RESULTS: Drivers aged 70 to 74 years had a driving life expectancy of approximately 11 years. A higher risk of mortality among men as a cause of driving cessation offset a higher risk of driving cessation not related to mortality among women that resulted in similar driving life expectancies. CONCLUSIONS: Nationwide, many elderly drivers quit driving each year and must seek alternative sources of transportation. Because of differences in life expectancy, women require more years of support for transportation, on average, than men after age 70.
Keywords: Accidents, Traffic; Activities of Daily Living; Aged; Aged, 80 and over; Automobile Driving; Decision making; Family Characteristics; Female; Frail Elderly; Humans; Interviews as Topic; Licensure; Life Expectancy; Logistic Models; Male; Risk Factors; Transportation; United States

Individual consequences of volunteer and paid work in old age: health and mortality. - Luoh, M.; A. Regula Herzog (J Health Soc Behav, 2002)
The impacts of the productive social activities of volunteer and paid work on health have rarely been investigated among the oldest Americans despite a recent claim for their beneficial effect (Rowe and Kahn 1998). This paper used data from Waves 3 and 4 of the Asset and Health Dynamics among the Oldest Old (AHEAD) Study to (1) investigate the impact of these activities on health measured as self-reported health and activities of daily living (ADL) functioning limitations and to (2) explore possible causal mechanisms. Using multinomial logistic regression analysis, amounts of volunteer and paid work over a minimum of 100 annual hours self-reported at Wave 3 were related to poor health and death as competing risks measured at Wave 4, controlling for health measured at Wave 2 and for other predictors of poor health and death. Findings suggest that performing more than 100 annual hours of volunteer work and of paid work have independent and significant protective effects against subsequent poor health and death. Additional analyses suggest that the quantity of volunteer and paid work beyond 100 annual hours is not related to health outcomes and that physical exercise and mental health measured as cognitive functioning and depressive symptoms explain not entirely overlapping parts of the relationship between productive activities and health.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Employment; Female; Health Status; Humans; Male; Mortality; Multivariate Analysis; Prospective Studies; United States; Volunteers

Informal caregiving for diabetes and diabetic complications among elderly americans. - Kenneth M. Langa; Sandeep Vijan; Rodney A. Hayward; M.E. Chernew; Caroline S Blaum; Mohammed U Kabeto; David R Weir; Steven J. Katz; Robert J. Willis; A. Mark Fendrick (J Gerontol B Psychol Sci Soc Sci, 2002)
OBJECTIVES: Little is known regarding the amount of time spent by unpaid caregivers providing help to elderly individuals for disabilities associated with diabetes mellitus (DM). We sought to obtain nationally representative estimates of the time, and associated cost, of informal caregiving provided to elderly individuals with diabetes, and to determine the complications of DM that contribute most significantly to the subsequent need for informal care. METHODS: We estimated multivariable regression models using data from the 1993 Asset and Health Dynamics Among the Oldest Old Study, a nationally representative survey of people aged 70 or older (N = 7,443), to determine the weekly hours of informal caregiving and imputed cost of caregiver time for community-dwelling elderly individuals with and without a diagnosis of DM. RESULTS: Those without DM received an average of 6.1 hr per week of informal care, those with DM taking no medications received 10.5 hr, those with DM taking oral medications received 10.1 hr, and those with DM taking insulin received 14.4 hr of care (p <.01). Disabilities related to heart disease, stroke, and visual impairment were important predictors of diabetes-related informal care. The total cost of informal caregiving for elderly individuals with diabetes in the United States was between $3 and $6 billion per year, similar to previous estimates of the annual paid long-term care costs attributable to DM. DISCUSSION: Diabetes imposes a substantial burden on elderly individuals, their families, and society, both through increased rates of disability and the significant time that informal caregivers must spend helping address the associated functional limitations. Future evaluations of the costs of diabetes, and the cost-effectiveness of diabetes interventions, should consider the significant informal caregiving costs associated with the disease.
Keywords: Aged; Aged, 80 and over; Caregivers; Cost of Illness; Costs and Cost Analysis; Diabetes Complications; Diabetes Mellitus; Disabled Persons; Female; Health Surveys; Humans; Hypoglycemic Agents; Insulin; Male; Time Factors

A longitudinal study of the effects of tobacco smoking and other modifiable risk factors on ill health in middle-aged and old Americans: results from the Health and Retirement Study and Asset and Health Dynamics among the Oldest Old survey. - Truls Ostbye; Donald H. Taylor Jr.; Sang-Hyuk Jung (Prev Med, 2002)
BACKGROUND: While the effects of smoking and other modifiable risk factors on mortality and specific diseases are well established, their effects on ill health more generally are less known. Using two national, longitudinal surveys, the objective of this study was to analyze the effect of smoking and other modifiable risk factors on ill health, defined in a multidimensional fashion (i.e., disability, impaired mobility, health care utilization, and self-reported health). METHODS: The analyses were based on the Health and Retirement Study (HRS) (12,652 persons 50-60 years old surveyed in 1992, 1994, 1996, and 1998) and the Asset and Health Dynamics among the Oldest Old survey (8,124 persons 60-70 years old surveyed in 1993, 1996, and 1998). RESULTS: Smoking was strongly related to mortality and to ill health, with similar relative effects in the middle-aged and the elderly. There were consistent adverse dose-response relationships between smoking and ill health in the HRS. Persons who had quit smoking at least 15 years prior to the survey were no more likely than never smokers to experience ill health. A dose-response relationship was found between exercise and ill health. For body mass index and alcohol, there were U-shaped relationships with ill health. CONCLUSIONS: Public health efforts designed to encourage smoking cessation should emphasize improvements in ill health in addition to decreased mortality.
Keywords: Age Distribution; Aged; Aged, 80 and over; Alcohol Drinking; Attitude to Health; Chi-Square Distribution; Exercise; Female; Health Behavior; Health Status; Health Surveys; Humans; Life Style; Logistic Models; Longitudinal Studies; Male; Middle Aged; Risk Assessment; Risk Factors; Sex Distribution; Smoking; Socioeconomic factors; Survival Rate; United States

A national study of the quantity and cost of informal caregiving for the elderly with stroke. - Hickenbottom, S.L.; A. Mark Fendrick; Kutcher, J.S.; Mohammed U Kabeto; Steven J. Katz; Kenneth M. Langa (Neurology, 2002)
BACKGROUND: As the US population ages, increased stroke incidence will result in higher stroke-associated costs. Although estimates of direct costs exist, little information is available regarding informal caregiving costs for stroke patients. OBJECTIVE: To determine a nationally representative estimate of the quantity and cost of informal caregiving for stroke. METHODS: The authors used data from the first wave of the Asset and Health Dynamics (AHEAD) Study, a longitudinal study of people over 70, to determine average weekly hours of informal caregiving. Two-part multivariable regression analyses were used to determine the likelihood of receiving informal care and the quantity of caregiving hours for those with stroke, after adjusting for important covariates. Average annual cost for informal caregiving was calculated. RESULTS: Of 7,443 respondents, 656 (8.8%) reported a history of stroke. Of those, 375 (57%) reported stroke-related health problems (SRHP). After adjusting for cormorbid conditions, potential caregiver networks, and sociodemographics, the proportion of persons receiving informal care increased with stroke severity, and there was an association of weekly caregiving hours with stroke +/- SRHP (p < 0.01). Using the median 1999 home health aide wage (8.20 dollars/hour) as the value for family caregiver time, the expected yearly caregiving cost per stroke ranged from 3,500 dollars to 8,200 dollars. Using conservative prevalence estimates from the AHEAD sample (750,000 US elderly patients with stroke but no SRHP and 1 million with stroke and SRHP), this would result in an annual cost of up to 6.1 billion dollars for stroke-related informal caregiving in the United States. CONCLUSIONS: Informal caregiving-associated costs are substantial and should be considered when estimating the cost of stroke treatment.
Keywords: Aged; Aged, 80 and over; Caregivers; Confidence Intervals; Female; Humans; Longitudinal Studies; Male; Multivariate Analysis; Stroke; United States

The role of smoking and other modifiable lifestyle risk factors in maintaining and restoring lower body mobility in middle-aged and older Americans: results from the HRS and AHEAD. Health and Retirement Study. Asset and Health Dynamics Among the Oldest Ol - Truls Ostbye; Donald H. Taylor Jr.; Katrina M. Krause; Scoyoc, L.V. (J Am Geriatr Soc, 2002)
OBJECTIVES: To analyze the effect of smoking, smoking cessation, and other modifiable risk factors on mobility in middle-aged and older Americans. DESIGN: Panel study; secondary data analysis. SETTING: United States (national sample). PARTICIPANTS: The Health and Retirement Study (HRS) includes data on 12,652 Americans aged 50 to 61 in four waves (1992-1998). The Asset and Health Dynamics Among the Oldest Old (AHEAD) survey followed 8,124 community-dwelling people aged 70 years and older in three waves (1993-1998). MEASUREMENTS: The relationships between the primary outcome measure, lower body mobility (ability to walk several blocks and walk up one flight of stairs without difficulty), and smoking, exercise (HRS only), body mass index (BMI), and alcohol use were estimated in bivariate and multivariate analyses. RESULTS: Not smoking was strongly positively related to mobility, and the relative effects were similar in both panels. Among those with impaired mobility at baseline, not smoking was also strongly related to recovery. In the middle aged, there were consistent dose-response relationships between amount smoked and impaired mobility. Fifteen years after quitting, the risk of impaired mobility returned to that of never smokers. There was also a strong dose-response relationship between level of exercise and mobility. Inverted U-shaped relationships with mobility were observed for BMI and alcohol consumption. CONCLUSIONS: The relationships between not smoking and lower body mobility in middle-aged and older Americans are strong and consistent. Interventions aimed at reducing smoking have the potential to preserve mobility and thereby prolong health and independence in later life.
Keywords: Age Distribution; Aged; Aged, 80 and over; Alcohol Drinking; Body Mass Index; Exercise; Female; Humans; Leg; Logistic Models; Longitudinal Studies; Male; Marital Status; Middle Aged; Risk Factors; Sex Distribution; Smoking; Smoking cessation; United States; Walking

State expenditures on home and community based services and use of formal and informal personal assistance: a multilevel analysis. - Muramatsu, Naoko; Richard T. Campbell (J Health Soc Behav, 2002)
Despite wide state variation in commitment to home and community-based services (HCBS) for functionally impaired older persons, little is known about how such variation affects older adults' strategies to compensate for their functional limitations. This study examines the association of state HCBS expenditures with use of formal and informal personal assistance among non-institutionalized older Americans aged 70 and older with functional limitations. We conducted multilevel multinomial logistic regression analysis using data from the first wave of the Assets and Health Dynamics among the Oldest Old Survey, combined with data on state HCBS expenditures. Controlling for individuals' demographic, socioeconomic, and care needs factors, persons residing in states with higher HCBS expenditures were more likely to use formal personal assistance, but not less likely to use informal assistance. Our study suggests state variation in HCBS expenditures leads to inequitable access to formal personal assistance, especially among those with high functional limitations.
RDA 1996-025
Keywords: Aged; Aged, 80 and over; Community Health Services; Female; Financing, Government; Frail Elderly; Health Care Surveys; Health Expenditures; Home Care Services; Humans; Logistic Models; Male; State Government

Arthritis prevalence and activity limitations in older adults. - Dorothy D Dunlop; Larry M Manheim; Song, Jing; Rowland W Chang (Arthritis Rheum, 2001)
OBJECTIVE: To evaluate the prevalence of arthritis and activity limitations among older Americans by assessing their demographic, ethnic, and economic characteristics. METHODS: Data from the Asset and Health Dynamic Survey Among the Oldest Old (AHEAD), a national probability sample of community-dwelling adults born before 1924, were analyzed cross-sectionally. Arthritis that resulted in a physician's visit or a joint replacement not associated with a hip fracture was ascertained by self-report. RESULTS: The prevalence of arthritis in older adults ranged from 25% in non-Hispanic whites to 40% in non-Hispanic blacks to 44% in Hispanics. A higher prevalence of arthritis was associated with less education as well as lower income and less wealth. The prevalence of limitations in activities of daily living (ADL) among non-Hispanic white, non-Hispanic black, and Hispanic adults who reported arthritis only was 29%, 30%, and 37%, respectively, and increased to 48%, 57%, and 56%, respectively, among those reporting arthritis plus other chronic conditions, after adjustment for age and sex. CONCLUSION: Non-Hispanic black and Hispanic older adults reported having arthritis at a substantially higher frequency than did non-Hispanic whites. In addition, Hispanics reported higher rates of ADL limitations than did non-Hispanic whites with comparable disease burden. Further study is needed to confirm and elucidate the reasons for these racial and economic disparities in older populations.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Arthritis; Data collection; Humans; Prevalence; Racial Groups; Socioeconomic factors; Surveys and Questionnaires

Caregiver report of hallucinations and paranoid delusions in elders aged 70 or older. - Carolyn L. Turvey; Schultz, Susan K.; Arndt, Stephan; Ellingrod, Vicki; Robert B Wallace; A. Regula Herzog (Int Psychogeriatr, 2001)
This study examined the demographic, medical, and psychiatric correlates of hallucinations and paranoid delusions reported by proxy informants for 822 elders aged 70 or older. This sample comprised people who were deemed unable to complete a direct interview in a large nationwide study of aging. Marital status, trouble with vision, and cognitive impairment were associated with report of both paranoid delusions and hallucinations. Depressive symptoms and stroke were associated with hallucinations only. These results suggest that inadequate external stimulation in the elderly leads to psychotic experiences.
Keywords: Aged; Aged, 80 and over; Aging; Caregivers; Cognition Disorders; Cohort Studies; Delusions; depression; Female; Follow-Up Studies; Hallucinations; Humans; Male; Marital Status; Paranoid Disorders; Risk Factors; Stroke; Surveys and Questionnaires; United States; Vision Disorders

Changes in driving patterns and worsening depressive symptoms among older adults. - Stephanie J. Fonda; Robert B Wallace; A. Regula Herzog (J Gerontol B Psychol Sci Soc Sci, 2001)
OBJECTIVES: This study examined whether changes in driving patterns-driving cessation and reduction-have negative consequences for the depressive symptoms of older Americans and whether these consequences are mitigated for people with a spouse who drives. METHODS: The project used data from 3 waves of the Asset and Health Dynamics Among the Oldest Old (AHEAD) study. Depressive symptoms were assessed with an abbreviated Center for Epidemiologic Studies-Depression scale. Using 2 models, the project examined how driving cessation and reduction that occurred between Waves 1 and 2 contributed to increases in depressive symptoms between Waves 2 and 3. The first model included the entire sample (N = 5,239), and the second model focused on drivers only (n = 3,543). A third model added interaction terms to the analysis to consider whether respondents who stopped driving but had a spouse who drove were less at risk of worsening depressive symptoms. RESULTS: Respondents who stopped driving had greater risk of worsening depressive symptoms. Drivers who restricted their driving distances before the study began also had greater risk of worsening depressive symptoms, but seemingly less so than the respondents who stopped driving altogether. For respondents who stopped driving, having a spouse available to drive them did not mitigate the risk of worsening symptoms. DISCUSSION: Changes in driving patterns can be deleterious for older people's depressive symptoms. Initiatives for assisting older people should focus on strategies that help them retain driving skills, that prepare them for the possible transition from driver to ex-driver, and that ensure that they have access to mental health therapies if driving changes are imminent.
Keywords: Activities of Daily Living; Adaptation, Psychological; Aged; Aged, 80 and over; Automobile Driving; depression; Female; Humans; Male; Quality of Life; Risk Factors; Social Environment

Childlessness and the psychological well-being of older persons. - Zhang, Zhenmei; Mark D Hayward (J Gerontol B Psychol Sci Soc Sci, 2001)
OBJECTIVES: Rapid growth in the size of the childless elderly population has prompted concerns about the negative effects of childlessness on psychological well-being. This study adds to this line of inquiry by examining the effects of childlessness on two important dimensions of elderly persons' psychological well-being: loneliness and depression. METHODS: Using the 1993 Asset and Health Dynamics Among the Oldest Old data set, the authors estimated logistic and ordinary least squares regression models of psychological well-being for a nationally representative sample of people aged 70 and older (N = 6,517). RESULTS: Childlessness per se did not significantly increase the prevalence of loneliness and depression at advanced ages, net of other factors. There also was no statistical evidence for the hypothesis that childlessness increases loneliness and depression for divorced, widowed, and never married elderly persons. Sex, however, altered how childlessness and marital status influenced psychological well-being. Divorced, widowed, and never married men who were childless had significantly higher rates of loneliness compared with women in comparable circumstances; divorced and widowed men who were childless also had significantly higher rates of depression than divorced and widowed women. DISCUSSION: The findings suggest that it is important to understand the consequences of childlessness in the context of marital status and sex.
Keywords: Aged; Aged, 80 and over; depression; Family Planning Services; Female; Geriatric Assessment; Humans; Loneliness; Male; Marital Status; Risk Factors; Sex Factors

Estimating the cost of informal caregiving for elderly patients with cancer. - Hayman, James A.; Kenneth M. Langa; Mohammed U Kabeto; Steven J. Katz; DeMonner, Sonya M.; M.E. Chernew; Slavin, Mitchell B.; A. Mark Fendrick (J Clin Oncol, 2001)
PURPOSE: As the United States population ages, the increasing prevalence of cancer is likely to result in higher direct medical and nonmedical costs. Although estimates of the associated direct medical costs exist, very little information is available regarding the prevalence, time, and cost associated with informal caregiving for elderly cancer patients. MATERIALS AND METHODS: To estimate these costs, we used data from the first wave (1993) of the Asset and Health Dynamics (AHEAD) Study, a nationally representative longitudinal survey of people aged 70 or older. Using a multivariable, two-part regression model to control for differences in health and functional status, social support, and sociodemographics, we estimated the probability of receiving informal care, the average weekly number of caregiving hours, and the average annual caregiving cost per case (assuming an average hourly wage of $8.17) for subjects who reported no history of cancer (NC), having a diagnosis of cancer but not receiving treatment for their cancer in the last year (CNT), and having a diagnosis of cancer and receiving treatment in the last year (CT). RESULTS: Of the 7,443 subjects surveyed, 6,422 (86%) reported NC, 718 (10%) reported CNT, and 303 (4%) reported CT. Whereas the adjusted probability of informal caregiving for those respondents reporting NC and CNT was 26%, it was 34% for those reporting CT (P <.05). Those subjects reporting CT received an average of 10.0 hours of informal caregiving per week, as compared with 6.9 and 6.8 hours for those who reported NC and CNT, respectively (P <.05). Accordingly, cancer treatment was associated with an incremental increase of 3.1 hours per week, which translates into an additional average yearly cost of $1,200 per patient and just over $1 billion nationally. CONCLUSION: Informal caregiving costs are substantial and should be considered when estimating the cost of cancer treatment in the elderly.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Family; Female; Home Nursing; Humans; Male; Multivariate Analysis; Neoplasms; Regression Analysis; United States

The explosion in paid home health care in the 1990s: who received the additional services? - Kenneth M. Langa; M.E. Chernew; Mohammed U Kabeto; Steven J. Katz (Med Care, 2001)
OBJECTIVE: Public expenditures for home health care grew rapidly in the 1990s, but it remains unclear to whom the additional services were targeted. This study tests whether the rapidly increasing expenditures were targeted to the elderly with high levels of disability and low levels of social support, 2 groups that have historically been higher users of paid home health and nursing home services. METHODS: The Asset and Health Dynamics Study, a nationally representative, longitudinal survey of people > or = 70 years of age (n = 7,443), was used to determine the association of level of disability and level of social support with the use of paid home care services in both 1993 and 1995. Multivariable regression models were used to adjust for sociodemographics, recent hospital or nursing home admissions, chronic medical conditions, and receipt of informal care from family members. RESULTS: Those with higher levels of disability received more adjusted weekly hours of paid home care in both 1993 and 1995. In 1993, users of paid home care with the least social support (unmarried living alone) received more adjusted weekly hours of care than the unmarried elderly living with others (24 versus 13 hours, P < 0.01) and the married (24 versus 18 hours, P = 0.06). However, by 1995, those who were unmarried and living with others were receiving the most paid home care: 40 versus 26 hours for the unmarried living alone (P < 0.05) and 24 hours for the married (P < 0.05). CONCLUSIONS: The recent large increase in formal home care services went disproportionately to those with greater social support. Home care policy changes in the early 1990s resulted in a shift in the distribution of home care services toward the elderly living with their children.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Family Characteristics; Female; Financing, Government; Frail Elderly; Geriatric Assessment; Health Care Surveys; Health Expenditures; health policy; Home Care Services; Home Nursing; Humans; Longitudinal Studies; Male; Marital Status; Multivariate Analysis; Social Support; Socioeconomic factors; Surveys and Questionnaires; United States; Utilization Review

National estimates of the quantity and cost of informal caregiving for the elderly with dementia. - Kenneth M. Langa; M.E. Chernew; Mohammed U Kabeto; A. Regula Herzog; Mary Beth Ofstedal; Robert J. Willis; Robert B Wallace; Mucha, L.M.; Walter L. Straus; A. Mark Fendrick (J Gen Intern Med, 2001)
OBJECTIVE: Caring for the elderly with dementia imposes a substantial burden on family members and likely accounts for more than half of the total cost of dementia for those living in the community. However, most past estimates of this cost were derived from small, nonrepresentative samples. We sought to obtain nationally representative estimates of the time and associated cost of informal caregiving for the elderly with mild, moderate, and severe dementia. DESIGN: Multivariable regression models using data from the 1993 Asset and Health Dynamics Study, a nationally representative survey of people age 70 years or older (N = 7,443). SETTING: National population-based sample of the community-dwelling elderly. MAIN OUTCOME MEASURES: Incremental weekly hours of informal caregiving and incremental cost of caregiver time for those with mild dementia, moderate dementia, and severe dementia, as compared to elderly individuals with normal cognition. Dementia severity was defined using the Telephone Interview for Cognitive Status. RESULTS: After adjusting for sociodemographics, comorbidities, and potential caregiving network, those with normal cognition received an average of 4.6 hours per week of informal care. Those with mild dementia received an additional 8.5 hours per week of informal care compared to those with normal cognition (P < .001), while those with moderate and severe dementia received an additional 17.4 and 41.5 hours (P < .001), respectively. The associated additional yearly cost of informal care per case was 3,630 dollars for mild dementia, 7,420 dollars for moderate dementia, and 17,700 dollars for severe dementia. This represents a national annual cost of more than 18 billion dollars. CONCLUSION: The quantity and associated economic cost of informal caregiving for the elderly with dementia are substantial and increase sharply as cognitive impairment worsens. Physicians caring for elderly individuals with dementia should be mindful of the importance of informal care for the well-being of their patients, as well as the potential for significant burden on those (often elderly) individuals providing the care.
Keywords: Aged; Aged, 80 and over; Caregivers; Cost of Illness; Dementia; Female; Health Care Costs; Humans; Male; Multivariate Analysis; Regression Analysis; Severity of Illness Index; Time Factors; United States

Prevalence and outcomes of comorbid metabolic and cardiovascular conditions in middle- and older-age adults. - Oldrige, Neil B.; Timothy E. Stump; Nothwehr, F.; Daniel O. Clark (J Clin Epidemiol, 2001)
UNLABELLED: To estimate age group differences in the prevalence and outcomes of three common and often comorbid metabolic conditions (i.e., obesity, hypertension, and diabetes) and heart disease. DESIGN: Nationally representative prospective cohort study. SETTING: PARTICIPANTS' homes. PARTICIPANTS: 9825 adults aged 51 to 61 years (middle-age) in 1992, and 7370 adults aged 70 years and over (older-age) in 1993. MEASUREMENTS: Two-year dichotomous outcomes included: doctor visits, hospitalization, mobility difficulty, activity of daily living limitation, poor perceived health, and mortality. Odds ratios (OR) were adjusted for sociodemographic characteristics and history of cancer or lung disease. RESULTS: Those with one condition represented 80% and 70% of the middle- and older-age groups, respectively, while just 1-2% of each age group reported all three metabolic conditions. Thirteen percent and 32%, respectively, reported heart disease with or without metabolic conditions. Diabetes comorbid with other metabolic conditions, and particularly with heart disease, substantially elevated the risk of adverse outcomes such as health-related quality of life deficits, health services use, and mortality in both middle- and older-age adults. In the middle-age group, the OR was 6.81 for mortality in patients with a combination of obesity and diabetes and 6.10 in those with a combination of heart disease and diabetes. There also were significant ORs for mortality in middle-aged patients with heart disease (OR = 2.40), diabetes (OR = 2.63) and for those with a combination of obesity, hypertension, and diabetes (OR = 3.26). CONCLUSION: The impact of these often comorbid conditions underscores the importance of targeted and aggressive prevention, particularly among middle-age adults.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Diabetes Complications; Diabetes Mellitus; Female; Health Services for the Aged; Humans; Hypertension; Male; Middle Aged; Obesity; Odds Ratio; Outcome Assessment, Health Care; Prevalence; Prospective Studies; Quality of Life; United States

Proportional treatment effects for count response panel data: effects of binary exercise on health care demand. - Lee, Myoung Jae; Satoru Kobayashi (Health Econ, 2001)
We define conditional and marginal treatment effects appropriate for count data, and then conduct an empirical analysis for the effects of exercise on health care demand using panel data from the Health Retirement Study. The response variables are office visits to doctors and hospitalization days, and the treatments of interest are light and vigorous exercises. We found that short-run light exercise increases health care demand by 3-5%, whereas long-run light exercise decreases it by 3-6%. We also found that short-run vigorous exercise decreases health care demand by 1-2%, whereas long-run vigorous exercise decreases it by 1-3%. However, many of these numbers are not statistically significantly different from zero. These findings suggest that it will be difficult to reduce health care cost much by encouraging people to do more exercise--at least in the short-run.
ProCite field 3 : Sungkyunkwan U; Mitsubishi Trust and Banking Corp, Tokyo
Keywords: Adult; Aged; Aged, 80 and over; Bias; Cost Control; Cross-Sectional Studies; Data Interpretation, Statistical; Effect Modifier, Epidemiologic; Exercise Therapy; Female; Health Promotion; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Needs Assessment; Regression Analysis; Research Design; Treatment Outcome; United States

Self-restriction of medications due to cost in seniors without prescription coverage. - Michael A Steinman; Laura Sands; Kenneth E Covinsky (J Gen Intern Med, 2001)
OBJECTIVE: Little is known about patients who skip doses or otherwise avoid using their medications because of cost. We sought to identify which elderly patients are at highest risk of restricting their medications because of cost, and how prescription coverage modifies this risk. DESIGN AND PARTICIPANTS: Cross-sectional study from the 1995-1996 wave of the Survey of Asset and Health Dynamics Among the Oldest Old, a population-based survey of Americans age 70 years and older. MEASUREMENTS: Subjects were asked the extent of their prescription coverage, and whether they had taken less medicine than prescribed for them because of cost over the prior 2 years. We used bivariate and multivariate analyses to identify risk factors for medication restriction in subjects who lacked prescription coverage. Among these high-risk groups, we then examined the effect of prescription coverage on rates of medication restriction. MAIN RESULTS: Of 4,896 seniors who regularly used prescription medications, medication restriction because of cost was reported by 8% of subjects with no prescription coverage, 3% with partial coverage, and 2% with full coverage (P <.01 for trend). Among subjects with no prescription coverage, the strongest independent predictors of medication restriction were minority ethnicity (odds ratio [OR], 2.9 compared with white ethnicity; 95% confidence interval [95% CI], 2.0 to 4.2), annual income <$10,000 (OR, 3.8 compared with income > or =$20,000; 95% CI, 2.4 to 6.1), and out-of-pocket prescription drug costs >$100 per month (OR, 3.3 compared to costs < or =$20; 95% CI, 1.5 to 7.2). The prevalence of medication restriction in members of these 3 risk groups was 21%, 16%, and 13%, respectively. Almost half (43%) of subjects with all 3 risk factors and no prescription coverage reported restricting their use of medications. After multivariable adjustment, high-risk subjects with no coverage had 3 to 15 times higher odds of medication restriction than subjects with partial or full coverage (P <.01). CONCLUSIONS: Medication restriction is common in seniors who lack prescription coverage, particularly among certain vulnerable groups. Seniors in these high-risk groups who have prescription coverage are much less likely to restrict their use of medications.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Cross-Sectional Studies; Female; Humans; Insurance, Pharmaceutical Services; Male; Prescription Fees; Risk Factors; Socioeconomic factors; Treatment Refusal; United States

The effect of smoking on health using a sequential self-selection model. - Kajal Chatterji Lahiri; Song, Jae G. (Health Econ, 2000)
We estimate a structural model of individual smoking behaviour emphasizing the role of individual risk belief on smoking choices. Our model consists of five equations: two selection equations for initiation and cessation decisions, and three switching outcome regressions for nonsmokers, ex-smokers, and current smokers. The presence of significant self-selectivity implies that the health effects of smoking based on sample proportions do not correctly indicate the true risk of cigarette smoking. Further, our evidence suggests that the self-selection in the cessation decision, but not in the initiation decision, is consistent with economic rationality. We estimate the model by full information maximum likelihood (FIML) with starting values from heteroskedasticity corrected Heckman-Lee two-step method using newly released Health and Retirement Study (HRS) data.
ProCite field 3 : SUNY, Albany; SUNY, Albany
Keywords: Adult; Aged; Aged, 80 and over; Attitude to Health; Decision making; Health Behavior; Health Status; Health Surveys; Humans; Middle Aged; Models, Econometric; Predictive Value of Tests; Reproducibility of Results; Risk Factors; Risk-Taking; Selection Bias; Smoking; Smoking cessation; Surveys and Questionnaires; United States

Memory complaint in a community sample aged 70 and older. - Carolyn L. Turvey; Schultz, Susan K.; Arndt, Stephan; Robert B Wallace; A. Regula Herzog (J Am Geriatr Soc, 2000)
OBJECTIVES: The ability of older people to estimate their own memory, often referred to as "metamemory," has been evaluated in previous studies with conflicting reports regarding accuracy. Some studies have suggested that an older person's metamemory is mostly accurate, whereas others have demonstrated little relationship between memory complaint and actual impairment. This study examines memory complaint in a large national sample of older people aged > or = 70. DESIGN: A longitudinal cohort study with two waves of data collection spaced 2 years apart. SETTING: A nationwide random sample of community-dwelling older persons. PARTICIPANTS: A total of 5,444 community-dwelling persons aged > or = 70 and their spouses. MEASUREMENTS: Participants were asked if they believed their memory was excellent, very good, good, fair, or poor. They were then administered a cognitive assessment derived from the Mini-Mental Status Exam. RESULTS: In general, people's assessment of their memory corresponded with their actual performance on cognitive measures. However, large portions of the sample inaccurately assessed their memory skills. People who reported depressive symptoms and had impairment in activities of daily living were more likely to state that their memory was impaired, although they performed very well on cognitive measures. CONCLUSIONS: The conditions that skew people's self-assessment are the ones most likely to bring them into contact with healthcare professionals. This may give clinicians the general impression that older people cannot assess their own cognitive skills. However, poor metamemory appears to be a characteristic of a specific subgroup of older persons, not necessarily characteristic of the general population.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cognition; Depressive Disorder; Educational Status; Female; Geriatric Assessment; Humans; Longitudinal Studies; Male; Marital Status; Memory; Self-Assessment

Older adults and financial bequests. - Goetting, Marsha A.; Peter Martin; Johnson, Christine (Int J Aging Hum Dev, 2000)
Using data from Aging and Health Dynamics (AHEAD), this research investigated a model predicting an older adult's assessment regarding the chances (from 0 to 100) of leaving a financial bequest. Structural equation modeling analyses revealed three significant predictors of a high assessment (i.e., older age, high sense of control, and high socioeconomic status) and three predictors of a low assessment (i.e., race, physical health problems, and assessment of the chances of medical expenses depleting savings). Whites had higher financial bequests assessments than non-Whites. Physical health problems and the depleting savings assessment exerted negative effects on the financial bequest assessment. Marital status and negative psychological functioning exerted indirect effects through sense of control and through the depleting savings assessment.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Aging; Attitude; Female; Health Care Costs; Health Status; Humans; Male; Mental Health; Michigan; Models, Economic; Sampling Studies; Sex Factors; Socioeconomic factors; Spouses; Surveys and Questionnaires; Wills

Preferences for surrogate decision makers, informal communication, and advance directives among community-dwelling elders: results from a national study. - Faith P. Hopp (Gerontologist, 2000)
This study, drawing on a nationally representative sample of community-dwelling adults aged 70 and older from the second wave of the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey, addresses the need for greater information on advance care planning among older adults. Older persons expect to draw on a diverse array of persons to make health care decisions for them when they are unable to do so, including spouses, when available, as well as younger generation members such as children and grandchildren. Completion of advance directives such as living wills and durable powers of attorney for health care was more common among White respondents than among African American respondents, and among high school- and college-educated respondents compared with those with less than a high school education. The results suggest the need to develop interventions aimed at strengthening knowledge and understanding of advance directives, particularly for African Americans and persons with lower levels of educational attainment. They further suggest the need for more research on the factors related to informal communication between older adults and their family members on issues related to advance care planning.
Keywords: Advance directives; Aged; Aged, 80 and over; Black or African American; Choice Behavior; Communication; Educational Status; Family; Female; Health education; Health Status; Humans; Logistic Models; Male; Needs Assessment; Surveys and Questionnaires; United States; White People

The racial crossover in comorbidity, disability, and mortality. - Nan E. Johnson (Demography, 2000)
This study analyzed one respondent per household who was age 70 or more at the time of the household's inclusion in Wave 1 (1993-1994) and whose survival status was determinable at Wave 2 (1995-1996) of the Survey on Asset and Health Dynamics Among the Oldest Old (AHEAD Survey). At age 76 at Wave 1, there was a racial crossover in the cumulative number of six potentially fatal diagnoses (chronic lung disease, cancer, heart disease, hypertension, diabetes, and stroke) from a higher cumulative average number for blacks to a higher average number for whites. Also, there was a racial crossover at age 86 in the cumulative average number of disabilities in the Advanced Activities of Daily Living (AADLs), from a higher average for blacks to a higher average for whites. Between Waves 1 and 2, there was a racial crossover in the odds of mortality from higher odds for blacks to higher odds for whites; this occurred at about age 81. The results are consistent with the interpretation that the racial crossover in comorbidity (but not the crossover in AADL disability) propelled the racial crossover in mortality.
RDA 2002-016
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Birth Certificates; Black People; Chronic disease; Comorbidity; Cross-Over Studies; Death Certificates; Disabled Persons; Female; Humans; Male; United States; White People

Racial variations in end-of-life care. - Faith P. Hopp; Sonia A. Duffy (J Am Geriatr Soc, 2000)
OBJECTIVES: To identify differences in advanced care planning and end-of-life decision-making between whites and blacks aged 70 and older. DESIGN: The Asset and Health Dynamics Among the Oldest Old (AHEAD) study is a nationally representative survey of adults who were aged 70 and older in 1993. Relatives (proxy respondents) for 540 persons who died between the first (1993) and second (1995) waves of the study were surveyed about advanced care planning and end-of-life decisions that were made for their family member who died. SETTING: Respondents were interviewed at home by telephone (n = 444) or in person (n = 95). PARTICIPANTS: The 540 proxy respondents included 454 whites and 86 blacks. MEASUREMENTS: Questions were asked about advance care planning and end-of-life decisions. RESULTS: Whites were significantly more likely than blacks to discuss treatment preferences before death (P = .002), to complete a living will (P = .001), and to designate a Durable Power of Attorney for Health Care (DPAHC) (P = .032). The treatment decisions for whites were more likely to involve limiting care in certain situations (P = .007) and withholding treatment before death (P = .034). In contrast, the treatment decisions for blacks were more likely to be based on the desire to provide all care possible in order to prolong life (P = .013). Logistic regression models revealed that race continued to be a significant predictor of advance care planning and treatment decisions even after controlling for sociodemographic factors. CONCLUSIONS: These findings suggest that there are important differences between blacks and whites regarding advanced care planning and end-of-life decision-making. Health professionals need to understand the diverse array of end-of-life preferences among various racial and ethnic groups and to develop greater awareness and sensitivity to these preferences when helping patients with end-of-life decision-making.
Keywords: Advance care planning; Advance directives; Aged; Aged, 80 and over; Attitude to Health; Black or African American; Cross-Cultural Comparison; Decision making; Female; Follow-Up Studies; Humans; Logistic Models; Male; Patient Care Planning; Terminal Care; United States; White People

A comparison of correlates of cognitive functioning in older persons in Taiwan and the United States. - Mary Beth Ofstedal; Zachary Zimmer; Hui-Sheng Lin (J Gerontol B Psychol Sci Soc Sci, 1999)
OBJECTIVES: This article compares patterns of association between cognitive functioning and a number of sociodemographic and health correlates among older persons in Taiwan and the United States. METHODS: The study uses data from the 1993 Survey of Health and Living Status of the Elderly in Taiwan and the 1993 Study of Asset and Health Dynamics Among the Oldest Old in the United States. Separate multivariate regression models are employed for each country to examine the effects of sociodemographic and health factors on cognitive functioning, and to examine the marginal impact of cognitive functioning on activities of daily living (ADL) and instrumental ADL (IADL) functioning. RESULTS: Results of the multivariate analyses show similar patterns of association across the two countries and replicate findings from previous studies. Increasing age, female gender, lower education, depression, and selected health conditions are associated with lower cognitive functioning. In addition, although a significant predictor of both ADL and IADL impairments, cognitive functioning is more powerful with respect to explaining IADL impairments. DISCUSSION: Study findings suggest that the cognitive measures are capturing similar dimensions in Taiwan and the United States, and that factors associated with cognitive functioning and its consequences with respect to physical functioning are similar in the two countries.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Cognition; Cross-Cultural Comparison; depression; Educational Status; Female; Geriatric Assessment; Health Status; Humans; Male; Multivariate Analysis; Regression Analysis; Sex Factors; Socioeconomic factors; Surveys and Questionnaires; Taiwan; United States

Conjugal loss and syndromal depression in a sample of elders aged 70 years or older. - Carolyn L. Turvey; Carney, C.; Arndt, Stephan; Robert B Wallace; A. Regula Herzog (Am J Psychiatry, 1999)
OBJECTIVE: The goal of this study was to describe the association between conjugal loss and both syndromal depression and depressive symptoms in a prospective cohort study of people aged 70 years or older. METHOD: A measure of syndromal depression, the shortform Composite International Diagnostic Interview (CIDI), and a revised version of the Center for Epidemiologic Studies--Depression Scale (CES-D Scale) were administered to a group of 5,449 elders in a longitudinal cohort study. The authors compared the rates of syndromal depression (CIDI diagnosis) and depressive symptoms (six CES-D Scale symptoms) in married participants and those who lost spouses between the first and second waves of assessment. RESULTS: The rate of syndromal depression in the newly bereaved was nearly nine times as high as the rate for married individuals, and the rate of depressive symptoms was nearly four times as high. The percentage of the bereaved respondents who had scores above threshold on the revised CES-D Scale was higher for those interviewed up to 2 years after loss of a spouse than for married respondents. Age, sex, prior psychiatric history, and the expectedness of the death did not differ between depressed and nondepressed newly bereaved subjects. CONCLUSIONS: Recent bereavement is a significant risk factor for syndromal depression in the elderly. Some widows and widowers experienced high levels of depressive symptoms up to 2 years after the loss of their spouses. Neither demographic variables nor variables concerning the nature of the spouse's death predicted bereavement-related depression.
Keywords: Age Factors; Aged; Aged, 80 and over; Bereavement; Cohort Studies; depression; Depressive Disorder; Female; Humans; Logistic Models; Longitudinal Studies; Male; Marital Status; Odds Ratio; Psychiatric Status Rating Scales; Risk Factors; Sex Factors; Widowhood

The influence of personal care and assistive devices on the measurement of disability. - Agree, E M (Soc Sci Med, 1999)
The goal of all long-term care arrangements is to reduce the disabling effects of physical impairments and functional limitations. However, the means with which individuals cope with disability may not be equivalent and these differences may influence self-reports of disability in surveys. This paper examines assistive devices and personal care as factors in the measurement of disability among persons aged 70 and older in the community using the 1994 Survey of Asset and Health Dynamics of the Oldest Old (AHEAD) in the US. The use of assistive technology differs from personal care on a fundamental level. It does not require the ongoing cooperation or coordination of other people and therefore increases the sense of independence with which a disabled individual can meet their long-term care needs. Results indicate that older individuals can expect to spend most of their remaining years in good functional health, but up to two-thirds of disabled years will be spent with unmet ADL needs. Among those who are disabled, those who use only equipment and no personal care report less residual difficulty with mobility than those who use personal assistance (either alone or in combination with equipment) but the use of equipment alone is most effective for those with the least severe limitations.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Disability Evaluation; Female; Humans; Life Expectancy; Logistic Models; Long-term Care; Male; Self-Help Devices

Prevalence and severity of urinary incontinence in older African American and Caucasian women. - Fultz, Nancy H.; A. Regula Herzog; Trivellore E. Raghunathan; Robert B Wallace; Diokno, A.C. (J Gerontol A Biol Sci Med Sci, 1999)
BACKGROUND: Few studies have investigated the prevalence and severity of urinary incontinence in older African American women. Comparisons of findings with those for older Caucasian women could provide important clues to the etiology of urinary incontinence and be used in planning screening programs and treatment services. METHODS: Data are from the first wave of the Asset and Health Dynamics Among the Oldest Old (AHEAD) study. A nationally representative sample of noninstitutionalized adults 70 years of age and older was interviewed. African Americans were oversampled to ensure that there would be enough minority respondents to compare findings across racial groups. RESULTS: A statistically significant relationship was found between race and urinary incontinence in the previous year: 23.02% of the Caucasian women reported incontinence, compared with 16.17% of the African American women. Other factors that appear to increase the likelihood of incontinence include education, age, functional impairment, sensory impairment, stroke, body mass, and reporting by a proxy. Race was not related to the severity (as measured by frequency) of urine loss among incontinent older women. CONCLUSION: This study identifies or confirms important risk factors for self-reported urinary incontinence in a national context, and suggests factors leading to protection from incontinence. Race is found to relate to incontinence, with older African American women reporting a lower prevalence.
Keywords: Aged; Aged, 80 and over; Black or African American; Female; Humans; Prevalence; Risk Factors; United States; Urinary incontinence; White People

The relationship of self-rated vision and hearing to functional status and well-being among seniors 70 years and older. - Paul P Lee; James P Smith; Raynard Kington (Am J Ophthalmol, 1999)
PURPOSE: To describe the relationship between self-reported visual and hearing impairment and an index of global functional status among seniors age 70 years or older. METHODS: A total of 7,320 United States community-dwelling persons aged 70 years or older participating in the 1993 Assets and Health Dynamics of the Oldest Old Survey (AHEAD) completed detailed questionnaires about their demographic, socioeconomic, and health status. Multivariate analyses of functional status (using a global index of functional status based on self-reported limitations in 11 activities) were conducted, controlling for demographic and socioeconomic status and common medical conditions, as well as independently for hearing and vision. RESULTS: Of the respondents, 27% rated their vision as fair or poor, whereas 25% rated their hearing as fair or poor. Controlling for demographic factors, socioeconomic status, medical conditions, and general health status, limitations in both vision and hearing correlated independently with worsened functional status. Controlling for income, wealth, and education did not greatly reduce the strength of the association between visual and hearing impairment and function. CONCLUSIONS: Visual and hearing impairment appear to have a significant relationship to overall functioning in the oldest old, regardless of income or wealth. By confirming these findings across income and household wealth groups, adjusted for medical conditions and general health status, in a nationally representative population of Americans age 70 years or older, this study provides a powerful added impetus to efforts for improving vision and hearing for all other Americans, including the oldest old.
Keywords: Aged; Aged, 80 and over; Female; Health Status; hearing; Hearing Disorders; Humans; Male; Multivariate Analysis; Quality of Life; Self Disclosure; Surveys and Questionnaires; Vision Disorders; Vision, Ocular; Visual Acuity

Do medical conditions affect cognition in older adults? - Elizabeth Zelinski; Eileen M. Crimmins; Sandra L Reynolds; Teresa Seeman (Health Psychol, 1998)
Analyses of a nationally representative sample who completed a list recall task (weighted n = 6,446) and 2 mental status tasks (weighted n = 6,646) were conducted to determine whether specific medical conditions such as high blood pressure and diabetes as well as general health ratings predict cognitive performance in adults aged 70 to 103. Presence of stroke and poorer health ratings predicted poorer performance on the 3 tasks. Presence of diabetes predicted poorer performance on recall and 1 mental status task. Age interacted with medical conditions including high blood pressure and diabetes in predicting mental status, with condition-related deficits confined to the younger end of the age continuum. Global health ratings interacted with age, with poorer ratings associated with worse mental status in the younger participants. Findings suggest that stroke and diabetes are associated with cognitive deficits. Some deficits are more pronounced in younger old adults with high blood pressure and poorer health ratings.
Keywords: Aged; Aged, 80 and over; Aging; Cerebrovascular Disorders; Cognition; Diabetes Complications; Diabetes Mellitus; Female; Health Status; Humans; Hypertension; Male; Mental Health

Occupational injuries among older workers with disabilities: a prospective cohort study of the Health and Retirement Survey, 1992 to 1994. - Zwerling, Craig; Nancy L. Sprince; Charles S. Davis; Paul S. Whitten; Robert B Wallace; Steven G Heeringa (Am J Public Health, 1998)
OBJECTIVES: We tested the hypothesis that among older workers, disabilities in general, and hearing and visual impairments in particular, are risk factors for occupational injuries. METHODS: Using the first 2 interviews of the Health and Retirement Study, a nationally representative survey of Americans aged 51 to 61 years, we conducted a prospective cohort study of 5600 employed nonfarmers. RESULTS: Testing a logistic regression model developed in a previous cross-sectional study, we found that the following occupations and risk factors were associated with occupational injury as estimated by odds ratios: service personnel, odds ratio = 1.71 (95% confidence interval = 1.13, 2.57); mechanics and repairers, 3.47 (1.98, 6.10); operators and assemblers, 2.33 (1.51, 3.61); laborers, 3.16 (1.67, 5.98); jobs requiring heavy lifting, 2.05 (1.55, 2.70); self-employment, 0.50 (0.34, 0.73); and self-reported disability, 1.58 (1.14, 2.19). Replacing the general disability variable with specific hearing and visual impairment variables, we found that poor hearing (1.35 [0.95, 1.93]) and poor sight (1.45 [0.94, 2.22]) both had elevated odds ratios. CONCLUSIONS: Poor sight and poor hearing, as well as work disabilities in general, are associated with occupational injuries among older workers.
Keywords: Accidents, Occupational; Age Distribution; Aged; Aged, 80 and over; Analysis of Variance; Cross-Sectional Studies; Disabled Persons; Female; Health Surveys; Humans; Logistic Models; Male; Middle Aged; Odds Ratio; Prospective Studies; Retirement; Risk Factors; United States

Asset and Health Dynamics Among the Oldest Old (AHEAD): initial results from the longitudinal study. Introduction. - Myers, George C.; Juster, F. Thomas; Richard M. Suzman (J Gerontol B Psychol Sci Soc Sci, 1997)
Keywords: Aged; Aged, 80 and over; Data collection; Health Status; Humans; Income; Longitudinal Studies; Research Design

A comparative analysis of ADL questions in surveys of older people. - Willard L Rodgers; Baila Miller (J Gerontol B Psychol Sci Soc Sci, 1997)
This article describes questions designed to assess limitations with respect to activities of daily living (ADLs) that were asked on the first wave of the AHEAD study, and it assesses their cross-sectional measurement properties. It also provides comparisons between those questions and parallel questions that have been asked on two other surveys of the elderly population in the United States: the 1984 Supplement on Aging (SOA) to the National Health Interview Survey and the screener for the 1982 National Long Term Care Survey (NLTCS). It also compares a single item from the 1990 Census. It then compares the ways in which the same individuals answer these different versions of ADL questions, using data from subsamples of the AHEAD respondents who were also asked the SOA, NLTCS, or Census questions. The analysis shows that there is a substantial amount of measurement error in the answers to ADL questions, and it suggests that this is a major contributor to apparent improvements and declines in functional health observed in longitudinal data.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Geriatric Assessment; Health Services; Health Status; Health Surveys; Humans; Regression Analysis; Reproducibility of Results; United States

Measures of cognitive functioning in the AHEAD Study. - A. Regula Herzog; Robert B Wallace (J Gerontol B Psychol Sci Soc Sci, 1997)
Decline in cognitive functioning and onset of cognitive impairment are potentially important predictors of elderly persons needing informal assistance and formal health care. This article describes the measures of cognitive functioning that were developed for the Asset and Health Dynamics Among the Oldest Old (AHEAD) study of some 6,500 Americans aged 70 years and older. The study was designed to investigate the impact of health on disbursement of family and economic resources. Evaluation of the cognitive measures in terms of psychometric properties and missing data, telephone administration, and formation of an aggregate index is encouraging. Their construct validity is evidenced by their correlations with sociodemographic characteristics and health indicators that replicate existing findings as well as by their prediction of IADL and ADL functioning that are consistent with theory.
Keywords: Aged; Aged, 80 and over; Cognition; Geriatric Assessment; Health Status; Health Surveys; Humans; Longitudinal Studies; Memory; Mental Status Schedule; Psychological Tests; Socioeconomic factors; United States

Patterns of in-home care among elderly black and white Americans. - Norgard, T.M.; Willard L Rodgers (J Gerontol B Psychol Sci Soc Sci, 1997)
This study examines the use of informal and formal sources of care by elderly Black and White Americans (n = 2,847) who are functionally impaired and noninstitutionalized. The data are from the Asset and Health Dynamics Among the Oldest Old (AHEAD) study. Detailed baseline characteristics are provided and logistic regressions are used to assess the likelihood of (a) receiving in-home assistance from any source, (b) using any informal sources of in-home care, (c) using any formal sources, and (d) using formal sources of in-home care with informal sources of home care. Results of the logistic regressions indicate that, compared to Whites, Black elders were less likely to receive assistance and to use informal sources of home care.
Keywords: Aged; Aged, 80 and over; Black or African American; Caregivers; Female; Home Care Services; Humans; Male; Socioeconomic factors; United States; White People

Prevalence and impact of risk factors for lower body difficulty among Mexican Americans, African Americans, and whites. - Daniel O. Clark; Mungai, S.M.; Timothy E. Stump; Frederic D Wolinsky (J Gerontol A Biol Sci Med Sci, 1997)
BACKGROUND: The purpose of the study was to estimate the prevalence of sociodemographic, health behavior, chronic disease, and impairment factors and their impact on difficulty in lower body function among two age-cohorts (51-61 and 71-81 years) of Mexican Americans, African Americans, and Whites. METHODS: Reports from 8,727 and 4,510 self-respondents of the 1992 baseline Health and Retirement Survey and the 1993 baseline Assets and Health Dynamics Study, respectively, were used to estimate prevalence. Multiple linear regression of the 4-item lower body difficulty scale (alpha = .80) was used to estimate the direct effects of the risk factors within the age-cohort and ethnicity groups. RESULTS: Overall, the risk factors are more prevalent among both minority groups and the older age-cohort. Lower body deficits are particularly high among Mexican Americans and the younger age-cohort of African Americans. The impact of risk factors does not vary much by ethnicity or age-cohort. Female gender, pain, arthritis, and heart and lung disease are the major risk factors, and they account for about one-third of the variance in lower body difficulty for each group. CONCLUSIONS: Efforts to prevent or reduce lower body difficulty should pay particular attention to pain, arthritis, and heart and lung disease. The central role of sociodemographic and behavioral factors in chronic disease argues for their continued inclusion in disability modeling and prevention.
Keywords: Aged; Aged, 80 and over; Black or African American; Chronic disease; Cohort Studies; Disabled Persons; Disease; Female; Health Behavior; Humans; Male; Memory Disorders; Mexican Americans; Middle Aged; Prevalence; Risk Factors; Socioeconomic factors; White People

Cross pressures on middle-aged adults: a broader view. - Beth J Soldo (J Gerontol B Psychol Sci Soc Sci, 1996)
Keywords: Adult; Age Distribution; Aged; Aged, 80 and over; Family; Female; Humans; Male; Middle Aged